2FHL: The SECOND CATALOG of HARD FERMI-LAT SOURCES - Ackermann, M.; Ajello, Marco; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal Supplement Series, 2016)
We present a catalog of sources detected above 50 GeV by the Fermi-Large Area Telescope (LAT) in 80 months of data. The newly delivered Pass 8 event-level analysis allows the detection and characterization of sources in the 50 GeV-2 TeV energy range. In this energy band, Fermi-LAT has detected 360 sources, which constitute the second catalog of hard Fermi-LAT sources (2FHL). The improved angular resolution enables the precise localization of point sources (∼1.′7 radius at 68% C. L.) and the detection and characterization of spatially extended sources. We find that 86% of the sources can be associated with counterparts at other wavelengths, of which the majority (75%) are active galactic nuclei and the rest (11%) are Galactic sources. Only 25% of the 2FHL sources have been previously detected by Cherenkov telescopes, implying that the 2FHL provides a reservoir of candidates to be followed up at very high energies. This work closes the energy gap between the observations performed at GeV energies by Fermi-LAT on orbit and the observations performed at higher energies by Cherenkov telescopes from the ground.
Keywords: catalogs; gamma-rays: general

3FHL: The Third Catalog of Hard Fermi-LAT Sources - Ajello, Marco; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bregeon, J.; et al. (Astrophysical Journal Supplement Series, 2017)
We present a catalog of sources detected above 10 GeV by the Fermi Large Area Telescope (LAT) in the first 7 years of data using the Pass 8 event-level analysis. This is the Third Catalog of Hard Fermi-LAT Sources (3FHL), containing 1556 objects characterized in the 10 GeV-2 TeV energy range. The sensitivity and angular resolution are improved by factors of 3 and 2 relative to the previous LAT catalog at the same energies (1FHL). The vast majority of detected sources (79%) are associated with extragalactic counterparts at other wavelengths, including 16 sources located at very high redshift (z > 2). Of the sources, 8% have Galactic counterparts and 13% are unassociated (or associated with a source of unknown nature). The high-latitude sky and the Galactic plane are observed with a flux sensitivity of 4.4 to 9.5 x 10(-11) ph cm(-2) s(-1), respectively (this is approximately 0.5% and 1% of the Crab Nebula flux above 10 GeV). The catalog includes 214 new gamma-ray sources. The substantial increase in the number of photons (more than 4 times relative to 1FHL and 10 times to 2FHL) also allows us to measure significant spectral curvature for 32 sources and find flux variability for 163 of them. Furthermore, we estimate that for the same flux limit of 10(-12) erg cm(-2) s(-1), the energy range above 10 GeV has twice as many sources as the range above 50 GeV, highlighting the importance, for future Cherenkov telescopes, of lowering the energy threshold as much as possible.
CRIS-Team WoS Importer:2020-01-15

3HWC: The Third HAWC Catalog of Very-high-energy Gamma-Ray Sources - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal, 2020)
We present a new catalog of TeV gamma-ray sources using 1523 days of data from the High-Altitude Water Cherenkov (HAWC) Observatory. The catalog represents the most sensitive survey of the northern gamma-ray sky at energies above several TeV, with three times the exposure compared to the previous HAWC catalog, 2HWC. We report 65 sources detected at >= 5 sigma significance, along with the positions and spectral fits for each source. The catalog contains eight sources that have no counterpart in the 2HWC catalog, but are within 1 degrees of previously detected TeV emitters, and 20 sources that are more than 1 degrees away from any previously detected TeV source. Of these 20 new sources, 14 have a potential counterpart in the fourth Fermi Large Area Telescope catalog of gamma-ray sources. We also explore potential associations of 3HWC sources with pulsars in the Australia Telescope National Facility (ATNF) pulsar catalog and supernova remnants in the Galactic supernova remnant catalog.
CRIS-Team WoS Importer:2021-01-01

Acceleration of petaelectronvolt protons in the Galactic Centre - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Nature, 2016)
Galactic cosmic rays reach energies of at least a few petaelectronvolts(1) (of the order of 1015 electronvolts). This implies that our Galaxy contains petaelectronvolt accelerators ('PeVatrons'), but all proposed models of Galactic cosmic-ray accelerators encounter difficulties at exactly these energies(2). Dozens of Galactic accelerators capable of accelerating particles to energies of tens of teraelectronvolts (of the order of 10(13) electronvolts) were inferred from recent gamma-ray observations(3). However, none of the currently known accelerators-not even the handful of shell-type supernova remnants commonly believed to supply most Galactic cosmic rays-has shown the characteristic tracers of petaelectronvolt particles, namely, power-law spectra of.-rays extending without a cut-off or a spectral break to tens of teraelectronvolts(4). Here we report deep.-ray observations with arcminute angular resolution of the region surrounding the Galactic Centre, which show the expected tracer of the presence of petaelectronvolt protons within the central 10 parsecs of the Galaxy. We propose that the supermassive black hole Sagittarius A* is linked to this PeVatron. Sagittarius A* went through active phases in the past, as demonstrated by X-ray outbursts(5) and an outflow from the Galactic Centre(6). Although its current rate of particle acceleration is not sufficient to provide a substantial contribution to Galactic cosmic rays, Sagittarius A* could have plausibly been more active over the last 10(6)-10(7) years, and therefore should be considered as a viable alternative to supernova remnants as a source of petaelectronvolt Galactic cosmic rays.

Active Personal Eye Lens Dosimetry with the Hybrid Pixelated Dosepix Detector - Beiser, Florian; Haag, Dennis; Ballabriga, Rafael; Behrens, Rolf; Campbell, Michael; Fuhg, Christian; Hufschmidt, Patrick; Hupe, Oliver; Kupillas, Carolin; Llopart, Xavier; Roth, Jurgen; Schmidt, Sebastian; et al. (IEEE Transactions on Radiation and Plasma Medical Sciences, 2023)
Eye lens dosimetry has been an important field of research in the last decade. Dose measurements with a prototype of an active personal eye lens dosemeter based on the Dosepix detector are presented. The personal dose equivalent at 3 mm depth of soft tissue, Hp(3), was measured in the center front of a water-filled cylinder phantom with a height and diameter of 20 cm. The energy dependence of the normalized response is investigated for mean photon energies between 12.4 keV and 248 keV for continuous reference radiation fields (N-series) according to ISO 4037. The response normalized to N-60 (E=47.9 keV) at 0∘ angle of irradiation stays within the approval limits of IEC 61526 for angles of incidence between -75∘ and +75∘. Performance in pulsed photon fields was tested for varying dose rates from 0.1 Svh up to 1000 Svh and pulse durations from 1 ms up to 10 s. The dose measurement works well within the approval limits (acc. to IEC 61526) up to 1 Svh. No significant influence of the pulse duration on the measured dose is found. Reproducibility measurements yield a coefficient of variation which does not exceed 1 % for two tested eye lens dosemeter prototypes.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Active personal dosemeter; Detectors; Dosepix; Dosimetry; dosimetry for interventional procedures; dosimetry for radiation based medical applications; eye lens dosimetry; Histograms; Lenses; Phantoms; Photonics; Prototypes; pulsed x-ray fields; radiation detectors for medical applications: semiconductors

A Decade of Gamma-Ray Bursts Observed by Fermi-LAT: The Second GRB Catalog - Ajello, M.; Arimoto, M.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bhat, P. N.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bonnell, J.; et al. (Astrophysical Journal, 2019)
The Large Area Telescope (LAT) aboard the Fermi spacecraft routinely observes high-energy emission from gamma-ray bursts (GRBs). Here we present the second catalog of LAT-detected GRBs, covering the first 10 yr of operations, from 2008 to 2018 August 4. A total of 186 GRBs are found; of these, 91 show emission in the range 30-100 MeV (17 of which are seen only in this band) and 169 are detected above 100 MeV. Most of these sources were discovered by other instruments (Fermi/GBM, Swift/BAT, AGILE, INTEGRAL) or reported by the Interplanetary Network (IPN); the LAT has independently triggered on four GRBs. This catalog presents the results for all 186 GRBs. We study onset, duration, and temporal properties of each GRB, as well as spectral characteristics in the 100 MeV-100 GeV energy range. Particular attention is given to the photons with the highest energy. Compared with the first LAT GRB catalog, our rate of detection is significantly improved. The results generally confirm the main findings of the first catalog: the LAT primarily detects the brightest GBM bursts, and the high-energy emission shows delayed onset as well as longer duration. However, in this work we find delays exceeding 1 ks and several GRBs with durations over 10 ks. Furthermore, the larger number of LAT detections shows that these GRBs not only cover the high-fluence range of GBM-detected GRBs but also sample lower fluences. In addition, the greater number of detected GRBs with redshift estimates allows us to study their properties in both the observer and rest frames. Comparison of the observational results with theoretical predictions reveals that no model is currently able to explain all results, highlighting the role of LAT observations in driving theoretical models.
CRIS-Team WoS Importer:2019-06-28

Adsorption dynamics of CO2 on copper-precovered ZnO(0001)-Zn: A molecular-beam scattering and thermal-desorption spectroscopy study - Funk, Stefan; et al. (Journal of Chemical Physics, 2005)
Initial, S-0, as well as coverage-dependent adsorption probability measurements, S(Theta), have been conducted at normal impact angle and as a function of the impact energy of CO2, E-i, adsorption temperature, T-s, and copper precoverage, Theta(Cu) (at 300 K). S-0, which decreased from similar to 0.4 exponentially to similar to 0.05 with E-i was independent of Theta(Cu). Astonishingly, S-0 for Cu on ZnO(0001)-Zn is smaller than for the clean support which indicates a chemical modification of the support by the Cu deposits. S(Theta) curves consist of two regimes, a Kisliuk-type and Langmuirian-type section. The first is consistent with capture zone models; the second may indicate direct adsorption of CO2 on the Cu cluster. The thermal-desorption (TDS) curves for Cu on ZnO(0001)-Zn consist of two structures with binding energies of 26 and similar to 40 kJ/mol (nu=1x10(13) l/s). The TDS results indicate that CO2 populates predominantly the Cu deposits and the rim along the Cu nanoparticles. No indications for CO2 dissociation could be obtained with Auger electron spectroscopy. (c) 2005 American Institute of Physics.
CRIS-Team WoS Importer:2020-01-15

Advanced Analysis of Night Sky Background Light for SSTCAM - Spencer, Samuel; Watson, Jason; Giavitto, Gianluca; Cotter, Garret; White, Richard (arXiv, 2023)
Keywords: Instrumentation and Methods for Astrophysics (astro-ph.IM); High Energy Astrophysical Phenomena (astro-ph.HE); FOS: Physical sciences; FOS: Physical sciences

A fast alignment method for grating-based X-ray phase-contrast imaging systems - Schuster, Max; Ludwig, Veronika; Akstaller, Bernhard; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Neumayer, P.; Funk, Stefan; Anton, Gisela (Journal of Instrumentation, 2019)
The alignment of a grating-based X-ray phase-contrast interferometer is an iterative process that requires numerous steps of changing the distances and angles between the gratings. For each alignment step an image is acquired to evaluate the detected intensity signature in order to optimize the observed moir'e pattern. Thus, a large number of images has to be taken for the alignment procedure. This is not feasible within reasonable time at X-ray sources like X-ray backlighters where the time between two X-ray shots is on the scale of hours. Here, we report on the development of a stable and transportable setup ready-to-use for grating-based X-ray phase-contrast imaging. A comprehensive set of reference images taken at a continuous beam serves as a look-up table which enables the grating alignment within very few alignment steps. Since this method features a fast, reliable and predictable alignment, it is also beneficial for grating-based X-ray phase-contrast imaging systems at common X-ray sources.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

A gamma-ray determination of the Universe's star formation history - Abdollahi, S.; Ackermann, M.; Ajello, M.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; et al. (Science, 2018)
The light emitted by all galaxies over the history of the Universe produces the extragalactic background light (EBL) at ultraviolet, optical, and infrared wavelengths. The EBL is a source of opacity for gamma rays via photon-photon interactions, leaving an imprint in the spectra of distant gamma-ray sources. We measured this attenuation using 739 active galaxies and one gamma-ray burst detected by the Fermi Large Area Telescope. This allowed us to reconstruct the evolution of the EBL and determine the star formation history of the Universe over 90% of cosmic time. Our star formation history is consistent with independent measurements from galaxy surveys, peaking at redshift z similar to 2. Upper limits of the EBL at the epoch of reionization suggest a turnover in the abundance of faint galaxies at z similar to 6.
CRIS-Team WoS Importer:2020-01-15

A gamma-ray pulsar timing array constrains the nanohertz gravitational wave background - Ajello, M.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bhattacharyya, B.; Bissaldi, E.; Blandford, R. D.; Bloom, E.; et al. (Science, 2022)
After large galaxies merge, their central supermassive black holes are expected to form binary systems. Their orbital motion should generate a gravitational wave background (GWB) at nanohertz frequencies. Searches for this background use pulsar timing arrays, which perform long-term monitoring of millisecond pulsars at radio wavelengths. We used 12.5 years of Fermi Large Area Telescope data to form a gamma-ray pulsar timing array. Results from 35 bright gamma-ray pulsars place a 95% credible limit on the GWB characteristic strain of 1.0 x 10(-14) at a frequency of 1 year(-1). The sensitivity is expected to scale with t(obs), the observing time span, as t(obs)(-13/6). This direct measurement provides an independent probe of the GWB while offering a check on radio noise models.
CRIS-Team WoS Importer:2022-05-20

Air shower reconstruction using HAWC and the Outrigger array - Joshi, Vikas; Schoorlemmer, Harm (Proceedings of Science, 2019)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory detects cosmic- and gamma-ray initiated air showers in the TeV energy range using 300 water Cherenkov detectors (WCDs). To improve its sensitivity at the highest energies, HAWC has been upgraded with a sparse array of 345 small WCDs (outrigger array) around the HAWC main array. The outrigger array increases the instrumented area of HAWC by a factor of 4 and has started taking data since August 2018. A new gamma-ray reconstruction method has been developed to improve the reconstruction of the air showers which combines the data of mixed type particle detector arrays. In this contribution, we will show the first results of the combined air shower reconstruction of HAWC and its outrigger array using Monte Carlo simulations and the first combined experimental data set.
CRIS-Team Scopus Importer:2021-04-20

A MeerKAT, e-MERLIN, HESS, and Swift search for persistent and transient emission associated with three localized FRBs - Chibueze, J. O.; Caleb, M.; Spitler, L.; Ashkar, H.; Schussler, F.; Stappers, B. W.; Venter, C.; Heywood,; Richards, A. M. S.; Williams, D. R. A.; Kramer, M.; Beswick, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report on a search for persistent radio emission from the one-off fast radio burst (11(B) 20190714A, as well as from two repeating FRBs, 20190711A and 20171019A, using the MeerKAT radio telescope. For FRB 20171019A, we also conducted simultaneous observations with the High-Energy Stereoscopic System (H.E.S.S.) in very high-energy gamma rays and searched for signals in the ultraviolet, optical, and X-ray bands. For this FRB, we obtain a UV flux upper limit of 1.39 x 10(-16) erg cm(-2) s(-1) angstrom(-1), X-ray limit of similar to 6.6 x 10(-14) erg cm(-2) s(-1) and a limit on the very high energy gamma-ray flux Phi(E > 120 GeV) < 1.7 x 10(-12) erg cm(-2) S-1. We obtain a radio upper limit of similar to 15 mu Jy beam(-1) for persistent emission at the locations of both FRBs 20190711A and 20171019A with MeerKAT. However, we detected an almost unresolved (ratio of integrated flux to peak flux is similar to 1.7 beam) radio emission, where the synthesized beam size was similar to 8 arcsec size with a peak brightness of similar to 53 mu Jy beam(-1) at MeerKAT and similar to 86 mu Jy beam(-1) at e-MERLIN, possibly associated with FRB 20190714A at z = 0.2365. This represents the first detection of persistent continuum radio emission potentially associated with a (as-yet) non- repeating FRB. If the association is confirmed, one of the strongest remaining distinction between repeaters and non-repeaters would no longer be applicable. A parallel search for repeat bursts from these FRBs revealed no new detections down to a fluence of 0.08 Jy ms for a 1 ms duration burst.
CRIS-Team WoS Importer:2022-08-05

Analysis of the HESS public data release with ctools - Knodlseder, J.; Tibaldo, L.; Tiziani, Domenico; Specovius, Andreas; Cardenzana, J.; Mayer, M.; Kelley-Hoskins, N.; Di Venere, L.; Bonnefoy, S.; Ziegler, A.; Eschbach, Stefan; Martin, P.; et al. (Astronomy & Astrophysics, 2019)
The ctools open-source software package was developed for the scientific analysis of astronomical data from Imaging Air Cherenkov Telescopes (IACTs), such as H.E.S.S., VERITAS, MAGIC, and the future Cherenkov Telescope Array (CTA). To date, the software has been mainly tested using simulated CTA data; however, upon the public release of a small set of H.E.S.S. observations of the Crab nebula, MSH 15-52, RX J1713.7-3946, and PKS 2155-304 validation using real data is now possible. We analysed the data of the H.E.S.S. public data release using ctools version 1.6 and compared our results to those published by the H.E.S.S. Collaboration for the respective sources. We developed a parametric background model that satisfactorily describes the expected background rate as a function of reconstructed energy and direction for each observation. We used that model, and tested all analysis methods that are supported by ctools, including novel unbinned and joint or stacked binned analyses of the measured event energies and reconstructed directions, and classical On-Off analysis methods that are comparable to those used by the H.E.S.S. Collaboration. For all analysis methods, we found a good agreement between the ctools results and the H.E.S.S. Collaboration publications considering that they are not always directly comparable due to differences in the datatsets and event processing software. We also performed a joint analysis of H.E.S.S. and Fermi-LAT data of the Crab nebula, illustrating the multi-wavelength capacity of ctools. The joint Crab nebula spectrum is compatible with published literature values within the systematic uncertainties. We conclude that the ctools software is mature for the analysis of data from existing IACTs, as well as from the upcoming CTA.
CRIS-Team WoS Importer:2020-01-03

A new benchmark of soft X-ray transition energies of Ne , CO 2 , and SF 6 : paving a pathway towards ppm accuracy - Stierhof, Jakob; Kühn, S.; Winter, Mirko; Micke, P.; Steinbrügge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
Abstract: A key requirement for the correct interpretation of high-resolution X-ray spectra is that transition energies are known with high accuracy and precision. We investigate the K-shell features of Ne , CO 2, and SF 6 gases, by measuring their photo ion-yield spectra at the BESSY II synchrotron facility simultaneously with the 1s–np fluorescence emission of He-like ions produced in the Polar-X EBIT. Accurate ab initio calculations of transitions in these ions provide the basis of the calibration. While the CO 2 result agrees well with previous measurements, the SF 6 spectrum appears shifted by ∼ 0.5 eV, about twice the uncertainty of the earlier results. Our result for Ne shows a large departure from earlier results, but may suffer from larger systematic effects than our other measurements. The molecular spectra agree well with our results of time-dependent density functional theory. We find that the statistical uncertainty allows calibrations in the desired range of 1–10 meV, however, systematic contributions still limit the uncertainty to ∼ 40–100 meV, mainly due to the temporal stability of the monochromator energy scale. Combining our absolute calibration technique with a relative energy calibration technique such as photoelectron energy spectroscopy will be necessary to realize its full potential of achieving uncertainties as low as 1–10 meV. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-03-11

A new population of very high energy gamma-ray sources in the Milky Way - Funk, Stefan; et al. (Science, 2005)
Very high energy gamma-rays probe the long-standing mystery of the origin of cosmic rays. Produced in the interactions of accelerated particles in astrophysical objects, they can be used to image cosmic particle accelerators. A first-sensitive survey of the inner part of the Milky Way with the High Energy Stereoscopic System (HESS) reveals a population of eight previously unknown firmly detected sources of very high energy gamma-rays. At least two have no known radio or x-ray counterpart and may be representative of a new class of "dark" nucleonic cosmic ray sources.
CRIS-Team WoS Importer:2020-01-15

A new SNR with TeV shell-type morphology: HESS J1731-347 - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. The recent discovery of the radio shell-type supernova remnant (SNR), G353.6-0.7, in spatial coincidence with the unidentified TeV source HESS J1731-347 has motivated further observations of the source with the High Energy Stereoscopic System (HESS) Cherenkov telescope array to test a possible association of the γ-ray emission with the SNR. Methods. With a total of 59 h of observation, representing about four times the initial exposure available in the discovery paper of HESS J1731-347, the γ-ray morphology is investigated and compared with the radio morphology. An estimate of the distance is derived by comparing the interstellar absorption derived from X-rays and the one obtained from CO and HI observations. Results. The deeper γ-ray observation of the source has revealed a large shell-type structure with similar position and extension (r ∼ 0.25°) as the radio SNR, thus confirming their association. By accounting for the HESS angular resolution and projection effects within a simple shell model, the radial profile is compatible with a thin, spatially unresolved, rim. Together with RX J1713.7-3946, RX J0852.0-4622 and SN 1006, HESS J1731-347 is now the fourth SNR with a significant shell morphology at TeV energies. The derived lower limit on the distance of the SNR of 3.2 kpc is used together with radio and X-ray data to discuss the possible origin of the γ-ray emission, either via inverse Compton scattering of electrons or the decay of neutral pions resulting from proton-proton interaction. © 2011 ESO.
Keywords: Astroparticle physics; Cosmic rays; ISM: supernova remnants

An extremely bright gamma-ray pulsar in the Large Magellanic Cloud - Ackermann, Markus; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Barbieri, C.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Science, 2015)
Pulsars are rapidly spinning, highly magnetized neutron stars, created in the gravitational collapse of massive stars. We report the detection of pulsed giga-electron volt gamma rays from the young pulsar PSR J0540-6919 in the Large Magellanic Cloud, a satellite galaxy of the Milky Way. This is the first gamma-ray pulsar detected in another galaxy. It has the most luminous pulsed gamma-ray emission yet observed, exceeding the Crab pulsar's by a factor of 20. PSR J0540-6919 presents an extreme test case for understanding the structure and evolution of neutron star magnetospheres.
CRIS-Team WoS Importer:2020-01-15

A phase-sampling method for an X-ray Talbot-Lau scanner with continuous grating movement - Ludwig, Veronika; Akstaller, Bernhard; Schuster, Max; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Anton, Gisela (Journal of Instrumentation, 2020)
A Talbot-Lau scanner enables fast grating-based X-ray phase-contrast and dark-field imaging of large samples. We present a fast and robust scanning method based on continuous phase-sampling during the usual scan process. For that purpose the source grating is moved back and forth during the whole image acquisition procedure. The scanning method needs no specific detuning of the interferometer. The acquired images are compared to the results of a standard phase-stepping procedure. We show that high quality images are obtained by this continuous phase-sampling scanning method. One main advantage of the method is its independence of the occurring moir'e pattern shape, thus enabling an optimal alignment of the interferometer. Furthermore, the method works with a priori unknown phase-step positions. To our knowledge, this is the first time a grating is moved continuously back and forth while also the sample is in linear motion during a continuous image acquisition in Talbot-Lau imaging.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Data acquisition concepts; Inspection with x-rays; X-ray radiography and digital radiography (DR)

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

A possible association of the new VHE gamma-ray source HESS J1825-137 with the pulsar wind nebula G18.0-0.7 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We report on a possible association of the recently discovered very high-energy gamma-ray source HESSJ1825-137 wit the pulsar wind nebula (commonly referred to as G 18.0-0.7) of the 2.1 x 10(4) year old Vela-like pulsar PSRB1823-13.HESSJ1825-137 was detected with a significance of 8.1 sigma in the Galactic Plane survey conducted wit the HESS instrument in 2004. The centroid position of HESSJ1825-137 is offset by 11' south of the pulsar position. XMM-Newton observations have revealed X-ray synchrotron emission of an asymmetric pulsar wind nebula extending to the south of the pulsar. We argue that the observed morphology and TeV spectral index suggest that HESSJ1825-137 and G18.0-0.7 may be associated: the lifetime of TeV emitting electrons is expected to be longer compared to the XMM-Newton X-ray emitting electrons, resulting in electrons from earlier epochs (when the spin-down power was larger) contributing to the present TeV flux. These electrons are expected to be synchrotron cooled, which explains the observed photon index of similar to 2.4, and the longer lifetime of TeV emitting electrons naturally explains why the TeV nebula is larger that the X-ray size. Finally, supernova remnant expansion into an inhomogeneous medium is expected to create reverse shocks interacting at different times wit the pulsar wind nebula, resulting in the offset X-ray and TeV gamma-ray morphology.
CRIS-Team WoS Importer:2020-01-15

Application of deep learning methods to analysis of imaging atmospheric Cherenkov telescopes data - Shilon, Idan; Kraus, Michael; Büchele, Matthias; Egberts, K.; Fischer, T.; Holch, T. L.; Lohse, T.; Schwanke, U.; Steppa, C.; Funk, Stefan (Astroparticle Physics, 2019)
Ground based gamma-ray observations with Imaging Atmospheric Cherenkov Telescopes (IACTs) play a significant role in the discovery of very high energy (E > 100 GeV) gamma-ray emitters. The analysis of IACT data demands a highly efficient background rejection technique, as well as methods to accurately determine the position of its source in the sky and the energy of the recorded gamma-ray. We present results for background rejection and signal direction reconstruction from first studies of a novel data analysis scheme for IACT measurements. The new analysis is based on a set of Convolutional Neural Networks (CNNs) applied to images from the four H.E.S.S. phase-I telescopes. As the H.E.S.S. cameras pixels are arranged in a hexagonal array, we demonstrate two ways to use such image data to train CNNs: by resampling the images to a square grid and by applying modified convolution kernels that conserve the hexagonal grid properties.
CRIS-Team WoS Importer:2019-02-21

Application of deep learning methods to analysis of imaging atmospheric Cherenkov telescopes data - Shilon, Idan; Kraus, Michael; Büchele, Matthias; Egberts, K.; Fischer, T.; Holch, T. L.; Lohse, T.; Schwanke, U.; Steppa, C.; Funk, Stefan (Astroparticle Physics, 2019)
Ground based gamma-ray observations with Imaging Atmospheric Cherenkov Telescopes (IACTs) play a significant role in the discovery of very high energy (E > 100 GeV) gamma-ray emitters. The analysis of IACT data demands a highly efficient background rejection technique, as well as methods to accurately determine the position of its source in the sky and the energy of the recorded gamma-ray. We present results for background rejection and signal direction reconstruction from first studies of a novel data analysis scheme for IACT measurements. The new analysis is based on a set of Convolutional Neural Networks (CNNs) applied to images from the four H.E.S.S. phase-I telescopes. As the H.E.S.S. cameras pixels are arranged in a hexagonal array, we demonstrate two ways to use such image data to train CNNs: by resampling the images to a square grid and by applying modified convolution kernels that conserve the hexagonal grid properties.The networks were trained on sets of Monte-Carlo simulated events and tested on both simulations and measured data from the H.E.S.S. array. A comparison between the CNN analysis to current state-of-the-art algorithms reveals a clear improvement in background rejection performance. When applied to H.E.S.S. observation data, the CNN direction reconstruction performs at a similar level as traditional methods. These results serve as a proof-of-concept for the application of CNNs to the analysis of events recorded by IACTs. (C) 2018 Published by Elsevier B.V.
Keywords: Gamma-ray astronomy; IACT; Analysis technique; Deep learning; Convolutional neural networks; Recurrent neural networks

Application of graph networks to background rejection in Imaging Air Cherenkov Telescopes - Glombitza, Jonas; Joshi, Vikas; Bruno, Benedetta; Funk, Stefan (Journal of Cosmology and Astroparticle Physics, 2023)
Imaging Air Cherenkov Telescopes (IACTs) are essential to ground-based observations of gamma rays in the GeV to TeV regime. One particular challenge of ground-based gamma-ray astronomy is an effective rejection of the hadronic background. We propose a new deep-learning-based algorithm for classifying images measured using single or multiple Imaging Air Cherenkov Telescopes. We interpret the detected images as a collection of triggered sensors that can be represented by graphs and analyzed by graph convolutional networks. For images cleaned of the light from the night sky, this allows for an efficient algorithm design that bypasses the challenge of sparse images in deep learning approaches based on computer vision techniques such as convolutional neural networks. We investigate different graph network architectures and find a promising performance with improvements to previous machine-learning and deep-learning-based methods.
CRIS-Team Scopus Importer:2023-12-01
Keywords: cosmic rays detectors; gamma ray detectors; Machine learning

A search for a dark matter annihilation signal toward the Canis major overdensity with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, V.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astrophysical Journal, 2009)
A search for a dark matter (DM) annihilation signal into γ-rays toward the direction of the Canis Major (CMa) overdensity is presented. The nature of CMa is still controversial and one scenario represents it as a dwarf galaxy, making it an interesting candidate for DM annihilation searches. A total of 9.6 hr of high-quality data were collected with the H.E.S.S. array of Imaging Atmospheric Cherenkov Telescopes, and no evidence for a very high energy γ-ray signal is found. Upper limits on the CMa dwarf galaxy mass of the order of 10 M are derived at the 95% confidence level (CL) assuming neutralino masses in the range 500 GeV-10 TeV and relatively large annihilation cross sections. Constraints on the velocity-weighted annihilation cross section 〈σv〉 are calculated for specific weakly interacting massive-particle scenarios, using a Navarro-Frenk-White model for the DM halo profile and taking advantage of numerical simulations of hierarchical structure formation. Assuming a total halo mass of 3 × 10 M, 95% CL exclusion limits of the order of 5 × 10 cm s are reached in the 500 GeV-10 TeV DM particle mass interval. © 2009. The American Astronomical Society. All rights reserved..
Keywords: dark matter; galaxies: dwarf; gamma rays: observations

A Search for Cosmic-Ray Proton Anisotropy with the Fermi Large Area Telescope - Ajello, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bottacini, E.; Brandt, T. J.; Bruel, P.; et al. (Astrophysical Journal, 2019)
The Fermi Large Area Telescope (LAT) has amassed a large data set of primary cosmic-ray protons throughout its mission. In fact, it is the largest set of identified cosmic-ray protons ever collected at this energy. The LAT' s wide field of view and full-sky survey capabilities make it an excellent instrument for studying cosmic-ray anisotropy. As a space-based survey instrument, the LAT is sensitive to anisotropy in both R.A. and decl., while ground-based observations only measure the anisotropy in R.A. We present the results of the first-ever proton anisotropy search using Fermi LAT. The data set was collected over eight years and consists of approximately 179 million protons above 78 GeV, enabling it to probe dipole anisotropy below an amplitude of 10(-3), resulting in the most stringent limits on the decl. dependence of the dipole to date. We measure a dipole amplitude delta = 3.9 +/- 1.5 x 10(-4) with a p-value of 0.01 (pretrials) for protons with energy greater than 78 GeV. We discuss various systematic effects that could give rise to a dipole excess and calculate upper limits on the dipole amplitude as a function of minimum energy. The 95% confidence level upper limit on the dipole amplitude is delta(UL) = 1.3 x 10(-3) for protons with energy greater than 78 GeV and delta(UL )= 1.2 x 10(-3) for protons with energy greater than 251 GeV.
CRIS-Team WoS Importer:2019-10-11

A search for new sources below 100 MeV in the Fermi-LAT data - Principe, Giacomo; Malyshev, Dmitry; Ballet, J.; Funk, Stefan (REND LINCEI-SCI FIS, 2019)
The Fermi Large Area Telescope (LAT) has discovered more than 3000 sources between 100 MeV and 300 GeV (3FGL), including over 200 γ-ray pulsars. The majority of these pulsars have their spectral energy peaks (in νFν) above 1 GeV. There exists another population of very energetic, young rotation-powered pulsars having non-thermal hard X-ray emission with spectral energy distributions (SEDs) peaking around 1 MeV, but having no detected emission by Fermi LAT above 100 MeV. Previous analyses of point sources in the gamma ray range were done only below 30 MeV (COMPTEL) or above 100 MeV (Fermi-LAT). Below 30 MeV, the imaging Compton telescope (COMPTEL) detected 26 steady sources in the energy range from 0.75 to 30 MeV. Since the Fermi LAT detects gamma rays down to 20 MeV, we create a list of sources detected in the energy range between 30 MeV and 100 MeV, using PGWave, a background-independent tool that makes use of a wavelet transform. This closes a gap of point source analysis between the COMPTEL catalog and the Fermi-LAT catalog and provides information and constraint for this missing MeV pulsar population.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Gamma rays: general-catalog; Pulsars

A search for new supernova remnant shells in the Galactic plane with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
A search for new supernova remnants (SNRs) has been conducted using TeV gamma-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534-571. The TeV source is therefore classified as a SNR. For the other two sources, HESS J1614-518 and HESS J1912 + 101, no identifying counterparts have been found, thus they remain SNR candidates for the time being. TeV-emitting SNRs are key objects in the context of identifying the accelerators of Galactic cosmic rays. The TeV emission of the relativistic particles in the new sources is examined in view of possible leptonic and hadronic emission scenarios, taking the current multiwavelength knowledge into account.
CRIS-Team WoS Importer:2020-01-15

A search for very high energy gamma-ray emission from the starburst galaxy NGC253 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We present the result of 28 h of observations of the nearby starburst galaxy NGC 253 with the HESS detector in 2003. We find no evidence for very high energy gamma-ray emission from this object. Gamma-ray emission above 400 GeV from NGC 253 had been reported by the CANGAROO collaboration in 2002. From the HESS data we derive upper limits on the flux above 300 GeV of 1.9 x 10(-12) photons cm(-2) s(-1) for a point-like source and 6.3 x 10(-12) photons cm(-2) s(-1) for a source of radius 0.5 degrees as reported by CANGAROO, both at a confidence level of 99%. These upper limits are inconsistent with the spectrum reported by CANGAROO. The expected very high energy gamma-ray emission from this object is discussed in the framework of a galactic wind propagation model.
CRIS-Team WoS Importer:2020-01-15

A set of tools for determining the LAT performance in specific applications - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

ASSOCIATING LONG-TERM gamma-RAY VARIABILITY WITH THE SUPERORBITAL PERIOD OF LS I+61 degrees 303 - Ackermann, M.; Ajello, M.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bonamente, E.; Brandt, T. J.; Bregeon, J.; Brigida, M.; Bruel, P.; Buehler, R.; et al. (Astrophysical Journal Letters, 2013)
Gamma-ray binaries are stellar systems for which the spectral energy distribution (discounting the thermal stellar emission) peaks at high energies. Detected from radio to TeV gamma rays, the gamma-ray binary LS I + 61 degrees 303 is highly variable across all frequencies. One aspect of this system's variability is the modulation of its emission with the timescale set by the similar to 26.4960 day orbital period. Here we show that, during the time of our observations, the gamma-ray emission of LS I + 61 degrees 303 also presents a sinusoidal variability consistent with the previously known superorbital period of 1667 days. This modulation is more prominently seen at orbital phases around apastron, whereas it does not introduce a visible change close to periastron. It is also found in the appearance and disappearance of variability at the orbital period in the power spectrum of the data. This behavior could be explained by a quasi-cyclical evolution of the equatorial outflow of the Be companion star, whose features influence the conditions for generating gamma rays. These findings open the possibility to use gamma-ray observations to study the outflows of massive stars in eccentric binary systems.
Keywords: gamma rays: general; gamma rays: stars; stars: emission-line; Be

Astro-COLIBRI-The COincidence LIBrary for Real-time Inquiry for Multimessenger Astrophysics - Reichherzer, P.; Schuessler, F.; Lefranc, V.; Yusafzai, Anke; Alkan, A. K.; Ashkar, H.; Tjus, J. Becker (Astrophysical Journal Supplement Series, 2021)
Astro-COLIBRI is a novel tool that evaluates alerts of transient observations in real time, filters them by user-specified criteria, and puts them into their multiwavelength and multimessenger context. Through fast generation of an overview of persistent sources as well as transient events in the relevant phase space, Astro-COLIBRI contributes to an enhanced discovery potential of both serendipitous and follow-up observations of the transient sky. The software's architecture comprises a Representational State Transfer Application Programming Interface, both a static and a real-time database, a cloud-based alert system, as well as a website and apps for iOS and Android as clients for users. The latter provide a graphical representation with a summary of the relevant data to allow for the fast identification of interesting phenomena along with an assessment of observing conditions at a large selection of observatories around the world.
CRIS-Team WoS Importer:2021-09-10

A Survey of Active Galaxies at TeV Photon Energies with the HAWC Gamma-Ray Observatory - Albert, A.; Alvarez, C.; Camacho, J. R. Angeles; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory continuously detects TeV photons and particles within its large field of view, accumulating every day a deeper exposure of two-thirds of the sky. We analyzed 1523 days of HAWC live data acquired over four and a half years, in a follow-up analysis of 138 nearby (z < 0.3) active galactic nuclei from the Third Catalog of Hard Fermi-LAT sources culminating within 40 degrees of the zenith at Sierra Negra, the HAWC site. This search for persistent TeV emission used a maximum-likelihood analysis assuming intrinsic power-law spectra attenuated by pair production of gamma-ray photons with the extragalactic background light. HAWC clearly detects persistent emission from Mkn 421 and Mkn 501, the two brightest blazars in the TeV sky, at 65 sigma and 17 sigma level, respectively. Marginal evidence, just above the 3 sigma level, was found for three other known very high-energy emitters: the radio galaxy M87 and the BL Lac objects VER J0521+211 and 1ES 1215+303, the latter two at z similar to 0.1. We find a 4.2 sigma evidence for collective emission from the set of 30 previously reported very high-energy sources, with Mkn 421 and Mkn 501 excluded. Upper limits are presented for the sample under the power-law assumption and in the predefined (0.5-2.0), (2.0-8.0), and (8.0-32.0) TeV energy intervals.
CRIS-Team WoS Importer:2021-03-05

A very-high-energy component deep in the γ-ray burst afterglow - Abdalla, H.; Adam, R.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Barnard, M.; et al. (Nature, 2019)
Gamma-ray bursts (GRBs) are brief flashes of γ-rays and are considered to be the most energetic explosive phenomena in the Universe1. The emission from GRBs comprises a short (typically tens of seconds) and bright prompt emission, followed by a much longer afterglow phase. During the afterglow phase, the shocked outflow—produced by the interaction between the ejected matter and the circumburst medium—slows down, and a gradual decrease in brightness is observed2. GRBs typically emit most of their energy via γ-rays with energies in the kiloelectronvolt-to-megaelectronvolt range, but a few photons with energies of tens of gigaelectronvolts have been detected by space-based instruments3. However, the origins of such high-energy (above one gigaelectronvolt) photons and the presence of very-high-energy (more than 100 gigaelectronvolts) emission have remained elusive4. Here we report observations of very-high-energy emission in the bright GRB 180720B deep in the GRB afterglow—ten hours after the end of the prompt emission phase, when the X-ray flux had already decayed by four orders of magnitude. Two possible explanations exist for the observed radiation: inverse Compton emission and synchrotron emission of ultrarelativistic electrons. Our observations show that the energy fluxes in the X-ray and γ-ray range and their photon indices remain comparable to each other throughout the afterglow. This discovery places distinct constraints on the GRB environment for both emission mechanisms, with the inverse Compton explanation alleviating the particle energy requirements for the emission observed at late times. The late timing of this detection has consequences for the future observations of GRBs at the highest energies.
CRIS-Team Scopus Importer:2019-12-03

Azimuthal single- and double-spin asymmetries in semi-inclusive deep-inelastic lepton scattering by transversely polarized protons - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Avakian, R.; Bacchetta, A.; Belostotski, S.; Bryzgalov,; Capitani, G. P.; Cisbani, E.; Ciullo, G.; et al. (Journal of High Energy Physics, 2020)
A comprehensive set of azimuthal single-spin and double-spin asymmetries in semi-inclusive leptoproduction of pions, charged kaons, protons, and antiprotons from transversely polarized protons is presented. These asymmetries include the previously published HERMES results on Collins and Sivers asymmetries, the analysis of which has been extended to include protons and antiprotons and also to an extraction in a three-dimensional kinematic binning and enlarged phase space. They are complemented by corresponding results for the remaining four single-spin and four double-spin asymmetries allowed in the one-photon-exchange approximation of the semi-inclusive deep-inelastic scattering process for target-polarization orientation perpendicular to the direction of the incoming lepton beam. Among those results, significant non-vanishing cos (phi-phi(S)) modulations provide evidence for a sizable worm-gear (II) distribution, g(1T)(q) (x, p(T)(2)). Most of the other modulations are found to be consistent with zero with the notable exception of large sin (phi(S)) modulations for charged pions and K+.
CRIS-Team WoS Importer:2021-01-22

Background modelling in very-high-energy gamma-ray astronomy - Funk, Stefan; et al. (Astronomy & Astrophysics, 2007)
Ground based Cherenkov telescope systems measure astrophysical gamma-ray emission against a background of cosmic-ray induced air showers. The subtraction of this background is a major challenge for the extraction of spectra and morphology of gamma-ray sources.
CRIS-Team WoS Importer:2020-01-15

Background rejection using image residuals from large telescopes in imaging atmospheric Cherenkov telescope arrays - Olivera-Nieto, L.; Ren, H. X.; Mitchell, Alison; Marandon, V.; Hinton, J. A. (European Physical Journal C: Particles and Fields, 2022)
Identification of Cherenkov light generated by muons has been suggested as a promising way to dramatically improve the background rejection power of Imaging Atmospheric Cherenkov Telescope (IACT) arrays at high energies. However, muon identification remains a challenging task, for which efficient algorithms are still being developed. We present an approach in which, rather than identifying Cherenkov light from muons, we simply consider the presence of Cherenkov light other than the main shower image in IACTs with large mirror area. We show that in the case of the H.E.S.S. array of five telescopes this approach results in background rejection improvements at all energies above 1 TeV. In particular, the rejection power can be improved by a factor ∼3–4 at energies above 20 TeV while keeping ∼90% of the original gamma-ray efficiency.
CRIS-Team Scopus Importer:2022-12-23

Beam-helicity asymmetries for single-hadron production in semi-inclusive deep-inelastic scattering from unpolarized hydrogen and deuterium targets - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Belostotski, S.; Blok, H. P.; Bryzgalov, V.; Capitani, G. P.; Cisbani, E.; Ciullo, G.; Contalbrigo, M.; et al. (Physics Letters B, 2019)
A measurement of beam-helicity asymmetries for single-hadron production in deep-inelastic scattering is presented. Data from the scattering of 27.6 GeV electrons and positrons off gaseous hydrogen and deuterium targets were collected by the HERMES experiment. The asymmetries are presented separately as a function of the Bjorken scaling variable, the hadron transverse momentum, and the fractional energy for charged pions and kaons as well as for protons and anti-protons. These asymmetries are also presented as a function of the three aforementioned kinematic variables simultaneously.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Beam-helicity asymmetries; Deep-inelastic scattering; Nucleon structure; Transverse-momentum dependence; Twist-3

Calibration of cameras of the HESS detector - Funk, Stefan; et al. (Astroparticle Physics, 2004)
H.E.S.S.-the high energy stereoscopic system-is a new system of large atmospheric Cherenkov telescopes for GeV/ TeV astronomy. Each of the four telescopes of 107 m(2) mirror area is equipped with a 960-pixel photomultiplier-tube camera. This paper describes the methods used to convert the photomultiplier signals into the quantities needed for Cherenkov image analysis. Two independent calibration techniques have been applied in parallel to provide an estimation of uncertainties. Results on the long-term stability of the H.E.S.S. cameras are also presented. (C) 2004 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Catalog of Long-term Transient Sources in the First 10 yr of Fermi-LAT Data - Baldini, Luca; Ballet, J.; Bastieri, Denis; Becerra Gonzalez, J.; Bellazzini, R.; Berretta, A.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; Bruel, P.; et al. (Astrophysical Journal Supplement Series, 2021)
We present the first Fermi Large Area Telescope (LAT) catalog of long-term gamma-ray transient sources (1FLT). This comprises sources that were detected on monthly time intervals during the first decade of Fermi-LAT operations. The monthly timescale allows us to identify transient and variable sources that were not yet reported in other Fermi-LAT catalogs. The monthly data sets were analyzed using a wavelet-based source detection algorithm that provided the candidate new transient sources. The search was limited to the extragalactic regions of the sky to avoid the dominance of the Galactic diffuse emission at low Galactic latitudes. The transient candidates were then analyzed using the standard Fermi-LAT maximum likelihood analysis method. All sources detected with a statistical significance above 4 sigma in at least one monthly bin were listed in the final catalog. The 1FLT catalog contains 142 transient gamma-ray sources that are not included in the 4FGL-DR2 catalog. Many of these sources (102) have been confidently associated with active galactic nuclei (AGNs): 24 are associated with flat-spectrum radio quasars, 1 with a BL Lac object, 70 with blazars of uncertain type, 3 with radio galaxies, 1 with a compact steep-spectrum radio source, 1 with a steep-spectrum radio quasar, and 2 with AGNs of other types. The remaining 40 sources have no candidate counterparts at other wavelengths. The median gamma-ray spectral index of the 1FLT-AGN sources is softer than that reported in the latest Fermi-LAT AGN general catalog. This result is consistent with the hypothesis that detection of the softest gamma-ray emitters is less efficient when the data are integrated over year-long intervals.
CRIS-Team WoS Importer:2021-09-24

Chandra and HESS observations of the supernova remnant CTB 37B - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel; et al. (Astronomy & Astrophysics, 2008)
We discovered the > 100 GeV γ-ray source, HESS J1713-381, apparently associated with the shell-type supernova remnant (SNR) CTB 37B, using HESS in 2006. In 2007 we performed X-ray follow-up observations with Chandra with the aim of identifying a synchrotron counterpart to the TeV source and/or thermal emission from the SNR shell. These new Chandra data, together with additional TeV data, allow us to investigate the nature of this object in much greater detail than was previously possible. The new X-ray data reveal thermal emission from a ∼4′ region in close proximity to the radio shell of CTB 37B. The temperature of this emission implies an age for the remnant of ∼5000 years and an ambient gas density of ∼0.5 cm. Both these estimates are considerably uncertain due to the asymmetry of the SNR and possible modifications of the kinematics due to efficient cosmic ray (CR) acceleration. A bright (≈7 × 10 erg cm s) and unresolved (<1″) source (CXOUJ17.1405.7-381031), with a soft (Γ ≈ 3.3) non-thermal spectrum is also detected in coincidence with the radio shell. Absorption indicates a column density consistent with the thermal emission from the shell, suggesting a genuine association rather than a chance alignment. The observed TeV morphology is consistent with an origin in the complete shell of CTB 37B. The lack of diffuse non-thermal X-ray emission suggests an origin of the γ-ray emission via the decay of neutral pions produced in interactions of protons and nuclei, rather than inverse Compton (IC) emission from relativistic electrons. © ESO 2008.
Keywords: Gamma rays: observations; ISM: supernova remnants; X-rays: individuals: G348.7+0.3

Characterisation and testing of CHEC-M-A camera prototype for the small-sized telescopes of the Cherenkov telescope array - Zorn, J.; White, Richard; Watson, J. J.; Armstrong, T. P.; Balzer, A.; Barcelo, M.; Berge, D.; Bose, R.; Brown, A. M.; Bryan, M.; Chadwick, P. M.; Clark, Paul; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
The Compact High Energy Camera (CHEC) is a camera design for the Small-Sized Telescopes (SSTs; 4 m diameter mirror) of the Cherenkov Telescope Array (CTA). The SSTs are focused on very-high-energy gamma-ray detection via atmospheric Cherenkov light detection over a very large area. This implies many individual units and hence cost-effective implementation, as well as shower detection at large impact distance, and hence large field of view (FoV), and efficient image capture in the presence of large time gradients in the shower image detected by the camera. CHEC relies on dual-mirror optics to reduce the plate-scale and make use of 6 x 6 mm(2) pixels, leading to a low-cost (similar to 150 k(sic)), compact (0.5 m x 0.5 m), and light (similar to 45 kg) camera with 2048 pixels providing a camera FoV of similar to 9 degrees. The CHEC electronics are based on custom TARGET (TeV array readout with GSa/s sampling and event trigger) application-specific integrated circuits (ASICs) and field programmable gate arrays (FPGAs) sampling incoming signals at a gigasample per second, with flexible camera-level triggering within a single backplane FPGA. CHEC is designed to observe in the gamma-ray energy range of 1-300 TeV, and at impact distances up to similar to 500 m. To accommodate this and provide full flexibility for later data analysis, full waveforms with 96 samples for all 2048 pixels can be read out at rates up to similar to 900 Hz. The first prototype, CHEC-M, based on mull-anode photomultipliers (MAPMs) as photosensors, was commissioned and characterised in the laboratory and during two measurement campaigns on a telescope structure at the Paris Observatory in Meudon. In this paper, the results and conclusions from the laboratory and on-site testing of CHEC-M are presented. They have provided essential input on the system design and on operational and data analysis procedures for a camera of this type. A second full-camera prototype based on Silicon photomultipliers (SiPMs), addressing the drawbacks of CHEC-M identified during the first prototype phase, has already been built and is currently being commissioned and tested in the laboratory.
CRIS-Team WoS Importer:2020-01-15
Keywords: Full-waveform readout; Cherenkov telescope array; Imaging atmospheric Cherenkov telescopes; Gamma-rays

Characterising the VHE diffuse emission in the central 200 parsecs of our Galaxy with H.E.S.S. - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
The diffuse very high-energy (VHE; > 100 GeV) gamma-ray emission observed in the central 200 pc of the Milky Way by H.E.S.S. was found to follow dense matter distribution in the central molecular zone (CMZ) up to a longitudinal distance of about 130 pc to the Galactic centre (GC), where the flux rapidly decreases. This was initially interpreted as the result of a burst-like injection of energetic particles 104 yr ago, but a recent more sensitive H.E.S.S. analysis revealed that the cosmic-ray (CR) density profile drops with the distance to the centre, making data compatible with a steady cosmic PeVatron at the GC. In this paper, we extend this analysis to obtain, for the first time, a detailed characterisation of the correlation with matter and to search for additional features and individual gamma-ray sources in the inner 200 pc. Taking advantage of 250 h of H.E.S.S. data and improved analysis techniques, we perform a detailed morphology study of the diffuse VHE emission observed from the GC ridge and reconstruct its total spectrum. To test the various contributions to the total gamma-ray emission, we used an iterative 2D maximum-likelihood approach that allows us to build a phenomenological model of the emission by summing a number of different spatial components. We show that the emission correlated with dense matter covers the full CMZ and that its flux is about half the total diffuse emission flux. We also detect some emission at higher latitude that is likely produced by hadronic collisions of CRs in less dense regions of the GC interstellar medium. We detect an additional emission component centred on the GC and extending over about 15 pc that is consistent with the existence of a strong CR density gradient and confirms the presence of a CR accelerator at the very centre of our Galaxy. We show that the spectrum of full ridge diffuse emission is compatible with that previously derived from the central regions, suggesting that a single population of particles fills the entire CMZ. Finally, we report the discovery of a VHE gamma-ray source near the GC radio arc and argue that it is produced by the pulsar wind nebula candidate G0.13-0.11.
Keywords: gamma rays: general; gamma rays: ISM; Galaxy: center; cosmic rays

Characterization of a prototype imaging calorimeter for the Advanced Particle-astrophysics Telescope from an Antarctic balloon flight and CERN beam test - Hughes, Zachary; Alnussirat, S.; Altomare, C.; Bose, R. G.; Braun, D.; Buckley, J. H.; Buhler, J. D.; Burns, E.; Chamberlain, R. D.; Chen, W.; Cherry, M. L.; Di Venere, L.; et al. (Proceedings of Science, 2022)
We report the results and analysis methods from field-testing the imaging calorimeter prototype for the Advanced Particle-astrophysics Telescope (APT) through an antarctic balloon flight (in the 2019 austral Antarctic balloon season) and through a CERN heavy-ion beam test in 2018. The Advanced Particle-astrophysics Telescope is a proposed space-based gamma- and cosmic-ray instrument that utilizes a novel distributed imaging calorimeter for both particle tracking and energy reconstruction. The imaging CsI calorimeter (ICC) consists of a CsI:Na scintillator read out by (WLS) fibers in both the x- and y-planes. To function both as a gamma-ray and cosmic-ray instrument APT must operate over a large dynamic range, from the single photon-election regime for low energy gamma-ray events to high-Z cosmic-ray events. Analysis of data from a 150 mm x 150 mm prototype instrument (APTlite) on a piggy-back flight on the 2019 SuperTIGER-2.3 balloon instrument provided cosmic ray data that were used to demonstrate the key detector and electronics elements of the ICC. Significantly, analysis of flight data demonstrated the large dynamic range of the instrument, showing the possibility to reconstruct the nuclear charge through analysis of the scintillation tail of saturating high-Z cosmic-ray events by utilizing the deep memory depth available to the TARGET waveform digitizer electronics. Spatial reconstruction of events was performed using a two-sided Voigt profile demonstrating position localization within the imaging calorimeter plane to less 3 WLS fiber widths. Charge resolution was evaluated on a 50 mm x 50 mm prototype placed in the 150 GeV/nuc, A/Z = 2.2 CERN SPS beam line. Nuclei were tagged using HNX/TIGERISS silicon-strip detectors and silicon pad detectors, which allowed for fragmentation cuts in the data. The vastly saturating signals were reconstructed from the CsI:Na scintillation tail and show an APT charge resolution up to Z = 11 (with experimental limitations preventing full evaluation for Z larger 11) and demonstrated no significant non-linearity in the Z2 measurement derived from the CsI:Na optical signal response up to Z = 82.
CRIS-Team Scopus Importer:2022-12-23

Characterizing the γ-ray long-term variability of PKS 2155 - 304 with H.E.S.S. and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Studying the temporal variability of BL Lac objects at the highest energies provides unique insights into the extreme physical processes occurring in relativistic jets and in the vicinity of super-massive black holes. To this end, the long-term variability of the BL Lac object PKS 2155 304 is analyzed in the high (HE, 100MeV < E < 300 GeV) and very high energy (VHE, E > 200 GeV) gamma-ray domain. Over the course of similar to 9 yr of H. E. S. S. observations the VHE light curve in the quiescent state is consistent with a log-normal behavior. The VHE variability in this state is well described by flicker noise (power-spectral-density index beta(VHE) = 1 .10(+ 0 : 10) (0 : 13)) on timescales larger than one day. An analysis of similar to 5.5 yr of HE Fermi-LAT data gives consistent results (beta(HE) = 1 : 20(+ 0 : 21) (0 : 23), on timescales larger than 10 days) compatible with the VHE findings. The HE and VHE power spectral densities show a scale invariance across the probed time ranges. A direct linear correlation between the VHE and HE fluxes could neither be excluded nor firmly established. These long-term-variability properties are discussed and compared to the red noise behavior (beta similar to 2) seen on shorter timescales during VHE-flaring states. The difference in power spectral noise behavior at VHE energies during quiescent and flaring states provides evidence that these states are influenced by different physical processes, while the compatibility of the HE and VHE long-term results is suggestive of a common physical link as it might be introduced by an underlying jet-disk connection.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Comparing different approaches for stellar intensity interferometry - Karl, Sebastian; Zmija, Andreas; Richter, Stefan; Vogel, Naomi; Malyshev, Dmitry; Zink, Adrian; Michel, Thilo; Anton, Gisela; von Zanthier, Joachim; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Stellar intensity interferometers correlate photons within their coherence time and could overcome the baseline limitations of existing amplitude interferometers. Intensity interferometers do not rely on phase coherence of the optical elements and thus function without high-grade optics and light combining delay lines. However, the coherence time of starlight observed with realistic optical filter bandwidths (> 0.1 nm) is usually much smaller than the time resolution of the detection system (> 10 ps), resulting in a greatly reduced correlation signal. Reaching high signal-to-noise ratio in a reasonably short measurement time can be achieved in different ways: either by increasing the time resolution, which increases the correlation signal height, or by increasing the photon rate, which decreases statistical uncertainties of the measurement. We present laboratory measurements employing both approaches and directly compare them in terms of signal-to-noise ratio. A high-time-resolution interferometry setup designed for small-to-intermediate-sized optical telescopes and thus lower photon rates (diameters < some metres) is compared to a setup capable of measuring high photon rates, which is planned to be installed at Cherenkov telescopes with dish diameters of > 10 m. We use a xenon lamp as a common light source simulating starlight. Both setups measure the expected correlation signal and work at the expected shot-noise limit of statistical uncertainties for measurement times between 10 min and 23 h. We discuss the quantitative differences in the measurement results and give an overview of suitable operation regimes for each of the interferometer concepts.
CRIS-Team WoS Importer:2022-04-08
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; telescopes; stars: imaging

Complementarity of dark matter searches in the phenomenological MSSM - Cahill-Rowley, M.; Cotta, R.; Drlica-Wagner, A.; Funk, Stefan; Hewett, J. L.; Ismail, A.; Rizzo, T. G.; Wood, M. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2015)
As is well known, the search for and eventual identification of dark matter in supersymmetry requires a simultaneous, multipronged approach with important roles played by the LHC as well as both direct and indirect dark matter detection experiments. We examine the capabilities of these approaches in the 19-parameter phenomenological MSSM which provides a general framework for complementarity studies of neutralino dark matter. We summarize the sensitivity of dark matter searches at the 7 and 8 (and eventually 14) TeV LHC, combined with those by Fermi, CTA, IceCube/DeepCore, COUPP, LZ and XENON. The strengths and weaknesses of each of these techniques are examined and contrasted and their interdependent roles in covering the model parameter space are discussed in detail. We find that these approaches explore orthogonal territory and that advances in each are necessary to cover the supersymmetric weakly interacting massive particle parameter space. We also find that different experiments have widely varying sensitivities to the various dark matter annihilation mechanisms, some of which would be completely excluded by null results from these experiments.

Constraining the cosmic-ray pressure in the inner Virgo Cluster using H.E.S.S. observations of M 87 - Aharonian, F.; Ait Benkhali, F.; Arcaro, C.; Aschersleben, J.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
The origin of the gamma-ray emission from M 87 is currently a matter of debate. This work aims to localize the very high-energy (VHE; 100 GeV - 100 TeV) gamma-ray emission from M 87 and probe a potential extended hadronic emission component in the inner Virgo Cluster. The search for a steady and extended gamma-ray signal around M 87 can constrain the cosmic-ray energy density and the pressure exerted by the cosmic rays onto the intracluster medium and allow us to investigate the role of cosmic rays in the active galactic nucleus feedback as a heating mechanism in the Virgo Cluster. The High Energy Stereoscopic System (H.E.S.S.) telescopes are sensitive to VHE gamma rays and have been used to observe M 87 since 2004. We utilized a Bayesian block analysis to identify M 87 emission states with H.E.S.S. observations from 2004 to 2021, dividing them into low, intermediate, and high states. Because of the causality argument, an extended (≳1 kpc) signal is allowed only in steady emission states. Hence, we fitted the morphology of the 120 h low-state data and find no significant gamma-ray extension. Therefore, we derive for the low state an upper limit of 58′ (corresponding to ≈4.6 kpc) in the extension of a single-component morphological model described by a rotationally symmetric 2D Gaussian model at the 99.7% confidence level. Our results exclude the radio lobes (≈30 kpc) as the principal component of the VHE gamma-ray emission from the low state of M 87. The gamma-ray emission is compatible with a single emission region at the radio core of M 87. These results, with the help of two multiple-component models, constrain the maximum cosmic-ray to thermal pressure ratio to XCR, max.≲0.32 and the total energy in cosmic-ray protons to UCR ≲ 5×1058 erg in the inner 20 kpc of the Virgo Cluster for an assumed cosmic-ray proton power-law distribution in momentum with spectral index αp=2.1.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Astroparticle physics; Galaxies: clusters: intracluster medium; Gamma rays: galaxies: clusters; Radio continuum: galaxies

Constraining the local burst rate density of primordial black holes with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Journal of Cosmology and Astroparticle Physics, 2020)
Primordial Black Holes (PBHs) may have been created by density fluctuations in the early Universe and could be as massive as > 109 solar masses or as small as the Planck mass. It has been postulated that a black hole has a temperature inversely-proportional to its mass and will thermally emit all species of fundamental particles via Hawking Radiation. PBHs with initial masses of ∼ 5 × 1014 g (approximately one gigaton) should be expiring today with bursts of high-energy gamma radiation in the GeV-TeV energy range. The High Altitude Water Cherenkov (HAWC) Observatory is sensitive to gamma rays with energies of ∼300 GeV to past 100 TeV, which corresponds to the high end of the PBH burst spectrum. With its large instantaneous field-of-view of ∼ 2 sr and a duty cycle over 95%, the HAWC Observatory is well suited to perform an all-sky search for PBH bursts. We conducted a search using 959 days of HAWC data and exclude the local PBH burst rate density above 3400 pc-3 yr-1 at 99% confidence, the strongest limit on the local PBH burst rate density from any existing electromagnetic measurement.
CRIS-Team Scopus Importer:2020-05-22

Constraints on an annihilation signal from a core of constant dark matter density around the milky way center with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review Letters, 2015)

Constraints on axionlike particles with H.E.S.S. from the irregularity of the PKS 2155-304 energy spectrum - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2013)
Axionlike particles (ALPs) are hypothetical light (sub-eV) bosons predicted in some extensions of the Standard Model of particle physics. In astrophysical environments comprising high-energy gamma rays and turbulent magnetic fields, the existence of ALPs can modify the energy spectrum of the gamma rays for a sufficiently large coupling between ALPs and photons. This modification would take the form of an irregular behavior of the energy spectrum in a limited energy range. Data from the H.E.S.S. observations of the distant BL Lac object PKS 2155-304 (z=0.116) are used to derive upper limits at the 95% C.L. on the strength of the ALP coupling to photons, g<2. 1×1011 GeV1 for an ALP mass between 15 and 60 neV. The results depend on assumptions on the magnetic field around the source, which are chosen conservatively. The derived constraints apply to both light pseudoscalar and scalar bosons that couple to the electromagnetic field. © 2013 American Physical Society.

Constraints on Lorentz Invariance Violation from HAWC Observations of Gamma Rays above 100 TeV - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Physical Review Letters, 2020)
Because of the high energies and long distances to the sources, astrophysical observations provide a unique opportunity to test possible signatures of Lorentz invariance violation (LIV). Superluminal LIV enables the decay of photons at high energy. The high altitude water Cherenkov (HAWC) observatory is among the most sensitive gamma-ray instruments currently operating above 10 TeV. HAWC finds evidence of 100 TeV photon emission from at least four astrophysical sources. These observations exclude, for the strongest of the limits set, the LIV energy scale to 2.2 x 10(31) eV, over 1800 times the Planck energy and an improvement of 1 to 2 orders of magnitude over previous limits.
CRIS-Team WoS Importer:2020-04-14

CONSTRAINTS ON THE COSMIC-RAY DENSITY GRADIENT BEYOND THE SOLAR CIRCLE FROM FERMI gamma-RAY OBSERVATIONS OF THE THIRD GALACTIC QUADRANT (vol 726, pg 81, 2011) - Ackermann, M.; Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Berenji, B.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2013)

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

CONSTRAINTS ON THE GALACTIC POPULATION OF TeV PULSAR WIND NEBULAE USING FERMI LARGE AREA TELESCOPE OBSERVATIONS - Acero, F.; Ackermann, M.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2013)
Pulsar wind nebulae (PWNe) have been established as the most populous class of TeV gamma-ray emitters. Since launch, the Fermi Large Area Telescope (LAT) has identified five high-energy (100 MeV < E < 100 GeV) gamma-ray sources as PWNe and detected a large number of PWN candidates, all powered by young and energetic pulsars. The wealth of multi-wavelength data available and the new results provided by Fermi-LAT give us an opportunity to find new PWNe and to explore the radiative processes taking place in known ones. The TeV gamma-ray unidentified (UNID) sources are the best candidates for finding new PWNe. Using 45 months of Fermi-LAT data for energies above 10 GeV, an analysis was performed near the position of 58 TeV PWNe and UNIDs within 5. of the Galactic plane to establish new constraints on PWN properties and find new clues on the nature of UNIDs. Of the 58 sources, 30 were detected, and this work provides their gamma-ray fluxes for energies above 10 GeV. The spectral energy distributions and upper limits, in the multi-wavelength context, also provide new information on the source nature and can help distinguish between emission scenarios, i.e., between classification as a pulsar candidate or as a PWN candidate. Six new GeV PWN candidates are described in detail and compared with existing models. A population study of GeV PWN candidates as a function of the pulsar/PWN system characteristics is presented.
Keywords: gamma rays: general

Constraints on the gamma-ray emission from the cluster-scale AGN outburst in the Hydra A galaxy cluster - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Context. In some galaxy clusters, powerful active galactic nuclei (AGN) have blown bubbles with cluster scale extent into the ambient medium. The main pressure support of these bubbles is not known to date, but cosmic rays are a viable possibility. For such a scenario copious gamma-ray emission is expected as a tracer of cosmic rays from these systems. Aims. Hydra A, the closest galaxy cluster hosting a cluster scale AGN outburst, located at a redshift of 0.0538, is investigated for being a gamma-ray emitter with the High Energy Stereoscopic System (H.E.S.S.) array and the Fermi Large Area Telescope (Fermi-LAT). Methods. Data obtained in 20.2 h of dedicated H.E.S.S. observations and 38 months of Fermi-LAT data, gathered by its usual all-sky scanning mode, have been analyzed to search for a gamma-ray signal. Results. No signal has been found in either data set. Upper limits on the gamma-ray flux are derived and are compared to models. These are the first limits on gamma-ray emission ever presented for galaxy clusters hosting cluster scale AGN outbursts. Conclusions. The non-detection of Hydra A in gamma-rays has important implications on the particle populations and physical conditions inside the bubbles in this system. For the case of bubbles mainly supported by hadronic cosmic rays, the most favorable scenario, which involves full mixing between cosmic rays and embedding medium, can be excluded. However, hadronic cosmic rays still remain a viable pressure support agent to sustain the bubbles against the thermal pressure of the ambient medium. The largest population of highly-energetic electrons, which are relevant for inverse-Compton gamma-ray production is found in the youngest inner lobes of Hydra A. The limit on the inverse-Compton gamma-ray flux excludes a magnetic field below half of the equipartition value of 16 μG in the inner lobes. © 2012 ESO.
Keywords: Galaxies: active; Galaxies: clusters: individual: Hydra A; Gamma rays: galaxies: clusters

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations - Aharonian, F.; Aschersleben, J.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bi, B.; Bouyahiaoui, M.; Breuhaus, M.; Brose, R.; Brun, F.; et al. (Astrophysical Journal Letters, 2023)

Constraints on the multi-TeV particle population in the Coma galaxy cluster with HESS observations - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Brion, E.; et al. (Astronomy & Astrophysics, 2009)
Alms. Galaxy clusters are key targets in the search for ultra high energy particle accelerators. The Coma cluster represents one of the best candidates for such a search owing to its high mass, proximity, and the established non-thermal radio emission centred on the cluster core. Methods. The HESS (High Energy Stereoscopic System) telescopes observed Coma for ∼8 h in a search for γ-ray emission at energies >1 TeV. The large 3.5° FWHM field of view of HESS is ideal for viewing a range of targets at various sizes including the Coma cluster core, the radio-relic (1253+275) and merger/infall (NGC 4839) regions to the southwest, and features greater than 1° away. Results. No evidence for point-like nor extended TeV γ-ray emission was found and upper limits to the TeV flux F(E) for E > 1, >5, and > 10 TeV were set for the Coma core and other regions. Converting these limits to an energy flux E F(E) the lowest or most constraining is the E > 5 TeV upper limit for the Coma core (0.2° radius) at ∼8% Crab flux units or ∼10 ph cm s . Conclusions. The upper limits for the Coma core were compared with a prediction for the γ-ray emission from proton-proton interactions, the level of which ultimately scales with the mass of the Coma cluster. A direct constraint using our most stringent limit for E > 5 TeV, on the total energy content in non-thermal protons with injection energy spectrum αE and spatial distribution following the thermal gas in the cluster, is found to be ∼0.2 times the thermal energy, or ∼10 erg. The E > 5 TeV γ-ray threshold in this case corresponds to cosmic- ray proton energies ≳50 TeV. Our upper limits rule out the most optimistic theoretical models for gamma ray emission from clusters and complement radio observations which constrain the cosmic ray content in clusters at significantly lower proton energies, subject to assumptions on the magnetic field strength. ©ESO 2009.
Keywords: Galaxies: Clusters: Individual: Coma (ACO 1656); Gamma rays: Observations

Cosmic-ray electron-positron spectrum from 7 GeV to 2 TeV with the Fermi Large Area Telescope - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bloom, E. D.; Bonino, Raffaella; Brandt, T. J.; Bregeon, J.; et al. (Physical Review D, 2017)
We present a measurement of the cosmic-ray electron + positron spectrum between 7 GeV and 2 TeV performed with almost seven years of data collected with the Fermi Large Area Telescope. We find that the spectrum is well fit by a broken power law with a break energy at about 50 GeV. Above 50 GeV, the spectrum is well described by a single power law with a spectral index of 3.07 +/- 0.02 (stat +/- syst) +/- 0.04 (energy measurement). An exponential cutoff lower than 1.8 TeV is excluded at 95% CL.
CRIS-Team WoS Importer:2020-01-15

Cosmic Ray Processes in Galactic Ecosystems - Owen, Ellis R.; Wu, Kinwah; Inoue, Yoshiyuki; Yang, H. Y.Karen; Mitchell, Alison (Galaxies, 2023)
Galaxy evolution is an important topic, and our physical understanding must be complete to establish a correct picture. This includes a thorough treatment of feedback. The effects of thermal–mechanical and radiative feedback have been widely considered; however, cosmic rays (CRs) are also powerful energy carriers in galactic ecosystems. Resolving the capability of CRs to operate as a feedback agent is therefore essential to advance our understanding of the processes regulating galaxies. The effects of CRs are yet to be fully understood, and their complex multi-channel feedback mechanisms operating across the hierarchy of galaxy structures pose a significant technical challenge. This review examines the role of CRs in galaxies, from the scale of molecular clouds to the circumgalactic medium. An overview of their interaction processes, their implications for galaxy evolution, and their observable signatures is provided and their capability to modify the thermal and hydrodynamic configuration of galactic ecosystems is discussed. We present recent advancements in our understanding of CR processes and interpretation of their signatures, and highlight where technical challenges and unresolved questions persist. We discuss how these may be addressed with upcoming opportunities.
CRIS-Team Scopus Importer:2023-09-08
Keywords: circumgalactic medium; cosmic rays; feedback; galaxy formation and evolution; inflows; interstellar medium; molecular clouds; outflows; star-formation

Cosmic ray spectrum of protons plus helium nuclei between 6 and 158 TeV from HAWC data - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Physical Review D, 2022)
A measurement with high statistics of the differential energy spectrum of light elements in cosmic rays, in particular, of primary H plus He nuclei, is reported. The spectrum is presented in the energy range from 6 to 158 TeV per nucleus. Data was collected with the High Altitude Water Cherenkov (HAWC) Observatory between June 2015 and June 2019. The analysis was based on a Bayesian unfolding procedure, which was applied on a subsample of vertical HAWC data that was enriched to 82% of events induced by light nuclei. To achieve the mass separation, a cut on the lateral age of air shower data was set guided by predictions of CORSIKA/QGSJET-II-04 simulations. The measured spectrum is consistent with a broken power-law spectrum and shows a kneelike feature at around E=24.0-3.1+3.6 TeV, with a spectral index γ=-2.51±0.02 before the break and with γ=-2.83±0.02 above it. The feature has a statistical significance of 4.1σ. Within systematic uncertainties, the significance of the spectral break is 0.8σ.
CRIS-Team Scopus Importer:2022-05-06

Cryogenic liquid jets for high repetition rate discovery science - Curry, Chandra B.; Schönwälder, Christopher; Goede, Sebastian; Kim, Jongjin B.; Rehwald, Martin; Treffert, Franziska; Zeil, Karl; Glenzer, Siegfried H.; Gauthier, Maxence (Journal of Visualized Experiments, 2020)
This protocol presents a detailed procedure for the operation of continuous, micron-sized cryogenic cylindrical and planar liquid jets. When operated as described here, the jet exhibits high laminarity and stability for centimeters. Successful operation of a cryogenic liquid jet in the Rayleigh regime requires a basic understanding of fluid dynamics and thermodynamics at cryogenic temperatures. Theoretical calculations and typical empirical values are provided as a guide to design a comparable system. This report identifies the importance of both cleanliness during cryogenic source assembly and stability of the cryogenic source temperature once liquefied. The system can be used for high repetition rate laser-driven proton acceleration, with an envisioned application in proton therapy. Other applications include laboratory astrophysics, materials science, and next-generation particle accelerators.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cryogenic liquids; Engineering; Fluid dynamics; High repetition rate; Issue 159; Laser-driven ion acceleration; Liquid jets

Dark matter annihilation and decay in dwarf spheroidal galaxies: the classical and ultrafaint dSphs - Bonnivard, V.; Combet, C.; Daniel, Michael K; Funk, Stefan; Geringer-Sameth, Alex; Hinton, J. A.; Maurin, D.; Read, J. I.; Sarkar, Subir; Walker, M. G.; Wilkinson, M. I. (Monthly Notices of the Royal Astronomical Society, 2015)
Dwarf spheroidal (dSph) galaxies are prime targets for present and future gamma-ray telescopes hunting for indirect signals of particle darkmatter. The interpretation of the data requires careful assessment of their dark matter content in order to derive robust constraints on candidate relic particles. Here, we use an optimized spherical Jeans analysis to reconstruct the 'astrophysical factor' for both annihilating and decaying dark matter in 21 known dSphs. Improvements with respect to previous works are: (i) the use of more flexible luminosity and anisotropy profiles to minimize biases, (ii) the use of weak priors tailored on extensive sets of contamination-free mock data to improve the confidence intervals, (iii) systematic cross-checks of binned and unbinned analyses on mock and real data, and (iv) the use of mock data including stellar contamination to test the impact on reconstructed signals. Our analysis provides updated values for the dark matter content of 8 'classical' and 13 'ultrafaint' dSphs, with the quoted uncertainties directly linked to the sample size; themore flexible parametrizationwe use results in changes compared to previous calculations. This translates into our ranking of potentially-brightest and most robust targets - namely Ursa Minor, Draco, Sculptor - and of the more promising, but uncertain targets -namely Ursa Major 2, Coma - for annihilating dark matter. Our analysis of Segue 1 is extremely sensitive to whether we include or exclude a few marginal member stars, making this target one of the most uncertain. Our analysis illustrates challenges that will need to be addressed when inferring the dark matter content of new 'ultrafaint' satellites that are beginning to be discovered in southern sky surveys.
CRIS-Team WoS Importer:2020-01-15

Dark matter constraints from observations of 25 Milky Way satellite galaxies with the Fermi Large Area Telescope - Ackermann, M.; Albert, A.; Anderson, B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonamente, E.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
The dwarf spheroidal satellite galaxies of the Milky Way are some of the most dark-matter-dominated objects known. Due to their proximity, high dark matter content, and lack of astrophysical backgrounds, dwarf spheroidal galaxies are widely considered to be among the most promising targets for the indirect detection of dark matter via gamma rays. Here we report on.-ray observations of 25 Milky Way dwarf spheroidal satellite galaxies based on 4 years of Fermi Large Area Telescope (LAT) data. None of the dwarf galaxies are significantly detected in. rays, and we present.-ray flux upper limits between 500 MeV and 500 GeV. We determine the dark matter content of 18 dwarf spheroidal galaxies from stellar kinematic data and combine LAT observations of 15 dwarf galaxies to constrain the dark matter annihilation cross section. We set some of the tightest constraints to date on the annihilation of dark matter particles with masses between 2 GeV and 10 TeV into prototypical standard model channels. We find these results to be robust against systematic uncertainties in the LAT instrument performance, diffuse.-ray background modeling, and assumed dark matter density profile.

Deeper HESS observations of Vela Junior (RX J0852.0-4622): Morphology studies and resolved spectroscopy - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
Aims. We study gamma-ray emission from the shell-type supernova remnant (SNR) RXJ0852.0-4622 to better characterize its spectral properties and its distribution over the SNR.Methods. The analysis of an extended High Energy Spectroscopic System (H.E.S.S.) data set at very high energies (E > 100 GeV) permits detailed studies, as well as spatially resolved spectroscopy, of the morphology and spectrum of the whole RXJ0852.0-4622 region. The H.E.S.S. data are combined with archival data from other wavebands and interpreted in the framework of leptonic and hadronic models. The joint Fermi-LAT-H.E.S.S. spectrum allows the direct determination of the spectral characteristics of the parent particle population in leptonic and hadronic scenarios using only GeV-TeV data.Results. An updated analysis of the H.E.S.S. data shows that the spectrum of the entire SNR connects smoothly to the high-energy spectrum measured by Fermi-LAT. The increased data set makes it possible to demonstrate that the H.E.S.S. spectrum deviates significantly from a power law and is well described by both a curved power law and a power law with an exponential cutoff at an energy of E-cut = (6.7 +/- 1.2(stat) +/- 1.2(syst)) TeV. The joint Fermi-LAT-H.E.S.S. spectrum allows the unambiguous identification of the spectral shape as a power law with an exponential cutoff. No significant evidence is found for a variation of the spectral parameters across the SNR, suggesting similar conditions of particle acceleration across the remnant. A simple modeling using one particle population to model the SNR emission demonstrates that both leptonic and hadronic emission scenarios remain plausible. It is also shown that at least a part of the shell emission is likely due to the presence of a pulsar wind nebula around PSR J0855-4644.
Keywords: astroparticle physics; gamma rays: general; acceleration of particles; cosmic rays; ISM: supernova remnants

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Deflectometric measurement of large mirrors - Olesch, Evelyn; Häusler, Gerd; Wörnlein, André; Stinzing, Friedrich; van Eldik, Christopher (Advanced Optical Technologies, 2014)
We discuss the inspection of large-sized, spherical mirror tiles by 'Phase Measuring Deflectometry' (PMD). About 10 000 of such mirror tiles, each satisfying strict requirements regarding the spatial extent of the point-spreadfunction (PSF), are planned to be installed on the Cherenkov Telescope Array (CTA), a future ground-based instrument to observe the sky in very high energy gamma-rays. Owing to their large radii of curvature of up to 60 m, a direct PSF measurement of these mirrors with concentric geometry requires large space. We present a PMD sensor with a footprint of only 5 ?2 ?1.2 m3 that overcomes this limitation. The sensor intrinsically acquires the surface slope; the shape data are calculated by integration. In this way, the PSF can be calculated for real case scenarios, e.g., when the light source is close to infinity and off-axis. The major challenge is the calibration of the PMD sensor, specifically because the PSF data have to be reconstructed from different camera views. The calibration of the setup is described, and measurements presented and compared to results obtained with the direct approach.
Keywords: 3D-metrology; Deflectometry; Interferometry; Optical testing; Telescope

Demystifying an unidentified EGRET source by VHE gamma-ray observations - Funk, Stefan; et al. (Astrophysics and Space Science, 2007)
In a novel approach in observational high-energy gamma-ray astronomy, observations carried out by imaging atmospheric Cherenkov telescopes provide necessary templates to pinpoint the nature of intriguing, yet unidentified EGRET gamma-ray sources. Using GeV-photons detected by EGRET and taking advantage of high spatial resolution images from H.E.S.S. observations, we were able to shed new light on the EGRET observed gamma-ray emission in the Kookaburra complex, whose previous coverage in the literature is somewhat contradictory. 3EG J 14206038 very likely accounts for two GeV gamma-ray sources (E > 1 GeV), both in positional coincidence with the recently reported pulsar wind nebulae (PWN) by HESS in the Kookaburra/Rabbit complex. PWN associations at VHE energies, supported by accumulating evidence from observations in the radio and X-ray band, are indicative for the PSR/plerionic origin of spatially coincident, but still unidentified Galactic gamma-ray sources from EGRET. This not only supports the already suggested connection between variable, but unidentified low-latitude gamma-ray sources with pulsar wind nebulae (3EG J1420-6038 has been suggested as PWN candidate previously), it also documents the ability of resolving apparently confused EGRET sources by connecting the GeV emission as measured from a large-aperture space-based gamma-ray instrument with narrow field-of-view but superior spatial resolution observations by ground-based atmospheric Cherenkov telescopes, a very promising identification technique for achieving convincing individual source identifications in the era of GLAST-LAT.
CRIS-Team WoS Importer:2020-01-15

Detailed Analysis of the TeV γ-Ray Sources 3HWC J1928+178, 3HWC J1930+188, and the New Source HAWC J1932+192 - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Rojas, D. Avila; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; et al. (Astrophysical Journal, 2023)
The latest High Altitude Water Cherenkov (HAWC) point-like source catalog up to 56 TeV reported the detection of two sources in the region of the Galactic plane at galactic longitude 52° < ℓ < 55°, 3HWC J1930+188 and 3HWC J1928+178. The first one is associated with a known TeV source, the supernova remnant SNR G054.1+00.3. It was discovered by one of the currently operating Imaging Atmospheric Cherenkov Telescope (IACT), the Very Energetic Radiation Imaging Telescope Array System (VERITAS), detected by the High Energy Stereoscopic System (H.E.S.S), and identified as a composite SNR. However, the source 3HWC J1928+178, discovered by HAWC and coincident with the pulsar PSR J1928+1746, was not detected by any IACT despite their long exposure on the region, until a recent new analysis of H.E.S.S. data was able to confirm it. Moreover, no X-ray counterpart has been detected from this pulsar. We present a multicomponent fit of this region using the latest HAWC data. This reveals an additional new source, HAWC J1932+192, which is potentially associated with the pulsar PSR J1932+1916, whose γ-ray emission could come from the acceleration of particles in its pulsar wind nebula. In the case of 3HWC J1928+178, several possible explanations are explored, in an attempt to unveil the origins of the very-high-energy γ-ray emission.
CRIS-Team Scopus Importer:2023-03-17

Detailed spectral and morphological analysis of the shell type SNR RCW 86 - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; Bernhard, S.; Bernlöhr, K.; et al. (Astronomy & Astrophysics, 2018)
Aims. We aim for an understanding of the morphological and spectral properties of the supernova remnant RCW 86 and for insights into the production mechanism leading to the RCW 86 very high-energy gamma-ray emission.Methods. We analyzed High Energy Spectroscopic System (H.E.S.S.) data that had increased sensitivity compared to the observations presented in the RCW 86 H.E.S.S. discovery publication. Studies of the morphological correlation between the 0.5-1 keV X-ray band, the 2-5 keV X-ray band, radio, and gamma-ray emissions have been performed as well as broadband modeling of the spectral energy distribution with two different emission models.Results. We present the first conclusive evidence that the TeV gamma-ray emission region is shell-like based on our morphological studies. The comparison with 2-5 keV X-ray data reveals a correlation with the 0.4-50 TeV gamma-ray emission. The spectrum of RCW 86 is best described by a power law with an exponential cutoff at E-cut = (3.5 +/- 1.2(stat)) TeV and a spectral index of Gamma approximate to 1.6 +/- 0.2. A static leptonic one-zone model adequately describes the measured spectral energy distribution of RCW 86, with the resultant total kinetic energy of the electrons above 1 GeV being equivalent to similar to 0.1% of the initial kinetic energy of a Type Ia supernova explosion (10(51) erg). When using a hadronic model, a magnetic field of B approximate to 100 mu G is needed to represent the measured data. Although this is comparable to formerly published estimates, a standard E-2 spectrum for the proton distribution cannot describe the gamma-ray data. Instead, a spectral index of Gamma(p) approximate to 1.7 would be required, which implies that similar to 7 x 10(49)/n(cm-3) erg has been transferred into high-energy protons with the effective density n(cm-3) = n/1 cm(-3). This is about 10% of the kinetic energy of a typical Type Ia supernova under the assumption of a density of 1 cm(-3).
Keywords: astroparticle physics; gamma rays: general; ISM: supernova remnants; cosmic rays

Detailed VHE studies of the pulsar wind nebula HESS J1825-137 - Mitchel, A. M. W.; Mariaud, C.; Eger, P.; Funk, Stefan; Hahn, J.; Hinton, J.; Parsons, R. D.; Marandon, V. (6th International Symposium on High Energy Gamma-Ray Astronomy, 2017)

Detection of extended γ -ray emission around the Geminga pulsar with H.E.S.S. - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
Geminga is an enigmatic radio-quiet γ-ray pulsar located at a mere 250 pc distance from Earth. Extended very-high-energy γ-ray emission around the pulsar was discovered by Milagro and later confirmed by HAWC, which are both water Cherenkov detector-based experiments. However, evidence for the Geminga pulsar wind nebula in gamma rays has long evaded detection by imaging atmospheric Cherenkov telescopes (IACTs) despite targeted observations. The detection of γ-ray emission on angular scales ≳2° poses a considerable challenge for the background estimation in IACT data analysis. With recent developments in understanding the complementary background estimation techniques of water Cherenkov and atmospheric Cherenkov instruments, the H.E.S.S. IACT array can now confirm the detection of highly extended γ-ray emission around the Geminga pulsar with a radius of at least 3° in the energy range 0.5-40 TeV. We find no indications for statistically significant asymmetries or energy-dependent morphology. A flux normalisation of (2.8 ± 0.7)×10-12 cm-2 s-1 TeV-1 at 1 TeV is obtained within a 1° radius region around the pulsar. To investigate the particle transport within the halo of energetic leptons around the pulsar, we fitted an electron diffusion model to the data. The normalisation of the diffusion coefficient obtained of D0 = 7.6-1.2+1.5×1027 cm2 s-1, at an electron energy of 100 TeV, is compatible with values previously reported for the pulsar halo around Geminga, which is considerably below the Galactic average.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Acceleration of particles; Diffusion; Gamma rays: general; Pulsars: general

Detection of gamma rays from a starburst galaxy - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Science, 2009)
Starburst galaxies exhibit in their central regions a highly increased rate of supernovae, the remnants of which are thought to accelerate energetic cosmic rays up to energies of -10 electron volts. We report the detection of gamma rays-tracers of such cosmic rays-from the starburst galaxy NGC 253 using the High Energy Stereoscopic System (H.E.S.S.) array of imaging atmospheric Cherenkov telescopes. The gamma-ray flux above 220 billion electron volts is F = (5.5 = 1.0 ± 2.8) x 10 cm s, implying a cosmic-ray density about three orders of magnitude larger than that in the center of the Milky Way. The fraction of cosmic-ray energy channeled into gamma rays in this starburst environment is five times as large as that in our Galaxy.

Detection of TeV gamma-ray emission from the shell-type supernova remnant RX J0852.0-4622 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We report the detection of TeV gamma-rays from the shell-type supernova remnant RXJ0852.0-4622 with data of 3.2 h of live time recorded with HESS in February 2004. An excess of ( 700 +/- 60) events from the whole remnant with a significance of 12 sigma was found. The observed emission region is clearly extended with a radius of the order of 1 degrees and the spatial distribution of the signal correlates with X-ray observations. The spectrum in the energy range between 500 GeV and 15 TeV is well described by a power law with a photon index of Gamma = 2.1 +/- 0. 1(stat) +/- 0.2(syst) and a differential flux at 1 TeV of (phi 1TeV) = (2.1 +/- 0.2(stat) +/- 0.6(syst)) x 10(-11) cm(-2) s(-1) TeV-1. The integral flux above 1 TeV was measured to be Phi(E > 1TeV) = (1.9 +/- 0.3(stat) +/- 0.6(syst)) x 10(-11) cm(-2) s(-1), which is at the level of the flux of the Crab nebula at these energies. More data are needed to draw firm, conclusions on the magnetic field in the remnant and the type of the particle population creating the TeV gamma-rays.
CRIS-Team WoS Importer:2020-01-15

Detection of the Crab Nebula with the 9.7 m prototype Schwarzschild-Couder telescope - Adams, C. B.; Alfaro, R.; Ambrosi, G.; Ambrosio, M.; Aramo, C.; Arlen, T.; Batista, P. I.; Benbow, W.; Bertucci, B.; Bissaldi, E.; Biteau, J.; Bitossi, M.; et al. (Astroparticle Physics, 2021)
The Schwarzschild-Couder Telescope (SCT) is a telescope concept proposed for the Cherenkov Telescope Array. It employs a dual-mirror optical design to remove comatic aberrations over an 8∘ field of view, and a high-density silicon photomultiplier camera (with a pixel resolution of 4 arcmin) to record Cherenkov emission from cosmic ray and gamma-ray initiated particle cascades in the atmosphere. The prototype SCT (pSCT), comprising a 9.7 m diameter primary mirror and a partially instrumented camera with 1536 pixels, has been constructed at the Fred Lawrence Whipple Observatory. The telescope was inaugurated in January 2019, with commissioning continuing throughout 2019. We describe the first campaign of observations with the pSCT, conducted in January and February of 2020, and demonstrate the detection of gamma-ray emission from the Crab Nebula with a statistical significance of 8.6σ.
CRIS-Team Scopus Importer:2021-02-12

Detection of variable VHE gamma-ray emission from the extra-galactic gamma-ray binary LMC P3 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Context. Recently, the high-energy (HE, 0.1-100 GeV) gamma-ray emission from the object LMC P3 in the Large Magellanic Cloud (LMC) has been discovered to be modulated with a 10.3-day period, making it the first extra-galactic gamma-ray binary.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Binaries: general; Stars: massive

Detection of very high energy radiation from HESS J1908+063 confirms the Milagro unidentified source MGRO J1908+06 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. Detection of a γ-ray source above 300 GeV is reported, confirming the unidentified source MGRO J1908+06, discovered by the Milagro collaboration at a median energy of 20 TeV. Methods. The source was observed during 27 h as part of the extension of the HESS Galactic plane survey to longitudes >30°. Results. HESS J108+063 is detected at a significance level of 10.9σ with an integral flux above 1 TeV of (3.76 ± 0.29 ph cm s, and a spectral photon index Γ = 2.10 ± 0.07 ± 0.2. The positions and fluxes of HESS J1908+063 and MGRO J1908+06 are in good agreement. Possible counterparts at other wavelengths and the origin of the γ-ray emission are discussed. The nearby unidentified GeV source, GRO J1908+0556 (GeV) which also remains unidentified and the new Fermi pulsar 0FGL J1907.5+0617, may be connected to the TeV source. © ESO 2009.
Keywords: Gamma rays; Observations

DEVELOPMENT of the MODEL of GALACTIC INTERSTELLAR EMISSION for STANDARD POINT-SOURCE ANALYSIS of FERMI LARGE AREA TELESCOPE DATA - Acero, F.; Ackermann, M.; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2016)
Most of the celestial γ rays detected by the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope originate from the interstellar medium when energetic cosmic rays interact with interstellar nucleons and photons. Conventional point-source and extended-source studies rely on the modeling of this diffuse emission for accurate characterization. Here, we describe the development of the Galactic Interstellar Emission Model (GIEM), which is the standard adopted by the LAT Collaboration and is publicly available. This model is based on a linear combination of maps for interstellar gas column density in Galactocentric annuli and for the inverse-Compton emission produced in the Galaxy. In the GIEM, we also include large-scale structures like Loop I and the Fermi bubbles. The measured gas emissivity spectra confirm that the cosmic-ray proton density decreases with Galactocentric distance beyond 5 kpc from the Galactic Center. The measurements also suggest a softening of the proton spectrum with Galactocentric distance. We observe that the Fermi bubbles have boundaries with a shape similar to a catenary at latitudes below 20°and we observe an enhanced emission toward their base extending in the north and south Galactic directions and located within ∼4°of the Galactic Center.
Keywords: gamma rays: diffuse background; gamma rays: general; gamma rays: ISM

Diamond formation kinetics in shock-compressed C─H─O samples recorded by small-angle x-ray scattering and x-ray diffraction - He, Zhiyu; Rödel, Melanie; Lütgert, Julian; Bergermann, Armin; Bethkenhagen, Mandy; Chekrygina, Deniza; Cowan, Thomas E.; Descamps, Adrien; French, Martin; Galtier, Eric; Gleason, Arianna E.; Glenn, Griffin D.; et al. (Science Advances, 2022)
Extreme conditions inside ice giants such as Uranus and Neptune can result in peculiar chemistry and structural transitions, e.g., the precipitation of diamonds or superionic water, as so far experimentally observed only for pure C─H and H2O systems, respectively. Here, we investigate a stoichiometric mixture of C and H2O by shock-compressing polyethylene terephthalate (PET) plastics and performing in situ x-ray probing. We observe diamond formation at pressures between 72 ± 7 and 125 ± 13 GPa at temperatures ranging from 3500 to 6000 K. Combining x-ray diffraction and small-angle x-ray scattering, we access the kinetics of this exotic reaction. The observed demixing of C and H2O suggests that diamond precipitation inside the ice giants is enhanced by oxygen, which can lead to isolated water and thus the formation of superionic structures relevant to the planets' magnetic fields. Moreover, our measurements indicate a way of producing nanodiamonds by simple laser-driven shock compression of cheap PET plastics.
CRIS-Team Scopus Importer:2022-09-16

Diffuse Galactic gamma-ray emission with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Diffuse γ-ray emission is the most prominent observable signature of celestial cosmic-ray interactions at high energies. While already being investigated at GeV energies over several decades, assessments of diffuse γ-ray emission at TeV energies remain sparse. After completion of the systematic survey of the inner Galaxy, the H.E.S.S. experiment is in a prime position to observe large-scale diffuse emission at TeV energies. Data of the H.E.S.S. Galactic Plane Survey are investigated in regions off known γ-ray sources. Corresponding γ-ray flux measurements were made over an extensive grid of celestial locations. Longitudinal and latitudinal profiles of the observed γ-ray fluxes show characteristic excess emission not attributable to known γ-ray sources. For the first time large-scale γ-ray emission along the Galactic plane using imaging atmospheric Cherenkov telescopes has been observed. While the background subtraction technique limits the ability to recover modest variation on the scale of the H.E.S.S. field of view or larger, which is characteristic of the inverse Compton scatter-induced Galactic diffuse emission, contributions of neutral pion decay as well as emission from unresolved γ-ray sources can be recovered in the observed signal to a large fraction. Calculations show that the minimum γ-ray emission from π0 decay represents a significant contribution to the total signal. This detection is interpreted as a mix of diffuse Galactic γ-ray emission and unresolved sources.

Discovery and follow-up studies of the extended, off-plane, VHE gamma-ray source HESS J1507-622 - Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2010)
Context. The detection of gamma-rays in the very-high-energy (VHE) range (100 GeV-100 TeV) offers the possibility of studying the parent population of ultrarelativistic particles found in astrophysical sources, so it is useful for understanding the underlying astrophysical processes in nonthermal sources. Aims. The discovery of the VHE gamma-ray source HESS J1507-622 is reported and possibilities regarding its nature are investigated. Methods. The H.E.S.S. array of imaging atmospheric Cherenkov telescopes (IACTs) has a high sensitivity compared with previous instruments (∼1% of the Crab flux in 25 h observation time for a 5σ point-source detection) and has a large field of view (∼5° in diameter). HESS J1507-622 was discovered within the ongoing H.E.S.S. survey of the inner Galaxy, and the source was also studied by means of dedicated multiwavelength observations. Results. A Galactic gamma-ray source, HESS J1507-622, located ∼3.5° from the Galactic plane was detected with a statistical significance >9σ. Its energy spectrum is well fitted by a power law with spectral index Γ = 2.24 ± 0.16 ± 0.20 and a flux above 1 TeV of (1.5 ± 0.4 ± 0.3) × 10 cm s. Possible interpretations (considering both hadronic and leptonic models) of the VHE gamma-ray emission are discussed in the absence of an obvious counterpart. © ESO 2010.
Keywords: gamma rays: general; X-rays: general

Discovery of an X-ray nebula around PSR J1718-3825 and implications for the nature of the gamma-ray source HESS J1718-385 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2007)
Combined X-ray synchrotron and inverse-Compton gamma-ray observations of pulsar wind nebulae (PWN) may help to elucidate the processes of acceleration and energy loss in these systems. In particular, such observations provide constraints on the particle injection history and the magnetic field strength in these objects. The newly discovered TeV gamma-ray source HESS J1718-385 has been proposed as the likely PWN of the high spin-down luminosity pulsar PSR J1718-3825. The absence of previous, sensitive X-ray measurements of this pulsar, and the unusual energy spectrum of the TeV source, motivated observations of this region with XMM-Newton. The data obtained reveal a hard-spectrum X-ray source at the position of PSR 1718-3825 and evidence of diffuse emission in the vicinity of the pulsar. We derive limits on the keV emission from the centroid of HESS J1718-385 and discuss the implications of these findings for the PWN nature of this object.
CRIS-Team WoS Importer:2020-01-15

Discovery of a VHE gamma-ray source coincident with the supernova remnant CTB 37A - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel; et al. (Astronomy & Astrophysics, 2008)
Aims. The supernova remnant (SNR) complex CTB 37 is an interesting candidate for observations with very high energy (VHE) γ-ray telescopes such as HESS. In this region, three SNRs are seen. One of them is potentially associated with several molecular clouds, a circumstance that can be used to probe the acceleration of hadronic cosmic rays. Methods. This region was observed with the HESS Cherenkov telescopes and the data were analyzed with standard HESS procedures. Recent X-ray observations with Chandra and XMM-Newton were used to search for X-ray counterparts. Results. The discovery of a new VHE γ-ray source HESS J1714-385 coincident with the remnant CTB 37A is reported. The energy spectrum is well described by a power-law with a photon index of Γ = 2.30 ± 0.13 and a differential flux at 1 TeV of Φ = (8.7 ± 1.0 ± 1.8) × 10 cm s TeV. The integrated flux above 1 TeV is equivalent to 3% of the flux of the Crab nebula above the same energy. This VHE γ-ray source is a counterpart candidate for the unidentified EGRET source 3EG J1714-3857. The observed VHE emission is consistent with the molecular gas distribution around CTB 37A; a close match is expected in a hadronic scenario for γ-ray production. The X-ray observations reveal the presence of thermal X-rays from the NE part of the SNR. In the NW part of the remnant, an extended non-thermal X-ray source, CXOU J171419.8-383023, is discovered as well. Possible connections of the X-ray emission to the newly found VHE source are discussed. © ESO 2008.
Keywords: Gamma rays: observations; ISM: supernova remnants; X-rays: individuals: G348.5+0.1

Discovery of extended VHE gamma-ray emission from the asymmetric pulsar wind nebula in MSH 15-52 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The Supernova Remnant MSH 15-52 has been observed in very high energy (VHE) gamma-rays using the HESS 4-telescope array located in Namibia. A gamma-ray signal is detected at the 25 sigma level during an exposure of 22.1 h live time. The image reveals an elliptically shaped emission region around the pulsar PSRB1509 - 58, with semi-major axis similar to 6' in the NW-SE direction and semi-minor axis similar to 2'. This morphology coincides with the diffuse pulsar wind nebula as observed at X-ray energies by ROSAT. The overall energy spectrum from 280 GeV up to 40 TeV can be fitted by a power law with photon index Gamma = 2.27 +/- 0.03(stat) +/- 0.20(syst). The detected emission can be plausibly explained by inverse Compton scattering of accelerated relativistic electrons with soft photons.
CRIS-Team WoS Importer:2020-01-15

Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N- 157B, located in the large Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N- 157B is associated with PSR- J0537-6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46- h. The gamma-ray spectrum between 600- GeV and 12- TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2 ± 0.3 and a normalisation at 1- TeV of (8.2 ± 0.8 ± 2.5 ) × 10 cm - s - TeV . A leptonic multi-wavelength model shows that an energy of about 4 × 10 erg is stored in electrons and positrons. The apparent efficiency, which is the ratio of the TeV gamma-ray luminosity to the pulsar's spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar's favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar's birth period is estimated to be shorter than 10 ms. © ESO, 201
Keywords: Gamma rays: general; ISM: supernova remnants; Magellanic Clouds; Pulsars: individual: PSR J0537-6910

Discovery of gamma-ray emission from the shell-type supernova remnant RCW 86 with Hess - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astrophysical Journal, 2009)
The shell-type supernova remnant (SNR) RCW 86, possibly associated with the historical supernova SN 185, with its relatively large size (about 40′ in diameter) and the presence of nonthermal X-rays is a promising target for γ-ray observations. The high sensitivity, good angular resolution of a few arcminutes and the large field of view of the High Energy Stereoscopic System (HESS) make it ideally suited for the study of γ-ray morphology of such extended sources. HESS observations have indeed led to the discovery of the SNR RCW 86 in very high energy (VHE; E > 100 GeV) γ-rays. With 31 hr of observation time, the source is detected with a statistical significance of 8.5σ and is significantly more extended than the HESS point-spread function. Morphological studies have been performed and show that the γ-ray flux does not correlate perfectly with the X-ray emission. The flux from the remnant is ∼10% of the flux from the Crab nebula, with a similar photon index of about 2.5. Possible origins of the VHE γ-ray emission, via either Inverse Compton scattering by electrons or the decay of neutral pions produced by proton interactions, are discussed on the basis of spectral features obtained both in the X-ray and γ-ray regimes. © 2009. The American Astronomical Society. All rights reserved.
Keywords: gamma rays: observations; ISM: individual (RCW 86; G315.4-2.3); supernova remnants

Discovery of Gamma Rays from the Quiescent Sun with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Physical Review Letters, 2023)
We report the first detection of a TeV γ-ray flux from the solar disk (6.3σ), based on 6.1 years of data from the High Altitude Water Cherenkov (HAWC) observatory. The 0.5-2.6 TeV spectrum is well fit by a power law, dN/dE=A(E/1 TeV)-γ, with A=(1.6±0.3)×10-12 TeV-1 cm-2 s-1 and γ=3.62±0.14. The flux shows a strong indication of anticorrelation with solar activity. These results extend the bright, hard GeV emission from the disk observed with Fermi-LAT, seemingly due to hadronic Galactic cosmic rays showering on nuclei in the solar atmosphere. However, current theoretical models are unable to explain the details of how solar magnetic fields shape these interactions. HAWC's TeV detection thus deepens the mysteries of the solar-disk emission.
CRIS-Team Scopus Importer:2023-08-25

Discovery of high and very high-energy emission from the BL Lacertae object SHBL J001355.9-185406 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy and Astrophysics, 2013)
Keywords: BL Lacertae objects: individual: SHBL J001355.9-185406; gamma rays: general

Discovery of TeV γ-ray emission from PKS 0447-439 and derivation of an upper limit on its redshift - Abramowski, A.; Acero, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Very high-energy γ-ray emission from PKS 0447-439 was detected with the H.E.S.S. Cherenkov telescope array in December 2009. This blazar is one of the brightest extragalactic objects in the Fermi bright source list and has a hard spectrum in the MeV to GeV range. In the TeV range, a photon index of 3.89 ± 0.37 (stat) ±0.22 (sys) and a flux normalisation at 1 TeV, Φ = (3.5 ± 1.1(stat) ± 0.9(sys)) × 10 cm s TeV were found. The detection with H.E.S.S. triggered observations in the X-ray band with the Swift and RXTE telescopes. Simultaneous UV and optical data from Swift UVOT and data from the optical telescopes ATOM and ROTSE are also available. The spectrum and light curve measured with H.E.S.S. are presented and compared to the multi-wavelength data at lower energies. A rapid flare is seen in the Swift XRT and RXTE data, together with a flux variation in the UV band, at a time scale of the order of one day. A firm upper limit of z < 0.59 on the redshift of PKS 0447-439 is derived from the combined Fermi-LAT and H.E.S.S. data, given the assumptions that there is no upturn in the intrinsic spectrum above the Fermi-LAT energy range and that absorption on the extragalactic background light (EBL) is not weaker than the lower limit provided by current models. The spectral energy distribution is well described by a simple one-zone synchrotron self-Compton scenario, if the redshift of the source is less than z â‰ 0.4. © 2013 ESO.
Keywords: BL Lacertae objects: individual: PKS 0447-439; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of the binary pulsar PSRB1259-63 in very-high-energy gamma rays around periastron with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We report the discovery of very-high-energy (VHE) gamma-ray emission of the binary system PSRB1259-63/SS2883 of a radio pulsar orbiting a massive, luminous Be star in a highly eccentric orbit. The observations around the 2004 periastron passage of the pulsar were performed with the four 13 m Cherenkov telescopes of the HESS experiment, recently installed in Namibia and in full operation since December 2003. Between February and June 2004, a gamma-ray signal from the binary system was detected with a total significance above 13 sigma. The flux was found to vary significantly on timescales of days which makes PSRB1259- 63 the first variable galactic source of VHE gamma-rays observed so far. Strong emission signals were observed in pre- and post-periastron phases with a flux minimum around periastron, followed by a gradual flux decrease in the months after. The measured time-averaged energy spectrum above a mean threshold energy of 380 GeV can be fitted by a simple power law F-0(E/1TeV)(-Gamma) with a photon index Gamma = 2.7 +/- 0.2(stat) +/- 0.2(sys) and flux normalisation F-0 = ( 1.3 +/- 0.1stat +/- 0.3(sys)) x 10(-12) TeV-1 cm(-2) s(-1). This detection of VHE gamma-rays provides unambiguous evidence for particle acceleration to multi-TeV energies in the binary system. In combination with coeval observations of the X-ray synchrotron emission by the RXTE and INTEGRAL instruments, and assuming the VHE gamma-ray emission to be produced by the inverse Compton mechanism, the magnetic field strength can be directly estimated to be of the order of 1G.
CRIS-Team WoS Importer:2020-01-15

Discovery of the Hard Spectrum VHE γ-Ray Source HESS J1641-463 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Uner, E. O. Ang; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal Letters, 2014)
Keywords: cosmic rays; gamma rays: general; ISM: individual objects (SNR G338.30.0; SNR G338.5+0.1)

Discovery of the source HESS J1356-645 associated with the young and energetic PSR J1357-6429 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astronomy & Astrophysics, 2011)
Context. Several newly discovered very-high-energy (VHE; E > 100 GeV) γ-ray sources in the Galaxy are thought to be associated with energetic pulsars. Among them, middle-aged (10 yr) systems exhibit large centre-filled VHE nebulae, offset from the pulsar position, which result from the complex relationship between the pulsar wind and the surrounding medium, and reflect the past evolution of the pulsar. Aims. Imaging Atmospheric Cherenkov Telescopes (IACTs) have been successful in revealing extended emission from these sources in the VHE regime. Together with radio and X-ray observations, this observational window allows one to probe the energetics and magnetic field inside these large-scale nebulae. Methods. H.E.S.S., with its large field of view, angular resolution of 0.1° and unprecedented sensitivity, has been used to discover a large population of such VHE sources. In this paper, the H.E.S.S. data from the continuation of the Galactic Plane Survey (-80° < < 60°, |b| < 3°), together with the existing multi-wavelength observations, are used. Results. A new VHE γ-ray source was discovered at RA (J2000) = 135600, Dec (J2000) =-64°30′00′′ with a 2′ statistical error in each coordinate, namely HESS J1356-645. The source is extended, with an intrinsic Gaussian width of (0.20 ± 0.02)°. Its integrated energy flux between 1 and 10 TeV of 8 × 10 erg cm s represents ∼11% of the Crab Nebula flux in the same energy band. The energy spectrum between 1 and 20 TeV is well described by a power law dN/dE E with photon index Γ = 2.2 ± 0.2 ± 0.2. The inspection of archival radio images at three frequencies and the analysis of X-ray data from ROSAT/PSPC and XMM-Newton/MOS reveal the presence of faint non-thermal diffuse emission coincident with HESS J1356-645. Conclusions. HESS J1356-645 is most likely associated with the young and energetic pulsar PSR J1357-6429 (d = 2.4 kpc, τ = 7.3 kyr and Å-= 3.1 × 10 erg s), located at a projected distance of ∼5 pc from the centroid of the VHE emission. HESS J1356-645 and its radio and X-ray counterparts would thus represent the nebula resulting from the past history of the PSR J1357-6429 wind. In a simple one-zone model, © 2011 ESO.
Keywords: gamma rays: general; ISM: individual objects: HESS J1356-645; ISM: individual objects: PSR J1357-6429; surveys

Discovery of the VHE gamma-ray source HESS J1832-093 in the vicinity of SNR G22.7-0.2 - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
Keywords: astroparticle physics; ISM: individual objects: HESS J1832-093; ISM: individual objects: SNR G22.7-0.2; gamma-rays: general

Discovery of variable VHE gamma-ray emission from the binary system 1FGL J1018.6-5856 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2015)
Re-observations with the HESS telescope array of the very high-energy (VHE) source HESS J1018-589A that is coincident with the Fermi-LAT gamma-ray binary 1FGL J1018.6-5856 have resulted in a source detection significance of more than 9 sigma and the detection of variability (chi(2)/nu of 238.3/155) in the emitted gamma-ray flux. This variability confirms the association of HESS J1018-589A with the high-energy gamma-ray binary detected Fermi-LAT and also confirms the point-like source as a new VHE binary system. The spectrum of HESS J1018-589A is best fit with a power-law function with photon index Gamma = 2.20 +/- 0.14(stat) +/- 0.2(sys). Emission is detected up to similar to 20 TeV. The mean differential flux level is (2.9 +/- 0.4) x 10(-13) TeV-1 cm(-2) s(-1) at 1 TeV, equivalent to similar to 1% of the flux from the Crab Nebula at the same energy. Variability is clearly detected the night-by-night light curve. When folded on the orbital period of 16.58 days, the rebinned light curve peaks in phase with the observed X-ray high-energy phaseograms. The fit of the HESS phaseogram to a constant flux provides evidence of periodicity at the level of N-sigma > 3 sigma. The of the VHE phaseogram and measured spectrum suggest a low-inclination, low-eccentricity system with a modest impact from VHE gamma-ray due to pair production (tau less than or similar to 1 at 300 GeV).
Keywords: Acceleration of particles; Gamma rays: stars; Radiation mechanisms: non-thermal; Stars: individual: 1FGL J1018.6-5856; X-rays: binaries

Discovery of very high energy gamma rays associated with an X-ray binary - Funk, Stefan; et al. (Science, 2005)
X-ray binaries are composed of a normal star in orbit around a neutron star or stellar-mass black hole. Radio and x-ray observations have led to the presumption that some x-ray binaries called microquasars behave as scaled-down active galactic nuclei. Microquasars have resolved radio emission that is thought to arise from a relativistic outflow akin to active galactic nuclei jets, in which particles can be accelerated to large energies. Very high energy gamma-rays produced by the interactions of these particles have been observed from several active galactic nuclei. Using the High Energy Stereoscopic System, we find evidence for gamma-ray emission of >100 gigaelectron volts from a candidate microquasar, LS 5039, showing that particles are also accelerated to very high energies in these systems.
CRIS-Team WoS Importer:2020-01-15

Discovery of very high energy γ-ray emission from centaurus a with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astrophysical Journal, 2009)
We report the discovery of faint very high energy (VHE; E > 100GeV) γ-ray emission from the radio galaxy Centaurus A in observations performed with the High Energy Stereoscopic System (H.E.S.S.) experiment, an imaging atmospheric Cherenkov telescope array consisting of four telescopes located in Namibia. Centaurus A has been observed for more than 120hr. A signal with a statistical significance of 5.0σ is detected from the region including the radio core and the inner kpc jets. The integral flux above an energy threshold of 250 GeV is measured to be 0.8% of the flux of the Crab Nebula (apparent luminosity: L(>250GeV) 2.6 × 10ergs, adopting a distance of 3.8Mpc). The spectrum can be described by a power law with a photon index of 2.7 0.5 0.2. No significant flux variability is detected in the data set. However, the low flux only allows detection of variability on the timescale of days to flux increments above a factor of 15-20 (3σ and 4σ, respectively). The discovery of VHE γ-ray emission from Centaurus A reveals particle acceleration in the source to >TeV energies and, together with M87, establishes radio galaxies as a class of VHE emitters. © 2009. The American Astronomical Society. All rights reserved..
Keywords: Galaxies: active; Galaxies: individual (Cen A); Gamma rays: observations

Discovery of very high energy γ-ray emission from the BL Lacertae object PKS 0301-243 with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2013)
The active galactic nucleus PKS 0301-243 (z = 0.266) is a high-synchrotron-peaked BL Lac object that is detected at high energies (HE, 100 MeV <e 0301-243="" 100="" at="" by="" discovery="" e="" energies="" fermi="" high="" lat.="" of="" on="" paper="" pks="" reports="" the="" this="" very=""> 100 GeV) by the High Energy Stereoscopic System (H.E.S.S.) from observations between September 2009 and December 2011 for a total live time of 34.9 h. Gamma rays above 200 GeV are detected at a significance of 9.4σ. A hint of variability at the 2.5σ level is found. An integral flux I(E > 200 GeV) = (3.3 ± 1.1 ± 0.7) × 10 ph cm s and a photon index Γ = 4.6 ± 0.7 ± 0.2 are measured. Multi-wavelength light curves in HE, X-ray and optical bands show strong variability, and a minimal variability timescale of eight days is estimated from the optical light curve. A single-zone leptonic synchrotron self-Compton scenario satisfactorily reproduces the multi-wavelength data. In this model, the emitting region is out of equipartition and the jet is particle dominated. Because of its high redshift compared to other sources observed at TeV energies, the very high energy emission from PKS 0301-243 is attenuated by the extragalactic background light (EBL) and the measured spectrum is used to derive an upper limit on the opacity of the EBL. © 2013 ESO.</e>
Keywords: BL Lacertae objects: general; BL Lacertae objects: individual: PKS 0301-243; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of VHE γ-ray emission and multi-wavelength observations of the BL Lacertae object 1RXS J101015.9-311909 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
Keywords: gamma rays: galaxies; galaxies: active; BL Lacertae objects: individual: 1RXS J101015.9-311909

Discovery of VHE γ-rays from the high-frequency-peaked BL Lacertae object RGB J0152+017 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astronomy & Astrophysics, 2008)
Keywords: galaxies: BL Lacertae objects: individual: RGB J0152+017; gamma rays: observations; galaxies: BL Lacertae objects: general; galaxies: active

Discovery of VHE emission towards the Carina arm region with the H.E.S.S. telescope array: HESS? J1018-589 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
The Carina arm region, containing the supernova remnant SNR? G284.3-1.8, the high-energy (HE; E > 100 MeV) binary 1FGL? J1018.6-5856 and the energetic pulsar PSR? J1016-5857 and its nebula, has been observed with the H.E.S.S. telescope array. The observational coverage of the region in very-high-energy (VHE; E > 0.1? TeV) γ-rays benefits from deep exposure (40? h) of the neighboring open cluster Westerlund 2. The observations have revealed a new extended region of VHE γ-ray emission. The new VHE source HESS? J1018-589 shows a bright, point-like emission region positionally coincident with SNR? G284.3-1.8 and 1FGL? J1018.6-5856 and a diffuse extension towards the direction of PSR? J1016-5857. A soft (Γ = 2.7 ± 0.5) photon? index, with a differential flux at 1? TeV of N = (4.2 ± 1.1) × 10? TeV? cm? s is found for the point-like source, whereas the total emission region including the diffuse emission region is well fit by a power-law function with spectral index Γ = 2.9 ± 0.4 and differential flux at 1? TeV of N = (6.8 ± 1.6) × 10? TeV? cm? s. This H.E.S.S. detection motivated follow-up X-ray observations with the XMM-Newton satellite to investigate the origin of the VHE emission. The analysis of the XMM-Newton data resulted in the discovery of a bright, non-thermal point-like source (XMMU J101855.4-58564) with a photon index of Γ = 1.65 ± 0.08 in the center of SNR? G284.3-1.8, and a thermal, extended emission region coincident with its bright northern filament. The characteristics of this thermal emission are used to estimate the plasma density in the region as n 0.5 cm (2.9? kpc/d). The position of XMMU? J101855.4-58564 is compatible with the position reported by the Fermi-LAT collaboration for the binary system 1FGL? J1018.6-5856 and the variable Swift XRT source identified with it. The new X-ray data are used alongside archival multi-wavelength data to investigate the relationship between the VHE γ-ray emission from HESS? J1018-589 and the various potential counterparts in the Carina arm region. © ESO, 2012.
Keywords: Gamma rays: stars; ISM: individual objects: 1FGL J1018.6-5856; ISM: individual objects: PSRJ1016-5857; ISM: individual objects: SNRG284.3-1.8

Discovery of VHE gamma rays from PKS 2005-489 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The high-frequency peaked BL Lac PKS 2005 2005-489 (z = 0.071) was observed in 2003 and 2004 with the HESS stereoscopic array of imaging atmospheric-Cherenkov telescopes in Namibia. A signal was detected at the 6.7 sigma level in the 2004 observations (24.2 h live time), but not in the 2003 data set (27.3 h live time). PKS 2005 2005-489 is the first blazar independently discovered by HESS to be an emitter of VHE photons, a independently and only the second such blazar in and the Southern Hemisphere. The integral flux above 200GeV observed in 2004 is (6.9 +/- 1.0(stat) +/- 1.4(syst)) x 10(-12) cm(-2) s(-1), corresponding to similar to 2.5% of the flux observed from the Crab Nebula. The 99% upper limit on the flux in 2003, I(> 200 GeV) < 5.2 x 10(-12) cm cm(-2) s(-1), is smaller than, the flux measured in 2004, suggesting an increased level of activity in 2004. However, the data show no evidence for significant variability on any time scale less than a year. An energy spectrum is measured and is characterized by a very soft power law (photon index of G = 4.0 +/- 0.4).
CRIS-Team WoS Importer:2020-01-15

Discovery of VHE γ -rays from the BL Lacertae object PKS 0548-322 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2010)
Aims. PKS 0548-322 (z = 0.069) is a "high-frequency-peaked" BL Lac object and a candidate very high energy (VHE, E > 100 GeV) γ-ray emitter, due to its high X-ray and radio flux. Observations at the VHE band provide insights into the origin of very energetic particles present in this source and the radiation processes at work. Methods. We report observations made between October 2004 and January 2008 with the HESS array, a four imaging atmospheric-Cherenkov telescopes. Contemporaneous UV and X-ray observations with the Swift satellite in November 2006 are also reported. Results. PKS 0548-322 is detected for the first time in the VHE band with HESS We measure an excess of 216 γ-rays corresponding to a significance of 5.6 standard deviations. The photon spectrum of the source is described by a power-law, with a photon index of Γ = 2.86 ± 0.34 ± 0.10 . The integral flux above 200 GeV is ∼1.3% of the flux of the Crab Nebula, and is consistent with being constant in time. Contemporaneous Swift/XRT observations reveal an X-ray flux between 2 and 10 keV of F = (2.3±0.2)×10 erg cm s, an intermediate intensity state with respect to previous observations. The spectral energy distribution can be reproduced using a simple one-zone synchrotron self Compton model, with parameters similar those observed for other sources of this type. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 0548-322; galaxies: active; gamma rays: observations

Efficient Polymer Solar Cells Based on Non-fullerene Acceptors with Potential Device Lifetime Approaching 10 Years - Du, Xiaoyan; Heumüller, Thomas; Gruber, Wolfgang; Classen, Andrej; Unruh, Tobias; Li, Ning; Brabec, Christoph (Joule, 2019)
Organic solar cells (OSCs) based on non-fullerene acceptors (NFAs) have developed very fast in recent years. A proper balance among power conversion efficiency (PCE), stability, and production cost needs further elaboration. Here we investigate the industrial viability of highly efficient OSCs based on several representative NFAs. The most stable OSCs exhibit PCE of ∼8% along with extrapolated T 80 lifetime (80% of the initial PCE) of over 11,000 hr under equivalent 1 sun illumination, which would lead to a very impressive operational lifetime approaching 10 years. Photo-stability is strongly dependent on the end-group and side-chain engineering of the NFAs. Breaking of conjugation during photo-aging leads to increased energetic traps. Fluorination of the end-group stabilizes molecules against light soaking, while adding methyl groups shows an opposite trend. Side-chain modification can significantly influence the morphological stability. Reducing synthetic complexity of this class of NFAs will ultimately push the organic photovoltaics technology into real-life applications. © 2018 Elsevier Inc. We investigate the industrial viability of highly efficient organic solar cells (OSCs) based on several representative non-fullerene acceptors (NFAs) by taking into consideration the three essential parameters: power conversion efficiency, photo-stability, and materials cost. End-group and side-chain modifications of NFAs strongly influence long-term photo-stability. Promising extrapolated operational lifetime approaching 10 years has been demonstrated with the most stable system. Industrial figure of merit (i-FoM) analysis highlights the importance of lowering the synthetic complexity of the NFAs for commercialization of this technology. © 2018 Elsevier Inc. Organic solar cells with non-fullerene acceptors (NFAs) have developed rapidly in recent years. Breakthroughs in power conversion efficiency (PCE) have significantly raised the confidence in the community for commercialization of this technology. In the phase of developing new materials via molecular engineering, more attention should be paid on industrial figure of merit (i-FoM), which considers the balance of PCE, stability, and production cost. Here we investigate industrial viability of highly efficient organic solar cells based on several representative NFAs. Molecular engineering on both end-groups and side chains significantly influences the long-term stability of organic solar cells by altering the intrinsic chemical stability of the molecules under light soaking as well as morphological stability. Promising lifetime approaching 10 years is demonstrated in stable candidates. Reducing synthetic complexity is highlighted in order to push this technology into real-life appli
Keywords: non-fullerene acceptors; organic photovoltaics; device operational stability; industrial figure of merit; bulk-heterojunction morphology

Einstein@Home discovers a radio-quiet gamma-ray millisecond pulsar - Clark, Colin J.; Pletsch, Holger J.; Wu, Jason; Guillemot, Lucas; Kerr, Matthew; Johnson, Tyrel J.; Camilo, Fernando; Salvetti, David; Allen, Bruce; Anderson, David; Aulbert, Carsten; Beer, Christian; et al. (Science Advances, 2018)
Millisecond pulsars (MSPs) are old neutron stars that spin hundreds of times per second and appear to pulsate as their emission beams cross our line of sight. To date, radio pulsations have been detected from all rotation-powered MSPs. In an attempt to discover radio-quiet gamma-ray MSPs, we used the aggregated power from the computers of tens of thousands of volunteers participating in the Einstein@Home distributed computing project to search for pulsations from unidentified gamma-ray sources in Fermi Large Area Telescope data. This survey discovered two isolated MSPs, one of which is the only known rotation-powered MSP to remain undetected in radio observations. These gamma-ray MSPs were discovered in completely blind searches without prior constraints from other observations, raising hopes for detecting MSPs from a predicted Galactic bulge population.
CRIS-Team WoS Importer:2020-01-15

Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11

Electron acceleration in laboratory-produced turbulent collisionless shocks - Fiuza, F.; Swadling, G. F.; Grassi, A.; Rinderknecht, H. G.; Higginson, D. P.; Ryutov, D. D.; Bruulsema, C.; Drake, R. P.; Funk, Stefan; Glenzer, S.; Gregori, G.; Li, C. K.; et al. (Nature Physics, 2020)
Astrophysical collisionless shocks are among the most powerful particle accelerators in the Universe. Generated by violent interactions of supersonic plasma flows with the interstellar medium, supernova remnant shocks are observed to amplify magnetic fields(1) and accelerate electrons and protons to highly relativistic speeds(2-4). In the well-established model of diffusive shock acceleration(5), relativistic particles are accelerated by repeated shock crossings. However, this requires a separate mechanism that pre-accelerates particles to enable shock crossing. This is known as the 'injection problem', which is particularly relevant for electrons, and remains one of the most important puzzles in shock acceleration(6). In most astrophysical shocks, the details of the shock structure cannot be directly resolved, making it challenging to identify the injection mechanism. Here we report results from laser-driven plasma flow experiments, and related simulations, that probe the formation of turbulent collisionless shocks in conditions relevant to young supernova remnants. We show that electrons can be effectively accelerated in a first-order Fermi process by small-scale turbulence produced within the shock transition to relativistic non-thermal energies, helping overcome the injection problem. Our observations provide new insight into electron injection at shocks and open the way for controlled laboratory studies of the physics underlying cosmic accelerators.
CRIS-Team WoS Importer:2020-06-26

Electron spectrum of the dragonfly pulsar wind nebula from X-ray to TeV - Brisbois, Chad; Joshi, Vikas (Proceedings of Science, 2019)
The Dragonfly nebula is a Vela-like Pulsar Wind Nebula (PWN) in the Cygnus region powered by the spin down of PSR J2021+3651. In X-rays, the inner nebula is a few arcseconds across, whereas at TeV energies VERITAS and HAWC has observed extended emission much larger than the extension in X-rays. The TeV gamma-ray source HAWC J2019+368 was originally discovered in 2007 by the Milagro Observatory and has been associated with this pulsar. Recent work has shown hints of energy dependent morphology for the source at TeV energies, supporting the interpretation of the gamma-ray emission being due to Inverse Compton scattering of electrons and positrons from interstellar radiation fields and cosmic microwave background photons. The hard spectral index and spectral softening above 30 TeV of the source are consistent with Klein-Nishina suppression of the electron-photon cross-section at high energies. We will present our most recent studies in modeling and analysis of HAWC J2019+368, explaining the X-ray and TeV emission up to the highest energies using the latest data from the HAWC Observatory.
CRIS-Team Scopus Importer:2021-04-20

Energy dependent morphology of the pulsar wind nebula HESSJ1825-137 with Fermi-LAT - Principe, G.; Mitchell, Alison M. W.; Caroff, S.; Hinton, J. A.; Parsons, R. D.; Funk, Stefan (Astronomy & Astrophysics, 2020)
Aims. Taking advantage of more than 11 years of Fermi-LAT data, we perform a new and deep analysis of the pulsar wind nebula (PWN) HESS J1825-137. Combining this analysis with recent H.E.S.S. results we investigate and constrain the particle transport mechanisms at work inside the source as well as the system evolution. Methods. The PWN is studied using 11.6 years of Fermi-LAT data between 1 GeV and 1 TeV. In particular, we present the results of the spectral analysis and the first energy-resolved morphological study of the PWN HESS J1825-137 at GeV energies, which provide new insights into the-ray characteristics of the nebula. Results. An optimised analysis of the source returns an extended emission region larger than 2, corresponding to an intrinsic size of about 150 pc, making HESS J1825-137 the most extended-ray PWN currently known. The nebula presents a strong energy dependent morphology within the GeV range, moving from a radius of 1:4 below 10 GeV to a radius of 0.8 above 100 GeV, with a shift in the centroid location. Conclusions. Thanks to the large extension and peculiar energy-dependent morphology, it is possible to constrain the particle transport mechanisms inside the PWN HESS J1825-137. Using the variation of the source extension and position, as well as the constraints on the particle transport mechanisms, we present a scheme for the possible evolution of the system. Finally, we provide an estimate of the electron energy density and we discuss its nature in the PWN and TeV halo-like scenario.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Acceleration of particles; Astroparticle physics; Gamma rays: stars; Pulsars: individual: HESS J1825-137; Pulsars: individual: PSR B1823-13

Energy spectrum of cosmic-ray electrons at TeV energies - Aharonian, F.; Akhperjanian, A. G.; Barres De Almeida, Ulisses; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Physical Review Letters, 2008)
The very large collection area of ground-based γ-ray telescopes gives them a substantial advantage over balloon or satellite based instruments in the detection of very-high-energy (>600GeV) cosmic-ray electrons. Here we present the electron spectrum derived from data taken with the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes. In this measurement, the first of this type, we are able to extend the measurement of the electron spectrum beyond the range accessible to direct measurements. We find evidence for a substantial steepening in the energy spectrum above 600 GeV compared to lower energies. © 2008 The American Physical Society.

Erratum: First fermi-LAT solar flare catalog (Astrophysical Journal, Supplement Series (2021) 252 (13) DOI: 10.3847/1538-4365/abd32e) - Ajello, Marco; Baldini, Luca; Bastieri, Denis; Bellazzini, R.; Berretta, A.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, Raffaella; Bruel, P.; Buson, S.; Cameron, R. A.; Caputo, R.; et al. (Astrophysical Journal Supplement Series, 2021)
In the published article, several references were accidentally left out of the text. The papers that we would like to cite are the following: 1. In the Introduction section, on page 2 the first sentence of the seventh paragraph should be: In this Fermi-LAT Solar Flare (FLSF) catalog we present the observations of 45 flares with >30?MeV emission in the period 2010–2018 January (covering most of the 24th solar cycle), extending on the work done by Share et al. (2018). 2. In the Results section, page 20 at the end of the first paragraph: All CME information was obtained from the CME online catalog of Gopalswamy et al. (2009, 2010). 3. In the Results section, page 23 at the end of the first paragraph: Winter et al. (2018) also reported that nearly all fast CMEs are associated with long-duration gamma-ray solar flares. 4. In subsection 4.2, Flare Series, on page 23 at the end of the paragraph: Similar results on the connection of long-lasting gamma-ray emission with SEPs were also reported by Gopalswamy et al. (2019). 5. In the Summary and Discussion section, end of list item 7: as first suggested by Gopalswamy et al. (2019). 6. In the Summary and Discussion section, after the second sentence on page 30: Fermi-LAT gamma-ray duration has been found to be correlated with the type II burst duration indicating the shock origin of the underlying electrons and ions (Gopalswamy et al. 2018). 7. In the Summary and Discussion section, at the end of the first paragraph on page 30: Further support for the CME-shock scenario has been reported by Gopalswamy et al. (2018, 2019, 2020, 2021), Kouloumvakos et al. (2020), Plotnikov et al. (2017), and Share et al. (2018). 8. In the Summary and Discussion section, at the end of the second sentence of the second paragraph on page 30, Ryan (2000) should be cited. 9. In the Summary and Discussion section, at the end of the second paragraph on page 30: Intriguing support for this scenario has been reported by Gary et al. (2018) and Grechnev et al. (2018).
CRIS-Team Scopus Importer:2021-10-29

Erratum: H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud (Astronomy and Astrophysics (2015)) - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Keywords: Errata; addenda; Gamma rays: general; ISM: clouds; ISM: supernova remnants

Erratum: Publisher's Note: "Electromagnetic pulse protective shielding for digital x-ray detectors" [Rev. Sci. Instrum. 94, 075106 (2023) (The Review of scientific instruments (2023) 94 7 PII: 089902) - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Frojdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
CRIS-Team Scopus Importer:2023-12-22

Erratum: "Search for Dark Matter Annihilation Signals from the Fornax Galaxy Cluster with H.E.S.S.'' (2012, ApJ, 750, 123) - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Barres De Almeida, U.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astrophysical Journal, 2014)

Erratum to HESS J1640-465 - an exceptionally luminous TeV γ -ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
Keywords: Addenda; Errata; ISM: individual objects: G338.3-0.0; ISM: supernova remnants; Radiation mechanisms: non-thermal

Erratum: Using interstellar clouds to search for Galactic PeVatrons: gamma-ray signatures from supernova remnants (Monthly Notices of the Royal Astronomical Society (2021) 503 (3522–3539) DOI: 10.1093/mnras/stab667) - Mitchell, Alison; Rowell, G. P.; Celli, S.; Einecke, S. (Monthly Notices of the Royal Astronomical Society, 2023)
The paper ‘Using interstellar clouds to search for Galactic PeVatrons: gamma-ray signatures from supernova remnants’ was published in MNRAS 503 3522–3539 (2021). Following publication, a few issues were found in the numerical implementation of the described method, which influenced the predicted fluxes and the sorting of SNR–cloud pairs. Also, the catalogue values for SNR sizes are diameters, yet were interpreted as radii. These issues have now been corrected and a brief summary of revised results are presented in this erratum. Additionally, the following equations require revision: (i) A typographical error in the units for f(E, r, t) which should read cm−3GeV−1; (ii) Equation (9) contained a typographical error yet was correct in the implementation, it should read: √πRd3 f0 = (√πRd2 + 2√πRSNR2 ) Rd + 4RSNRRd2; (iii) Equation (11) should be replaced by the following equation from Reynolds (2008): RSNR(t) = 0.31 ( (n/(E1cmSN/−103)(51μerg)1/1.4) )1/5 (t/yr)2/5 pc; (iv) Equation (14) should read F(Eγ , t) = γ (Eγ , t)Vc/(4πD2 ). The combined effect of the corrections affects the shape of the curves in figs 3–5 and the predicted fluxes in subsequent figures and tables, in particular a reduction in flux at energies above 100 TeV, although the absolute flux normalization is at a comparable level for energies above 10 TeV. We provide here replacements for figs 3–5 (here Figs 1–3) and tables 2–4 (here Tables 1–3), for an integral γ -ray flux above 100 TeV. The coordinates of the cloud and SNR pairs and new predictions for the integral γ -ray flux are shown in Tables 2 and 3 and A1, with cloud properties and flux upper limits from H.E.S.S. Collaboration (2018). Replacements are also provided for figs 6 and 7 (here Figs 4 and 5). After these changes, the slow diffusion case is more favourable in generating a detectable gamma-ray flux. Indeed, in the fast diffusion case, there are no clouds predicted to have a gamma-ray flux detectable by CTA-S above 100 TeV. Consequently, we now show Figs 6 and 7 (replacements for figs 8 and 9 respectively) and Table 1 (replacement for table 2) for the slow diffusion case. Additionally, we note that after correcting the issues described above, none of the clouds have a predicted flux that violates an upper limit obtained from the HGPS in either fast or slow diffusion cases. An additional issue affecting the matching of SNRs to nearby clouds, leading to pairs listed in the original work with large angular distances or SNRs overlapping with clouds along the line-of-sight, has also been corrected in the revised tables. The discussion of section 5.1 is focused on the clouds with the brightest predicted gamma-ray flux as compared to the HGPS and in section 5.2 to HAWC observations. As the predicted fluxes are revised (see figs B1–B4), so the comparison should be interpreted in the context of these new results. From Tables 2 and 3, we see that the four clouds located at (333.46, −0.31), (16.97, 0.53), (110.43, 1.89), and (336.73, −0.98) are now the most favourable candidates for detecting a significant gamma-ray flux above 100 TeV. Further replacement figures and tables for the remaining results affected can be found in the online supplementary material.
CRIS-Team Scopus Importer:2023-06-30

Evaluation of the Weighted Mean X-ray Energy for an Imaging System Via Propagation-Based Phase-Contrast Imaging - Seifert, Maria; Weule, Mareike; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Michel, Thilo; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Anton, Gisela; Funk, Stefan; et al. (Journal of Imaging, 2020)
For imaging events of extremely short duration, like shock waves or explosions, it is necessary to be able to image the object with a single-shot exposure. A suitable setup is given by a laser-induced X-ray source such as the one that can be found at GSI (Helmholtzzentrum fur Schwerionenforschung GmbH) in Darmstadt (Society for Heavy Ion Research), Germany. There, it is possible to direct a pulse from the high-energy laser Petawatt High Energy Laser for Heavy Ion eXperiments (PHELIX) on a tungsten wire to generate a picosecond polychromatic X-ray pulse, called backlighter. For grating-based single-shot phase-contrast imaging of shock waves or exploding wires, it is important to know the weighted mean energy of the X-ray spectrum for choosing a suitable setup. In propagation-based phase-contrast imaging the knowledge of the weighted mean energy is necessary to be able to reconstruct quantitative phase images of unknown objects. Hence, we developed a method to evaluate the weighted mean energy of the X-ray backlighter spectrum using propagation-based phase-contrast images. In a first step wave-field simulations are performed to verify the results. Furthermore, our evaluation is cross-checked with monochromatic synchrotron measurements with known energy at Diamond Light Source (DLS, Didcot, UK) for proof of concepts.
CRIS-Team WoS Importer:2020-08-28

Event reconstruction for KM3NeT/ORCA using convolutional neural networks - Aiello, S.; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; Ardid, M.; Aublin, J.; et al. (Journal of Instrumentation, 2020)
The KM3NeT research infrastructure is currently under construction at two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. This work aims at demonstrating the general applicability of deep convolutional neural networks to neutrino telescopes, using simulated datasets for the KM3NeT/ORCA detector as an example. To this end, the networks are employed to achieve reconstruction and classification tasks that constitute an alternative to the analysis pipeline presented for KM3NeT/ORCA in the KM3NeT Letter of Intent. They are used to infer event reconstruction estimates for the energy, the direction, and the interaction point of incident neutrinos. The spatial distribution of Cherenkov light generated by charged particles induced in neutrino interactions is classified as shower- or track-like, and the main background processes associated with the detection of atmospheric neutrinos are recognized. Performance comparisons to machine-learning classification and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this application of deep convolutional neural networks to simulated datasets for a large-volume neutrino telescope yields competitive reconstruction results and performance improvements with respect to classical approaches.
CRIS-Team WoS Importer:2020-10-30

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Evidence of 200 TeV photons from HAWC J1825-134 - Albert, A.; Alfaro, R.; Alvarez, C.; Camacho, J. R. Angeles; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2021)
The Earth is bombarded by ultrarelativistic particles, known as cosmic rays (CRs). CRs with energies up to a few PeV (=1015 eV), the knee in the particle spectrum, are believed to have a Galactic origin. One or more factories of PeV CRs, or PeVatrons, must thus be active within our Galaxy. The direct detection of PeV protons from their sources is not possible since they are deflected in the Galactic magnetic fields. Hundred TeV γ-rays from decaying π0, produced when PeV CRs collide with the ambient gas, can provide the decisive evidence of proton acceleration up to the knee. Here we report the discovery by the High Altitude Water Cerenkov (HAWC) observatory of the γ-ray source, HAWC J1825-134, whose energy spectrum extends well beyond 200 TeV without a break or cutoff. The source is found to be coincident with a giant molecular cloud. The ambient gas density is as high as 700 protons cm-3. While the nature of this extreme accelerator remains unclear, CRs accelerated to energies of several PeV colliding with the ambient gas likely produce the observed radiation.
CRIS-Team Scopus Importer:2021-02-26

Evidence that Ultra-high-energy Gamma Rays Are a Universal Feature near Powerful Pulsars - Albert, A.; Alfaro, R.; Alvarez, C.; Alvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; et al. (Astrophysical Journal Letters, 2021)
The highest-energy known gamma-ray sources are all located within 0.°5 of extremely powerful pulsars. This raises the question of whether ultra-high-energy (UHE; >56 TeV) gamma-ray emission is a universal feature expected near pulsars with a high spin-down power. Using four years of data from the High Altitude Water Cherenkov Gamma-Ray Observatory, we present a joint-likelihood analysis of 10 extremely powerful pulsars to search for subthreshold UHE gamma-ray emission correlated with these locations. We report a significant detection (>3σ), indicating that UHE gamma-ray emission is a generic feature of powerful pulsars. We discuss the emission mechanisms of the gamma rays and the implications of this result. The individual environment, such as the magnetic field and particle density in the surrounding area, appears to play a role in the amount of emission.
CRIS-Team Scopus Importer:2021-05-14

Exploring a SNR/molecular cloud association within HESS J1745-303 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Aims. HESS J1745-303 is an extended, unidentified VHE (very high energy) gamma-ray source discovered using HESS in the Galactic Plane Survey. Since no obvious counterpart has previously been found in longer-wavelength data, the processes that power the VHE emission are not well understood.Methods. Combining the latest VHE data with recent XMM-Newton observations and a variety of source catalogs and lower-energy survey data, we attempt to match (from an energetic and positional standpoint) the various parts of the emission of HESS J1745-303 with possible candidates.Results. Though no single counterpart is found to fully explain the VHE emission, we postulate that at least a fraction of the VHE source may be explained by a supernova-remnant/molecular-cloud association and/or a high-spin-down-flux pulsar. © 2008 ESO.
Keywords: Galaxy: general; Gamma rays: observations; ISM: clouds; ISM: cosmic rays; X-rays: general

Extended Gamma-Ray Emission from the G25.0+0.0 Region: A Star-forming Region Powered by the Newly Found OB Association? - Katsuta, J.; Uchiyama, Y.; Funk, Stefan (Astrophysical Journal, 2017)
We report a study of extended gamma-ray emission with the Large Area Telescope (LAT) on board the Fermi Gammaray Space Telescope, which is likely to be the second case of gamma-ray detection from a star-forming region (SFR) in our Galaxy. The LAT source is located in the G25 region, 1 degrees.7. x. 2 degrees.1 around (l, b) = (25 degrees.0, 0 degrees.0). The gamma-ray emission is found to be composed of two extended sources and one pointlike source. The extended sources have similar sizes of about 1 degrees.4. x. 0 degrees.1. An similar to 0 degrees.4 diameter subregion of one has a photon index of Gamma = 1.53 +/- 0.15, and is spatially coincident with HESS J1837-069, likely a pulsar wind nebula. The other parts of the extended sources have a photon index of Gamma = 2.1 +/- 0.2 without significant spectral curvature. Given their spatial and spectral properties, they have no clear associations with sources at other wavelengths. Their gamma-ray properties are similar to those of the Cygnus cocoon SFR, the only firmly established gamma-ray detection of an SFR in the Galaxy. Indeed, we find bubble-like structures of atomic and molecular gas in G25, which may be created by a putative OB association/cluster. The gamma-ray emitting regions appear confined in the bubble-like structure; similar properties are also found in the Cygnus cocoon. In addition, using observations with the XMM-Newton, we find a candidate young massive OB association/cluster G25.18+0.26 in the G25 region. We propose that the extended gamma-ray emission in G25 is associated with an SFR driven by G25.18+0.26. Based on this scenario, we discuss possible acceleration processes in the SFR and compare them with the Cygnus cocoon.
CRIS-Team WoS Importer:2020-01-15

Extended VHE gamma-ray emission towards SGR1806-20, LBV 1806-20, and stellar cluster Cl*1806-20 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Using the High Energy Spectroscopic System (H.E.S.S.) telescopes we have discovered a steady and extended very high-energy (VHE) gamma-ray source towards the luminous blue variable candidate LBV 1806-20, massive stellar cluster Cl* 1806-20, and magnetar SGR 1806-20. The new VHE source, HESS J1808-204, was detected at a statistical significance of >6 sigma (post-trial) with a photon flux normalisation (2.9 +/- 0.4(stat) +/- 0.5(sys)) x 10(-13) ph cm(-2) s(-1) TeV-1 at 1 TeV and a power-law photon index of 2.3 +/- 0.2(stat) +/- 0.3(sys). The luminosity of this source (0.2 to 10 TeV; scaled to distance d = 8 : 7 kpc) is L-VHE similar to 1.6 x 10(34)(d = 8.7 kpc)(2) erg s(-1). The VHE gamma-ray emission is extended and is well fit by a single Gaussian with statistical standard deviation of 0.095 degrees +/- 0.015 degrees. This extension is similar to that of the synchrotron radio nebula G10.0-0.3, which is thought to be powered by LBV 1806-20. The VHE gamma-ray luminosity could be provided by the stellar wind luminosity of LBV 1806-20 by itself and/or the massive star members of Cl* 1806-20. Alternatively, magnetic dissipation (e.g. via reconnection) from SGR 1806-20 can potentially account for the VHE luminosity. The origin and hadronic and/or leptonic nature of the accelerated particles responsible for HESS J1808-204 is not yet clear. If associated with SGR 1806 20, the potentially young age of the magnetar (650 yr) can be used to infer the transport limits of these particles to match the VHE source size. This discovery provides new interest in the potential for high-energy particle acceleration from magnetars, massive stars, and/or stellar clusters.
Keywords: gamma rays: general; stars: magnetars; stars: massive

Fermi and Swift Observations of GRB 190114C: Tracing the Evolution of High-energy Emission from Prompt to Afterglow - Ajello, M.; Arimoto, M.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bottacini, E.; et al. (Astrophysical Journal, 2020)
We report on the observations of gamma-ray burst (GRB) 190114C by the Fermi Gamma-ray Space Telescope and the Neil Gehrels Swift Observatory. The prompt gamma-ray emission was detected by the Fermi GRB Monitor (GBM), the Fermi Large Area Telescope (LAT), and the Swift Burst Alert Telescope (BAT) and the long-lived afterglow emission was subsequently observed by the GBM, LAT, Swift X-ray Telescope (XRT), and Swift UV Optical Telescope. The early-time observations reveal multiple emission components that evolve independently, with a delayed power-law component that exhibits significant spectral attenuation above 40 MeV in the first few seconds of the burst. This power-law component transitions to a harder spectrum that is consistent with the afterglow emission observed by the XRT at later times. This afterglow component is clearly identifiable in the GBM and BAT light curves as a slowly fading emission component on which the rest of the prompt emission is superimposed. As a result, we are able to observe the transition from internal-shock- to external-shock-dominated emission. We find that the temporal and spectral evolution of the broadband afterglow emission can be well modeled as synchrotron emission from a forward shock propagating into a wind-like circumstellar environment. We estimate the initial bulk Lorentz factor using the observed high-energy spectral cutoff. Considering the onset of the afterglow component, we constrain the deceleration radius at which this forward shock begins to radiate in order to estimate the maximum synchrotron energy as a function of time. We find that even in the LAT energy range, there exist high-energy photons that are in tension with the theoretical maximum energy that can be achieved through synchrotron emission from a shock. These violations of the maximum synchrotron energy are further compounded by the detection of very high-energy (VHE) emission above 300 GeV by MAGIC concurrent with our observations. We conclude that the observations of VHE photons from GRB 190114C necessitates either an additional emission mechanism at very high energies that is hidden in the synchrotron component in the LAT energy range, an acceleration mechanism that imparts energy to the particles at a rate that is faster than the electron synchrotron energy-loss rate, or revisions of the fundamental assumptions used in estimating the maximum photon energy attainable through the synchrotron process.
CRIS-Team Scopus Importer:2020-04-03

FERMI LARGE AREA TELESCOPE DETECTION OF A BREAK IN THE GAMMA-RAY SPECTRUM OF THE SUPERNOVA REMNANT CASSIOPEIA A - Yuan, Yajie; Funk, Stefan; Johannesson, Guelauger; Lande, Joshua; Tibaldo, Luigi; Uchiyama, Yasunobu (Astrophysical Journal, 2013)
We report on observations of the supernova remnant Cassiopeia A in the energy range from 100 MeV to 100 GeV using 44 months of observations from the Large Area Telescope on board the Fermi Gamma-Ray Space Telescope. We perform a detailed spectral analysis of this source and report on a low-energy break in the spectrum at 1.72(-0.89)(+1.35) GeV. By comparing the results with models for the gamma-ray emission, we find that hadronic emission is preferred for the GeV energy range.
Keywords: acceleration of particles; gamma rays: general; ISM: supernova remnants; radiation mechanisms: non-thermal; supernovae: individual (Cassiopeia A)

FERMI LARGE AREA TELESCOPE DETECTION OF EXTENDED GAMMA-RAY EMISSION FROM THE RADIO GALAXY FORNAX A - Ackermann, M.; Ajello, Marco; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; Bonino, R.; Brandt, T. J.; et al. (Astrophysical Journal, 2016)
We report the Fermi Large Area Telescope detection of extended gamma-ray emission from the lobes of the radio galaxy Fornax. A using 6.1 years of Pass. 8 data. After Centaurus. A, this is now the second example of an extended gamma-ray source attributed to a radio galaxy. Both an extended flat disk morphology and a morphology following the extended radio lobes were preferred over a point-source description, and the core contribution was constrained to be < 14% of the total gamma-ray flux. A preferred alignment of the gamma-ray elongation with the radio lobes was demonstrated by rotating the radio lobes template. We found no significant evidence for variability on similar to 0.5 year timescales. Taken together, these results strongly suggest a lobe origin for the gamma-rays. With the extended nature of the > 100 MeV gamma-ray emission established, we model the source broadband emission considering currently available total lobe radio and millimeter flux measurements, as well as X-ray detections attributed to inverse Compton (IC) emission off the cosmic microwave background (CMB). Unlike the Centaurus. A case, we find that a leptonic model involving IC scattering of CMB and extragalactic background light (EBL) photons underpredicts the gamma-ray fluxes by factors of about similar to 2-3, depending on the EBL model adopted. An additional gamma-ray spectral component is thus required, and could be due to hadronic emission arising from proton-proton collisions of cosmic rays with thermal plasma within the radio lobes.
Keywords: galaxies: active; galaxies: individual (Fornax A); galaxies: jets; gamma rays: galaxies; radiation mechanisms: non-thermal

Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Ackermann, M.; Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; et al. (Astrophysical Journal Supplement Series, 2020)
We present the fourth Fermi Large Area Telescope catalog (4FGL) of gamma-ray sources. Based on the first eight years of science data from the Fermi Gamma-ray Space Telescope mission in the energy range from 50 MeV to 1 TeV, it is the deepest yet in this energy range. Relative to the 3FGL catalog, the 4FGL catalog has twice as much exposure as well as a number of analysis improvements, including an updated model for the Galactic diffuse gamma-ray emission, and two sets of light curves (one-year and two-month intervals). The 4FGL catalog includes 5064 sources above 4 sigma significance, for which we provide localization and spectral properties. Seventy-five sources are modeled explicitly as spatially extended, and overall, 358 sources are considered as identified based on angular extent, periodicity, or correlated variability observed at other wavelengths. For 1336 sources, we have not found plausible counterparts at other wavelengths. More than 3130 of the identified or associated sources are active galaxies of the blazar class, and 239 are pulsars.
CRIS-Team WoS Importer:2020-04-03

Fermi Large Area Telescope Performance after 10 Years of Operation - Ajello, M.; Atwood, W. B.; Axelsson, M.; Bagagli, R.; Bagni, M.; Baldini, L.; Bastieri, D.; Bellardi, F.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal Supplement Series, 2021)
The Large Area Telescope (LAT), the primary instrument for the Fermi Gamma-ray Space Telescope (Fermi) mission, is an imaging, wide field-of-view, high-energy gamma-ray telescope, covering the energy range from 30 MeV to more than 300 GeV. We describe the performance of the instrument at the 10 yr milestone. LAT performance remains well within the specifications defined during the planning phase, validating the design choices and supporting the compelling case to extend the duration of the Fermi mission. The details provided here will be useful when designing the next generation of high-energy gamma-ray observatories.
CRIS-Team WoS Importer:2021-09-17

FERMI LARGE AREA TELESCOPE STUDY OF COSMIC-RAYS AND THE INTERSTELLAR MEDIUM IN NEARBY MOLECULAR CLOUDS (vol 755, 22, 2012) - Ackermann, M.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Berenji, B.; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2013)

FERMI LARGE AREA TELESCOPE THIRD SOURCE CATALOG - Acero, F.; Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Belfiore, A.; Bellazzini, R.; et al. (Astrophysical Journal Supplement Series, 2015)
We present the third Fermi Large Area Telescope (LAT) source catalog (3FGL) of sources in the 100 MeV-300 GeV range. Based on the first 4 yr of science data from the Fermi Gamma-ray Space Telescope mission, it is the deepest yet in this energy range. Relative to the Second Fermi LAT catalog, the 3FGL catalog incorporates twice as much data, as well as a number of analysis improvements, including improved calibrations at the event reconstruction level, an updated model for Galactic diffuse.-ray emission, a refined procedure for source detection, and improved methods for associating LAT sources with potential counterparts at other wavelengths. The 3FGL catalog includes 3033 sources above 4 sigma significance, with source location regions, spectral properties, and monthly light curves for each. Of these, 78 are flagged as potentially being due to imperfections in the model for Galactic diffuse emission. Twenty-five sources are modeled explicitly as spatially extended, and overall 238 sources are considered as identified based on angular extent or correlated variability (periodic or otherwise) observed at other wavelengths. For 1010 sources we have not found plausible counterparts at other wavelengths. More than 1100 of the identified or associated sources are active galaxies of the blazar class; several other classes of non-blazar active galaxies are also represented in the 3FGL. Pulsars represent the largest Galactic source class. From source counts of Galactic sources we estimate that the contribution of unresolved sources to the Galactic diffuse emission is similar to 3% at 1 GeV.
Keywords: catalogs; gamma-rays: general

Fermi-LAT Observations of LIGO/Virgo Event GW170817 - Ajello, Marco; Allafort, A.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2018)
We present the Fermi Large Area Telescope (LAT) observations of the binary neutron star merger event GW170817 and the associated short gamma-ray burst (SGRB) GRB 170817A detected by the Fermi Gamma-ray Burst Monitor. The LAT was entering the South Atlantic Anomaly at the time of the LIGO/Virgo trigger (t(GW)) and therefore cannot place constraints on the existence of high-energy (E > 100 MeV) emission associated with the moment of binary coalescence. We focus instead on constraining high-energy emission on longer timescales. No candidate electromagnetic counterpart was detected by the LAT on timescales of minutes, hours, or days after the LIGO/Virgo detection. The resulting flux upper bound (at 95% C. L.) from the LAT is 4.5. x. 10(-10) erg cm(-2) s(-1) in the 0.1-1 GeV range covering a period from tGW. +. 1153 s to t(GW). +. 2027 s. At the distance of GRB 170817A, this flux upper bound corresponds to a luminosity upper bound of 9.7. x. 10(43) erg s(-1), which is five orders of magnitude less luminous than the only other LAT SGRB with known redshift, GRB 090510. We also discuss the prospects for LAT detection of electromagnetic counterparts to future gravitational-wave events from Advanced LIGO/Virgo in the context of GW170817/GRB 170817A.
Keywords: gamma-ray burst: general; gamma rays: general; gravitational waves

Fermi-LAT Observations of LIGO/Virgo Event GW170817 - Ajello, Marco; Allafort, A.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2018)
We present the Fermi Large Area Telescope (LAT) observations of the binary neutron star merger event GW170817 and the associated short gamma-ray burst (SGRB) GRB 170817A detected by the Fermi Gamma-ray Burst Monitor. The LAT was entering the South Atlantic Anomaly at the time of the LIGO/Virgo trigger (t(GW)) and therefore cannot place constraints on the existence of high-energy (E > 100 MeV) emission associated with the moment of binary coalescence. We focus instead on constraining high-energy emission on longer timescales. No candidate electromagnetic counterpart was detected by the LAT on timescales of minutes, hours, or days after the LIGO/Virgo detection. The resulting flux upper bound (at 95% C. L.) from the LAT is 4.5. x. 10(-10) erg cm(-2) s(-1) in the 0.1-1 GeV range covering a period from tGW. +. 1153 s to t(GW). +. 2027 s. At the distance of GRB 170817A, this flux upper bound corresponds to a luminosity upper bound of 9.7. x. 10(43) erg s(-1), which is five orders of magnitude less luminous than the only other LAT SGRB with known redshift, GRB 090510. We also discuss the prospects for LAT detection of electromagnetic counterparts to future gravitational-wave events from Advanced LIGO/Virgo in the context of GW170817/GRB 170817A.
Keywords: gamma-ray burst: general; gamma rays: general; gravitational waves

Fermi-LAT Observations of the Gamma-Ray Burst GRB 130427A - Ackermann, M.; Ajello, M.; Asano, K.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; et al. (Science, 2014)
The observations of the exceptionally bright gamma-ray burst (GRB) 130427A by the Large Area Telescope aboard the Fermi Gamma-ray Space Telescope provide constraints on the nature of these unique astrophysical sources. GRB 130427A had the largest fluence, highest-energy photon (95 GeV), longest gamma-ray duration (20 hours), and one of the largest isotropic energy releases ever observed from a GRB. Temporal and spectral analyses of GRB 130427A challenge the widely accepted model that the nonthermal high-energy emission in the afterglow phase of GRBs is synchrotron emission radiated by electrons accelerated at an external shock.

FERMI-LAT OBSERVATIONS OF THE LIGO EVENT GW150914 - Ackermann, M.; Ajello, Marco; Albert, A.; Anderson, B.; Arimoto, M.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; et al. (Astrophysical Journal Letters, 2016)
The Fermi Large Area Telescope (LAT) has an instantaneous field of view (FoV) covering similar to 1/5 of the sky and it completes a survey of the entire sky in high-energy gamma-rays every 3 hr. It enables searches for transient phenomena over timescales from milliseconds to years. Among these phenomena could be electromagnetic counterparts to gravitational wave (GW) sources. In this paper, we present a detailed study of the LAT observations relevant to Laser Interferometer Gravitational-wave Observatory (LIGO) event GW150914, which is the first direct detection of gravitational waves and has been interpreted as being due to the coalescence of two stellar-mass black holes. The localization region for GW150914 was outside the LAT FoV at the time of the GW signal. However, as part of routine survey observations, the LAT observed the entire LIGO localization region within similar to 70 minutes of the trigger and thus enabled a comprehensive search for a.-ray counterpart to GW150914. The study of the LAT data presented here did not find any potential counterparts to GW150914, but it did provide limits on the presence of a transient counterpart above 100 MeV on timescales of hours to days over the entire GW150914 localization region.
Keywords: gamma-ray burst: general; gamma-rays: general; gravitational waves; methods: observational

FERMI LAT STACKING ANALYSIS OF SWIFT LOCALIZED GRBs - Ackermann, M.; Ajello, M.; Anderson, B.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bhat, P. N.; Bissaldi, Elisabetta; Bonino, R.; et al. (Astrophysical Journal, 2016)
We perform a comprehensive stacking analysis of data collected by the Fermi. Large Area Telescope (LAT) of gamma-ray bursts (GRBs) localized by the Swift. spacecraft, which were not detected by the LAT but which fell within the instrument's field of view at the time of trigger. We examine a total of 79 GRBs by comparing the observed counts over a range of time intervals to that expected from designated background orbits, as well as by using a joint likelihood technique to model the expected distribution of stacked counts. We find strong evidence for subthreshold emission at MeV to GeV energies using both techniques. This observed excess is detected during intervals that include and exceed the durations typically characterizing the prompt emission observed at keV energies and lasts at least 2700 s after the co-aligned burst trigger. By utilizing a novel cumulative likelihood analysis, we find that although a burst's prompt gamma-ray and afterglow X-ray flux both correlate with the strength of the subthreshold emission, the X-ray afterglow flux measured by Swift's X-ray Telescope at 11 hr post trigger correlates far more significantly. Overall, the extended nature of the subthreshold emission and its connection to the burst's afterglow brightness lend. further support to the external forward shock origin of the late-time emission detected by the LAT. These results suggest that the extended high-energy emission observed by the LAT may be a relatively common feature but remains undetected in a majority of bursts owing. to instrumental threshold effects.
Keywords: gamma-ray burst: general; gamma rays: general; methods: data analysis; X-rays: bursts

First detection of VHE γ-rays from SN 1006 by HESS - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims. Recent theoretical predictions of the lowest very high energy (VHE) luminosity of SN 1006 are only a factor 5 below the previously published HESS upper limit, thus motivating further in-depth observations of this source. Methods. Deep observations at VHE energies (above 100 GeV) were carried out with the high energy stereoscopic system (HESS) of Cherenkov Telescopes from 2003 to 2008. More than 100 h of data have been collected and subjected to an improved analysis procedure. Results. Observations resulted in the detection of VHE γ-rays from SN 1006. The measured γ-ray spectrum is compatible with a power-law, the flux is of the order of 1% of that detected from the Crab Nebula, and is thus consistent with the previously established HESS upper limit. The source exhibits a bipolar morphology, which is strongly correlated with non-thermal X-rays. Conclusions. Because the thickness of the VHE-shell is compatible with emission from a thin rim, particle acceleration in shock waves is likely to be the origin of the γ-ray signal. The measured flux level can be accounted for by inverse Compton emission, but a mixed scenario that includes leptonic and hadronic components and takes into account the ambient matter density inferred from observations also leads to a satisfactory description of the multi-wavelength spectrum. © 2010 ESO.
Keywords: Gamma rays: stars; Supernovae: individual: SN 1006 (G327.6+14.6)

First Fermi-LAT Solar Flare Catalog - Ajello, M.; Baldini, L.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bruel, P.; Buson, S.; Cameron, R. A.; Caputo, R.; et al. (Astrophysical Journal Supplement Series, 2021)
We present the first Fermi-Large Area Telescope (LAT) solar flare catalog covering the 24th solar cycle. This catalog contains 45 Fermi-LAT solar flares (FLSFs) with emission in the gamma-ray energy band (30 MeV-10 GeV) detected with a significance of >= 5 sigma over the years 2010-2018. A subsample containing 37 of these flares exhibits delayed emission beyond the prompt-impulsive hard X-ray phase, with 21 flares showing delayed emission lasting more than two hours. No prompt-impulsive emission is detected in four of these flares. We also present in this catalog observations of GeV emission from three flares originating from active regions located behind the limb of the visible solar disk. We report the lightcurves, spectra, best proton index, and localization (when possible) for all FLSFs. The gamma-ray spectra are consistent with the decay of pions produced by >300 MeV protons. This work contains the largest sample of high-energy gamma-ray flares ever reported and provides a unique opportunity to perform population studies on the different phases of the flare and thus allowing a new window in solar physics to be opened.
CRIS-Team WoS Importer:2021-02-12

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

First intensity interferometry measurements with the H.E.S.S. telescopes - Zmija, Andreas; Vogel, Naomi; Wohlleben, Frederik; Anton, Gisela; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2024)
Intensity interferometry for astrophysical observations has gained increasing interest in the last decade. The method of correlating photon fluxes at different telescopes for high resolution astronomy without access to the phase of the incoming light is insensitive to atmospheric turbulence and does not require high-precision optical path control. The necessary large collection areas can be provided by Imaging Atmospheric Cherenkov Telescopes. Implementation of intensity interferometers to existing telescope systems such as VERITAS and MAGIC has proven to be successful for high-resolution imaging of stars. In 2022 April we equipped two telescopes of the H.E.S.S. array in Namibia with an intensity interferometry setup to measure southern sky stars and star systems during the bright moon period. We mounted an external optical system to the lid of the telescope cameras, which splits the incoming light and feeds it into two photomultipliers in order to measure the zero-baseline correlation within one telescope in addition to the cross-correlation between the telescopes. The optical elements are motorized, which enables live correction of tracking inaccuracies of the telescopes. During the campaign we measured the spatial correlation curves and thereby the angular diameters of λ Sco (Shaula) and σ Sgr (Nunki), while we also performed systematic studies of our interferometer using the multiple star system of α Cru (Acrux).
CRIS-Team Scopus Importer:2024-01-26
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; methods: observational; stars: imaging; techniques: interferometric; telescopes

First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst: H.E.S.S. Observations of FRB 150418 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Aims. Following the detection of the fast radio burst FRB150418 by the SUPERB project at the Parkes radio telescope, we aim to search for very-high energy gamma-ray afterglow emission.Methods. Follow-up observations in the very-high energy gamma-ray domain were obtained with the H.E.S.S. imaging atmospheric Cherenkov telescope system within 14.5 h of the radio burst.Results. The obtained 1.4 h of gamma-ray observations are presented and discussed. At the 99% C.L. we obtained an integral upper limit on the gamma-ray flux of Phi(gamma)(E > 350 GeV) < 1.33 x 10(-8) m(-2) s(-1). Differential flux upper limits as function of the photon energy were derived and used to constrain the intrinsic high-energy afterglow emission of FRB 150418.Conclusions. No hints for high-energy afterglow emission of FRB 150418 were found. Taking absorption on the extragalactic background light into account and assuming a distance of z = 0 : 492 based on radio and optical counterpart studies and consistent with the FRB dispersion, we constrain the gamma-ray luminosity at 1 TeV to L < 5 : 1 x 10(47) erg/s at 99% C.L.
Keywords: Astroparticle physics; Gamma rays: general

FlashCam: A fully digital camera for the Cherenkov telescope array medium-sized telescopes - Pühlhofer, G.; Barcelo, M.; Bauer, C.; Bi, B.; Catalano, Jacqueline; Diebold, S.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
FlashCam is an innovative camera designed for the focal plane instrumentation of Cherenkov telescopes. The concept of the FlashCam trigger and readout system is based on the continuous digitization and digital processing of the photo detector signals on FPGAs, and on a high performance, Ethernet-based front-end readout. Because of the modular design, the electronics that have been developed can serve either photomultiplier tubes or silicon-based photon detectors. In the framework of the CTA (Cherenkov telescope array) project, the FlashCam team has developed a PMT-based camera that is suitable for the medium-sized telescopes. With over 100 Cherenkov telescopes, the CTA observatory will run the most sensitive ground-based telescope systems for TeV gamma-ray astronomy when the two arrays in the Northern and Southern Hemisphere (with three different telescope sizes) will go into operation in the upcoming years.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Cherenkov Telescope Array; electronics; gamma-rays; Imaging Atmospheric Cherenkov Telescopes

Flux upper limits for 47 AGN observed with H.E.S.S. in 2004 - 2011 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. About 40% of the observation time of the High Energy Stereoscopic System (H.E.S.S.) is dedicated to studying active galactic nuclei (AGN), with the aim of increasing the sample of known extragalactic very-high-energy (VHE, E > 100 GeV) sources and constraining the physical processes at play in potential emitters. Aims. H.E.S.S. observations of AGN, spanning a period from April 2004 to December 2011, are investigated to constrain their γ-ray fluxes. Only the 47 sources without significant excess detected at the position of the targets are presented. Methods. Upper limits on VHE fluxes of the targets were computed and a search for variability was performed on the nightly time scale. Results. For 41 objects, the flux upper limits we derived are the most constraining reported to date. These constraints at VHE are compared with the flux level expected from extrapolations of Fermi-LAT measurements in the two-year catalog of AGN. The H.E.S.S. upper limits are at least a factor of two lower than the extrapolated Fermi-LAT fluxes for 11 objects. Taking into account the attenuation by the extragalactic background light reduces the tension for all but two of them, suggesting intrinsic curvature in the high-energy spectra of these two AGN. Conclusions. Compilation efforts led by current VHE instruments are of critical importance for target-selection strategies before the advent of the Cherenkov Telescope Array (CTA). © ESO, 2014.
Keywords: Galaxies: active; Gamma rays: galaxies

Front-end electronics of the Compact High Energy Camera - Leach, S. A.; Lapington, J. S.; Ross, D.; Thornhill, J.; Duffy, C.; Funk, Stefan; Zink, Adrian; Jankowsky, David; White, R.; Zorn, J.; Tibaldo, L.; Varner, G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The Compact High Energy Camera is a focal plane camera designed for two mirror Schwarzschild–Couder design imaging air Cherenkov telescopes such as the SST-2M variants on the Cherenkov Telescope Array. It utilises a 2048-pixel array of silicon photomultipliers arranged in thirty-two 8 x 8 pixel 2 tiles. Each detector tile is instrumented with a front-end electronics module designed to provide single photon counting with sub-nanosecond timing, full-waveform digitisation and event triggering capabilities based around TARGET ASICs. Performance results including triggering, digitiser noise, signal crosstalk, linearity and dynamic range from initial laboratory tests have been collated and are presented.
CRIS-Team Scopus Importer:2019-05-07
Keywords: CHEC; CTA; Front-end electronics; Full-waveform readout; Readout; Silicon photomultipliers; SST-2M; TARGET

Future GLAST observations of SNRs and PWNe - Funk, Stefan (First GLAST Symposium, 2007)
CRIS-Team WoS Importer:2020-01-15

Galactic Cosmic Ray increase associated with an interplanetary magnetic cloud observed by HAWC - Lara, Alejandro; Arunbabu, K. P.; Niembro, Tatiana; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; et al. (Proceedings of Science, 2022)
We present the observation of an anomalous increment of the galactic cosmic ray (GCR) flux observed by the HAWC array during October 2016. We propose that this anisotropy of the GCR flux was caused by a magnetic flux rope (MFR) i. e., by the helicoidal magnetic field of an interplanetary coronal mass ejection observed at 1 AU at the same time. We computed the trajectory of protons with energy in the range of 10 to 60 GeV, traveling inside the helicoidal magnetic field observed in situ. The direction of these particles changes towards the axis of the MFR resulting in an anisotropy of the GCR flux along this axis. This model shows that the alignment between the MFR axis and the HAWC's asymptotic direction, combined with the high sensitivity of HAWC, allowed us to observe the effect of the passage of the MFR on the GCR flux. We present the HAWC observation associated with the passage of the MFR as well as the heliospheric circumstances around such phenomenon.
CRIS-Team Scopus Importer:2022-12-23

Galactic gamma-ray and neutrino emission from interacting cosmic-ray nuclei - Breuhaus, M.; Hinton, J. A.; Joshi, Vikas; Reville, B.; Schoorlemmer, H. (Astronomy & Astrophysics, 2022)
We present a study of the expectations for very-high-energy (VHE) to ultra-high-energy (UHE) gamma-ray and neutrino emission from interacting cosmic rays in our Galaxy as well as a comparison to the latest results for the Galactic UHE diffuse emission. We demonstrate the importance of properly accounting for both the mixed cosmic-ray composition and the gamma-ray absorption. We adopt the wounded-nucleon model of nucleus interactions and provide parameterisations of the resulting gamma-ray and neutrino production. Nucleon shielding due to clustering inside nuclei is shown to have a measurable effect on the production of gamma rays and is particularly evident close to breaks and cutoffs in mixed-composition particle spectra. The change in composition around the 'knee' in the cosmic ray spectrum has a noticeable impact on the diffuse neutrino and gamma-ray emission spectra. We show that current and near-future detectors can probe these differences in the key energy range from 10 TeV to 1 PeV, testing the paradigm of the universality of the cosmic ray spectrum and composition throughout the Galaxy.
CRIS-Team WoS Importer:2022-05-20
Keywords: radiation mechanisms: non-thermal; cosmic rays; neutrinos; gamma rays: ISM

Galactic Gamma-Ray Diffuse Emission at TeV Energies with HAWC Data - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Babu, R.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Astrophysical Journal, 2024)
Galactic gamma-ray diffuse emission (GDE) is emitted by cosmic rays (CRs), ultra-relativistic protons, and electrons, interacting with gas and electromagnetic radiation fields in the interstellar medium. Here we present the analysis of teraelectronvolt diffuse emission from a region of the Galactic plane over the range in longitude of l ∈ [43°, 73°], using data collected with the High Altitude Water Cherenkov (HAWC) detector. Spectral, longitudinal, and latitudinal distributions of the teraelectronvolt diffuse emission are shown. The radiation spectrum is compatible with the spectrum of the emission arising from a CR population with an index similar to that of the observed CRs. When comparing with the DRAGON base model, the HAWC GDE flux is higher by about a factor of 2. Unresolved sources such as pulsar wind nebulae and teraelectronvolt halos could explain the excess emission. Finally, deviations of the Galactic CR flux from the locally measured CR flux may additionally explain the difference between the predicted and measured diffuse fluxes.
CRIS-Team Scopus Importer:2024-02-09

Gamma/hadron separation with the HAWC observatory - Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2022)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory observes atmospheric showers produced by incident gamma rays and cosmic rays with energy from 300 GeV to more than 100 TeV. A crucial phase in analyzing gamma-ray sources using ground-based gamma-ray detectors like HAWC is to identify the showers produced by gamma rays or hadrons. The HAWC observatory records roughly 25,000 events per second, with hadrons representing the vast majority (>99.9%) of these events. The standard gamma/hadron separation technique in HAWC uses a simple rectangular cut involving only two parameters. This work describes the implementation of more sophisticated gamma/hadron separation techniques, via machine learning methods (boosted decision trees and neural networks), and summarizes the resulting improvements in gamma/hadron separation obtained in HAWC.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Crab Nebula; G/H separation; High energy; Machine Learning

Gammapy: A Python package for gamma-ray astronomy - Donath, Axel; Terrier, Régis; Remy, Quentin; Sinha, Atreyee; Nigro, Cosimo; Pintore, Fabio; Khélifi, Bruno; Olivera-Nieto, Laura; Ruiz, Jose Enrique; Brügge, Kai; Linhoff, Maximilian; Contreras, Jose Luis; et al. (Astronomy & Astrophysics, 2023)
Context. Traditionally, TeV-γ-ray astronomy has been conducted by experiments employing proprietary data and analysis software. However, the next generation of γ-ray instruments, such as the Cherenkov Telescope Array Observatory (CTAO), will be operated as open observatories. Alongside the data, they will also make the associated software tools available to a wider community. This necessity prompted the development of open, high-level, astronomical software customized for high-energy astrophysics. Aims. In this article, we present Gammapy, an open-source Python package for the analysis of astronomical γ-ray data, and illustrate the functionalities of its first long-term-support release, version 1.0. Built on the modern Python scientific ecosystem, Gammapy provides a uniform platform for reducing and modeling data from different γ-ray instruments for many analysis scenarios. Gammapy complies with several well-established data conventions in high-energy astrophysics, providing serialized data products that are interoperable with other software packages. Methods. Starting from event lists and instrument response functions, Gammapy provides functionalities to reduce these data by binning them in energy and sky coordinates. Several techniques for background estimation are implemented in the package to handle the residual hadronic background affecting γ-ray instruments. After the data are binned, the flux and morphology of one or more γ-ray sources can be estimated using Poisson maximum likelihood fitting and assuming a variety of spectral, temporal, and spatial models. Estimation of flux points, likelihood profiles, and light curves is also supported. Results. After describing the structure of the package, we show, using publicly available gamma-ray data, the capabilities of Gammapy in multiple traditional and novel γ-ray analysis scenarios, such as spectral and spectro-morphological modeling and estimations of a spectral energy distribution and a light curve. Its flexibility and its power are displayed in a final multi-instrument example, where datasets from different instruments, at different stages of data reduction, are simultaneously fitted with an astrophysical flux model.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Astroparticle physics; Gamma rays: general; Methods: data analysis; Methods: statistical

Gamma-ray blazar spectra with H.E.S.S. II mono analysis: The case of PKS 2155-304 and PG 1553+113 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Context. The addition of a 28 m Cherenkov telescope (CT5) to the H.E.S.S. array extended the experiment's sensitivity to lower energies. The lowest energy threshold is obtained using monoscopic analysis of data taken with CT5, providing access to gamma-ray energies below 100 GeV for small zenith angle observations. Such an extension of the instrument's energy range is particularly beneficial for studies of active galactic nuclei with soft spectra, as expected for those at a redshift ≥0.5. The high-frequency peaked BL Lac objects PKS 2155-304 (z = 0:116) and PG 1553+113 (0:43 < z < 0:58) are among the brightest objects in the gamma-ray sky, both showing clear signatures of gamma-ray absorption at E > 100 GeV interpreted as being due to interactions with the extragalactic background light (EBL). Aims. The aims of this work are twofold: to demonstrate the monoscopic analysis of CT5 data with a low energy threshold, and to obtain accurate measurements of the spectral energy distributions (SED) of PKS 2155-304 and PG 1553+113 near their SED peaks at energies 100 GeV. Methods. Multiple observational campaigns of PKS 2155-304 and PG 1553+113 were conducted during 2013 and 2014 using the full H.E.S.S. II instrument (CT1'5). A monoscopic analysis of the data taken with the new CT5 telescope was developed along with an investigation into the systematic uncertainties on the spectral parameters which are derived from this analysis. Results. Using the data from CT5, the energy spectra of PKS 2155-304 and PG 1553+113 were reconstructed down to conservative threshold energies of 80 GeV for PKS 2155-304, which transits near zenith, and 110 GeV for the more northern PG 1553+113. The measured spectra, well fitted in both cases by a log-parabola spectral model (with a 5.0φ statistical preference for non-zero curvature for PKS 2155-304 and 4.5φ for PG 1553+113), were found consistent with spectra derived from contemporaneous Fermi-LAT data, indicating a sharp break in the observed spectra of both sources at E 100 GeV. When corrected for EBL absorption, the intrinsic H.E.S.S. II mono and Fermi-LAT spectrum of PKS 2155-304 was found to show significant curvature. For PG 1553+113, however, no significant detection of curvature in the intrinsic spectrum could be found within statistical and systematic uncertainties.
Keywords: BL Lacertae objects: individual: PG 1553+113; BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Gamma rays: galaxies

Gamma-Ray Blazars within the First 2 Billion Years - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal Letters, 2017)
The detection of high-redshift (z > 3) blazars enables the study of the evolution of the most luminous relativistic jets over cosmic time. More importantly, high-redshift blazars tend to host massive black holes and can be used to constrain the space density of heavy black holes in the early universe. Here, we report the first detection with the Fermi-Large Area Telescope of five gamma-ray-emitting blazars beyond z. =. 3.1, more distant than any blazars previously detected in.-rays gamma Among these five objects, NVSS J151002+570243 is now the most distant known gamma-ray-emitting blazar at z =. 4.31. These objects have steeply falling gamma-ray spectral energy distributions (SEDs), and. those that have been observed in X-rays have a very hard X-ray spectrum, both typical of powerful blazars. Their Compton dominance ( ratio of the inverse Compton to synchrotron peak luminosities) is also very large (>20). All of these properties place these objects among the most extreme members of the blazar population. Their optical spectra and the modeling of their optical-UV SEDs confirm that these objects harbor massive black holes (MBH similar to 10(8-10) M circle dot 8 10). We find that, at z approximate to 4, the space density of >10(9)M circle dot black holes hosted in radio-loud and radio-quiet active galactic nuclei are similar, implying that radio-loudness may play a key role in rapid black hole growth in the early universe.
CRIS-Team WoS Importer:2020-01-15

Gamma Rays from Fast Black-hole Winds - Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; Bonino, R.; Bruel, P.; et al. (Astrophysical Journal, 2021)
Massive black holes at the centers of galaxies can launch powerful wide-angle winds that, if sustained over time, can unbind the gas from the stellar bulges of galaxies. These winds may be responsible for the observed scaling relation between the masses of the central black holes and the velocity dispersion of stars in galactic bulges. Propagating through the galaxy, the wind should interact with the interstellar medium creating a strong shock, similar to those observed in supernovae explosions, which is able to accelerate charged particles to high energies. In this work we use data from the Fermi Large Area Telescope to search for the gamma-ray emission from galaxies with an ultrafast outflow (UFO): a fast (v similar to 0.1 c), highly ionized outflow, detected in absorption at hard X-rays in several nearby active galactic nuclei (AGN). Adopting a sensitive stacking analysis we are able to detect the average gamma-ray emission from these galaxies and exclude that it is due to processes other than UFOs. Moreover, our analysis shows that the gamma-ray luminosity scales with the AGN bolometric luminosity and that these outflows transfer similar to 0.04% of their mechanical power to gamma-rays. Interpreting the observed gamma-ray emission as produced by cosmic rays (CRs) accelerated at the shock front, we find that the gamma-ray emission may attest to the onset of the wind-host interaction and that these outflows can energize charged particles up to the transition region between galactic and extragalactic CRs.
CRIS-Team WoS Importer:2021-11-26

Giant gamma-ray bubbles in the Milky Way - Franckowiak, Anna; Funk, Stefan (Physics Today, 2014)

GLAST and ground-based gamma-ray astronomy - Funk, Stefan; et al. (First GLAST Symposium, 2007)
CRIS-Team WoS Importer:2020-01-15

Ground- and Space-Based Gamma-Ray Astronomy - Funk, Stefan (Annual Review of Nuclear and Particle Science, 2015)
Keywords: Cosmic rays; Dark matter; Fermi-LAT; Galactic center; Imaging atmospheric Cherenkov telescopes; γ-ray astronomy

Hadronic re-acceleration at the Crab pulsar wind termination shock as a source of PeV gamma-rays - Spencer, Samuel; Mitchell, Alison; Reville, Brian (38th International Cosmic Ray Conference (ICRC2023), 2023)
Recent results from LHAASO and Tibet ASγ suggest that the Crab Nebula’s gamma-ray spectrum extends to the PeV energy range, however the production mechanisms of this highest energy emission remain unclear. It has been postulated that a secondary component of hadronic emission could explain the highest energy gamma-ray flux points, however the origin and acceleration mechanism for this hadronic population has yet to be explained. We postulate one scenario in which hadrons diffuse over time into the Crab pulsar wind nebula from the surrounding supernova ejecta, and are subsequently re-accelerated by the pulsar wind termination shock. We present results of direct particle transport simulations (including radial evolution) to determine if this scenario is viable over the lifetime of the Crab system.<br

Halo fraction in TeV-bright pulsar wind nebulae - Giacinti, G.; Mitchell, Alison M. W.; Lopez-Coto, R.; Joshi, Vikas; Parsons, R. D.; Hinton, J. A. (Astronomy & Astrophysics, 2020)
The discovery of extended TeV emission around the Geminga and PSR B0656+14 pulsars, with properties consistent with free particle propagation in the interstellar medium (ISM), has led to the suggestion of "TeV halos" as a separate source class, which is distinct from pulsar wind nebulae. This has sparked considerable discussion on the possible presence of such halos in other systems. In defining halos as regions where the pulsar no longer dominates the dynamics of the interstellar medium, yet where an over-density of relativistic electrons is present, we make an assessment of the current TeV source population associated with energetic pulsars in terms of size and estimated energy density. Based on two alternative estimators, we conclude that a large majority of the known TeV sources have emission originating in the zone that is energetically and dynamically dominated by the pulsar (i.e. the pulsar wind nebula), rather than from a surrounding halo of escaped particles diffusing into the ISM. Furthermore, whilst the number of established halos will surely increase in the future since there is a known large population of older, less energetic pulsars, we find that it is unlikely that such halos contribute significantly to the total TeV gamma -ray luminosity from electrons accelerated in pulsar wind nebulae due to their lower intrinsic surface brightness.
CRIS-Team WoS Importer:2020-05-19
Keywords: Pulsars: general; Diffusion; Gamma rays: general; Cosmic rays

Hard and bright gamma-ray emission at the base of the Fermi bubbles - Herold, Laura; Malyshev, Dmitry (Astronomy & Astrophysics, 2019)
Context. The Fermi bubbles (FBs) are large gamma-ray emitting lobes extending up to 55◦ in latitude above and below the Galactic center (GC). Although the FBs were discovered eight years ago, their origin and the nature of the gamma-ray emission are still unresolved. Understanding the properties of the FBs near the Galactic plane may provide a clue to their origin. Previous analyses of the gamma-ray emission at the base of the FBs, what remains after subtraction of Galactic foregrounds, have shown an increased intensity compared to the FBs at high latitudes, a hard power-law spectrum without evidence of a cutoff up to approximately 1 TeV, and a displacement of the emission to negative longitudes relative to the GC. Aims. We analyze nine years of Fermi Large Area Telescope data in order to study in more detail than the previous analyses the gamma-ray emission at the base of the FBs, especially at energies above 10 GeV. Methods. We used a template analysis method to model the observed gamma-ray data and calculate the residual emission after subtraction of the expected foreground and background emission components. Since there are large uncertainties in the determination of the Galactic gamma-ray emission toward the GC, we used several methods to derive Galactic gamma-ray diffuse emission and the contribution from point sources to estimate the uncertainties in the emission at the base of the FBs. Results. We confirm that the gamma-ray emission at the base of the FBs is well described by a simple power law up to 1 TeV energies. The 95% confidence lower limit on the cutoff energy is about 500 GeV. It has larger intensity than the FBs emission at high latitudes and is shifted to the west (negative longitudes) from the GC. If the emission at the base of the FBs is indeed connected to the high-latitude FBs, then the shift of the emission to negative longitudes disfavors models in which the FBs are created by the supermassive black hole at the GC. We find that the gamma-ray spectrum can be explained either by gamma rays produced in hadronic interactions or by leptonic inverse Compton scattering. In the hadronic scenario, the emission at the base of the FBs can be explained either by several hundred supernova remnants (SNRs) near the GC or by about ten SNRs at a distance of ∼1 kpc. In the leptonic scenario, the necessary number of SNRs that can produce the required density of CR electrons is a factor of a few larger than in the hadronic scenario.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Astroparticle physics; Galaxy: bulge; Galaxy: center; Gamma rays: diffuse background; ISM: bubbles; ISM: jets and outflows

HAWC and Fermi-LAT Detection of Extended Emission from the Unidentified Source 2HWC J2006+341 - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Araya, M.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
The discovery of the TeV point source 2HWC J2006+341 was reported in the second HAWC gamma-ray catalog. We present a follow-up study of this source here. The TeV emission is best described by an extended source with a soft spectrum. At GeV energies, an extended source is significantly detected in Fermi-LAT data. The matching locations, sizes, and spectra suggest that both gamma-ray detections correspond to the same source. Different scenarios for the origin of the emission are considered and we rule out an association to the pulsar PSR J2004 +3429 due to extreme energetics required, if located at a distance of 10.8 kpc.
CRIS-Team Scopus Importer:2020-11-20

HAWC as a Ground-Based Space-Weather Observatory - Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; BenZvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Colín-Farias, P.; et al. (Solar Physics, 2021)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory is located close to the equator (latitude 18 ∘ N), at an altitude of 4100 m above sea level. HAWC has 295 water Cherenkov detectors (WCD), each containing four photomultiplier tubes (PMT). The main purpose of HAWC is the determination of the energy and arrival direction of very high energy gamma rays produced by energetic processes in the universe, HAWC also has a scaler system which counts the arrival of secondary particles to the detector. In this work we show that the scaler system of HAWC is an ideal instrument for solar modulation and space-weather studies due to its large area and high sensitivity. In order to prepare the scaler system for low energy heliospheric studies, we model and correct the efficiency variation of each PMT of the array, which result in a capability to measure variations > 0.01 % with high accuracy. Using the singular value decomposition method, we correct the rate deviations of all PMTs of the array, due to changes in efficiency, gain and operational voltage. We isolate and remove the atmospheric modulations of the PMTs count rates measured by the TDC-scaler data acquisition system. In particular, the atmospheric pressure at the HAWC site exhibits an oscillating behavior with a period of ∼12 hours and we make use of this periodic property to estimate the pressure coefficients for the HAWC TDC-scaler system. These corrections performed on the TDC-scaler system make the HAWC TDC-scaler system an ideal instrument for solar modulation and space-weather studies. As examples of this capability, we present the preliminary analysis of the solar modulation of cosmic rays at three time scales observed by HAWC, with an unprecedented accuracy.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Atmospheric pressure modulation; Cosmic rays; Fast Fourier transform; Solar modulation

HAWC Detection of a TeV Halo Candidate Surrounding a Radio-quiet Pulsar - Albert, A.; Alfaro, R.; Arteaga-Velázquez, J. C.; Ayala Solares, H. A.; Belmont-Moreno, E.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotzomi, J.; De León, S. Coutiño; Fuente, E. De la; de León, C.; et al. (Astrophysical Journal Letters, 2023)
Extended very-high-energy (VHE; 0.1-100 TeV) γ-ray emission has been observed around several middle-aged pulsars and referred to as “TeV halos.” Their formation mechanism remains under debate. It is also unknown whether they are ubiquitous or related to a certain subgroup of pulsars. With 2321 days of observation, the High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory detected VHE γ-ray emission at the location of the radio-quiet pulsar PSR J0359+5414 with >6σ significance. By performing likelihood tests with different spectral and spatial models and comparing the TeV spectrum with multiwavelength observations of nearby sources, we show that this excess is consistent with a TeV halo associated with PSR J0359+5414, though future observation of HAWC and multiwavelength follow-ups are needed to confirm this nature. This new halo candidate is located in a noncrowded region in the outer galaxy. It shares similar properties to the other halos but its pulsar is younger and radio-quiet. Our observation implies that TeV halos could commonly exist around pulsars and their formation does not depend on the configuration of the pulsar magnetosphere.
CRIS-Team Scopus Importer:2023-03-03

HAWC J2227+610 and Its Association with G106.3+2.7, a New Potential Galactic PeVatron - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
We present the detection of very-high-energy gamma-ray emission above 100 TeV from HAWC J2227+610 with the High-Altitude Water Cherenov Gamma-Ray Observatory (HAWC) observatory. Combining our observations with previously published results by the Very Energetic Radiation Imaging Telescope Array System (VERTIAS), we interpret the gamma-ray emission from HAWC J2227+610 as emission from protons with a lower limit in their cutoff energy of 800 TeV. The most likely source of the protons is the associated supernova remnant G106.3+2.7, making it a good candidate for a Galactic PeVatron. However, a purely leptonic origin of the observed emission cannot be excluded at this time.
CRIS-Team Scopus Importer:2020-07-10

HAWC observations of the acceleration of very-high-energy cosmic rays in the Cygnus Cocoon - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Camacho, J. R.Angeles; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; BenZvi, S. Y.; et al. (Nature Astronomy, 2021)
Cosmic rays with energies up to a few PeV are known to be accelerated within the Milky Way1,2. Traditionally, it has been presumed that supernova remnants were the main source of these very-high-energy cosmic rays3,4, but theoretically it is difficult to accelerate protons to PeV energies5,6 and observationally there simply is no evidence of the remnants being sources of hadrons with energies above a few tens of TeV7,8. One possible source of protons with those energies is the Galactic Centre region9. Here, we report observations of 1–100 TeV γ rays coming from the ‘Cygnus Cocoon’10, which is a superbubble that surrounds a region of massive star formation. These γ rays are likely produced by 10–1,000 TeV freshly accelerated cosmic rays that originate from the enclosed star-forming region Cyg OB2. Until now it was not known that such regions could accelerate particles to these energies. The measured flux likely originates from hadronic interactions. The spectral shape and the emission profile of the Cocoon changes from GeV to TeV energies, which reveals the transport of cosmic particles and historical activity in the superbubble.
CRIS-Team Scopus Importer:2021-04-02

HAWC Search for High-mass Microquasars - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2021)
Microquasars with high-mass companion stars are promising very high energy (VHE; 0.1-100 TeV) gamma-ray emitters, but their behaviors above 10 TeV are poorly known. Using the High Altitude Water Cerenkov (HAWC) observatory, we search for excess gamma-ray emission coincident with the positions of known high-mass microquasars (HMMQs). No significant emission is observed for LS 5039, Cyg X-1, Cyg X-3, and SS 433 with 1523 days of HAWC data. We set the most stringent limit above 10 TeV obtained to date on each individual source. Under the assumption that HMMQs produce gamma rays via a common mechanism, we have performed source-stacking searches, considering two different scenarios: (I) gamma-ray luminosity is a fraction epsilon ( gamma ) of the microquasar jet luminosity, and (II) VHE gamma rays are produced by relativistic electrons upscattering the radiation field of the companion star in a magnetic field B. We obtain epsilon ( gamma ) < 5.4 x 10(-6) for scenario I, which tightly constrains models that suggest observable high-energy neutrino emission by HMMQs. In the case of scenario II, the nondetection of VHE gamma rays yields a strong magnetic field, which challenges synchrotron radiation as the dominant mechanism of the microquasar emission between 10 keV and 10 MeV.
CRIS-Team WoS Importer:2021-05-21

HAWC Study of the Ultra-high-energy Spectrum of MGRO J1908+06 - Albert, A.; Alfaro, R.; Alvarez, C.; Alvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Astrophysical Journal, 2022)
We report TeV gamma-ray observations of the ultra-high-energy source MGRO J1908+06 using data from the High Altitude Water Cherenkov Observatory. This source is one of the highest-energy known gamma-ray sources, with emission extending past 200 TeV. Modeling suggests that the bulk of the TeV gamma-ray emission is leptonic in nature, driven by the energetic radio-faint pulsar PSR J1907+0602. Depending on what assumptions are included in the model, a hadronic component may also be allowed. Using the results of the modeling, we discuss implications for detection prospects by multi-messenger campaigns.
CRIS-Team WoS Importer:2022-04-22
Keywords: Gamma-ray sources; Gamma-rays; Pulsars; Supernova remnants; Gamma-ray astronomy

HAWC Study of the Very-high-energy γ-Ray Spectrum of HAWC J1844−034 - Albert, A.; Alvarez, C.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Belmont-Moreno, E.; Breuhaus, M.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotzomi, J.; de León, S. Coutiño; et al. (Astrophysical Journal, 2023)
Recently, the region surrounding eHWC J1842−035 has been studied extensively by γ-ray observatories due to its extended emission reaching up to a few hundred TeV and potential as a hadronic accelerator. In this work, we use 1910 days of cumulative data from the High Altitude Water Cherenkov (HAWC) observatory to carry out a dedicated systematic source search of the eHWC J1842−035 region. During the search, we found three sources in the region, namely, HAWC J1844−034, HAWC J1843−032, and HAWC J1846−025. We have identified HAWC J1844−034 as the extended source that emits photons with energies up to 175 TeV. We compute the spectrum for HAWC J1844−034, and by comparing with the observational results from other experiments, we have identified HESS J1843−033, LHAASO J1843−0338, and TASG J1844−038 as very-high-energy γ-ray sources with a matching origin. Also, we present and use the multiwavelength data to fit the hadronic and leptonic particle spectra. We have identified four pulsar candidates in the nearby region in which PSR J1844−0346 is found to be the most likely candidate due to its proximity to HAWC J1844−034 and the computed energy budget. We have also found SNR G28.6−0.1 as a potential counterpart source of HAWC J1844−034 for which both leptonic and hadronic scenarios are feasible.
CRIS-Team Scopus Importer:2023-09-22

HESS and Fermi-LAT discovery of γ-rays from the blazar 1ES 1312-423 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
A deep observation campaign carried out by the High Energy Stereoscopic System (HESS) on Centaurus A enabled the discovery of γ-rays from the blazar 1ES 1312-423, 2° away from the radio galaxy. With a differential flux at 1 TeV of f(1 TeV) = (1.9 ± 0.6 ± 0.4) × 10 cm s TeV corresponding to 0.5 per cent of the Crab nebula differential flux and a spectral index γ = 2.9 ± 0.5 ± 0.2, 1ES 1312-423 is one of the faintest sources ever detected in the very high energy (E <100 GeV) extragalactic sky. A careful analysis using three and a half years of Fermi Large Area Telescope (Fermi-LAT) data allows the discovery at high energies (100 < E MeV) of a hard spectrum (γ =1.4±0.4stat ±0.2sys) source coincident with 1ES 1312-423. Radio, optical, UV and X-ray observations complete the spectral energy distribution of this blazar, now covering 16 decades in energy. The emission is successfully fitted with a synchrotron self-Compton model for the non-thermal component, combined with a blackbody spectrum for the optical emission from the host galaxy. © 2013 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Bl Lacertae objects: individual: 1ES 1312-423; Galaxies: active; Galaxies: jets; Gamma-rays: galaxies.; Radiation mechanisms: non-thermal

HESS and Fermi-LAT observations of PSR B1259-63/LS 2883 during its 2014 and 2017 periastron passages - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. PSR B1259-63/LS 2883 is a gamma-ray binary system consisting of a pulsar in an eccentric orbit around a bright Oe stellar-type companion star that features a dense circumstellar disc. The bright broad-band emission observed at phases close to periastron offers a unique opportunity to study particle acceleration and radiation processes in binary systems. Observations at gamma-ray energies constrain these processes through variability and spectral characterisation studies.
CRIS-Team WoS Importer:2020-01-31
Keywords: Pulsars: general; Radiation mechanisms: non-thermal; Shock waves; γ-rays: general; Binaries: general; Astroparticle physics

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

H.E.S.S. constraints on dark matter annihilations towards the sculptor and carina dwarf galaxies - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; Barres De Almeida, U.; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astroparticle Physics, 2011)
The Sculptor and Carina dwarf spheroidal galaxies were observed with the H.E.S.S. Cherenkov telescope array between January 2008 and December 2009. The data sets consist of a total of 11.8 h and 14.8 h of high quality data, respectively. No gamma-ray signal was detected at the nominal positions of these galaxies above 220 GeV and 320 GeV, respectively. Upper limits on the gamma-ray fluxes at 95% CL assuming two forms for the spectral energy distribution (a power law shape and one derived from dark matter annihilation) are obtained at the level of 10-10 cm s in the TeV range. Constraints on the velocity weighted dark matter particle annihilation cross section for both Sculptor and Carina dwarf galaxies range from 〈σv〉 ∼ 10 cm s down to 〈σv〉 ∼ 10 cm s depending on the dark matter halo model used. Possible enhancements of the gamma-ray flux are studied: the Sommerfeld effect, which is found to exclude some dark matter particle masses, the internal Bremsstrahlung and clumps in the dark-matter halo distributions. © 2011 Published by Elsevier B.V.
Keywords: Carina; Dark matter; Gamma-rays: observations - Dwarf spheroidal galaxy; Internal Bremsstrahlung; Sculptor; Sommerfeld enhancement

H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderans, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
G349.7+0.2 is a young Galactic supernova remnant (SNR) located at the distance of 11.5 kpc and observed across the entire electromagnetic spectrum from radio to high energy (HE; 0.1 GeV < E < 100 GeV) γ-rays. Radio and infrared observations indicate that the remnant is interacting with a molecular cloud. In this paper, the detection of very high energy (VHE, E > 100 GeV) γ-ray emission coincident with this SNR with the High Energy Stereoscopic System (H.E.S.S.) is reported. This makes it one of the farthest Galactic SNR ever detected in this domain. An integral flux F (E > 400 GeV) = (6.5 ± 1.1 ± 1.3) × 10 ph cm s corresponding to ∼0.7% of that of the Crab Nebula and to a luminosity of ∼10 erg s above the same energy threshold, and a steep photon index Γ = 2.8 ± 0.27stat ± 0.20 are measured. The analysis of more than 5 yr of Fermi-LAT data towards this source shows a power-law like spectrum with a best-fit photon index Γ = 2.2 ± 0.04 . The combined γ-ray spectrum of G349.7+0.2 can be described by either a broken power-law (BPL) or a power-law with exponential (or sub-exponential) cutoff(PLC). In the former case, the photon break energy is found at E = 55 GeV, slightly higher than what is usually observed in the HE/VHE γ-ray emitting middle-aged SNRs known to be interacting with molecular clouds. In the latter case, the exponential (respectively sub-exponential) cutoff energy is measured at E = 1.4 (respectively 0.35 ) TeV. A pion-decay process resulting from the interaction of the accelerated protons and nuclei with the dense surrounding medium is clearly the preferred scenario to explain the γ-ray emission. The BPL with a spectral steepening of 0.5-1 and the PLC provide equally good fits to the data. The product of the average gas density and the total energy content of accelerated protons and nuclei amounts to n W ∼ 5 × 10 erg cm.
Keywords: Gamma rays: General; ISM: clouds; ISM: supernova remnants

HESS detection of very high-energy gamma-ray emission from the quasar PKS 0736+017 - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. Flat-spectrum radio-quasars (FSRQs) are rarely detected at very high energies (E& x2004;>=& x2004;100 GeV) due to their low-frequency-peaked spectral energy distributions. At present, only six FSRQs are known to emit very high-energy (VHE) photons, representing only 7% of the VHE extragalactic catalog, which is largely dominated by high-frequency-peaked BL Lacertae objects. Aims. Following the detection of MeV-GeV gamma-ray flaring activity from the FSRQ PKS 0736+017 (z& x2004;=& x2004;0.189) with Fermi-LAT, the H.E.S.S. array of Cherenkov telescopes triggered target-of-opportunity (ToO) observations on February 18, 2015, with the goal of studying the gamma-ray emission in the VHE band. Methods. H.E.S.S. ToO observations were carried out during the nights of February 18, 19, 21, and 24, 2015. Together with Fermi-LAT, the multi-wavelength coverage of the flare includes Swift observations in soft X-ray and optical-UV bands, and optical monitoring (photometry and spectro-polarimetry) by the Steward Observatory, and the ATOM, the KAIT, and the ASAS-SN telescopes. Results. VHE emission from PKS 0736+017 was detected with H.E.S.S. only during the night of February 19, 2015. Fermi-LAT data indicate the presence of a gamma-ray flare, peaking at the time of the H.E.S.S. detection, with a flux doubling timescale of around six hours. The gamma-ray flare was accompanied by at least a 1 mag brightening of the non-thermal optical continuum. No simultaneous observations at longer wavelengths are available for the night of the H.E.S.S. detection. The gamma-ray observations with H.E.S.S. and Fermi-LAT are used to put constraints on the location of the gamma-ray emitting region during the flare: it is constrained to be just outside the radius of the broad-line region r(BLR) with a bulk Lorentz factor Gamma& x2004;similar or equal to& x2004;20, or at the level of the radius of the dusty torus r(torus) with Gamma& x2004;similar or equal to& x2004;60. Conclusions. PKS 0736+017 is the seventh FSRQ known to emit VHE photons, and at z& x2004;=& x2004;0.189 is the nearest so far. The location of the gamma-ray emitting region during the flare can be tightly constrained thanks to opacity, variability, and collimation arguments.
CRIS-Team WoS Importer:2020-02-18
Keywords: Astroparticle physics; Gamma rays: general; Quasars: individual: PKS 0736+017; Relativistic processes

HESS discovery of very high energy gamma-ray emission from PKS 0625-354 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguner, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
PKS 0625-354 (z = 0.055) was observed with the four High Energy Stereoscopic System (H.E.S.S.) telescopes in 2012 during 5.5 h. The source was detected above an energy threshold of 200 GeV at a significance level of 6.1 sigma. No significant variability is found in these observations. The source is well described with a power-law spectrum with photon index Gamma = 2.84 +/- 0.50(stat) +/- 0.10(syst) and normalization (at E-0 = 1.0 TeV) N-0(E-0)=(0.58 +/- 0.22(stat) +/- 0.12(syst)) x 10(-12) TeV-1 cm(-2) s(-1). Multiwavelength data collected with Fermi-LAT, Swift-XRT, Swift-UVOT, ATOM and WISE are also analysed. Significant variability is observed only in the Fermi-LAT gamma-ray and Swift-XRT X-ray energy bands. Having a good multiwavelength coverage from radio to very high energy, we performed a broad-band modelling from two types of emission scenarios. The results from a one zone lepto-hadronic and a multizone leptonic models are compared and discussed. On the grounds of energetics, our analysis favours a leptonic multizone model. Models associated to the X-ray variability constraint support previous results, suggesting a BL Lac nature of PKS 0625-354 with, however, a large-scale jet structure typical of a radio galaxy.
Keywords: radiation mechanisms: non-thermal; galaxies: active; galaxies: individual: PKS 0625-354; galaxies: jets; gamma-rays: galaxies

H.E.S.S. discovery of VHE γ-rays from the quasar PKS 1510-089 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2013)
The quasar PKS 1510-089 (z = 0.361) was observed with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes during high states in the optical and GeV bands, to search for very high energy (VHE, defined as E ≥ 0.1 TeV) emission. VHE γ-rays were detected with a statistical significance of 9.2 standard deviations in 15.8 h of H.E.S.S. data taken during March and April 2009. A VHE integral flux of I(0.15 TeV < E < 1.0TeV) = (1.0 ±0.2 ±0.2) ×10 cm s is measured. The best-fit power law to the VHE data has a photon index of γ = 5.4 ± 0.7 ± 0.3. The GeV and optical light curves show pronounced variability during the period of H.E.S.S. observations. However, there is insufficient evidence to claim statistically significant variability in the VHE data. Because of its relatively high redshift, the VHE flux from PKS 1510-089 should suffer considerable attenuation in the intergalactic space due to the extragalactic background light (EBL). Hence, the measured γ-ray spectrum is used to derive upper limits on the opacity due to EBL, which are found to be comparable with the previously derived limits from relatively-nearby BL Lac objects. Unlike typical VHE-detected blazars where the broadband spectrum is dominated by nonthermal radiation at all wavelengths, the quasar PKS 1510-089 has a bright thermal component in the optical to UV frequency band. Among all VHE detected blazars, PKS 1510-089 has the most luminous broad line region. The detection of VHE emission from this quasar indicates a low level of γ - γ absorption on the internal optical to UV photon field. © 2013 ESO.
Keywords: Gamma rays: galaxies; Infrared: diffuse background; Quasars: individual: PKS 1510; 089

HESS Follow-up Observations of Binary Black Hole Coalescence Events during the Second and Third Gravitational-wave Observing Runs of Advanced LIGO and Advanced Virgo - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Ashkar, H.; Backes, M.; Baghmanyan,; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlohr, K.; et al. (Astrophysical Journal, 2021)
We report on the observations of four well-localized binary black hole (BBH) mergers by the High Energy Stereoscopic System (H.E.S.S.) during the second and third observing runs of Advanced LIGO and Advanced Virgo, O2 and O3. H.E.S.S. can observe 20 deg(2) of the sky at a time and follows up gravitational-wave (GW) events by "tiling" localization regions to maximize the covered localization probability. During O2 and O3, H.E.S.S. observed large portions of the localization regions, between 35% and 75%, for four BBH mergers (GW170814, GW190512_180714, GW190728_064510, and S200224ca). For these four GW events, we find no significant signal from a pointlike source in any of the observations, and we set upper limits on the very high energy (>100 GeV) gamma-ray emission. The 1-10 TeV isotropic luminosity of these GW events is below 10(45) erg s(-1) at the times of the H.E.S.S. observations, around the level of the low-luminosity GRB 190829A. Assuming no changes are made to how follow-up observations are conducted, H.E.S.S. can expect to observe over 60 GW events per year in the fourth GW observing run, O4, of which eight would be observable with minimal latency.
CRIS-Team WoS Importer:2021-12-24

H.E.S.S. Follow-up Observations of GRB 221009A - Aharonian, F.; Benkhali, F. Ait; Aschersleben, J.; Ashkar, H.; Backes, M.; Baktash, A.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; et al. (Astrophysical Journal Letters, 2023)
GRB 221009A is the brightest gamma-ray burst (GRB) ever detected. To probe the very-high-energy (VHE; >100 GeV) emission, the High Energy Stereoscopic System (H.E.S.S.) began observations 53 hr after the triggering event, when the brightness of the moonlight no longer precluded observations. We derive differential and integral upper limits using H.E.S.S. data from the third, fourth, and ninth nights after the initial GRB detection, after applying atmospheric corrections. The combined observations yield an integral energy flux upper limit of Φ UL 95 % = 9.7 × 10 − 12 erg cm − 2 s − 1 above E thr = 650 GeV. The constraints derived from the H.E.S.S. observations complement the available multiwavelength data. The radio to X-ray data are consistent with synchrotron emission from a single electron population, with the peak in the spectral energy distribution occurring above the X-ray band. Compared to the VHE-bright GRB 190829A, the upper limits for GRB 221009A imply a smaller gamma-ray to X-ray flux ratio in the afterglow. Even in the absence of a detection, the H.E.S.S. upper limits thus contribute to the multiwavelength picture of GRB 221009A, effectively ruling out an IC-dominated scenario.
CRIS-Team Scopus Importer:2023-04-14

HESS J0632+057: A NEW GAMMA-RAY BINARY? - Hinton, J. A.; Skilton, J. L.; Funk, Stefan; Brucker, Julia; Aharonian, F. A.; Dubus, Guillaume; Fiasson, A.; Gallant, Y.; Hofmann, W.; Marcowith, A.; Reimer, Olaf (Astrophysical Journal Letters, 2009)
The High Energy Stereoscopic System (HESS) survey of the Galactic plane has established the existence of a substantial number (similar to 40) of Galactic TeV gamma-ray sources, a large fraction of which remain unidentified. HESS J0632+057 is one of a small fraction of these objects, which is point-like in nature (< 2' rms), and is one of only two point-like sources that remain unidentified. Follow-up observations of this object with XMM-Newton have revealed an X-ray source coincident with the TeV source and with the massive star MWC 148, of the spectral type B0pe. This source exhibits a hard spectrum, consistent with an absorbed power law with Gamma = 1.26 +/- 0.04, and shows significant variability on hour timescales. We discuss this spatial coincidence and the implied spectral energy distribution of this object and argue that it is likely a new gamma-ray binary system with a close resemblance to the three known members of this class and, in particular, to LS I+61 303. Further, X-ray, radio, and optical observations of this system are needed to firmly establish HESS J0632+057 as a new member of this rare class of Galactic objects.
CRIS-Team WoS Importer:2020-01-15

HESS J1640-465-an exceptionally luminous TeV γ-ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The results of follow-up observations of the TeV γ-ray source HESS J1640-465 from 2004 to 2011 with the High Energy Stereoscopic System (HESS) are reported in this work. The spectrum is well described by an exponential cut-offpower law with photon index γ = 2.11 ± 0.09 ± 0.10, and a cut-offenergy of E = 6.0 TeV. The TeV emission is significantly extended and overlaps with the northwestern part of the shell of the SNR G338.3-0.0. The new HESS results, a re-analysis of archival XMM-Newton data and multiwavelength observations suggest that a significant part of the γ-ray emission from HESS J1640-465 originates in the supernova remnant shell. In a hadronic scenario, as suggested by the smooth connection of the GeV and TeV spectra, the product of total proton energy and mean target density could be as high as W 4 × 10(d/10kpc) erg cm. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: G338.3-0.0-ISM; Individual objects; Non-thermal-ISM; Radiation mechanisms; Supernova remnants

HESS J1741-302: a hidden accelerator in the Galactic plane - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
The H.E.S.S. Collaboration has discovered a new very high energy (VHE, E > 0.1 TeV) gamma-ray source, HESS J1741-302, located in the Galactic plane. Despite several attempts to constrain its nature, no plausible counterpart has been found so far at X-ray and MeV/GeV gamma-ray energies, and the source remains unidentified. An analysis of 145-h of observations of HESS J1741-302 at VHEs has revealed a steady and relatively weak TeV source (similar to 1% of the Crab Nebula flux), with a spectral index of Gamma = 2.3 +/- 0.2(stat) +/- 0.2(sys), extending to energies up to 10 TeV without any clear signature of a cut-off. In a hadronic scenario, such a spectrum implies an object with particle acceleration up to energies of several hundred TeV. Contrary to most H.E.S.S. unidentified sources, the angular size of HESS J1741-302 is compatible with the H.E.S.S. point spread function at VHEs, with an extension constrained to be below 0.068 degrees at a 99% confidence level. The gamma-ray emission detected by H.E.S.S. can be explained both within a hadronic scenario, due to collisions of protons with energies of hundreds of TeV with dense molecular clouds, and in a leptonic scenario, as a relic pulsar wind nebula, possibly powered by the middle-aged (20 kyr) pulsar PSR B1737-30. A binary scenario, related to the compact radio source 1LC 358.266+0.038 found to be spatially coincident with the best fit position of HESS J1741-302, is also envisaged.
Keywords: gamma rays: ISM; gamma rays: general; cosmic rays; ISM: clouds

HESS J1809-193: A halo of escaped electrons around a pulsar wind nebula? - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Boettcher, M.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2023)
Context. HESS J1809-193 is an unassociated very-high-energy gamma-ray source located on the Galactic plane. While it has been connected to the nebula of the energetic pulsar PSR J1809-1917, supernova remnants and molecular clouds present in the vicinity also constitute possible associations. Recently, the detection of gamma-ray emission up to energies of similar to 100 TeV with the HAWC observatory has led to renewed interest in HESS J1809-193.Aims. We aim to understand the origin of the gamma-ray emission of HESS J1809-193.Methods. We analysed 93.2 h of data taken on HESS J1809-193 above 0.27 TeV with the High Energy Stereoscopic System (H.E.S.S.), using a multi-component, three-dimensional likelihood analysis. In addition, we provide a new analysis of 12.5 yr of Fermi-LAT data above 1 GeV within the region of HESS J1809-193. The obtained results are interpreted in a time-dependent modelling framework.Results. For the first time, we were able to resolve the emission detected with H.E.S.S. into two components: an extended component (modelled as an elongated Gaussian with a 1-sigma semi-major and semi-minor axis of similar to 0.62 degrees and similar to 0.35 degrees, respectively) that exhibits a spectral cutoff at similar to 13 TeV, and a compact component (modelled as a symmetric Gaussian with a 1-sigma radius of similar to 0.1 degrees) that is located close to PSR J1809-1917 and shows no clear spectral cutoff. The Fermi-LAT analysis also revealed extended gamma-ray emission, on scales similar to that of the extended H.E.S.S. component.Conclusions. Our modelling indicates that based on its spectrum and spatial extent, the extended H.E.S.S. component is likely caused by inverse Compton emission from old electrons that form a halo around the pulsar wind nebula. The compact component could be connected to either the pulsar wind nebula or the supernova remnant and molecular clouds. Due to its comparatively steep spectrum, modelling the Fermi-LAT emission together with the H.E.S.S. components is not straightforward.
CRIS-Team WoS Importer:2023-05-05

HESS J1818-154, a new composite supernova remnant discovered in TeV gamma rays and X-rays - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Composite supernova remnants (SNRs) constitute a small subclass of the remnants of massive stellar explosions where non-thermal radiation is observed from both the expanding shell-like shock front and from a pulsar wind nebula (PWN) located inside of the SNR. These systems represent a unique evolutionary phase of SNRs where observations in the radio, X-ray, and γ-ray regimes allow the study of the co-evolution of both these energetic phenomena. In this article, we report results from observations of the shell-type SNR G 15.4+0.1 performed with the High Energy Stereoscopic System (H.E.S.S.) and XMM-Newton. A compact TeV γ-ray source, HESS J1818-154, located in the center and contained within the shell of G 15.4+0.1 is detected by H.E.S.S. and featurs a spectrum best represented by a power-law model with a spectral index of-2.3 ± 0.3 ± 0.2 and an integral flux of F(> 0.42 TeV) = (0.9 ± 0.3 ± 0.2) × 10 cm s. Furthermore, a recent observation with XMM-Newton reveals extended X-ray emission strongly peaked in the center of G 15.4+0.1. The X-ray source shows indications of an energy-dependent morphology featuring a compact core at energies above 4 keV and more extended emission that fills the entire region within the SNR at lower energies. Together, the X-ray and VHE γ-ray emission provide strong evidence of a PWN located inside the shell of G 15.4+0.1 and this SNR can therefore be classified as a composite based on these observations. The radio, X-ray, and γ-ray emission from the PWN is compatible with a one-zone leptonic model that requires a low average magnetic field inside the emission region. An unambiguous counterpart to the putative pulsar, which is thought to power the PWN, has been detected neither in radio nor in X-ray observations of G 15.4+0.1. © 2014 ESO.
Keywords: Gamma rays: general; Methods: observational; Supernovae: individual: HESS J1818-154; X-rays: general; X-rays: individuals: G15.4+0.1

HESS J1825-137: A pulsar wind nebula associated with PSR B1823-13? - Funk, Stefan; et al. (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

HESS J1943+213: A candidate extreme BL Lacertae object - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; et al. (Astronomy & Astrophysics, 2011)
Context. The H.E.S.S. Cherenkov telescope array has been surveying the Galactic plane for new VHE (>100 GeV) gamma-ray sources. Aims. We report on a newly detected point-like source, HESS J1943+213. This source coincides with an unidentified hard X-ray source IGR J19443+2117, which was proposed to have radio and infrared counterparts. Methods. We combine new H.E.S.S., Fermi/LAT and Nançay Radio Telescope observations with pre-existing non-simultaneous multi-wavelength observations of IGR J19443+2117 and discuss the likely source associations as well as the interpretation as an active galactic nucleus, a gamma-ray binary or a pulsar wind nebula. Results. HESS J1943+213 is detected at the significance level of 7.9σ (post-trials) at RA(J2000)= 19 4355 ± 1 ± 1 , Dec(J2000)= +21° 18'8" ± 17" ± 20". The source has a soft spectrum with photon index Γ = 3.1 ± 0.3 ± 0.2 and a flux above 470 GeV of (1.3 ± 0.2 ± 0.3) × 10 cm s . There is no Fermi/LAT counterpart down to a flux limit of 6 × 10 cm s in the 0.1-100 GeV energy range (95% confidence upper limit calculated for an assumed power-law model with a photon index Γ = 2.0). The data from radio to VHE gamma-rays do not show any significant variability. Conclusions. The lack of a massive stellar counterpart disfavors the binary hypothesis, while the soft VHE spectrum would be very unusual in case of a pulsar wind nebula. In addition, the distance estimates for Galactic counterparts places them outside of the Milky Way. All available observations favor an interpretation as an extreme, high-frequency peaked BL Lac object with a redshift z > 0.14. This would be the first time a blazar is detected serendipitously from ground-based VHE observations, and the first VHE AGN detected in the Galactic Plane. © 2011 ESO.
Keywords: BL Lacertae objects: individual: IGR J19443+2117; galaxies: active; gamma rays: general

H.E.S.S. Limits on Linelike Dark Matter Signatures in the 100 GeV to 2 TeV Energy Range Close to the Galactic Center - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Physical Review Letters, 2016)
A search for dark matter linelike signals iss performed in the vicinity of the Galactic Center by the H.E.S.S. experiment on observational data taken in 2014. An unbinned likelihood analysis iss developed to improve the sensitivity to linelike signals. The upgraded analysis along with newer data extend the energy coverage of the previous measurement down to 100 GeV. The 18 h of data collected with the H.E.S.S. array allow one to rule out at 95% C.L. the presence of a 130 GeV line (at l=-1.5°, b=0° and for a dark matter profile centered at this location) previously reported in Fermi-LAT data. This new analysis overlaps significantly in energy with previous Fermi-LAT and H.E.S.S. results. No significant excess associated with dark matter annihilations was found in the energy range of 100 GeV to 2 TeV and upper limits on the gamma-ray flux and the velocity weighted annihilation cross section are derived adopting an Einasto dark matter halo profile. Expected limits for present and future large statistics H.E.S.S. observations are also given.

Hess observarions of the prompt and afterglow phases of GRB 060602B - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astrophysical Journal, 2009)
We report on the first completely simultaneous observation of a gamma-ray burst (GRB) using an array of Imaging Atmospheric Cherenkov Telescopes, which is sensitive to photons in the very high energy (VHE) γ-ray range (≳ 100 GeV). On 2006 June 2, the Swift Burst Alert Telescope (BAT) registered an unusually soft γ-ray burst (GRB 060602B). The burst position was under observation using the High Energy Stereoscopic System (HESS) at the time the burst occurred. Data were taken before, during, and after the burst. A total of 5 hr of observations were obtained during the night of 2006 June 2-3, and five additional hours were obtained over the next three nights. No VHE γ-ray signal was found during the period covered by the HESS observations. The 99% confidence level flux upper limit (> 1 TeV) for the prompt phase (9 s) of GRB 060602B is 2.9 × 10 erg cm s. Due to the very soft BAT spectrum of the burst compared with other Swift GRBs and its proximity to the Galactic center, the burst is likely associated with a Galactic X-ray burster, although the possibility of it being a cosmological GRB cannot be ruled out. We discuss the implications of our flux limits in the context of these two bursting scenarios. © 2009. The American Astronomical Society. All rights reserved.
Keywords: Bursts-gamma rays; Gamma rays; Observations

HESS observations and VLT spectroscopy of PG 1553+113 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Keywords: galaxies: active; galaxies: BL Lacertae objects: individual: PG 1553+113; gamma rays: observations

HESS observations of PKS 2155-304 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The high-frequency peaked BL Lac PKS 2155-304 at redshift z=0.117 has been detected with high significance (similar to45sigma) at energies greater than 160 GeV, using the H.E.S.S. stereoscopic array of imaging air-Cherenkov telescopes in Namibia. A strong signal is found in each of the data sets corresponding to the dark periods of July and October, 2002, and June-September, 2003. The observed flux of VHE gamma rays shows variability on time scales of months, days, and hours. The monthly-averaged integral flux above 300 GeV varies between 10% and 60% of the flux observed from the Crab Nebula. Energy spectra are measured for these individual periods of data taking and are characterized by a steep power law with a time-averaged photon index of Gamma=3.32+/-0.06. An improved chi(2) per degree of freedom is found when either a power law with an exponential cutoff energy or a broken power law are fit to the time-averaged energy spectrum. However, the significance of the improvement is marginal (similar to2sigma). The suggested presence of features in the energy spectrum may be intrinsic to the emission from the blazar, or an indication of absorption of TeV gamma rays by the extragalactic infrared background light.
CRIS-Team WoS Importer:2020-01-15

HESS observations of RX J1713.7-3946 with improved angular and spectral resolution: Evidence for gamma-ray emission extending beyond the X-ray emitting shell - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
Supernova remnants exhibit shock fronts (shells) that can accelerate charged particles up to very high energies. In the past decade, measurements of a handful of shell-type supernova remnants in very high-energy gamma rays have provided unique insights into the acceleration process. Among those objects, RX J1713.7-3946 (also known as G347.3-0.5) has the largest surface brightness, allowing us in the past to perform the most comprehensive study of morphology and spatially resolved spectra of any such very high-energy gamma-ray source. Here we present extensive new H.E.S.S. measurements of RX J1713.7-3946, almost doubling the observation time compared to our previous publication. Combined with new improved analysis tools, the previous sensitivity is more than doubled. The H.E.S.S. angular resolution of 0.048 degrees (0.036 degrees above 2 TeV) is unprecedented in gamma-ray astronomy and probes physical scales of 0.8 (0.6) parsec at the remnant's location. The new H. E. S. S. image of RX J1713.7-3946 allows us to reveal clear morphological di ff erences between X-rays and gamma rays. In particular, for the outer edge of the brightest shell region, we find the first ever indication for particles in the process of leaving the acceleration shock region. By studying the broadband energy spectrum, we furthermore extract properties of the parent particle populations, providing new input to the discussion of the leptonic or hadronic nature of the gamma-ray emission mechanism.
CRIS-Team WoS Importer:2020-01-15
Keywords: ISM: Supernova remnants; cosmic rays; gamma rays: General; Acceleration of particles; astroparticle physic

H.E.S.S. observations of the binary system PSR B1259-63/LS 2883 around the 2010/2011 periastron passage - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Aims. We present very high energy (VHE; E > 100 GeV) data from the γ-ray binary system PSR B1259-63/LS 2883 taken around its periastron passage on 15th of December 2010 with the High Energy Stereoscopic System (H.E.S.S.) of Cherenkov Telescopes. We aim to search for a possible TeV counterpart of the GeV flare detected by the Fermi LAT. In addition, we aim to study the current periastron passage in the context of previous observations taken at similar orbital phases, testing the repetitive behaviour of the source. Methods. Observations at VHEs were conducted with H.E.S.S. from 9th to 16th of January 2011. The total dataset amounts to 6 h of observing time. The data taken around the 2004 periastron passage were also re-analysed with the current analysis techniques in order to extend the energy spectrum above 3 TeV to fully compare observation results from 2004 and 2011. Results. The source is detected in the 2011 data at a significance level of 11.5σ revealing an averaged integral flux above 1 TeV of (1.01 ± 0.18 ± 0.20) × 10 cm s. The differential energy spectrum follows a power-law shape with a spectral index Γ = 2.92 ± 0.30 ± 0.20 and a flux normalisation at 1 TeV of N = (1.95 ± 0.32 ± 0.39) × 10 TeV cm s. The measured light curve does not show any evidence for variability of the source on the daily scale. The re-analysis of the 2004 data yields results compatible with the published ones. The differential energy spectrum measured up to 10 TeV is consistent with a power law with a spectral index Γ = 2.81 ± 0.10 ± 0.20 and a flux normalisation at 1 TeV of N = (1.29 ± 0.08 ± 0.26) × 10 TeV cm s. Conclusions. The measured integral flux and the spectral shape of the 2011 data are compatible with the results obtained around previous periastron passages. The absence of variability in the H.E.S.S. data indicates that the GeV flare observed by Fermi LAT in the time period covered also by H.E.S.S. observations originates in a different physical scenario than the TeV emission. Moreover, the comparison of the new results to the results from the 2004 observations made at a similar orbital phase provides a stronger evidence of the repetitive behaviour of the source. © ESO, 2013.
Keywords: Gamma rays: general; Pulsars: individual: PSR B1259-63; Stars: individual: LS 2883; X-rays: binaries

HESS observations of the Carina nebula and its enigmatic colliding wind binary Eta Carinae - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
The massive binary system Eta Carinae and the surrounding Hii complex, the Carina nebula, are potential particle acceleration sites from which very high energy (VHE; E≥ 100GeV) γ-ray emission could be expected. This paper presents data collected during VHE γ-ray observations with the HESS telescope array from 2004 to 2010, which cover a full orbit of Eta Carinae. In the 33.1-h data set no hint of significant γ-ray emission from Eta Carinae has been found and an upper limit on the γ-ray flux of (99per cent confidence level) is derived above the energy threshold of 470GeV. Together with the detection of high energy (HE; 0.1 ≤E≤ 100GeV) γ-ray emission by the Fermi Large Area Telescope up to 100GeV, and assuming a continuation of the average HE spectral index into the VHE domain, these results imply a cut-off in the γ-ray spectrum between the HE and VHE γ-ray range. This could be caused either by a cut-off in the accelerated particle distribution or by severe γ-γ absorption losses in the wind collision region. Furthermore, the search for extended γ-ray emission from the Carina nebula resulted in an upper limit on the γ-ray flux of (99per cent confidence level). The derived upper limit of ∼23 on the cosmic ray enhancement factor is compared with results found for the old-age mixed-morphology supernova remnant W28. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Acceleration of particles; ISM: individual objects: Carina nebula; ISM: individual objects: Eta Carina; Open clusters and associations: general; Radiation mechanisms: non-thermal; X-rays: binaries

H.E.S.S. observations of the Crab during its March 2013 GeV gamma-ray flare - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. On March 4, 2013 the Fermi-LAT and AGILE reported a flare from the direction of the Crab nebula in which the high-energy (HE; E > 100 MeV) flux was six times above its quiescent level. Simultaneous observations in other energy bands give us hints about the emission processes during the flare episode and the physics of pulsar wind nebulae in general. Aims. We search for variability in the emission of the Crab nebula at very-high energies (VHE; E > 100 GeV), using contemporaneous data taken with the H.E.S.S. array of Cherenkov telescopes. Methods. Observational data taken with the H.E.S.S. instrument on five consecutive days during the flare were analysed for the flux and spectral shape of the emission from the Crab nebula. Night-wise light curves are presented with energy thresholds of 1 TeV and 5 TeV. Results. The observations conducted with H.E.S.S. on March 6 to March 10, 2013 show no significant changes in the flux. They limit the variation in the integral flux above 1 TeV to less than 63% and the integral flux above 5 TeV to less than 78% at a 95% confidence level. © 2014 ESO.
Keywords: Gamma rays: ISM; ISM: individual objects: Crab nebula; Radiation mechanisms: non-thermal; Relativistic processes

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

H.E.S.S. observations of the globular clusters NGC 6388 and M15 and search for a dark matter signal - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astrophysical Journal, 2011)
Observations of the globular clusters (GCs) NGC 6388 and M15 were carried out by the High Energy Stereoscopic System array of Cherenkov telescopes for a live time of 27.2 and 15.2 hr, respectively. No gamma-ray signal is found at the nominal target position of NGC 6388 and M15. In the primordial formation scenario, GCs are formed in a dark matter (DM) halo and DM could still be present in the baryon-dominated environment of GCs. This opens the possibility of observing a DM self-annihilation signal. The DM content of the GCs NGC 6388 and M15 is modeled taking into account the astrophysical processes that can be expected to influence the DM distribution during the evolution of the GC: the adiabatic contraction of DM by baryons, the adiabatic growth of a black hole in the DM halo, and the kinetic heating of DM by stars. Ninety-five percent confidence level exclusion limits on the DM particle velocity-weighted annihilation cross section are derived for these DM halos. In the TeV range, the limits on the velocity-weighted annihilation cross section are derived at the 10 cm s level and a few 10 cm s for NGC 6388 and M15, respectively. © 2011. The American Astronomical Society. All rights reserved..
Keywords: black hole physics; dark matter; gamma rays: general; globular clusters: individual (NGC 6388; M15)

H.E.S.S. reveals a lack of TeV emission from the supernova remnant Puppis A - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Results. The analysis of the H.E.S.S. data does not reveal any significant emission towards Puppis A. The derived upper limits on the differential photon flux imply that its broadband γ-ray spectrum must exhibit a spectral break or cutoff. By combining Fermi-LAT and H.E.S.S. measurements, the 99% confidence-level upper limits on such a cutoff are found to be 450 and 280 GeV, assuming a power law with a simple exponential and a sub-exponential cutoff, respectively. It is concluded that none of the standard limitations (age, size, radiative losses) on the particle acceleration mechanism, assumed to be continuing at present, can explain the lack of VHE signal. The scenario in which particle acceleration has ceased some time ago is considered as an alternative explanation. The HE/VHE spectrum of Puppis A could then exhibit a break of non-radiative origin (as observed in several other interacting SNRs, albeit at somewhat higher energies), owing to the interaction with dense and neutral material, in particular towards the NE region.
Keywords: Acceleration of particles; Cosmic rays; Gamma rays: ISM; ISM: individual objects: Puppis A; Radiation mechanisms: non-thermal

HESS upper limit on the very high energy γ-ray emission from the globular cluster 47 Tucanae - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Observations of the globular cluster 47 Tucanae (NGC 104), which contains at least 23 ms pulsars, were performed with the HESS telescope system. The observations lead to an upper limit of F(E < 800 GeV) < 6.7 × 10-13 cm-2 s-1 on the integral γ-ray photon flux from 47 Tucanae. Considering millisecond pulsars as the unique potential source of γ-rays in the globular cluster, constraints based on emission models are derived: on the magnetic field in the average pulsar nebula and on the conversion efficiency of spin-down power to γ-ray photons or to relativistic leptons. © 2009 ESO.
Keywords: Galaxy: globular clusters: individual: 47 Tucanae; Gamma rays: observations; Stars: pulsars: general

HESS upper limits for Kepler's supernova remnant - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Berge, David; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; et al. (Astronomy & Astrophysics, 2008)
Keywords: gamma rays: observations; ISM: supernova remnants; ISM: individual objects: Kepler's SNR; SN1604; G4.5+6.8

Hess upper limits on very high energy gamma-ray emission from the microquasar grs 1915+105 - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2009)
Context: High energy particles reside in the relativistic jets of microquasars, making them possible sources of very high energy radiation (VHE, < 100 GeV). Detecting this emission would provide a new handle on jet physics. Aims: Observations of the microquasar GRS 1915+105 with the HESS telescope array were undertaken in 2004-2008 to search for VHE emission. Methods: Stereoscopic imaging of Cherenkov radiation from extensive air showers is used to reconstruct the energy and direction of the incident gamma rays. Results: There is no evidence for a VHE gamma-ray signal either from the direction of the microquasar or its vicinity. An upper limit of 6.1 × 10ph cms (99.9% confidence level) is set on the photon flux above 410 GeV, equivalent to a VHE luminosity of ̃ 10erg s at 11 kpc. Conclusions. The VHE to X-ray luminosity ratio in GRS 1915+105 is at least four orders of magnitude lower than the ratio observed in gamma-ray binaries. The VHE radiative efficiency of the compact jet is less than 0.01% based on its estimated total power of 10 erg s. Particle acceleration in GRS 1915+105 is not efficient at high energies and/or the magnetic field is too strong. It is also possible that VHE gamma-rays are produced by GRS 1915+105, but the emission is highly time-dependent. © 2009 ESO.
Keywords: Gamma rays: observations; X-rays: binaries; X-rays: individuals: GRS 1915+105

HESS very-high-energy gamma-ray sources without identified counterparts - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Context. The detection of gamma rays in the very-high-energy (VHE) energy range (100 GeV-100 TeV) provides a direct view of the parent population of ultra-relativistic particles found in astrophysical sources. For this reason, VHE gamma rays are useful for understanding the underlying astrophysical processes in non-thermal sources. Aims. We investigate unidentified VHE gamma-ray sources that have been discovered with HESS in the most sensitive blind survey of the Galactic plane at VHE energies conducted so far. Methods. The HESS array of imaging atmospheric Cherenkov telescopes (IACTs) has a high sensitivity compared with previous instruments (∼0.01 Crab in 25 h observation time for a 5σ point-source detection), and with its large field of view, is well suited for scan-based observations. The on-going HESS survey of the inner Galaxy has revealed a large number of new VHE sources, and for each we attempt to associate the VHE emission with multi-wavelength data in the radio through X-ray wavebands. Results. For each of the eight unidentified VHE sources considered here, we present the energy spectra and. sky maps of the sources and their environment. The VHE morphology is compared with available multi-wavelength data (mainly radio and X-rays). No plausible counterparts are found. © ESO 2007.
Keywords: Cosmic rays; Galaxy: general; Gamma rays: observations; Surveys

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Alfaro, Ruben; Alvarez, César; Arteaga-Velázquez, Juan Carlos; Kollamparambil Paul, Arun Babu; Rojas, Daniel Avila; Ayala Solares, Hugo Alberto; Babu, Rishi; Belmont-Moreno, Ernesto; Brisbois, Chad; Caballero-Mora, Karen S.; Capistrán, Tomás; Carramiñana, Alberto; et al. (Advances in Space Research, 2023)
High-energy cosmic rays that hit the Earth can be used to study large-scale atmospheric perturbations. After a first interaction in the upper parts of the atmosphere, cosmic rays produce a shower of particles that sample it down to the detector level. The HAWC (High-Altitude Water Cherenkov) gamma-ray observatory in Central Mexico at 4,100 m elevation detects air shower particles continuously with 300 water Cherenkov detectors with an active area of 12,500 m2. On January 15th, 2022, HAWC detected the passage of the pressure wave created by the explosion of the Hunga volcano in the Tonga islands, 9,000 km away, as an anomaly in the measured rate of shower particles. The HAWC measurements are used to determine the propagation speed of four pressure wave passages, and correlate the variations of the shower particle rates with the barometric pressure changes. The profile of the shower particle rate and atmospheric pressure variations for the first transit of the pressure wave at HAWC is compared to the pressure measurements at the Tonga island, near the volcanic explosion. By using the cosmic-ray propagation in the atmosphere as a probe for the pressure, it is possible to achieve very high time-resolution measurements. Moreover, the high-altitude data from HAWC allows to observe the shape of the pressure anomaly with less perturbations compared to sea level detectors. Given the particular location and the detection method of HAWC, our high-altitude data provides valuable information that contributes to fully characterize this once-in-a-century phenomenon.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Cosmic rays; HAWC observatory; Hunga volcano; Lamb wave

High deuteron and neutron yields from the interaction of a petawatt laser with a cryogenic deuterium jet - Jiao, X.; Curry, C. B.; Gauthier, M.; Chou, H. G.J.; Fiuza, F.; Kim, J. B.; Phan, D. D.; McCary, E.; Galtier, E. C.; Dyer, G. M.; Ofori-Okai, B. K.; Labun, L.; et al. (Frontiers in Physics, 2023)
A compact high-flux, short-pulse neutron source would have applications from nuclear astrophysics to cancer therapy. Laser-driven neutron sources can achieve fluxes much higher than spallation and reactor neutron sources by reducing the volume and time in which the neutron-producing reactions occur by orders of magnitude. We report progress towards an efficient laser-driven neutron source in experiments with a cryogenic deuterium jet on the Texas Petawatt laser. Neutrons were produced both by laser-accelerated multi-MeV deuterons colliding with Be and mixed metallic catchers and by d (d,n)3He fusion reactions within the jet. We observed deuteron yields of 1013/shot in quasi-Maxwellian distributions carrying (Formula presented.) of the input laser energy. We obtained neutron yields greater than 1010/shot and found indications of a deuteron-deuteron fusion neutron source with high peak flux ((Formula presented.) cm−2 s−1). The estimated fusion neutron yield in our experiment is one order of magnitude higher than any previous laser-induced dd fusion reaction. Though many technical challenges will have to be overcome to convert this proof-of-principle experiment into a consistent ultra-high flux neutron source, the neutron fluxes achieved here suggest laser-driven neutron sources can support laboratory study of the rapid neutron-capture process, which is otherwise thought to occur only in astrophysical sites such as core-collapse supernova, and binary neutron star mergers.
CRIS-Team Scopus Importer:2023-02-10
Keywords: high-flux neutron source; laboratory astro-nuclear physics experiment; laser-driven fusion; laser-driven ion source; laser-driven neutron source; rapid neutron capture process

High-energy and ultra-high-energy neutrinos: A Snowmass white paper - Ackermann, Markus; Bustamante, Mauricio; Lu, Lu; Otte, Nepomuk; Reno, Mary Hall; Wissel, Stephanie; Agarwalla, Sanjib K.; Alvarez-Muñiz, Jaime; Alves Batista, Rafael; Argüelles, Carlos A.; Clark, Brian A.; Cummings, Austin; et al. (Journal of High Energy Astrophysics, 2022)
Astrophysical neutrinos are excellent probes of astroparticle physics and high-energy physics. With energies far beyond solar, supernovae, atmospheric, and accelerator neutrinos, high-energy and ultra-high-energy neutrinos probe fundamental physics from the TeV scale to the EeV scale and beyond. They are sensitive to physics both within and beyond the Standard Model through their production mechanisms and in their propagation over cosmological distances. They carry unique information about their extreme non-thermal sources by giving insight into regions that are opaque to electromagnetic radiation. This white paper describes the opportunities astrophysical neutrino observations offer for astrophysics and high-energy physics, today and in coming years.
CRIS-Team Scopus Importer:2022-09-16

High-energy emission from a magnetar giant flare in the Sculptor galaxy - Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; et al. (Nature Astronomy, 2021)
Magnetars are the most highly magnetized neutron stars in the cosmos (with magnetic field 10(13)-10(15) G). Giant flares from magnetars are rare, short-duration (about 0.1 s) bursts of hard X-rays and soft gamma rays(1,2). Owing to the limited sensitivity and energy coverage of previous telescopes, no magnetar giant flare has been detected at gigaelectronvolt (GeV) energies. Here, we report the discovery of GeV emission from a magnetar giant flare on 15 April 2020 (refs. (3,4) and A. J. Castro-Tirado et al., manuscript in preparation). The Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope detected GeV gamma rays from 19 s until 284 s after the initial detection of a signal in the megaelectronvolt (MeV) band. Our analysis shows that these gamma rays are spatially associated with the nearby (3.5 megaparsecs) Sculptor galaxy and are unlikely to originate from a cosmological gamma-ray burst. Thus, we infer that the gamma rays originated with the magnetar giant flare in Sculptor. We suggest that the GeV signal is generated by an ultra-relativistic outflow that first radiates the prompt MeV-band photons, and then deposits its energy far from the stellar magnetosphere. After a propagation delay, the outflow interacts with environmental gas and produces shock waves that accelerate electrons to very high energies; these electrons then emit GeV gamma rays as optically thin synchrotron radiation. This observation implies that a relativistic outflow is associated with the magnetar giant flare, and suggests the possibility that magnetars can power some short gamma-ray bursts.
CRIS-Team WoS Importer:2021-01-29

HIGH-ENERGY GAMMA-RAY EMISSION FROM SOLAR FLARES: SUMMARY OF FERMI LARGE AREA TELESCOPE DETECTIONS AND ANALYSIS OF TWO M-CLASS FLARES - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Bonamente, E.; Bottacini, E.; et al. (Astrophysical Journal, 2014)
We present the detections of 18 solar flares detected in high-energy gamma-rays (above 100 MeV) with the Fermi Large Area Telescope (LAT) during its first 4 yr of operation. This work suggests that particle acceleration up to very high energies in solar flares is more common than previously thought, occurring even in modest flares, and for longer durations. Interestingly, all these flares are associated with fairly fast coronal mass ejections (CMEs). We then describe the detailed temporal, spatial, and spectral characteristics of the first two long-lasting events: the 2011 March 7 flare, a moderate (M3.7) impulsive flare followed by slowly varying gamma-ray emission over 13 hr, and the 2011 June 7 M2.5 flare, which was followed by gamma-ray emission lasting for 2 hr. We compare the Fermi LAT data with X-ray and proton data measurements from GOES and RHESSI. We argue that the gamma-rays are more likely produced through pion decay than electron bremsstrahlung, and we find that the energy spectrum of the proton distribution softens during the extended emission of the 2011 March 7 flare. This would disfavor a trapping scenario for particles accelerated during the impulsive phase of the flare and point to a continuous acceleration process at play for the duration of the flares. CME shocks are known for accelerating the solar energetic particles (SEPs) observed in situ on similar timescales, but it might be challenging to explain the production of gamma-rays at the surface of the Sun while the CME is halfway to the Earth. A stochastic turbulence acceleration process occurring in the solar corona is another likely scenario. Detailed comparison of characteristics of SEPs and gamma-ray-emitting particles for several flares will be helpful to distinguish between these two possibilities.
Keywords: Sun: flares; Sun: X-rays; gamma rays

High-energy particle acceleration in the shell of a supernova remnant - Funk, Stefan; et al. (Nature, 2004)
A significant fraction of the energy density of the interstellar medium is in the form of high-energy charged particles ( cosmic rays)(1). The origin of these particles remains uncertain. Although it is generally accepted that the only sources capable of supplying the energy required to accelerate the bulk of Galactic cosmic rays are supernova explosions, and even though the mechanism of particle acceleration in expanding supernova remnant (SNR) shocks is thought to be well understood theoretically(2,3), unequivocal evidence for the production of high-energy particles in supernova shells has proven remarkably hard to find. Here we report on observations of the SNR RX J1713.7 - 3946 ( G347.3 - 0.5), which was discovered by ROSAT(4) in the X-ray spectrum and later claimed as a source of high-energy gamma-rays(5,6) of TeV energies (1 TeV = 10(12) eV). We present a TeV gamma-ray image of the SNR: the spatially resolved remnant has a shell morphology similar to that seen in X-rays, which demonstrates that very-high-energy particles are accelerated there. The energy spectrum indicates efficient acceleration of charged particles to energies beyond 100 TeV, consistent with current ideas of particle acceleration in young SNR shocks.
CRIS-Team WoS Importer:2020-01-15

High-repetition-rate, multi-MeV deuteron acceleration from converging heavy water microjets at laser intensities of 1021W/cm2 - Treffert, F.; Curry, C. B.; Chou, H. G.J.; Crissman, C. J.; Deponte, D. P.; Fiuza, F.; Glenn, G. D.; Hollinger, R. C.; Nedbailo, R.; Park, J.; Schönwälder, Christopher; Song, H.; et al. (Applied Physics Letters, 2022)
We demonstrate high repetition-rate deuteron acceleration by irradiating a continuously flowing, ambient temperature liquid heavy water jet with the high-intensity ALEPH laser. The laser delivered up to 5.5 J (120 TW, 1.2 × 1021 W/cm2) laser energy on target at 0.5 Hz. A high repetition-rate Thomson parabola spectrometer measured the deuteron beam energy spectra on each shot for 60 sequential shots (two minutes). Peak fluxes of 5 × 10 10 deuterons/sr/pulse, corresponding to an average flux of 1.5 × 10 12 deuterons/sr/min, were demonstrated with deuteron energies reaching up to 4.4 MeV. High shot-to-shot stability is observed up to 40%-50% of the maximum deuteron energy. These deuteron beams are suited for fast neutron production through deuteron breakup in a converter yielding energies similar to deuteron-deuteron (D-D, 2.45 MeV) fusion reactions of importance for material damage studies.
CRIS-Team Scopus Importer:2022-09-09

Hitomi (ASTRO-H) X-ray Astronomy Satellite - Takahashi, Tadayuki; Kokubun, Motohide; Mitsuda, Kazuhisa; Kelley, Richard L.; Ohashi, Takaya; Aharonian, Felix; Akamatsu, Hiroki; Akimoto, Fumie; Allen, Steven W.; Anabuki, Naohisa; Angelini, Lorella; Arnaud, Keith; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2018)
The Hitomi (ASTRO-H) mission is the sixth Japanese x-ray astronomy satellite developed by a large international collaboration, including Japan, USA, Canada, and Europe. The mission aimed to provide the highest energy resolution ever achieved at E > 2 keV, using a microcalorimeter instrument, and to cover a wide energy range spanning four decades in energy from soft x-rays to gamma rays. After a successful launch on February 17, 2016, the spacecraft lost its function on March 26, 2016, but the commissioning phase for about a month provided valuable information on the onboard instruments and the spacecraft system, including astrophysical results obtained from first light observations. The paper describes the Hitomi (ASTRO-H) mission, its capabilities, the initial operation, and the instruments/spacecraft performances confirmed during the commissioning operations for about a month. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License.
CRIS-Team WoS Importer:2020-01-15

Identification of HESS J1303-631 as a pulsar wind nebula through γ -ray, X-ray, and radio observations - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Aims. The previously unidentified very high-energy (VHE; E > 100 GeV) γ-ray source HESS J1303-631, discovered in 2004, is re-examined including new data from the H.E.S.S. Cherenkov telescope array in order to identify this object. Archival data from the XMM-Newton X-ray satellite and from the PMN radio survey are also examined. Methods. Detailed morphological and spectral studies of VHE γ-ray emission as well as of the XMM-Newton X-ray data are performed. Radio data from the PMN survey are used as well to construct a leptonic model of the source. The γ-ray and X-ray spectra and radio upper limit are used to construct a one zone leptonic model of the spectral energy distribution (SED). Results. Significant energy-dependent morphology of the γ-ray source is detected with high-energy emission (E > 10 TeV) positionally coincident with the pulsar PSR J1301-6305 and lower energy emission (E < 2 TeV) extending ∼0.4° to the southeast of the pulsar. The spectrum of the VHE source can be described with a power-law with an exponential cut-off N = (5.6 ± 0.5) × 10 ± TeV ± cm ± s, Γ = 1.5 ± 0.2) and E = (7.7 ± ± ± 2.2) TeV. The pulsar wind nebula (PWN) is also detected in X-rays, extending ∼2-3′ from the pulsar position towards the center of the γ-ray emission region. A potential radio counterpart from the PMN survey is also discussed, showing a hint for a counterpart at the edge of the X-ray PWN trail and is taken as an upper limit in the SED. The extended X-ray PWN has an unabsorbed flux of F ∼ 1.6 × 10 erg cm and is detected at a significance of 6.5σ. The SED is well described by a one zone leptonic scenario which, with its associated caveats, predicts a very low average magnetic field for this source. Conclusions. Significant energy-dependent morphology of this source, as well as the identification of an associated X-ray PWN from XMM-Newton observations enable identification of the VHE source as an evolved PWN associated to the pulsar PSR J1301-6305. This identification is supported by the one zone leptonic model, which suggests that the energetics of the γ-ray and X-ray radiation are such that they may have a similar origin in the pulsar nebula. However, the large discrepancy in emission region sizes and the low level of synchrotron radiation suggest a multi-population leptonic nature. The low implied magnetic field suggests that the PWN has undergone significant expansion. This would explain the low level of synchrotron radiation and the difficulty in detecting counterparts at lower energies, the reason this source was originally classified as a "dark" VHE γ-ray source. © ESO, 2012.
Keywords: Gamma rays: general; ISM: individual objects: HESS J1303-631; Pulsars: individual: PSR J1301-6305

Impact of satellite trails on H.E.S.S. astronomical observations - Lang, Thomas; Spencer, Samuel; Mitchell, Alison (Astronomy & Astrophysics, 2023)
Context. The number of satellites launched into Earth’s orbit has almost tripled in the last three years (to over 4000) due to the increasing commercialisation of space. Multiple satellite constellations, consisting of over 400,000 individual satellites, have either been partially launched or are proposed for launch in the near future. Many of these satellites are highly reflective, resulting in a high optical brightness that affects ground-based astronomical observations. Despite this caveat, the potential effect of these satellites on gamma-ray-observing Imaging Atmospheric Cherenkov Telescopes (IACTs) has largely been assumed to be negligible due to their nanosecond-scale integration times. However, this assumption has not been verified to date. Aims. As IACTs are sensitive to optical wavelength light, we aim to identify satellite trails in data taken by the High Energy Stereo-scopic System (H.E.S.S.) IACT array. In particular, this study is aimed at quantifying the potential effects on data quality and extensive air shower event classification and reconstruction. Methods. Using night sky background measurements from H.E.S.S., we determined which observation times and pointing directions are affected most by these satellite trails. We then evaluated their impact on the standard Hillas parameter variables used for event analysis. Results. Due to the brightest trails, false trigger events can occur, however, for most modern analyses, the effect on astronomical results will be minimal. We observe a mild increase in the rate of trail detections over time (approximately doubling in three years), which is partially correlated with the number of satellite launches. Overall, the fraction of H.E.S.S. data affected (∼ 0.2% of dark time observations) is currently minimal. We note that these trails could still have a non-negligible effect on future Cherenkov Telescope Array observations if advanced analysis techniques designed to lower the energy threshold of the instrument are applied.<br
Keywords: Astroparticle Physics; Light Pollution; Methods: Data Analysis; Instrumentation: Detectors; Gamma-Rays: General

Implementation of a Talbot-Lau Interferometer in a Clinical-like C-Arm Setup: A Feasibility Study - Horn, Florian; Leghissa, Martino; Käppler, Sebastian; Pelzer, Georg; Rieger, Jens; Seifert, Maria; Wandner, Johannes; Weber, Thomas; Michel, Thilo; Riess, Christian; Anton, Gisela (Scientific Reports, 2018)

Inauguration and First Light of the GCT-M Prototype for the Cherenkov Telescope Array - Watson, J. J.; De Franco, A.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, D.; Boisson, C.; Bousquet, J. -J.; Brown, A. M.; Bryan, M.; et al. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2017)
CRIS-Team WoS Importer:2020-01-15

Incremental Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Baldini, L.; Ballet, J.; Bastieri, D.; Bellazzini, R.; Berenji, B.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bloom, E.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2022)
We present an incremental version (4FGL-DR3, for Data Release 3) of the fourth Fermi Large Area Telescope (LAT) catalog of gamma-ray sources. Based on the first 12 years of science data in the energy range from 50 MeV to 1 TeV, it contains 6658 sources. The analysis improves on that used for the 4FGL catalog over eight years of data: more sources are fit with curved spectra, we introduce a more robust spectral parameterization for pulsars, and we extend the spectral points to 1 TeV. The spectral parameters, spectral energy distributions, and associations are updated for all sources. Light curves are rebuilt for all sources with 1 yr intervals (not 2 month intervals). Among the 5064 original 4FGL sources, 16 were deleted, 112 are formally below the detection threshold over 12 yr (but are kept in the list), while 74 are newly associated, 10 have an improved association, and seven associations were withdrawn. Pulsars are split explicitly between young and millisecond pulsars. Pulsars and binaries newly detected in LAT sources, as well as more than 100 newly classified blazars, are reported. We add three extended sources and 1607 new point sources, mostly just above the detection threshold, among which eight are considered identified, and 699 have a plausible counterpart at other wavelengths. We discuss the degree-scale residuals to the global sky model and clusters of soft unassociated point sources close to the Galactic plane, which are possibly related to limitations of the interstellar emission model and missing extended sources.
CRIS-Team WoS Importer:2022-07-15

Inferred Cosmic-Ray Spectrum from Fermi Large Area Telescope gamma-Ray Observations of Earth's Limb - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; et al. (Physical Review Letters, 2014)
Recent accurate measurements of cosmic-ray (CR) species by ATIC-2, CREAM, and PAMELA reveal an unexpected hardening in the proton and He spectra above a few hundred GeV, a gradual softening of the spectra just below a few hundred GeV, and a harder spectrum of He compared to that of protons. These newly discovered features may offer a clue to the origin of high-energy CRs. We use the Fermi Large Area Telescope observations of the gamma-ray emission from Earth's limb for an indirect measurement of the local spectrum of CR protons in the energy range similar to 90 GeV-6 TeV (derived from a photon energy range 15 GeV-1 TeV). Our analysis shows that single power law and broken power law spectra fit the data equally well and yield a proton spectrum with index 2.68 +/- 0.04 and 2.61 +/- 0.08 above similar to 200 GeV, respectively.

INSIGHTS INTO THE HIGH-ENERGY gamma-RAY EMISSION OF MARKARIAN 501 FROM EXTENSIVE MULTIFREQUENCY OBSERVATIONS IN THE FERMI ERA - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2011)
We report on the gamma-ray activity of the blazar Mrk 501 during the first 480 days of Fermi operation. We find that the average Large Area Telescope (LAT) gamma-ray spectrum of Mrk 501 can be well described by a single power-law function with a photon index of 1.78 +/- 0.03. While we observe relatively mild flux variations with the Fermi-LAT (within less than a factor of two), we detect remarkable spectral variability where the hardest observed spectral index within the LAT energy range is 1.52 +/- 0.14, and the softest one is 2.51 +/- 0.20. These unexpected spectral changes do not correlate with the measured flux variations above 0.3 GeV. In this paper, we also present the first results from the 4.5 month long multifrequency campaign (2009 March 15-August 1) on Mrk 501, which included the Very Long Baseline Array (VLBA), Swift, RXTE, MAGIC, and VERITAS, the F-GAMMA, GASP-WEBT, and other collaborations and instruments which provided excellent temporal and energy coverage of the source throughout the entire campaign. The extensive radio to TeV data set from this campaign provides us with the most detailed spectral energy distribution yet collected for this source during its relatively low activity. The average spectral energy distribution of Mrk 501 is well described by the standard one-zone synchrotron self-Compton (SSC) model. In the framework of this model, we find that the dominant emission region is characterized by a size less than or similar to 0.1 pc (comparable within a factor of few to the size of the partially resolved VLBA core at 15-43 GHz), and that the total jet power (similar or equal to 10(44) erg s(-1)) constitutes only a small fraction (similar to 10(-3)) of the Eddington luminosity. The energy distribution of the freshly accelerated radiating electrons required to fit the time-averaged data has a broken power-law form in the energy range 0.3 GeV-10 TeV, with spectral indices 2.2 and 2.7 below and above the break energy of 20 GeV. We argue that such a form is consistent with a scenario in which the bulk of the energy dissipation within the dominant emission zone of Mrk 501 is due to relativistic, proton-mediated shocks. We find that the ultrarelativistic electrons and mildly relativistic protons within the blazar zone, if comparable in number, are in approximate energy equipartition, with their energy dominating the jet magnetic field energy by about two orders of magnitude.
CRIS-Team WoS Importer:2020-01-15

Interplanetary Magnetic Flux Rope Observed at Ground Level by HAWC - Akiyama, S.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; et al. (Astrophysical Journal, 2020)
We report the ground-level detection of a Galactic cosmic-ray (GCR) flux enhancement lasting similar to 17 hr and associated with the passage of a magnetic flux rope (MFR) over the Earth. The MFR was associated with a slow coronal mass ejection (CME) caused by the eruption of a filament on 2016 October 9. Due to the quiet conditions during the eruption and the lack of interactions during the interplanetary CME transport to the Earth, the associated MFR preserved its configuration and reached the Earth with a strong magnetic field, low density, and a very low turbulence level compared to local background, thus generating the ideal conditions to redirect and guide GCRs (in the similar to 8-60 GV rigidity range) along the magnetic field of the MFR. An important negative B-Z component inside the MFR caused large disturbances in the geomagnetic field and a relatively strong geomagnetic storm. However, these disturbances are not the main factors behind the GCR enhancement. Instead, we found that the major factor was the alignment between the MFR axis and the asymptotic direction of the observer.
CRIS-Team WoS Importer:2021-01-01

Introducing the CTA concept - Acharya, B. S.; Actis, M.; Aghajani, T.; Agnetta, G.; Aguilar, J.; Aharonian, F.; Ajello, M.; Akhperjanian, A.; Alcubierre, M.; Aleksic, J.; Alfaro, R.; Aliu, E.; et al. (Astroparticle Physics, 2013)
The Cherenkov Telescope Array (CTA) is a new observatory for very high-energy (VHE) gamma rays. CTA has ambitions science goals, for which it is necessary to achieve full-sky coverage, to improve the sensitivity by about an order of magnitude, to span about four decades of energy, from a few tens of GeV to above 100 TeV with enhanced angular and energy resolutions over existing VHE gamma-ray observatories. An international collaboration has formed with more than 1000 members from 27 countries in Europe, Asia, Africa and North and South America. In 2010 the CTA Consortium completed a Design Study and started a three-year Preparatory Phase which leads to production readiness of CTA in 2014. In this paper we introduce the science goals and the concept of CTA, and provide an overview of the project. © 2013 Elsevier B.V. All rights reserved.
Keywords: Air showers; Cherenkov Telescopes; TeV gamma-ray astronomy

Investigating the Nature of Late-time High-energy GRB Emission through Joint Fermi/Swift Observations - Ajello, Marco; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; Bruel, P.; Buehler, R.; et al. (Astrophysical Journal, 2018)
We use joint observations by the Swift X-ray Telescope (XRT) and the Fermi Large Area Telescope (LAT) of gamma-ray burst (GRB) afterglows to investigate the nature of the long-lived high-energy emission observed by Fermi LAT. Joint broadband spectral modeling of XRT and LAT data reveals that LAT nondetections of bright X-ray afterglows are consistent with a cooling break in the inferred electron synchrotron spectrum below the LAT and/or XRT energy ranges. Such a break is sufficient to suppress the high-energy emission so as to be below the LAT detection threshold. By contrast, LAT-detected bursts are best fit by a synchrotron spectrum with a cooling break that lies either between or above the XRT and LAT energy ranges. We speculate that the primary difference between GRBs with LAT afterglow detections and the nondetected population may be in the type of circumstellar environment in which these bursts occur, with late-time LAT detections preferentially selecting GRBs that occur in low wind-like circumburst density profiles. Furthermore, we find no evidence of high-energy emission in the LAT-detected population significantly in excess of the flux expected from the electron synchrotron spectrum fit to the observed X-ray emission. The lack of excess emission at high energies could be due to a shocked external medium in which the energy density in the magnetic field is stronger than or comparable to that of the relativistic electrons behind the shock, precluding the production of a dominant synchrotron self-Compton (SSC) component in the LAT energy range. Alternatively, the peak of the SSC emission could be beyond the 0.1-100 GeV energy range considered for this analysis.
Keywords: gamma-ray burst: general

Investigating the Nature of Late-time High-energy GRB Emission through Joint Fermi/Swift Observations - Ajello, Marco; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; Bruel, P.; Buehler, R.; et al. (Astrophysical Journal, 2018)
We use joint observations by the Swift X-ray Telescope (XRT) and the Fermi Large Area Telescope (LAT) of gamma-ray burst (GRB) afterglows to investigate the nature of the long-lived high-energy emission observed by Fermi LAT. Joint broadband spectral modeling of XRT and LAT data reveals that LAT nondetections of bright X-ray afterglows are consistent with a cooling break in the inferred electron synchrotron spectrum below the LAT and/or XRT energy ranges. Such a break is sufficient to suppress the high-energy emission so as to be below the LAT detection threshold. By contrast, LAT-detected bursts are best fit by a synchrotron spectrum with a cooling break that lies either between or above the XRT and LAT energy ranges. We speculate that the primary difference between GRBs with LAT afterglow detections and the nondetected population may be in the type of circumstellar environment in which these bursts occur, with late-time LAT detections preferentially selecting GRBs that occur in low wind-like circumburst density profiles. Furthermore, we find no evidence of high-energy emission in the LAT-detected population significantly in excess of the flux expected from the electron synchrotron spectrum fit to the observed X-ray emission. The lack of excess emission at high energies could be due to a shocked external medium in which the energy density in the magnetic field is stronger than or comparable to that of the relativistic electrons behind the shock, precluding the production of a dominant synchrotron self-Compton (SSC) component in the LAT energy range. Alternatively, the peak of the SSC emission could be beyond the 0.1-100 GeV energy range considered for this analysis.
Keywords: gamma-ray burst: general

IT’S A BLAZAR. . . IT’S A RADIO GALAXY. . . IT’S PKS 0625-354! - Wierzcholska, Alicja; Glawion, Dorit (Acta Physica Polonica B, Proceedings Supplement, 2022)
The catalogue of TeV gamma-ray emitting objects includes about 90 extragalactic sources, among which only a few belong to the class of radio galaxies or misaligned blazars. This smaller class includes PKS 0625-354, a source detected as a TeV gamma-ray emitter already in 2012. Here, we report on H.E.S.S. observations of this active galaxy performed in November 2018. The classification of the object is still a matter of debate in the context of blazar and radio-galaxy scenarios. With the recent H.E.S.S. observations, supported with multi-wavelength observations collected with Fermi-LAT, Swift-XRT, and Swift-UVOT, we report on the detection of TeV gamma-ray variability of the sources. Ten days of H.E.S.S. observations revealed an outburst observed on November 1 followed by a decrease in the gamma-ray flux. We report on the result of H.E.S.S. and multiwavelength observations of PKS 0625-354. We also discuss the possible interpretation of the broadband spectral energy distribution of the source and the implication of the TeV gamma-ray variability detected.
CRIS-Team Scopus Importer:2022-11-25

LAT perspectives in detection of high energy cosmic ray electrons - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

LED as laboratory test source for astronomical intensity interferometry - Zmija, Andreas; Deiml, Peter; Malyshev, Dmitry; Zink, Adrian; Anton, Gisela; Michel, Thilo; Funk, Stefan (Optics Express, 2020)
The challenge of astronomical intensity interferometry is to detect the small photon-bunching signals of distant sources with a broad optical bandwidth. We have built a Hanbury Brown-Twiss-like laboratory intensity interferometer with a focus on a relatively broad bandwidth (1 nm FWHM optical filter) and high photon rates (up to 10 MHz) per channel compared to typical (non-astronomical) intensity interferometry applications. As a light source we use a green LED to simulate starlight. The LED has proven to be a compact high-power source of stochastic light with a special advantage of a small emission area, which favours spatial coherence. Using single-photon correlations, we detect a bunching signal in the second-order correlation function with a coherence time of <1 ps and an amplitude of <4 · 10−4 and describe signal and background quantitatively for a 40 hours measurement. In this paper we show our setup, present the correlation measurements and compare them to theoretical expectations.
CRIS-Team Scopus Importer:2020-02-21

Limits on an energy dependence of the speed of light from a flare of the active galaxy PKS 2155-304 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Physical Review Letters, 2008)
In the past few decades, several models have predicted an energy dependence of the speed of light in the context of quantum gravity. For cosmological sources such as active galaxies, this minuscule effect can add up to measurable photon-energy dependent time lags. In this Letter a search for such time lags during the High Energy Stereoscopic System observations of the exceptional very high energy flare of the active galaxy PKS 2155-304 on 28 July 2006 is presented. Since no significant time lag is found, lower limits on the energy scale of speed of light modifications are derived. © 2008 The American Physical Society.

Limits on primordial black hole evaporation from H.E.S.S. observations - Abdalla, H.; Spencer, Samuel; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa Martins, V.; et al. (Proceedings of Science, 2022)
Primordial Black Holes are expected to be formed in the early Universe by the gravitational collapse of overdense regions, among other mechanisms. They are also expected to loose their mass over time by the Hawking radiation process. As the rates of this radiation increase with temperature, the PBH evaporation should result in a violent explosion. The current upper limits on explosion rates are on the order of 104 − 105pc−3yr−1. In this contribution we’ll present the results of a search for TeV γ-ray burst within timescale of few seconds, using nearly 5000 hours of H.E.S.S. data. The search algorithm and statistical estimation strategy will be presented as well as cosmological implications of this measurement.
CRIS-Team Scopus Importer:2022-12-23

Localizing the VHE γ-ray source at the galactic centre - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
The inner 10 pc of our Galaxy contains many counterpart candidates of the very high energy (VHE; >100 GeV) γ-ray point source HESS J1745-290. Within the point spread function of the H.E.S.S. measurement, at least three objects are capable of accelerating particles to VHE and beyond and of providing the observed γ-ray flux. Previous attempts to address this source confusion were hampered by the fact that the projected distances between these objects were of the order of the error circle radius of the emission centroid (34 arcsec, dominated by the pointing uncertainty of the H.E.S.S. instrument). Here we present H.E.S.S. data of the Galactic Centre region, recorded with an improved control of the instrument pointing compared to H.E.S.S. standard pointing procedures. Stars observed during γ-ray observations by optical guiding cameras mounted on each H.E.S.S. telescope are used for off-line pointing calibration, thereby decreasing the systematic pointing uncertainties from 20 to 6 arcsec per axis. The position of HESS J1745-290 is obtained by fitting a multi-Gaussian profile to the background-subtracted γ-ray count map. A spatial comparison of the best-fitting position of HESS J1745-290 with the position and morphology of candidate counterparts is performed. The position is, within a total error circle radius of 13 arcsec, coincident with the position of the supermassive black hole Sgr A* and the recently discovered pulsar wind nebula candidate G359.95-0.04. It is significantly displaced from the centroid of the supernova remnant Sgr A East, excluding this object with high probability as the dominant source of the VHE γ-ray emission. © 2009 The Authors. Journal compilation © 2009 RAS.
Keywords: Galaxy: centre; Gamma-rays: observations; ISM: individual: G 359.95-0.04; ISM: individual: Sgr A East; ISM: individual: Sgr A*

Locating the TeV-excess from the galactic centre region - Funk, Stefan; et al. (High Energy Gamma-Ray Astronomy, 2005)
CRIS-Team WoS Importer:2020-01-15

Longitudinal double-spin asymmetries in semi-inclusive deep-inelastic scattering of electrons and positrons by protons and deuterons - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Avakian, R.; Avetissian, A.; Belostotski, S.; Blok, H. P.; Borissov, A.; Bryzgalov, V.; Capitani, G. P.; et al. (Physical Review D, 2019)
A comprehensive collection of results on longitudinal double-spin asymmetries is presented for charged pions and kaons produced in semi-inclusive deep-inelastic scattering of electrons and positrons on the proton and deuteron, based on the full HERMES data set. The dependence of the asymmetries on hadron transverse momentum and azimuthal angle extends the sensitivity to the flavor structure of the nucleon beyond the distribution functions accessible in the collinear framework. No strong dependence on those variables is observed. In addition, the hadron charge-difference asymmetry is presented, which under certain model assumptions provides access to the helicity distributions of valence quarks.
CRIS-Team WoS Importer:2019-06-21

Long-term monitoring of PKS 2155-304 with ATOM and H.E.S.S.: Investigation of optical/γ-ray correlations in different spectral states - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2014)
In this paper we report on the analysis of all the available optical and very high-energy γ-ray (>200 GeV) data for the BL Lac object PKS 2155-304, collected simultaneously with the ATOM and H.E.S.S. telescopes from 2007 until 2009. This study also includes X-ray (RXTE, Swift) and high-energy γ-ray (Fermi-LAT) data. During the period analysed, the source was transitioning from its flaring to quiescent optical states, and was characterized by only moderate flux changes at different wavelengths on the timescales of days and months. A flattening of the optical continuum with an increasing optical flux can be noted in the collected dataset, but only occasionally and only at higher flux levels. We did not find any universal relation between the very high-energy γ-ray and optical flux changes on the timescales from days and weeks up to several years. On the other hand, we noted that at higher flux levels the source can follow two distinct tracks in the optical flux-colour diagrams, which seem to be related to distinct γ-ray states of the blazar. The obtained results therefore indicate a complex scaling between the optical and γ-ray emission of PKS 2155-304, with different correlation patterns holding at different epochs, and a γ-ray flux depending on the combination of an optical flux and colour rather than a flux alone.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Black hole physics; Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Long-term Spectra of the Blazars Mrk 421 and Mrk 501 at TeV Energies Seen by HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan,; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistran, T.; et al. (Astrophysical Journal, 2022)
The High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory surveys the very high-energy sky in the 300 GeV to >100 TeV energy range. HAWC has detected two blazars above 11 sigma, Markarian 421 (Mrk 421) and Markarian 501 (Mrk 501). The observations are comprised of data taken in the period between 2015 June and 2018 July, resulting in similar to 1038 days of exposure. In this work, we report the time-averaged spectral analyses for both sources, above 0.5 TeV. Taking into account the flux attenuation due to the extragalactic background light, the intrinsic spectrum of Mrk 421 is described by a power law with an exponential energy cutoff with index alpha = 2.26 +/- (0.12)(stat)((+0.17)(-0.2))(sys) and energy cutoff E-c = 5.1 +/- (1.6)(stat)((+1.4)(-2.5))(sys) TeV, while the intrinsic spectrum of Mrk 501 is better described by a simple power law with index alpha = 2.61 +/- (0.11)(stat)((+)(0.01)(-0.07))(sys). The maximum energies at which the Mrk 421 and Mrk 501 signals are detected are 9 and 12 TeV, respectively. This makes these some of the highest energy detections to date for spectra averaged over years-long timescales. Since the observation of gamma radiation from blazars provides information about the physical processes that take place in their relativistic jets, it is important to study the broadband spectral energy distributions (SEDs) of these objects. For this purpose, contemporaneous data in the gamma-ray band to the X-ray range, and literature data in the radio to UV range, were used to build time-averaged SEDs that were modeled within a synchrotron-self Compton leptonic scenario.
CRIS-Team WoS Importer:2022-05-13

Long-term TeV and X-ray observations of the gamma-ray binary hess j0632+057 - Aliu, E.; Archambault, S.; Aune, T.; Behera, B.; Beilicke, M.; Benbow, W.; Berger, K.; Bird, Ralph; Bouvier, A.; Buckley, J. H.; Bugaev, V.; Byrum, K.; et al. (Astrophysical Journal, 2014)
HESS J0632+057 is the only gamma-ray binary known so far whose position in the sky allows observations with ground-based observatories in both the northern and southern hemispheres. Here we report on long-term observations of HESS J0632+057 conducted with the Very Energetic Radiation Imaging Telescope Array System and High Energy Stereoscopic System Cherenkov telescopes and the X-ray satellite Swift, spanning a time range from 2004 to 2012 and covering most of the system's orbit. The very-high-energy (VHE) emission is found to be variable and is correlated with that at X-ray energies. An orbital period of days is derived from the X-ray data set, which is compatible with previous results, P = (321 ± 5) days. The VHE light curve shows a distinct maximum at orbital phases close to 0.3, or about 100 days after periastron passage, which coincides with the periodic enhancement of the X-ray emission. Furthermore, the analysis of the TeV data shows for the first time a statistically significant (>6.5σ) detection at orbital phases 0.6-0.9. The obtained gamma-ray and X-ray light curves and the correlation of the source emission at these two energy bands are discussed in the context of the recent ephemeris obtained for the system. Our results are compared to those reported for other gamma-ray binaries. © 2014. The American Astronomical Society. All rights reserved..
Keywords: acceleration of particles; binaries:general

Machine learning methods for constructing probabilistic Fermi -LAT catalogs - Bhat, Aakash; Malyshev, Dmitry (Astronomy & Astrophysics, 2022)
Context. Classification of sources is one of the most important tasks in astronomy. Sources detected in one wavelength band, for example using gamma rays, may have several possible associations in other wavebands, or there may be no plausible association candidates. Aims. In this work we aim to determine the probabilistic classification of unassociated sources in the third Fermi Large Area Telescope (LAT) point source catalog (3FGL) and the fourth Fermi LAT data release 2 point source catalog (4FGL-DR2) using two classes - pulsars and active galactic nuclei (AGNs) - or three classes - pulsars, AGNs, and OTHER sources. Methods. We use several machine learning (ML) methods to determine a probabilistic classification of Fermi-LAT sources. We evaluate the dependence of results on the meta-parameters of the ML methods, such as the maximal depth of the trees in tree-based classification methods and the number of neurons in neural networks. Results. We determine a probabilistic classification of both associated and unassociated sources in the 3FGL and 4FGL-DR2 catalogs. We cross-check the accuracy by comparing the predicted classes of unassociated sources in 3FGL with their associations in 4FGL-DR2 for cases where such associations exist. We find that in the two-class case it is important to correct for the presence of OTHER sources among the unassociated ones in order to realistically estimate the number of pulsars and AGNs. We find that the three-class classification, despite different types of sources in the OTHER class, has a similar performance as the two-class classification in terms of reliability diagrams and, at the same time, it does not require adjustment due to presence of the OTHER sources among the unassociated sources. We show an example of the use of the probabilistic catalogs for population studies, which include associated and unassociated sources.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Catalogs; Gamma rays: general; Methods: statistical

MAGIC and Fermi-LAT gamma-ray results on unassociated HAWC sources - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Baack, D.; Babic, A.; Banerjee, Biswajit; Bangale, P.; Barres De Almeida, U.; Barrio, J. A.; Becerra Gonzalez, J.; Bednarek, W.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
The HAWC Collaboration released the 2HWC catalogue of TeV sources, in which 19 show no association with any known high-energy (HE; E ≳ 10 GeV) or very-high-energy (VHE; E ≳ 300 GeV) sources. This catalogue motivated follow-up studies by both the Major Atmospheric Gamma-ray Imaging Cherenkov (MAGIC) and Fermi-LAT (Large Area Telescope) observatories with the aim of investigating gamma-ray emission over a broad energy band. In this paper, we report the results from the first joint work between High Altitude Water Cherenkov (HAWC), MAGIC, and Fermi-LAT on three unassociated HAWC sources: 2HWC J2006+341, 2HWC J1907+084∗, and 2HWC J1852+013∗. Although no significant detection was found in the HE and VHE regimes, this investigation shows that a minimum 1° extension (at 95 per cent confidence level) and harder spectrum in the GeV than the one extrapolated from HAWC results are required in the case of 2HWC J1852+013∗, whilst a simply minimum extension of 0.16° (at 95 per cent confidence level) can already explain the scenario proposed by HAWC for the remaining sources. Moreover, the hypothesis that these sources are pulsar wind nebulae is also investigated in detail.
CRIS-Team Scopus Importer:2019-09-24
Keywords: astroparticle physics; gamma rays: general; pulsars: general

Maximum likelihood reconstruction for grating-based X-ray microscopy - Wolf, Andreas; Schuster, Max; Ludwig, Veronika; Anton, Gisela; Funk, Stefan (Optics Express, 2020)
The combination of grating-based phase-contrast imaging with X-ray microscopy can result in a complicated image formation. Generally, transverse shifts of the interference fringes are nonlinearly dependent on phase differences of the measured wave front. We present an iterative reconstruction scheme based on a regularized maximum likelihood cost function that fully takes this dependency into account. The scheme is validated by numerical simulations. It is particularly advantageous at low photon numbers and when the premises for deconvolution-based reconstructions are not met. Our reconstruction scheme hence enables a broader applicability of X-ray grating interferometry in imaging and wave front sensing.
CRIS-Team Scopus Importer:2020-05-22

Measurement of the EBL spectral energy distribution using the VHE gamma-ray spectra of HESS blazars - Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Very high-energy gamma rays (VHE, E greater than or similar to 100 GeV) propagating over cosmological distances can interact with the low-energy photons of the extragalactic background light (EBL) and produce electron-positron pairs. The transparency of the Universe to VHE gamma rays is then directly related to the spectral energy distribution (SED) of the EBL. The observation of features in the VHE energy spectra of extragalactic sources allows the EBL to be measured, which otherwise is very difficult. An EBL model-independent measurement of the EBL SED with the H.E.S.S. array of Cherenkov telescopes is presented. It was obtained by extracting the EBL absorption signal from the reanalysis of high-quality spectra of blazars. From H.E.S.S. data alone the EBL signature is detected at a significance of 9.5 sigma, and the intensity of the EBL obtained in different spectral bands is presented together with the associated gamma-ray horizon.
CRIS-Team WoS Importer:2020-01-15
Keywords: Infrared: diffuse background; Cosmic background radiation; Gamma rays: galaxies; BL Lacertae objects: general

Measurement of the extragalactic background light imprint on the spectra of the brightest blazars observed with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
The extragalactic background light (EBL) is the diffuse radiation with the second highest energy density in the Universe after the cosmic microwave background. The aim of this study is the measurement of the imprint of the EBL opacity to γ-rays on the spectra of the brightest extragalactic sources detected with the High Energy Stereoscopic System (H.E.S.S.). The originality of the method lies in the joint fit of the EBL optical depth and of the intrinsic spectra of the sources, assuming intrinsic smoothness. Analysis of a total of ∼10γ-ray events enables the detection of an EBL signature at the 8.8σ level and constitutes the first measurement of the EBL optical depth using very-high energy (E > 100 GeV) γ-rays. The EBL flux density is constrained over almost two decades of wavelengths [0.30 μm, 17 μm] and the peak value at 1.4 μm is derived as λF = 15 ± 2 ± 3 nW m sr. © 2013 ESO.
Keywords: BL Lacertae objects: general; Cosmic background radiation; Gamma rays: galaxies

Measurement of the high-energy gamma-ray emission from the Moon with the Fermi Large Area Telescope - Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, R.; Bottacini, E.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We have measured the gamma-ray emission spectrum of the Moon using the data collected by the Large Area Telescope onboard the Fermi satellite during its first seven years of operation, in the energy range from 30 MeV up to a few GeV. We have also studied the time evolution of the flux, finding a correlation with the solar activity. We have developed a full Monte Carlo simulation describing the interactions of cosmic rays with the lunar surface. The results of the present analysis can be explained in the framework of this model, where the production of gamma rays is due to the interactions of cosmic-ray proton and helium nuclei with the surface of the Moon. Finally, we have used our simulation to derive the cosmic-ray proton and helium spectra near Earth from the Moon gamma-ray data.

Micro-cylinder-lens testing using computer-generated holograms - Mantel, Klaus Peter; Lamprecht, Jürgen; Lindlein, Norbert; Schreiner, Roland; Schwider, Johannes; Ferstl, Manfred (Fringe 2001, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.microc

MINUTE-TIMESCALE > 100 MeV gamma-RAY VARIABILITY DURING THE GIANT OUTBURST OF QUASAR 3C 279 OBSERVED BY FERMI-LAT IN 2015 JUNE - Uchiyama, Y.; Sikora, M.; Nalewajko, K.; Ohsugi, T.; Maldera, S.; Negro, M.; La Mura, G.; Mirabal, N.; Anantua, R.; Yuan, Y.; Cavazzuti, E.; Bonino, R.; et al. (Astrophysical Journal Letters, 2016)
On 2015 June 16, Fermi- LAT observed a giant outburst from the flat spectrum radio quasar 3C 279 with a peak >100 MeV flux of similar to 3.6 x 10(-5) photons cm(-2) s(-1), averaged over orbital period intervals. It is historically the highest gamma-ray flux observed from the source, including past EGRET observations, with the gamma-ray isotropic luminosity reaching similar to 10(49) erg s(-1). During the outburst, the Fermi spacecraft, which has an orbital period of 95.4 minutes, was operated in a special pointing mode to optimize the exposure for 3C 279. For the first time, significant flux variability at sub-orbital timescales was found in blazar observations by Fermi- LAT. The source flux variability was resolved down to 2-minute binned timescales, with flux doubling times of less than 5 minutes. The observed minute-scale variability suggests a very compact emission region at hundreds of Schwarzschild radii from the central engine in conical jet models. A minimum bulk jet Lorentz factor (Gamma) of 35 is necessary to avoid both internal gamma-ray absorption and super-Eddington jet power. In the standard external radiation Comptonization scenario, G should be at least 50 to avoid overproducing the synchrotron self-Compton component. However, this predicts extremely low magnetization (similar to 5 x 10(-4)). Equipartition requires Gamma as high as 120, unless the emitting region is a small fraction of the dissipation region. Alternatively, we consider. rays originating as synchrotron radiation of gamma e similar to 1.6 x 10(6) electrons, in a magnetic field B similar to 1.3 kG, accelerated by strong electric fields E similar to B in the process of magnetoluminescence. At such short distance scales, one cannot immediately exclude the production of gamma-rays in hadronic processes.
Keywords: galaxies: active; galaxies: jets; gamma rays: galaxies; quasars: individual (3C 279); radiation mechanisms: non-thermal

Monte Carlo studies for the optimisation of the Cherenkov Telescope Array layout - Acharyya, A.; Agudo, I.; Angüner, E. O.; Alfaro, R.; Alfaro, J.; Alispach, C.; Aloisio, R.; Alves Batista, R.; Amans, J. P.; Amati, L.; Amato, E.; Ambrosi, G.; et al. (Astroparticle Physics, 2019)
The Cherenkov Telescope Array (CTA) is the major next-generation observatory for ground-based very-high-energy gamma-ray astronomy. It will improve the sensitivity of current ground-based instruments by a factor of five to twenty, depending on the energy, greatly improving both their angular and energy resolutions over four decades in energy (from 20 GeV to 300 TeV). This achievement will be possible by using tens of imaging Cherenkov telescopes of three successive sizes. They will be arranged into two arrays, one per hemisphere, located on the La Palma island (Spain) and in Paranal (Chile). We present here the optimised and final telescope arrays for both CTA sites, as well as their foreseen performance, resulting from the analysis of three different large-scale Monte Carlo productions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cherenkov telescopes; Cosmic rays; Gamma rays; IACT technique; Monte Carlo simulations

Monte Carlo studies of medium-size telescope designs for the Cherenkov Telescope Array - Wood, M.; Jogler, T.; Dumm, J.; Funk, Stefan; Funk, Stefan (Astroparticle Physics, 2016)
We present studies for optimizing the next generation of ground-based imaging atmospheric Cherenkov telescopes (IACTs). Results focus on mid-sized telescopes (MSTs) for CTA, detecting very high energy gamma rays in the energy range from a few hundred GeV to a few tens of TeV. We describe a novel, flexible detector Monte Carlo package, FAST (FAst Simulation for imaging air cherenkov Telescopes), that we use to simulate different array and telescope designs. The simulation is somewhat simplified to allow for efficient exploration over a large telescope design parameter space. We investigate a wide range of telescope performance parameters including optical resolution, camera pixel size, and light collection area. In order to ensure a comparison of the arrays at their maximum sensitivity, we analyze the simulations with the most sensitive techniques used in the field, such as maximum likelihood template reconstruction and boosted decision trees for background rejection. Choosing telescope design parameters representative of the proposed Davies-Cotton (DC) and Schwarzchild-Couder (SC) MST designs, we compare the performance of the arrays by examining the gamma-ray angular resolution and differential point-source sensitivity. We-further investigate the array performance under a wide range of conditions, determining the impact of the number of telescopes, telescope separation, night sky background, and geomagnetic field. We find a 30-40% improvement in the gamma-ray angular resolution at all energies when comparing arrays with an equal number of SC and DC telescopes, significantly enhancing point-source sensitivity in the MST energy range. We attribute the increase in point-source sensitivity to the improved optical point-spread function and smaller pixel size of the SC telescope design. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Monte Carlo simulations; Cherenkov telescopes; IACT technique; Gamma rays; Cosmic rays

Morphological and spectral studies of the shell-type SNRs RX J1713.7-3946 and RX J0852.0-4622 with HESS - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

Morphometric analysis in gamma-ray astronomy using Minkowski functionals Source detection via structure quantification - Göring, Daniel; Klatt, Michael; Stegmann, C.; Mecke, Klaus (Astronomy & Astrophysics, 2013)
Results. We have successfully applied our method to data of the H.E.S.S. experiment. The morphometric analysis presented here is dedicated to detecting faint extended sources.
Keywords: methods: data analysis; methods: statistical; techniques: image processing; gamma rays: diffuse background

Multiclass classification of Fermi-LAT sources with hierarchical class definition - Malyshev, Dmitry; Bhat, Aakash (Monthly Notices of the Royal Astronomical Society, 2023)
In this paper, we develop multiclass classification of Fermi-large area telescope (LAT) gamma-ray sources using machine learning with hierarchical determination of classes. One of the main challenges in the multiclass classification of the Fermi-LAT sources is that the size of some of the classes is relatively small, for example with less than 10 associated sources belonging to a class. In this paper, we propose a hierarchical structure for the determination of the classes. This enables us to have control over the size of classes and to compare the performance of the classification for different numbers of classes. In particular, the class probabilities in the two-class case can be computed either directly by the two-class classification or by summing probabilities of children classes in multiclass classification. We find that the classifications with few large classes have comparable performance with classifications with many smaller classes. Thus, on one hand, the few-class classification can be recovered by summing probabilities of classification with more classes while, on the other hand, the classification with many classes gives a more detailed information about the physical nature of the sources. As a result of this work, we construct three probabilistic catalogues, which are available online. This work opens up a possibility to perform population studies of sources including unassociated sources and to narrow down searches for possible counterparts of unassociated sources, such as active galactic nuclei, pulsars, or millisecond pulsars.
CRIS-Team Scopus Importer:2023-06-02
Keywords: catalogues; gamma-rays: general; methods: statistical

Multimessenger gamma-ray and neutrino coincidence alerts using hawc and icecube subthreshold data - Solares, H. A.Ayala; Coutu, S.; DeLaunay, J. J.; Fox, D. B.; Grégoire, T.; Keivani, A.; Krauß, F.; Mostafá, M.; Murase, K.; Turley, C. F.; Albert, A.; Alfaro, R.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cerenkov (HAWC) and IceCube observatories, through the Astrophysical Multimessenger Observatory Network (AMON) framework, have developed a multimessenger joint search for extragalactic astrophysical sources. This analysis looks for sources that emit both cosmic neutrinos and gamma rays that are produced in photohadronic or hadronic interactions. The AMON system is running continuously, receiving subthreshold data (i.e., data that are not suited on their own to do astrophysical searches) from HAWC and IceCube, and combining them in real time. Here we present the analysis algorithm, as well as results from archival data collected between 2015 June and 2018 August, with a total live time of 3.0 yr. During this period we found two coincident events that have a false-alarm rate (FAR) of <1 coincidence yr-1, consistent with the background expectations. The real-time implementation of the analysis in the AMON system began on 2019 November 20 and issues alerts to the community through the Gamma-ray Coordinates Network with an FAR threshold of <4 coincidences yr-1.
CRIS-Team Scopus Importer:2021-01-22

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multiple Galactic Sources with Emission Above 56 TeV Detected by HAWC - Albert, A.; Alfaro, R.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Capistran, T.; Carraminana, A.; Casanova, S.; Cotti, U.; Cotzomi, J.; Coutino De Leon, S.; et al. (Physical Review Letters, 2020)
We present the first catalog of gamma-ray sources emitting above 56 and 100 TeV with data from the High Altitude Water Cherenkov Observatory, a wide field-of-view observatory capable of detecting gamma rays up to a few hundred TeV. Nine sources are observed above 56 TeV, all of which are likely galactic in origin. Three sources continue emitting past 100 TeV, making this the highest-energy gamma-ray source catalog to date. We report the integral flux of each of these objects. We also report spectra for three high-estenergy sources and discuss the possibility that they are PeVatrons.
CRIS-Team WoS Importer:2020-01-31

Multi-wavelength observations of H 2356-309 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Aims. The properties of the broad-band emission from the high-frequency peaked BL Lac H 2356-309 (z = 0.165) are investigated. Methods. Very high energy (VHE; E > 100 GeV) observations of H 2356-309 were performed with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Simultaneous optical/UV and X-ray observations were made with the XMM-Newton satellite on June 12/13 and June 14/15, 2005. NRT radio observations were also contemporaneously performed in 2005. ATOM optical monitoring observations were also made in 2007. Results. A strong VHE signal, ∼13σ total, was detected by HESS after the four years HESS observations (116.8 h live time). The integral flux above 240 GeV is I(>240 GeV) = (3.06 ± 0.26 ± 0.61) × 10 cm s, corresponding to ∼1.6% of the flux observed from the Crab Nebula. A time-averaged energy spectrum is measured from 200 GeV to 2 TeV and is characterized by a power law (photon index of Γ = 3.06 ± 0.15 ± 0.10). Significant small-amplitude variations in the VHE flux from H 2356-309 are seen on time scales of months and years, but not on shorter time scales. No evidence for any variations in the VHE spectral slope are found within these data. The XMM-Newton X-ray measurements show a historically low X-ray state, characterized by a hard, broken-power-law spectrum on both nights. Conclusions. The broad-band spectral energy distribution (SED) of the blazar can be adequately fit using a simple one-zone synchrotron self-Compton (SSC) model. In the SSC scenario, higher VHE fluxes could be expected in the future since the observed X-ray flux is at a historically low level. © 2010 ESO.
Keywords: BL Lacertae objects: individual: H 2356-309; Galaxies: active; Gamma rays: galaxies

Multi-wavelength observations of PKS 2155-304 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The High Energy Stereoscopic System (HESS) has observed the high-frequency peaked BL Lac object PKS 2155- 304 in 2003 between October 19 and November 26 in Very High Energy (VHE) gamma-rays (E >= 160 GeV for these observations). Observations were carried out simultaneously with the Proportional Counter Array (PCA) on board the Rossi X-ray Timing Explorer satellite ( RXTE), the Robotic Optical Transient Search Experiment (ROTSE) and the Nancay decimetric radiotelescope (NRT). Intra-night variability is seen in the VHE band, the source being detected with a high significance on each night it was observed. Variability is also found in the X-ray and optical bands on kilosecond timescales, along with flux-dependent spectral changes in the X-rays. A transient X-ray event with a 1500 s timescale is detected, making this the fastest X-ray flare seen in this object. No correlation can be established between the X-ray and the gamma-ray fluxes, or any of the other wavebands, over the small range of observed variability. The average HESS spectrum shows a very soft power law shape with a photon index of 3.37 +/- 0.07(stat) +/- 0.10(sys). The energy outputs in the 2 - 10 keV and in the VHE gamma-ray range are found to be similar, with the X-rays and the optical fluxes at a level comparable to some of the lowest historical measurements, indicating that PKS 2155- 304 was in a low or quiescent state during the observations. Both a leptonic and a hadronic model are used to derive source parameters from these observations. These parameters are found to be sensitive to the model of Extragalactic Background Light (EBL) that attenuates the VHE signal at this source's redshift (z = 0.117).
CRIS-Team WoS Importer:2020-01-15

Noise reduction for single-shot grating-based phase-contrast imaging at an x-ray backlighter - Schreiner, Stephan; Akstaller, Bernhard; Dietrich, Lisa; Meyer, Pascal; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Zielbauer, Bernhard; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2021)
X-ray backlighters allow the capture of sharp images of fast dynamic processes due to extremely short exposure times. Moiré imaging enables simultaneously measuring the absorption and differential phase-contrast (DPC) of these processes. Acquiring images with one single shot limits the X-ray photon flux, which can result in noisy images. Increasing the photon statistics by repeating the experiment to gain the same image is not possible if the investigated processes are dynamic and chaotic. Furthermore, to reconstruct the DPC and transmission image, an additional measurement captured in absence of the object is required. For these reference measurements, shot-to-shot fluctuations in X-ray spectra and a source position complicate the averaging of several reference images for noise reduction. Here, two approaches of processing multiple reference images in combination with one single object image are evaluated regarding the image quality. We found that with only five reference images, the contrast-to-noise ratio can be improved by approximately 13% in the DPC image. This promises improvements for short-exposure single-shot acquisitions of rapid processes, such as laser-produced plasma shock-waves in high-energy density experiments at backlighter X-ray sources such as the PHELIX high-power laser facility.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Grating-based phase-contrast; Image processing; Image quality improvement; Single-shot X-ray phase-contrast imaging; X-ray back-lighter; X-ray generators and sources

Novel technique for monitoring the performance of the LAT instrument on board the GLAST satellite - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

Observation of the microquasar LS 5039 with HESS - Funk, Stefan; et al. (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

Observations of M31 and M33 with the Fermi Large Area Telescope: A Galactic Center Excess in Andromeda? - Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal, 2017)
The Fermi Large Area Telescope (LAT) has opened the way for comparative studies of cosmic rays (CRs) and high-energy objects in the Milky Way (MW) and in other, external, star-forming galaxies. Using 2 yr of observations with the Fermi LAT, Local Group galaxy M31 was detected as a marginally extended gamma-ray source, while only an upper limit has been derived for the other nearby galaxy M33. We revisited the gamma-ray emission in the direction of M31 and M33 using more than 7 yr of LAT Pass 8 data in the energy range 0.1-100 GeV, presenting detailed morphological and spectral analyses. M33 remains undetected, and we computed an upper limit of 2.0 x 10(-12) erg cm(-2) s(-1) on the 0.1-100 GeV energy flux (95% confidence level). This revised upper limit remains consistent with the observed correlation between gamma-ray luminosity and star formation rate tracers and implies an average CR density in M33 that is at most half of that of the MW. M31 is detected with a significance of nearly 10 sigma. Its spectrum is consistent with a power law with photon index Gamma = 2.4 +/- 0.1(stat) (vertical bar) (syst) and a 0.1-100 GeV energy flux of (5.6 +/- 0.6(stat vertical bar syst)) x 10(-12) erg cm(-1) s(-1). M31 is detected to be extended with a 4 sigma significance. The spatial distribution of the emission is consistent with a uniform-brightness disk with a radius of 0 degrees.4 and no offset from the center of the galaxy, but nonuniform intensity distributions cannot be excluded. The flux from M31 appears confined to the inner regions of the galaxy and does not fill the disk of the galaxy or extend far from it. The gamma-ray signal is not correlated with regions rich in gas or star formation activity, which suggests that the emission is not interstellar in origin, unless the energetic particles radiating in gamma rays do not originate in recent star formation. Alternative and nonexclusive interpretations are that the emission results from a population of millisecond pulsars dispersed in the bulge and disk of M31 by disrupted globular clusters or from the decay or annihilation of dark matter particles, similar to what has been proposed to account for the so-called Galactic center excess found in Fermi-LAT observations of the MW.
CRIS-Team WoS Importer:2020-01-15

Observations of Mkn 421 in 2004 with HESS at large zenith angles - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Mkn 421 was observed during a high flux state for nine nights in April and May 2004 with the fully operational High Energy Stereoscopic System (HESS) in Namibia. The observations were carried out at zenith angles of 60 degrees- 65 degrees, which result in an average energy threshold of 1.5 TeV and a collection area reaching 2 km(2) at 10 TeV. Roughly 7000 photons from Mkn 421 were accumulated with an average gamma-ray rate of 8 photons/min. The overall significance of the detection exceeds 100 standard deviations. The light-curve of integrated fluxes above 2 TeV shows changes of the diurnal flux up to a factor of 4.3. For nights of high flux, intra-night variability is detected with a decay time of less than 1 h. The time averaged energy spectrum is curved and is well described by a power-law with a photon index Gamma = 2.1 +/- 0.1(stat) +/- 0.3(sys) and an exponential cutoff at E-c = 3.1(+ 0.5 - 0.4)(stat) +/- 0.9(sys) TeV and an average integral flux above 2 TeV of 3 Crab flux units. Significant variations of the spectral shape are detected with a spectral hardening as the flux increases. Contemporaneous multi-wavelength observations at lower energies (X-rays and gamma-rays above approximate to 300 GeV) indicate smaller relative variability amplitudes than seen above 2 TeV during high flux state observed in April 2004.
CRIS-Team WoS Importer:2020-01-15

Observations of selected AGN with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
A sample of selected active galactic nuclei (AGN) was observed in 2003 and 2004 with the High Energy Stereoscopic System (HESS), an array of imaging atmospheric-Cherenkov telescopes in Namibia. The redshifts of these candidate very-high-energy (VHE, > 100 GeV) gamma-ray emitters range from z = 0.00183 to z = 0.333. Significant detections were already reported for some of these objects, such as PKS 2155-304 and Markarian 421. Marginal evidence (3.1 sigma) for a signal is found from large-zenith-angle observations of Markarian 501, corresponding to an integral flux of I(> 1.65 TeV) = (1.5 +/- 0.6(stat)+/- 0.3(syst)) x 10(-12) cm(-2) s(-1) or similar to 15% of the Crab Nebula flux. Integral flux upper limits for 19 other AGN, based on exposures of similar to 1 to similar to 8 h live time, and with average energy thresholds between 160 GeV and 610 GeV, range from 0.4% to 5.1% of the Crab Nebula flux. All the upper limits are the most constraining ever reported for these objects.
CRIS-Team WoS Importer:2020-01-15

Observations of SNR RX J1713.7-3946 with HESS - Funk, Stefan; et al. (High Energy Gamma-Ray Astronomy, 2005)
CRIS-Team WoS Importer:2020-01-15

Observations of the Galactic Centre region in very high energy gamma-rays with HESS - Funk, Stefan; et al. (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

Operating performance of the gamma-ray Cherenkov telescope: An end-to-end Schwarzschild-Couder telescope prototype for the Cherenkov Telescope Array - Dournaux, J. L.; De Franco, A.; Laporte, P.; White, R.; Greenshaw, T.; Sol, H.; Abchiche, A.; Allan, D.; Amans, J. P.; Armstrong, T. P.; Balzer, A.; Berge, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
The Cherenkov Telescope Array (CTA) consortium aims to build the next-generation ground-based very-high-energy gamma-ray observatory. The array will feature different sizes of telescopes allowing it to cover a wide gamma-ray energy band from about 20. GeV to above 100. TeV. The highest energies, above 5. TeV, will be covered by a large number of Small-Sized Telescopes (SSTs) with a field-of-view of around 9°. The Gamma-ray Cherenkov Telescope (GCT), based on Schwarzschild-Couder dual-mirror optics, is one of the three proposed SST designs. The GCT is described in this contribution and the first images of Cherenkov showers obtained using the telescope and its camera are presented. These were obtained in November 2015 in Meudon, France.
Keywords: Cherenkov detector; Cherenkov telescopes; CTA; GCT; IACT; Schwarzschild-Couder telescope

Optical intensity interferometry lab tests in preparation of stellar diameter measurements at IACTs at GHz photon rates - Zmija, Andreas; Vogel, Naomi; Anton, Gisela; Malyshev, Dmitry; Michel, Thilo; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Astronomical intensity interferometry enables quantitative measurements of the source geometry by measuring the photon fluxes in individual telescopes and correlating them, rather than correlating the electromagnetic waves' amplitudes. This simplifies the realization of large telescope baselines and high angular resolutions. Imaging Atmospheric Cherenkov Telescopes (IACTs), intended to detect the optical emission of γ-ray-induced air showers, are excellent candidates to perform intensity correlations in the optical at reasonable signal-to-noise ratios. The detected coherence time is on the scale of (10-12)-(10-15) s-depending on the optical bandwidth of the measurement-which challenges the detection system to work in a stable and accurate way. We developed an intensity interferometry set-up applicable to IACTs, which measures the photocurrents from photomultipliers and correlates them offline, and as such is designed to handle the very large photon rates provided by the telescopes. We present measurements in the lab simulating starlight using a xenon lamp and measured at different degrees of temporal and spatial coherence. Necessary calibration procedures are described with the goal of understanding the measurements quantitatively. Measured coherence times between 5 femtoseconds (corresponding signal-to-background ratio 5 × 10-7) and 110 femtoseconds (signal-to-background ratio 10-5) are in good agreement with expectations, and so are the noise levels in the correlations, reaching down to 6 × 10-8, after measurements between 30 min and 1 h.
CRIS-Team Scopus Importer:2021-12-24
Keywords: instrumentation: detectors; instrumentation: interferometers; stars: imaging; techniques: interferometric

OPTICAL SPECTROSCOPIC OBSERVATIONS OF BLAZARS AND gamma-RAY BLAZAR CANDIDATES IN THE SLOAN DIGITAL SKY SURVEY DATA RELEASE NINE - Massaro, F.; Masetti, N.; D'Abrusco, R.; Paggi, A.; Funk, Stefan (Astronomical Journal, 2014)
We present an analysis of the optical spectra available in the Sloan Digital Sky Survey data release nine (SDSS DR9) for the blazars listed in the ROMA-BZCAT and for the gamma-ray blazar candidates selected according to their IR colors. First, we adopt a statistical approach based on Monte Carlo simulations to find the optical counterparts of the blazars listed in the ROMA-BZCAT catalog. Then, we crossmatched the SDSS spectroscopic catalog with our selected samples of blazars and gamma-ray blazar candidates, searching for those with optical spectra available to classify our blazar-like sources and, whenever possible, to confirm their redshifts. Our main objectives are to determine the classification of uncertain blazars listed in the ROMA-BZCAT and to discover new gamma-ray blazars. For the ROMA-BZCAT sources, we investigated a sample of 84 blazars, confirming the classification for 20 of them and obtaining 18 new redshift estimates. For the gamma-ray blazars, indicated as potential counterparts of unassociated Fermi sources or with uncertain nature, we established the blazar-like nature of 8 out of the 27 sources analyzed and confirmed 14 classifications.
Keywords: galaxies: active; quasars: general; methods: statistical; radiation mechanisms: non-thermal; surveys

OPTICAL SPECTROSCOPIC OBSERVATIONS OF gamma-RAY BLAZAR CANDIDATES. I. PRELIMINARY RESULTS - Paggi, A.; Milisavljevic, D.; Masetti, N.; Jimenez-Bailon, E.; Chavushyan, V.; D'Abrusco, R.; Massaro, F.; Giroletti, M.; Smith, H. A.; Margutti, R.; Tosti, G.; Martinez-Galarza, J. R.; et al. (Astronomical Journal, 2014)
A significant fraction (similar to 30%) of the gamma-ray sources listed in the second Fermi/LAT (2FGL) catalog is still of unknown origin, being not yet associated with counterparts at lower energies. Using the available information at lower energies and optical spectroscopy on the selected counterparts of these gamma-ray objects, we can pinpoint their exact nature. Here, we present a pilot project pointing to assess the effectiveness of the several classification methods developed to select gamma-ray blazar candidates. To this end, we report optical spectroscopic observations of a sample of five gamma-ray blazar candidates selected on the basis of their infrared Wide-field Infrared Survey Explorer (WISE) colors or of their low-frequency radio properties. Blazars come in two main classes, BL Lac objects and FSRQs, showing similar optical spectra except for the stronger emission lines of the latter. For three of our sources, the almost featureless optical spectra obtained confirm their BL Lac nature, while for the source WISEJ022051.24+250927.6 we observe emission lines with equivalent width EW similar to 31 angstrom, identifying it as a FSRQ with z = 0.48. The source WISEJ064459.38+603131.7, although not featuring a clear radio counterpart, shows a blazar-like spectrum with weak emission lines with EW similar to 7 angstrom, yielding a redshift estimate of z = 0.36. In addition, we report optical spectroscopic observations of four WISE sources associated with known gamma-ray blazars without a firm classification or redshift estimate. For the latter sources, we confirm a BL Lac classification, with a tentative redshift estimate for the source WISEJ100800.81+062121.2 of z = 0.65.
Keywords: BL Lacertae objects: general; galaxies: active; radiation mechanisms: non-thermal

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

PKS 1502+106: A NEW AND DISTANT GAMMA-RAY BLAZAR IN OUTBURST DISCOVERED BY THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2010)
The Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope discovered a rapid (similar to 5 days duration), high-energy (E > 100 MeV) gamma-ray outburst from a source identified with the blazar PKS 1502+106 (OR 103, S3 1502+10, z = 1.839) starting on 2008 August 5 (similar to 23 UTC, MJD 54683.95), and followed by bright and variable flux over the next few months. Results on the gamma-ray localization and identification, as well as spectral and temporal behavior during the first months of the Fermi all-sky survey, are reported here in conjunction with a multiwaveband characterization as a result of one of the first Fermi multifrequency campaigns. The campaign included a Swift ToO (followed up by a 16 day observation on August 7-22, MJD 54685-54700), VLBA (within the MOJAVE program), Owens Valley Radio Observatory (OVRO) 40 m, Effelsberg-100 m, Metsahovi-14 m, RATAN-600, and Kanata-Hiroshima radio/optical observations. Results from the analysis of archival observations by INTEGRAL, XMM-Newton, and Spitzer space telescopes are reported for a more complete picture of this new gamma-ray blazar. PKS 1502+106 is a sub-GeV peaked, powerful flat spectrum radio quasar (luminosity at E > 100 MeV, L-gamma, is about 1.1 x 10(49) erg s(-1), and black hole mass likely close to 10(9) M-circle dot), exhibiting marked gamma-ray bolometric dominance, in particular during the asymmetric outburst (L-gamma/L-opt similar to 100, and 5 day averaged flux F-E > 100MeV = 2.91 +/- 1.4 x 10(-6) ph cm(-2) s(-1)), which was characterized by a factor greater than 3 of flux increase in less than 12 hr. The outburst was observed simultaneously from optical to X-ray bands (F0.3-10keV = 2.18(-0.12)(+0.15) x 10(-12) erg cm(-2) s(-1), and hard photon index similar to 1.5, similar to past values) with a flux increase of less than 1 order of magnitude with respect to past observations, and was likely controlled by Comptonization of external-jet photons produced in the broad-line region (BLR) in the gamma-ray band. No evidence of a possible blue bump signature was observed in the optical-UV continuum spectrum, while some hints for a possible 4 day time lag with respect to the gamma-ray flare were found. Nonetheless, the properties of PKS 1502+106 and the strict optical/UV, X-, and gamma-ray cross-correlations suggest the contribution of the synchrotron self-Compton (SSC), in-jet, process should dominate from radio to X- rays. This mechanism may also be responsible for the consistent gamma-ray variability observed by the LAT on longer timescales, after the ignition of activity at these energies provided by the BLR-dissipated outburst. Modulations and subsequent minor, rapid flare events were detected, with a general fluctuation mode between pink-noise and a random-walk. The averaged gamma-ray spectrum showed a deviation from a simple power law, and can be described by a log-parabola curved model peaking around 0.4-0.5 GeV. The maximum energy of photons detected from the source in the first four months of LAT observations was 15.8 GeV, with no significant consequences on extragalactic background light predictions. A possible radio counterpart of the gamma-ray outburst can be assumed only if a delay of more than three months is considered on the basis of opacity effects at cm and longer wavelengths.
CRIS-Team WoS Importer:2020-01-15

PKS2005-489 at VHE: Four years of monitoring with HESS and simultaneous multi-wavelength observations - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims: Our aim is to study the very high energy (VHE; E > 100 GeV) Γ-ray emission from BL Lac objects and the evolution in time of their broad-band spectral energy distribution (SED). Methods: VHE observations of the high-frequency peaked BL Lac object PKS 2005-489 were made with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Three simultaneous multi-wavelength campaigns at lower energies were performed during the HESS data taking, consisting of several individual pointings with the XMM-Newton and RXTE satellites. Results: A strong VHE signal, ∼17ρ total, from PKS 2005-489 was detected during the four years of HESS observations (90.3 h live time). The integral flux above the average analysis threshold of 400 GeV is ∼3% of the flux observed from the Crab Nebula and varies weakly on time scales from days to years. The average VHE spectrum measured from ∼300 GeV to ∼5 TeV is characterized by a power law with a photon index, Γ = 3.20 ± 0.16 ± 0.10 At X-ray energies the flux is observed to vary by more than an order of magnitude between 2004 and 2005. Strong changes in the X-ray spectrum (ΔΓ ≈ 0.7) are also observed, which appear to be mirrored in the VHE band. Conclusions: The SED of PKS 2005-4 constructed for the first time with contemporaneous data on both humps, shows significant evolution. The large flux variations in the X-ray band, coupled with weak or no variations in the VHE band and a similar spectral behavior, suggest the emergence of a new, separate, harder emission component in September 2005. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 2005-489; Galaxies: active; Gamma rays: galaxies; X-rays: individuals: PKS 2005-489

Population study of Galactic supernova remnants at very high gamma-ray energies with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Shell-type supernova remnants (SNRs) are considered prime candidates for the acceleration of Galactic cosmic rays (CRs) up to the knee of the CR spectrum at E approximate to 3 x 10(15) eV. Our MilkyWay galaxy hosts more than 350 SNRs discovered at radio wavelengths and at high energies, of which 220 fall into the H.E.S.S. Galactic Plane Survey (HGPS) region. Of those, only 50 SNRs are coincident with a H.E.S.S source and in 8 cases the very high-energy (VHE) emission is firmly identified as an SNR. The H.E.S.S. GPS provides us with a legacy for SNR population study in VHE gamma-rays and we use this rich data set to extract VHE flux upper limits from all undetected SNRs. Overall, the derived flux upper limits are not in contradiction with the canonical CR paradigm. Assuming this paradigm holds true, we can constrain typical ambient density values around shell-type SNRs to n <= 7 cm(-3) and electron-to-proton energy fractions above 10 TeV to epsilon(ep) <= 5 x 10(-3). Furthermore, comparisons of VHE with radio luminosities in non-interacting SNRs reveal a behaviour that is in agreement with the theory of magnetic field amplification at shell-type SNRs.
Keywords: gamma rays: general; ISM: supernova remnants

Possible Evidence for Cosmic-Ray Acceleration in the Type Ia SNR RCW 86: Spatial Correlation between TeV Gamma-Rays and Interstellar Atomic Protons - Sano, H.; Rowell, G.; Reynoso, E. M.; Jung-Richardt, Ira; Yamane, Y.; Nagaya, T.; Yoshiike, S.; Hayashi, K.; Torii, K.; Maxted, N.; Mitsuishi, I.; Inoue, T.; et al. (Astrophysical Journal, 2019)
We present a detailed morphological study of TeV gamma-rays, synchrotron radiation, and interstellar gas in the young Type Ia supernova remnant (SNR) RCW 86. We find that the interstellar atomic gas shows good spatial correlation with the gamma-rays, indicating that the TeV gamma-rays from RCW 86 are likely predominantly of hadronic origin. In contrast, the spatial correlation between the interstellar molecular cloud and the TeV gamma-rays is poor in the southeastern shell of the SNR. We argue that this poor correlation can be attributed to the low-energy cosmic rays (similar to 1 TeV) not penetrating into the dense molecular cloud due to an enhancement of the turbulent magnetic field around the dense cloud of similar to 10-100 mu G. We also find that the southwestern shell, which is bright in both synchrotron X-ray and radio continuum radiation, shows a significant gamma-ray excess compared with the interstellar proton column density, suggesting that leptonic gamma-rays via inverse Compton scattering possibly contribute alongside the hadronic gamma-rays. The total cosmic-ray energies of the young TeV gamma-ray SNRs-RX J1713.7-3946, Vela Jr, HESS J1731-347, and RCW 86-are roughly similar, which indicates that cosmic rays can be accelerated in both the core-collapse and Type Ia supernovae. The total energy of cosmic rays derived using the gas density, similar to 10(48)-10(49) erg, gives a safe lower limit due mainly to the low filling factor of interstellar gas within the shell.
CRIS-Team WoS Importer:2019-05-21

Precision measurement of optical pulsation using a Cherenkov telescope - Funk, Stefan; et al. (Astroparticle Physics, 2006)
During 2003, a camera designed to measure the optical pulsations of pulsars was installed on a telescope of the H.E.S.S. array. The array is designed for gamma-ray astronomy in the similar to 100 GeV-100 TeV energy regime. The aims of this exercise were two-fold: to prove the pulsar timing capabilities of H.E.S.S. on all relevant time-scales, and to explore the possibility of performing sensitive optical pulsar measurements using the similar to 100m(2) mirror of a Cherenkov telescope. Measurements of the Crab pulsar with this instrument demonstrate an order of magnitude sensitivity improvement over previous attempts using Cherenkov telescopes. Here we describe the design and performance of the system and discuss design considerations for future instruments of this type. (c) 2006 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Preliminary results of the LAT calibration unit beam tests - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

Probing the ATIC peak in the cosmic-ray electron spectrum with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
The measurement of an excess in the cosmic-ray electron spectrum between 300 and 800 GeV by the ATIC experiment has - together with the PAMELA detection of a rise in the positron fraction up to ≈100 GeV - motivated many interpretations in terms of dark matter scenarios; alternative explanations assume a nearby electron source like a pulsar or supernova remnant. Here we present a measurement of the cosmic-ray electron spectrum with H.E.S.S. starting at 340 GeV. While the overall electron flux measured by H.E.S.S. is consistent with the ATIC data within statistical and systematic errors, the H.E.S.S. data exclude a pronounced peak in the electron spectrum as suggested for interpretation by ATIC. The H.E.S.S. data follow a power-law spectrum with spectral index of 3.0 ±0.1(stat.) ±0.3(syst.), which steepens at about 1 TeV. © ESO 2009.
Keywords: Cosmic rays; Methods: data analysis

Probing the Extragalactic Mid-infrared Background with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Rojas, D. Avila; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistran, T.; Carraminana, A.; Casanova, S.; et al. (Astrophysical Journal, 2022)
The extragalactic background light (EBL) contains all the radiation emitted by nuclear and accretion processes in stars and compact objects since the epoch of recombination. Measuring the EBL density directly is challenging, especially in the near-to-far-infrared wave band, mainly due to the zodiacal light foreground. Instead, gamma-ray astronomy offers the possibility to indirectly set limits on the EBL by studying the effects of gamma-ray absorption in the very high energy (VHE: >100 GeV) spectra of distant blazars. The High Altitude Water Cherenkov Gamma Ray Observatory (HAWC) is one of the few instruments sensitive to gamma rays with energies above 10 TeV. This offers the opportunity to probe the EBL in the near/mid-IR region: lambda = 1-100 mu m. In this study, we fit physically motivated emission models to Fermi-LAT gigaelectronvolt data to extrapolate the intrinsic teraelectronvolt spectra of blazars. We then simulate a large number of absorbed spectra for different randomly generated EBL model shapes and calculate Bayesian credible bands in the EBL intensity space by comparing and testing the agreement between the absorbed spectra and HAWC extragalactic observations of two blazars. The resulting bands are in agreement with current EBL lower and upper limits, showing a downward trend toward higher wavelength values lambda > 10 mu m also observed in previous measurements.
CRIS-Team WoS Importer:2022-07-29

Probing the gamma-ray emission from HESS J1834-087 using H.E.S.S. and Fermi LAT observations - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
Aims. Previous observations with the High Energy Stereoscopic System (H.E.S.S.) have revealed an extended very-high-energy (VHE; E > 100 GeV) γ-ray source, HESS J1834-087, coincident with the supernova remnant (SNR)W41. The origin of the γ-ray emission was investigated in more detail with the H.E.S.S. array and the Large Area Telescope (LAT) onboard the Fermi Gamma-ray Space Telescope. Methods. The γ-ray data provided by 61 h of observations with H.E.S.S., and four years with the Fermi LAT were analyzed, covering over five decades in energy from 1.8 GeV up to 30 TeV. The morphology and spectrum of the TeV and GeV sources were studied and multiwavelength data were used to investigate the origin of the γ-ray emission toward W41. Results. The TeV source can be modeled with a sum of two components: one point-like and one significantly extended (σ = 0.17° ± 0. 01°), both centered on SNR W41 and exhibiting spectra described by a power law with index Γ ≃ 2.6. The GeV source detected with Fermi LAT is extended (σ = 0.15° ± 0.03°) and morphologically matches the VHE emission. Its spectrum can be described by a power-law model with an index Γ = 2.15 ± 0.12 and smoothly joins the spectrum of the whole TeV source. A break appears in the γ-ray spectra around 100 GeV. No pulsations were found in the GeV range. Conclusions. Two main scenarios are proposed to explain the observed emission: a pulsar wind nebula (PWN) or the interaction of SNRW41 with an associated molecular cloud. X-ray observations suggest the presence of a point-like source (a pulsar candidate) near the center of the remnant and nonthermal X-ray di ffuse emission that could arise from the possibly associated PWN. The PWN scenario is supported by the compatible positions of the TeV and GeV sources with the putative pulsar. However, the spectral energy distribution from radio to γ-rays is reproduced by a one-zone leptonic model only if an excess of low-energy electrons is injected following a Maxwellian distribution by a pulsar with a high spin-down power (>10 ergs). This additional low-energy component is not needed if we consider that the point-like TeV source is unrelated to the extended GeV and TeV sources. The interacting SNR scenario is supported by the spatial coincidence between the γ-ray sources, the detection of OH (1720 MHz) maser lines, and the hadronic modeling.
Keywords: Acceleration of particles; Cosmic rays; Ism: Clouds; Ism: Supernova remnants

Probing the Pulsar Population of Terzan 5 via Spectral Modeling - Ndiyavala, H.; Venter, Christo; Johnson, T. J.; Harding, A. K.; Smith, D. A.; Eger, Peter; Kopp, A.; Van Der Walt, D. J. (Astrophysical Journal, 2019)
Terzan 5 is the only Galactic globular cluster that has plausibly been detected at very high energies by the High Energy Stereoscopic System. It has an unexpectedly asymmetric very high energy morphology that is offset from the cluster center, in addition to a large-scale, offset radio structure and compact diffuse X-ray emission associated with this cluster. We present new data from the Fermi Large Area Telescope on this source. We model the updated broadband spectral energy distribution, attributing this to cumulative pulsed emission from a population of embedded millisecond pulsars, as well as unpulsed emission from the interaction of their leptonic winds with the ambient magnetic and soft-photon fields. In particular, our model invokes unpulsed synchrotron and inverse Compton components to model the radio and TeV data and cumulative pulsed curvature radiation to fit the Fermi data, and it explains the hard Chandra X-ray spectrum via a "new" cumulative synchrotron component from electron-positron pairs within the pulsar magnetospheres that has not been implemented before. We find reasonable spectral fits for plausible model parameters. We also derive constraints on the millisecond pulsar luminosity function using the diffuse X-ray data and the Chandra sensitivity. Future higher-quality spectral and spatial data will help discriminate between competing scenarios (such as dark matter annihilation, white dwarf winds, or hadronic interactions) proposed for the broadband emission, as well as constraining degenerate model parameters.
CRIS-Team WoS Importer:2019-08-09

Probing the Sea of Cosmic Rays by Measuring Gamma-Ray Emission from Passive Giant Molecular Clouds with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal, 2021)
The study of high-energy gamma rays from passive giant molecular clouds (GMCs) in our Galaxy is an indirect way to characterize and probe the paradigm of the "sea" of cosmic rays in distant parts of the Galaxy. By using data from the High Altitude Water Cerenkov (HAWC) Observatory, we measure the gamma-ray flux above 1 TeV of a set of these clouds to test the paradigm. We selected high galactic latitude clouds that are in HAWC's field of view and that are within 1 kpc distance from the Sun. We find no significant excess emission in the cloud regions, nor when we perform a stacked log-likelihood analysis of GMCs. Using a Bayesian approach, we calculate 95% credible interval upper limits of the gamma-ray flux and estimate limits on the cosmic-ray energy density of these regions. These are the first limits to constrain gamma-ray emission in the multi-TeV energy range (>1 TeV) using passive high galactic latitude GMCs. Assuming that the main gamma-ray production mechanism is due to proton-proton interaction, the upper limits are consistent with a cosmic-ray flux and energy density similar to that measured at Earth.
CRIS-Team WoS Importer:2021-07-02

Prospects for Cherenkov Telescope Array Observations of the Young Supernova Remnant RX J1713.73946 - Acero, F.; Aloisio, R.; Amans, J.; Amato, E.; Antonelli, L. A.; Aramo, C.; Armstrong, T.; Arqueros, F.; Asano, K.; Ashley, M.; Backes, M.; Balazs, C.; et al. (Astrophysical Journal, 2017)
Keywords: cosmic rays; gamma rays: ISM; ISM: individual objects: RX J1713.7 dash3946; G347.3 dash0.5

Prospects for the use of photosensor timing information with machine learning techniques in background rejection - Spencer, Samuel; et al. (2019)

Prospects for the Use of Photosensor Timing Information with Machine Learning Techniques in Background Rejection. - Spencer, Samuel; et al. (2019)

Quantum gravity phenomenology at the dawn of the multi-messenger era—A review - Addazi, A.; Alvarez-Muniz, J.; Alves Batista, R.; Amelino-Camelia, G.; Antonelli, V.; Arzano, M.; Asorey, M.; Atteia, J. L.; Bahamonde, S.; Bajardi, F.; Ballesteros, A.; Baret, B.; et al. (Progress in Particle and Nuclear Physics, 2022)
The exploration of the universe has recently entered a new era thanks to the multi-messenger paradigm, characterized by a continuous increase in the quantity and quality of experimental data that is obtained by the detection of the various cosmic messengers (photons, neutrinos, cosmic rays and gravitational waves) from numerous origins. They give us information about their sources in the universe and the properties of the intergalactic medium. Moreover, multi-messenger astronomy opens up the possibility to search for phenomenological signatures of quantum gravity. On the one hand, the most energetic events allow us to test our physical theories at energy regimes which are not directly accessible in accelerators; on the other hand, tiny effects in the propagation of very high energy particles could be amplified by cosmological distances. After decades of merely theoretical investigations, the possibility of obtaining phenomenological indications of Planck-scale effects is a revolutionary step in the quest for a quantum theory of gravity, but it requires cooperation between different communities of physicists (both theoretical and experimental). This review, prepared within the COST Action CA18108 “Quantum gravity phenomenology in the multi-messenger approach”, is aimed at promoting this cooperation by giving a state-of-the art account of the interdisciplinary expertise that is needed in the effective search of quantum gravity footprints in the production, propagation and detection of cosmic messengers.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Cosmic neutrinos; Gamma-ray astronomy; Gravitational waves; Lorentz invariance violation and deformation; Ultra-high-energy cosmic rays

Radiation measurements and simulations at the PHELIX laser facility, GSI - Behrens, R.; Hufschmidt, Patrick; Roth, J.; Akstaller, Bernhard; Hupe, O.; Haag, D.; Schmidt, Sebastian; Schreiner, Stephan; Michel, Thilo (Journal of Instrumentation, 2022)
The absolute spectral electron and photon emission from a Tungsten target irradiated by the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility was measured inside the PHELIX target chamber. For this, a thermo-lumi-nescence detector (TLD)-based few-channel spectrometer (FCS) was used in combination with a Bayesian data analysis. The results of the FCS measurement served as input for a Monte-Carlo particle transport simulation to determine the spectra and dose out of the PHELIX target chamber. Two different simulation methods proved to be consistent and, therefore, reliable. The simulation results were compared to the dose measured with a dosemeter that consists of three Dosepix detectors in combination with a neural network analysis. The two dose results show a satisfactory agreement.
CRIS-Team WoS Importer:2022-06-10

Radio and X-ray Observations of the Possible New Gamma-ray binary HESS J0632+057 - Skilton, J. L.; Hinton, J. A.; Brucker, Julia; Pandey-Pommier, M.; Cheung, C. C.; Aharonian, F. A.; Dubus, G.; Fiasson, A.; Funk, Stefan; Gallant, Y.; Marcowith, A.; Reimer, Olaf (HIGH ENERGY PHENOMENA IN MASSIVE STARS, 2010)
CRIS-Team WoS Importer:2020-01-15

Radio imaging of the very-high-energy γ-ray emission region in the central engine of a radio galaxy - van Eldik, Christopher; Acciari, V. A.; Aliu, E.; Arlen, T.; Bautista, M.; Beilicke, M.; Benbow, W.; Bradbury, S. M.; Buckley, J. H.; Bugaev, V.; Butt, Y.; Byrum, K.; et al. (Science, 2009)
The accretion of matter onto a massive black hole is believed to feed the relativistic plasma jets found in many active galactic nuclei (AGN). Although some AGN accelerate particles to energies exceeding 10 electron volts and are bright sources of very-high-energy (VHE) y-ray emission, it is not yet known where the VHE emission originates. Here we report on radio and VHE observations of the radio galaxy Messier 87, revealing a period of extremely strong VHE y-ray flares accompanied by a strong increase of the radio flux from its nucleus. These results imply that charged particles are accelerated to very high energies in the immediate vicinity of the black hole.

Readout electronics testing during mass production of FlashCam cameras for the Cherenkov Telescope Array - Diebold, S.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Capasso, M.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; et al. (OPTICS FOR EUV, X-RAY, AND GAMMA-RAY ASTRONOMY VIII, 2017)
CRIS-Team WoS Importer:2020-01-15

Reconstruction of stereoscopic CTA events using deep learning with CTLearn - Spencer, Samuel; et al. (2022)

Relevance of jet magnetic field structure for blazar axionlike particle searches - Davies, James; Meyer, Manuel; Cotter, Garret (Physical Review D, 2021)
Many theories beyond the Standard Model of particle physics predict the existence of axionlike particles (ALPs) that mix with photons in the presence of a magnetic field. One prominent indirect method of searching for ALPs is to look for irregularities in blazar gamma-ray spectra caused by ALP-photon mixing in astrophysical magnetic fields. This requires the modeling of magnetic fields between Earth and the blazar. So far, only very simple models for the magnetic field in the blazar jet have been used. Here, we investigate the effects of more complicated jet magnetic field configurations on these spectral irregularities by imposing a magnetic field structure model onto the jet model proposed by Potter & Cotter. We simulate gamma-ray spectra of Mrk 501 with ALPs and fit them to ALP-less spectra, scanning the ALP and B-field configuration parameter space, and show that the jet can be an important mixing region, able to probe new ALP parameter space around ma 1-1000 neV and ga 5×10-12 GeV-1. However, reasonable (i.e., consistent with observation) changes of the magnetic field structure can have a large effect on the mixing. For jets in highly magnetized clusters, mixing in the cluster can overpower mixing in the jet. This means that the current constraints using mixing in the Perseus cluster are still valid.
CRIS-Team Scopus Importer:2021-01-22

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Resolving the extragalactic γ-ray background above 50 GeV with the fermi large area telescope - Reposeur, T.; Di Mauro, M.; Zimmer, S.; Negro, M.; La Mura, G.; Sanchez-Conde, M.; Britto, R. J.; Cavazzuti, E.; Bonino, R.; Iafrate, G.; Moskalenko, I. V.; Orlando, E.; et al. (Physical Review Letters, 2016)
The Fermi Large Area Telescope (LAT) Collaboration has recently released a catalog of 360 sources detected above 50 GeV (2FHL). This catalog was obtained using 80 months of data re-processed with Pass 8, the newest event-level analysis, which significantly improves the acceptance and angular resolution of the instrument. Most of the 2FHL sources at high Galactic latitude are blazars. Using detailed Monte Carlo simulations, we measure, for the first time, the source count distribution, dN= dS, of extragalactic.-ray sources at E > 50 GeV and find that it is compatible with a Euclidean distribution down to the lowest measured source flux in the 2FHL (8 x 10(-12) ph cm(-2) s(-1)). We employ a one-point photon fluctuation analysis to constrain the behavior of dN= dS below the source detection threshold. Overall, the source count distribution is constrained over three decades in flux and found compatible with a broken power law with a break flux, Sb, in the range [8 x 10-12; 1.5 x 10-11] ph cm(-2) s(-1) and power-law indices below and above the break of a 2. [1.60; 1.75] and a 1 +/- 2.49 +/- 0.12, respectively. Integration of dN= dS shows that point sources account for at least 86_16 -14 % of the total extragalactic gamma-ray background. The simple form of the derived source count distribution is consistent with a single population (i. e., blazars) dominating the source counts to the minimum flux explored by this analysis. We estimate the density of sources detectable in blind surveys that will be performed in the coming years by the Cherenkov Telescope Array.

Results from the HESS Galactic plane survey - Funk, Stefan (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

REVEALING W51C AS A COSMIC RAY SOURCE USING FERMI-LAT DATA - Jogler, T.; Funk, Stefan (Astrophysical Journal, 2016)
Supernova remnants (SNRs) are commonly believed to be the primary sources of Galactic cosmic rays. Despite intensive study of the non-thermal emission of many SNRs the identification of the accelerated particle type relies heavily on assumptions of ambient-medium parameters that are only loosely constrained. Compelling evidence of hadronic acceleration can be provided by detecting a strong roll-off in the secondary γ-ray spectrum below the production threshold energy of about 135 MeV, the so called "pion bump." Here we use five years of Fermi-Large Area Telescope data to study the spectrum above 60 MeV of the middle-aged SNR W51C. A clear break in the power-law γ-ray spectrum at is detected with significance and we show that this break is most likely associated with the energy production threshold of mesons. A high-energy break in the γ-ray spectrum at about 2.7 GeV is found with significance. The spectral index at energies beyond this second break is and closely matches the spectral index derived by the MAGIC Collaboration above 75 GeV. Therefore our analysis provides strong evidence to explain the γ-ray spectrum of W51C by a single particle population of protons with a momentum spectrum best described by a broken power law with break momentum W51C is the third middle-aged SNR that displays compelling evidence for cosmic-ray acceleration and thus strengthens the case of SNRs as the main source of Galactic cosmic rays.
Keywords: astroparticle physics; gamma-rays: general; ISM: supernova remnants

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

Revisiting the Westerlund 2 field with the HESS telescope array - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. Previous observations with the HESS telescope array revealed the existence of extended very-high-energy (VHE; E > 100 GeV) γ-ray emission, HESS J1023-575, coincident with the young stellar cluster Westerlund 2. At the time of discovery, the origin of the observed emission was not unambiguously identified, and follow-up observations have been performed to further investigate the nature of this γ-ray source. Methods. The Carina region towards the open cluster Westerlund 2 has been re-observed, increasing the total exposure to 45.9 h. The combined dataset includes 33 h of new data and now permits a search for energy-dependent morphology and detailed spectroscopy. Results. A new, hard spectrum VHE γ-ray source, HESS J1026-582, was discovered with a statistical significance of 7σ. It is positionally coincident with the Fermi LAT pulsar PSR J1028-5819. The positional coincidence and radio/γ-ray characteristics of the LAT pulsar favors a scenario where the TeV emission originates from a pulsar wind nebula. The nature of HESS J1023-575 is discussed in light of the deep HESS observations and recent multi-wavelength discoveries, including the Fermi LAT pulsar PSR J1022-5746 and giant molecular clouds in the region. Despite the improved VHE dataset, a clear identification of the object responsible for the VHE emission from HESS J1023-575 is not yet possible, and contribution from the nearby high-energy pulsar and/or the open cluster remains a possibility. © 2010 ESO.
Keywords: gamma rays: stars; HII regions

Science Case for a Wide Field-of-View Very-High-Energy Gamma-Ray Observatory in the Southern Hemisphere - Spencer, Samuel; et al. (2019)

Science with e-ASTROGAM A space mission for MeV-GeV gamma-ray astrophysics - Funk, Stefan; et al. (Journal of High Energy Astrophysics, 2018)
e-ASTROGAM ('enhanced ASTROGAM') is a breakthrough Observatory space mission, with a detector composed by a Silicon tracker, a calorimeter, and an anticoincidence system, dedicated to the study of the non-thermal Universe in the photon energy range from 0.3 MeV to 3 GeV - the lower energy limit can be pushed to energies as low as 150 keV for the tracker, and to 30 keV for calorimetric detection. The mission is based on an advanced space-proven detector technology, with unprecedented sensitivity, angular and energy resolution, combined with polarimetric capability. Thanks to its performance in the MeV-GeV domain, substantially improving its predecessors, e-ASTROGAM will open a new window on the non-thermal Universe, making pioneering observations of the most powerful Galactic and extragalactic sources, elucidating the nature of their relativistic outflows and their effects on the surroundings. With a line sensitivity in the MeV energy range one to two orders of magnitude better than previous generation instruments, e-ASTROGAM will determine the origin of key isotopes fundamental for the understanding of supernova explosion and the chemical evolution of our Galaxy. The mission will provide unique data of significant interest to a broad astronomical community, complementary to powerful observatories such as LIGO-Virgo-GEO600-KAGRA, SKA, ALMA, E-ELT, TMT, LSST, JWST, Athena, CTA, IceCube, KM3NeT, and LISA. (C) 2018 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Searches for gamma-ray lines and 'pure WIMP' spectra from Dark Matter annihilations in dwarf galaxies with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about less than or similar to 3 x 10(-25) cm(3) s(-1) are obtained in the mass range of 400 GeV to 1TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.
CRIS-Team WoS Importer:2020-01-15

Search for a dark matter annihilation signal from the galactic center halo with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Physical Review Letters, 2011)
A search for a very-high-energy (VHE; 100GeV) γ-ray signal from self-annihilating particle dark matter (DM) is performed towards a region of projected distance r∼45-150pc from the Galactic center. The background-subtracted γ-ray spectrum measured with the High Energy Stereoscopic System (H.E.S.S.) γ-ray instrument in the energy range between 300-GeV and 30-TeV shows no hint of a residual γ-ray flux. Assuming conventional Navarro-Frenk-White and Einasto density profiles, limits are derived on the velocity-weighted annihilation cross section σv as a function of the DM particle mass. These are among the best reported so far for this energy range and in particular differ only little between the chosen density profile parametrizations. In particular, for the DM particle mass of ∼1TeV, values for σ above 3×1025cm3s1 are excluded for the Einasto density profile. © 2011 American Physical Society.

Search for Axionlike-Particle-Induced Prompt gamma-Ray Emission from Extragalactic Core-Collapse Supernovae with the Fermi Large Area Telescope - Meyer, Manuel; Petrushevska, Tanja (Physical Review Letters, 2020)
During a core-collapse supernova (SN), axionlike particles (ALPs) could be produced through the Primakoff process and subsequently convert into gamma rays in the magnetic field of the Milky Way. We do not find evidence for such a gamma-ray burst in observations of extragalactic SNe with the Fermi Large Area Telescope (LAT). The SN explosion times are estimated from optical light curves and we find a probability of about similar to 90% that the LAT observed at least one SN at the time of the core collapse. Under the assumption that at least one SN was contained within the LAT field of view, we exclude photon-ALP couplings greater than or similar to 2.6 x 10(-12) GeV-1 for ALP masses m(a) less than or similar to 3 x 10(-10) eV, improving previous limits from SN1987A by a factor of 2.
CRIS-Team WoS Importer:2020-06-26

Search for Cosmic-Ray Electron and Positron Anisotropies with Seven Years of Fermi Large Area Telescope Data - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Physical Review Letters, 2017)
The Large Area Telescope on board the Fermi Gamma-ray Space Telescope has collected the largest ever sample of high-energy cosmic-ray electron and positron events since the beginning of its operation. Potential anisotropies in the arrival directions of cosmic-ray electrons or positrons could be a signature of the presence of nearby sources. We use almost seven years of data with energies above 42 GeV processed with the Pass 8 reconstruction. The present data sample can probe dipole anisotropies down to a level of 10(-3). We take into account systematic effects that could mimic true anisotropies at this level. We present a detailed study of the event selection optimization of the cosmic-ray electrons and positrons to be used for anisotropy searches. Since no significant anisotropies have been detected on any angular scale, we present upper limits on the dipole anisotropy. The present constraints are among the strongest to date probing the presence of nearby young and middle-aged sources.
CRIS-Team WoS Importer:2020-01-15

SEARCH FOR COSMIC-RAY-INDUCED GAMMA-RAY EMISSION IN GALAXY CLUSTERS - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bloom, E. D.; et al. (Astrophysical Journal, 2014)
Current theories predict relativistic hadronic particle populations in clusters of galaxies in addition to the already observed relativistic leptons. In these scenarios hadronic interactions give rise to neutral pions which decay into gamma rays that are potentially observable with the Large Area Telescope (LAT) on board the Fermi space telescope. We present a joint likelihood analysis searching for spatially extended gamma-ray emission at the locations of 50 galaxy clusters in four years of Fermi-LAT data under the assumption of the universal cosmic-ray (CR) model proposed by Pinzke & Pfrommer. We find an excess at a significance of 2.7 sigma, which upon closer inspection, however, is correlated to individual excess emission toward three galaxy clusters: A400, A1367, and A3112. We discuss these cases in detail and conservatively attribute the emission to unmodeled background systems (for example, radio galaxies within the clusters). Through the combined analysis of 50 clusters, we exclude hadronic injection efficiencies in simple hadronic models above 21% and establish limits on the CR to thermal pressure ratio within the virial radius, R-200, to be below 1.25%-1.4% depending on the morphological classification. In addition, we derive new limits on the gamma-ray flux from individual clusters in our sample.
Keywords: galaxies: clusters: intracluster medium; gamma rays: galaxies: clusters

Search for dark matter annihilation in the Wolf-Lundmark-Melotte dwarf irregular galaxy with H.E.S.S. - Abdallah, H.; Spencer, Samuel; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Physical Review D, 2021)
We search for an indirect signal of dark matter through very high-energy γ rays from the Wolf-Lundmark-Melotte (WLM) dwarf irregular galaxy. The pair annihilation of dark matter particles would produce Standard Model particles in the final state such as γ rays, which might be detected by ground-based Cherenkov telescopes. Dwarf irregular galaxies represent promising targets as they are dark matter dominated objects with well-measured kinematics and small uncertainties on their dark matter distribution profiles. In 2018, the five-telescopes of the high energy stereoscopic system observed the dwarf irregular galaxy WLM for 18 hours. We present the first analysis based on data obtained from an imaging atmospheric Cherenkov telescope for this subclass of dwarf galaxy. As we do not observe any significant excess in the direction of WLM, we interpret the result in terms of constraints on the velocity-weighted cross section for dark matter pair annihilation «σv» as a function of the dark matter particle mass for various continuum channels, as well as the prompt γγ emission. For the τ+τ- channel, the limits reach a «σv» value of about 4×10-22 cm3 s-1 for a dark matter particle mass of 1 TeV. For the prompt γγ channel, the upper limit reaches a «σv» value of about 5×10-24 cm3 s-1 for a mass of 370 GeV. These limits represent an improvement of up to a factor 200, with respect to previous results for the dwarf irregular galaxies for TeV dark matter search.
CRIS-Team Scopus Importer:2021-06-04

Search for dark matter annihilation signals from the Fornax galaxy cluster with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astrophysical Journal, 2012)
The Fornax galaxy cluster was observed with the High Energy Stereoscopic System for a total live time of 14.5hr, searching for very high energy (VHE; E > 100GeV) γ-rays from dark matter (DM) annihilation. No significant signal was found in searches for point-like and extended emissions. Using several models of the DM density distribution, upper limits on the DM velocity-weighted annihilation cross-section 〈σv〉 as a function of the DM particle mass are derived. Constraints are derived for different DM particle models, such as those arising from Kaluza-Klein and supersymmetric models. Various annihilation final states are considered. Possible enhancements of the DM annihilation γ-ray flux, due to DM substructures of the DM host halo, or from the Sommerfeld effect, are studied. Additional γ-ray contributions from internal bremsstrahlung and inverse Compton radiation are also discussed. For a DM particle mass of 1TeV, the exclusion limits at 95% of confidence level reach values of 〈σv〉 10 cm s, depending on the DM particle model and halo properties. Additional contribution from DM substructures can improve the upper limits on 〈σv〉 by more than two orders of magnitude. At masses around 4.5TeV, the enhancement by substructures and the Sommerfeld resonance effect results in a velocity-weighted annihilation cross-section upper limit at the level of 〈σv〉 10 cm s. © 2012. The American Astronomical Society. All rights reserved.

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for dark matter annihilation signatures in H.E.S.S. observations of dwarf spheroidal galaxies - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Dwarf spheroidal galaxies of the Local Group are close satellites of the Milky Way characterized by a large mass-to-light ratio and are not expected to be the site of nonthermal high-energy gamma-ray emission or intense star formation. Therefore they are among the most promising candidates for indirect dark matter searches. During the last years the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes observed five of these dwarf galaxies for more than 140 hours in total, searching for TeV gamma-ray emission from annihilation of dark matter particles. The new results of the deep exposure of the Sagittarius dwarf spheroidal galaxy, the first observations of the Coma Berenices and Fornax dwarves and the reanalysis of two more dwarf spheroidal galaxies already published by the H.E.S.S. Collaboration, Carina and Sculptor, are presented. In the absence of a significant signal new constraints on the annihilation cross section applicable to weakly interacting massive particles (WIMPs) are derived by combining the observations of the five dwarf galaxies. The combined exclusion limit depends on the WIMP mass and the best constraint is reached at 1-2 TeV masses with a cross-section upper bound of ∼3.9×10-24cm3s-1 at a 95% confidence level.

Search for Dark Matter Annihilations towards the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2016)
The inner region of the Milky Way halo harbors a large amount of dark matter (DM). Given its proximity, it is one of the most promising targets to look for DM. We report on a search for the annihilations of DM particles using gamma-ray observations towards the inner 300 pc of the Milky Way, with the H.E.S.S. array of ground-based Cherenkov telescopes. The analysis is based on a 2D maximum likelihood method using Galactic Center (GC) data accumulated by H.E.S.S. over the last 10 years (2004-2014), and does not show any significant gamma-ray signal above background. Assuming Einasto and Navarro-Frenk-White DM density profiles at the GC, we derive upper limits on the annihilation cross section <sigma nu="">. These constraints are the strongest obtained so far in the TeV DM mass range and improve upon previous limits by a factor 5. For the Einasto profile, the constraints reach <sigma nu=""> values of 6 x 10(-26) cm(3) s(-1) in the W+W- channel for a DM particle mass of 1.5 TeV, and 2 x 10(-26) cm(3) s(-1) in the tau(+)tau(-) channel for a 1 TeV mass. For the first time, ground-based gamma-ray observations have reached sufficient sensitivity to probe <sigma nu=""> values expected from the thermal relic density for TeV DM particles.</sigma></sigma></sigma>

SEARCH FOR EARLY GAMMA-RAY PRODUCTION IN SUPERNOVAE LOCATED IN A DENSE CIRCUMSTELLAR MEDIUM WITH THE FERMI LAT - Ackermann, M.; Arcavi, I.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Astrophysical Journal, 2015)
Supernovae (SNe) exploding in a dense circumstellar medium (CSM) are hypothesized to accelerate cosmic rays in collisionless shocks and emit GeV gamma-rays and TeV neutrinos on a timescale of several months. We perform the first systematic search for gamma-ray emission in Fermi Large Area Telescope data in the energy range from 100 MeV to 300 GeV from the ensemble of 147 SNe Type IIn exploding in a dense CSM. We search for a gamma-ray excess at each SNe location in a one-year time window. In order to enhance a possible weak signal, we simultaneously study the closest and optically brightest sources of our sample in a joint-likelihood analysis in three different time windows (1 year, 6 months, and 3 months). For the most promising source of the sample, SN 2010jl (PTF 10aaxf), we repeat the analysis with an extended time window lasting 4.5 years. We do not find a significant excess in gamma-rays for any individual source nor for the combined sources and provide model-independent flux upper limits for both cases. In addition, we derive limits on the gamma-ray luminosity and the ratio of gamma-ray-to-optical luminosity ratio as a function of the index of the proton injection spectrum assuming a generic gamma-ray production model. Furthermore, we present detailed flux predictions based on multi-wavelength observations and the corresponding flux upper limit at a 95% confidence level (CL) for the source SN 2010jl (PTF 10aaxf).
Keywords: cosmic rays; gamma rays: general; methods: data analysis; supernovae: general

SEARCH FOR EXTENDED GAMMA-RAY EMISSION FROM THE VIRGO GALAXY CLUSTER WITH FERMI-LAT - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2015)
Galaxy clusters are one of the prime sites to search for dark matter (DM) annihilation signals. Depending on the substructure of the DM halo of a galaxy cluster and the cross sections for DM annihilation channels, these signals might be detectable by the latest generation of gamma-ray telescopes. Here we use three years of Fermi-Large Area Telescope data, which are the most suitable for searching for very extended emission in the vicinity of the nearby Virgo galaxy cluster. Our analysis reveals statistically significant extended emission which can be well characterized by a uniformly emitting disk profile with a radius of 3 degrees that moreover is offset from the cluster center. We demonstrate that the significance of this extended emission strongly depends on the adopted interstellar emission model (IEM) and is most likely an artifact of our incomplete description of the IEM in this region. We also search for and find new point source candidates in the region. We then derive conservative upper limits on the velocity-averaged DM pair annihilation cross section from Virgo. We take into account the potential gamma-ray flux enhancement due to DM sub-halos and its complex morphology as a merging cluster. For DM annihilating into b (b) over bar, assuming a conservative sub-halo model setup, we find limits that are between 1 and 1.5 orders of magnitude above the expectation from the thermal cross section for m(DM) <= 100 GeV. In a more optimistic scenario, we exclude similar to 3 x 10(-26)cm(3)s(-1) for m(DM)less than or similar to 40 GeV for the same channel. Finally, we derive upper limits on the gamma-ray-flux produced by hadronic cosmic-ray interactions in the inter cluster medium. We find that the volume-averaged cosmic-ray-to-thermal pressure ratio is less than similar to 6%.
CRIS-Team WoS Importer:2020-01-15

Search for Extended Sources in the Galactic Plane Using Six Years of Fermi-Large Area Telescope Pass 8 Data above 10GeV - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Astrophysical Journal, 2017)
The spatial extension of gamma-ray source is an essential ingredient to determine its spectral properties, as well as its potential multiwavelength counterpart. The capability to spatially resolve gamma-ray sources is greatly improved by the newly delivered Fermi-Large Area Telescope (LAT) Pass 8 event-level analysis, which provides a greater acceptance and an improved point-spread function, two crucial factors for the detection of extended sources. Here, we present a complete search for extended sources located within 7 degrees from the Galactic plane, using 6 yr of Fermi-LAT data above 10 GeV. We find 46 extended sources and provide their morphological and spectral characteristics. This constitutes the first catalog of hard Fermi-LAT extended sources, named the Fermi Galactic Extended Source Catalog, which allows a thorough study of the properties of the Galactic plane in the sub-TeV domain.
CRIS-Team WoS Importer:2020-01-15

Search for extended γ-ray emission around AGN with H.E.S.S. and Fermi -LAT - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2014)
Context. Very-high-energy (VHE; E > 100 GeV) γ-ray emission from blazars inevitably gives rise to electron-positron pair production through the interaction of these γ-rays with the extragalactic background light (EBL). Depending on the magnetic fields in the proximity of the source, the cascade initiated from pair production can result in either an isotropic halo around an initially beamed source or a magnetically broadened cascade flux. Aims. Both extended pair-halo (PH) and magnetically broadened cascade (MBC) emission from regions surrounding the blazars 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 were searched for using VHE γ-ray data taken with the High Energy Stereoscopic System (H.E.S.S.) and high-energy (HE; 100 MeV < E < 100 GeV) γ-ray data with the Fermi Large Area Telescope (LAT). Methods. By comparing the angular distributions of the reconstructed γ-ray events to the angular profiles calculated from detailed theoretical models, the presence of PH and MBC was investigated. Results. Upper limits on the extended emission around 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 are found to be at a level of a few per cent of the Crab nebula flux above 1 TeV, depending on the assumed photon index of the cascade emission. Assuming strong extra-Galactic magnetic field (EGMF) values, >10 G, this limits the production of pair haloes developing from electromagnetic cascades. For weaker magnetic fields, in which electromagnetic cascades would result in MBCs, EGMF strengths in the range (0.3-3) × 10 G were excluded for PKS 2155-304 at the 99% confidence level, under the assumption of a 1 Mpc coherence length. © ESO, 2014.
Keywords: BL Lacertae objects: individual: 1ES 0229+200; BL Lacertae objects: individual: 1ES 1101-232; BL Lacertae objects: individual: PKS 2155-304; Galaxies: magnetic fields; Gamma rays: galaxies; Intergalactic medium

SEARCH FOR GAMMA-RAY EMISSION FROM DES DWARF SPHEROIDAL GALAXY CANDIDATES WITH FERMI-LAT DATA - Drlica-Wagner, A.; Albert, A.; Bechtol, K.; Wood, M.; Strigari, L.; Sanchez-Conde, M.; Baldini, L.; Essig, R.; Cohen-Tanugi, J.; Anderson, B.; Bellazzini, R.; Bloom, E. D.; et al. (Astrophysical Journal Letters, 2015)
Due to their proximity, high dark-matter (DM) content, and apparent absence of non-thermal processes, Milky Way dwarf spheroidal satellite galaxies (dSphs) are excellent targets for the indirect detection of DM. Recently, eight new dSph candidates were discovered using the first year of data from the Dark Energy Survey (DES). We searched for gamma-ray emission coincident with the positions of these new objects in six years of Fermi Large Area Telescope data. We found no significant excesses of gamma-ray emission. Under the assumption that the DES candidates are dSphs with DM halo properties similar to the known dSphs, we computed individual and combined limits on the velocity-averaged DM annihilation cross section for these new targets. If the estimated DM content of these dSph candidates is confirmed, they will constrain the annihilation cross section to lie below the thermal relic cross section for DM particles with masses less than or similar to 20 GeV annihilating via the b (b) over bar or pi(+)pi(-) channels.
Keywords: dark matter; galaxies: dwarf; gamma rays: galaxies; Local Group

Search for Gamma-Ray Emission from Local Primordial Black Holes with the Fermi Large Area Telescope - Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2018)
Black holes with masses below approximately 10(15) g are expected to emit gamma-rays with energies above a few tens of MeV, which can be detected by the Fermi Large Area Telescope (LAT). Although black holes with these masses cannot be formed as a result of stellar evolution, they may have formed in the early universe and are therefore called primordial black holes (PBHs). Previous searches for PBHs have focused on either short-timescale bursts or the contribution of PBHs to the isotropic gamma-ray emission. We show that, in cases of individual PBHs, the Fermi-LAT is most sensitive to PBHs with temperatures above approximately 16 GeV and masses 6 x 10(11) g, which it can detect out to a distance of about 0.03 pc. These PBHs have a remaining lifetime of months to years at the start of the Fermi mission. They would appear as potentially moving point sources with gamma-ray emission that become spectrally harder and brighter with time until the PBH completely evaporates. In this paper, we develop a new algorithm to detect the proper motion of gamma-ray point sources, and apply it to 318 unassociated point sources at a high galactic latitude in the third Fermi-LAT source catalog. None of the unassociated point sources with spectra consistent with PBH evaporation show significant proper motion. Using the nondetection of PBH candidates, we derive a 99% confidence limit on the PBH evaporation rate in the vicinity of Earth, <(rho)over dot>(PBH) < 7.2 x 10(3) pc(-3) yr(-1). This limit is similar to the limits obtained with ground-based gamma-ray observatories.
Keywords: astroparticle physics; black hole physics; methods: data analysis

Search for Gamma-Ray Emission from Local Primordial Black Holes with the Fermi Large Area Telescope - Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2018)
Black holes with masses below approximately 10(15) g are expected to emit gamma-rays with energies above a few tens of MeV, which can be detected by the Fermi Large Area Telescope (LAT). Although black holes with these masses cannot be formed as a result of stellar evolution, they may have formed in the early universe and are therefore called primordial black holes (PBHs). Previous searches for PBHs have focused on either short-timescale bursts or the contribution of PBHs to the isotropic gamma-ray emission. We show that, in cases of individual PBHs, the Fermi-LAT is most sensitive to PBHs with temperatures above approximately 16 GeV and masses 6 x 10(11) g, which it can detect out to a distance of about 0.03 pc. These PBHs have a remaining lifetime of months to years at the start of the Fermi mission. They would appear as potentially moving point sources with gamma-ray emission that become spectrally harder and brighter with time until the PBH completely evaporates. In this paper, we develop a new algorithm to detect the proper motion of gamma-ray point sources, and apply it to 318 unassociated point sources at a high galactic latitude in the third Fermi-LAT source catalog. None of the unassociated point sources with spectra consistent with PBH evaporation show significant proper motion. Using the nondetection of PBH candidates, we derive a 99% confidence limit on the PBH evaporation rate in the vicinity of Earth, <(rho)over dot>(PBH) < 7.2 x 10(3) pc(-3) yr(-1). This limit is similar to the limits obtained with ground-based gamma-ray observatories.
Keywords: astroparticle physics; black hole physics; methods: data analysis

SEARCH for GAMMA-RAY EMISSION from the COMA CLUSTER with SIX YEARS of FERMI-LAT DATA - Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; et al. (Astrophysical Journal, 2016)
We present results from γ-ray observations of the Coma cluster incorporating six years of Fermi-LAT data and the newly released "Pass 8" event-level analysis. Our analysis of the region reveals low-significance residual structures within the virial radius of the cluster that are too faint for a detailed investigation with the current data. Using a likelihood approach that is free of assumptions on the spectral shape we derive upper limits on the γ-ray flux that is expected from energetic particle interactions in the cluster. We also consider a benchmark spatial and spectral template motivated by models in which the observed radio halo is mostly emission by secondary electrons. In this case, the median expected and observed upper limits for the flux above 100 are 1.7 times;10 ph cm s and 5.2 times;10 ph cm s respectively (the latter corresponds to residual emission at the level of 1.8σ). These bounds are comparable to or higher than predicted levels of hadronic gamma-ray emission in cosmic-ray (CR) models with or without reacceleration of secondary electrons, although direct comparisons are sensitive to assumptions regarding the origin and propagation mode of CRs and magnetic field properties. The minimal expected γ-ray flux from radio and star-forming galaxies within the Coma cluster is roughly an order of magnitude below the median sensitivity of our analysis.
Keywords: galaxies: clusters: individual (Coma); gamma rays: galaxies: cluster

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Search for gamma rays from dark matter annihilations around intermediate mass black holes with the HESS experiment - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Bertone, G.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2008)
The HESS array of Cherenkov telescopes has performed, from 2004 to 2007, a survey of the inner galactic plane at photon energies above 100 GeV. About 400 hours of data have been accumulated in the region between -30 and +60degrees in galactic longitude, and between -3 and +3degrees in galactic latitude. Assuming that dark matter is composed of weakly interacting massive particles, we calculate here the HESS sensitivity map for dark matter annihilations, and derive the first experimental constraints on the ("minispikes") scenario, in which a gamma-ray signal arises from dark matter annihilation around intermediate mass black holes. The data exclude the proposed scenario at a 90% confidence level for dark matter particles with velocity-weighted annihilation cross section σv above 10-28cm3s-1 and mass between 800 GeV and 10 TeV. © 2008 The American Physical Society.

Search for gamma-ray spectral lines from dark matter annihilation in dwarf galaxies with the High-Altitude Water Cherenkov observatory - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Solares, H. A. Ayala; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; Capistran, T.; et al. (Physical Review D, 2020)
Local dwarf spheroidal galaxies (dSphs) are nearby dark-matter dominated systems, making them excellent targets for searching for gamma rays from particle dark matter interactions. If dark matter annihilates or decays directly into two gamma rays (or a gamma ray and a neutral particle), a monochromatic spectral line is created. At TeV energies, no other process is predicted to produce spectral lines, making this a very clean indirect dark matter search channel. With the development of event-by event energy reconstruction, we can now search for spectral lines with the High Altitude Water Cherenkov (HAWC) Observatory. HAWC is a wide field of view survey instrument located in central Mexico that observes gamma rays from similar to 200 GeV to similar to 200 TeV. In this work we present results from a recent search for spectral lines from local, dark matter dominated, dwarf galaxies using 1038 days of HAWC data. We also present updated limits on several continuum channels that were reported in a previous publication. Our gamma-ray spectral line limits are the most constraining obtained so far from 20 TeV to 100 TeV.
CRIS-Team WoS Importer:2020-05-15

Search for gamma-ray spectral lines with the Fermi Large Area Telescope and dark matter implications - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonamente, E.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2013)
Weakly interacting massive particles (WIMPs) are a theoretical class of particles that are excellent dark matter candidates. WIMP annihilation or decay may produce essentially monochromatic gamma rays detectable by the Fermi Large Area Telescope (LAT) against the astrophysical gamma-ray emission of the Galaxy. We have searched for spectral lines in the energy range 5-300 GeV using 3.7 years of data, reprocessed with updated instrument calibrations and an improved energy dispersion model compared to the previous Fermi-LAT Collaboration line searches. We searched in five regions selected to optimize sensitivity to different theoretically motivated dark matter density distributions. We did not find any globally significant lines in our a priori search regions and present 95% confidence limits for annihilation cross sections of self-conjugate WIMPs and decay lifetimes. Our most significant fit occurred at 133 GeV in our smallest search region and had a local significance of 3.3 standard deviations, which translates to a global significance of 1.5 standard deviations. We discuss potential systematic effects in this search, and examine the feature at 133 GeV in detail. We find that the use both of reprocessed data and of additional

Search for New Cosmic-Ray Acceleration Sites within the 4FGL Catalog Galactic Plane Sources - Abdollahi, S.; Acero, F.; Ackermann, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berenji, B.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; et al. (Astrophysical Journal, 2022)
Cosmic rays are mostly composed of protons accelerated to relativistic speeds. When those protons encounter interstellar material, they produce neutral pions, which in turn decay into gamma-rays. This offers a compelling way to identify the acceleration sites of protons. A characteristic hadronic spectrum, with a low-energy break around 200 MeV, was detected in the gamma-ray spectra of four supernova remnants (SNRs), IC 443, W44, W49B, and W51C, with the Fermi Large Area Telescope. This detection provided direct evidence that cosmic-ray protons are (re-)accelerated in SNRs. Here, we present a comprehensive search for low-energy spectral breaks among 311 4FGL catalog sources located within 5 degrees from the Galactic plane. Using 8 yr of data from the Fermi Large Area Telescope between 50 MeV and 1 GeV, we find and present the spectral characteristics of 56 sources with a spectral break confirmed by a thorough study of systematic uncertainty. Our population of sources includes 13 SNRs for which the proton-proton interaction is enhanced by the dense target material; the high-mass gamma-ray binary LS I+61 303; the colliding wind binary eta Carinae; and the Cygnus star-forming region. This analysis better constrains the origin of the gamma-ray emission and enlarges our view to potential new cosmic-ray acceleration sites.
CRIS-Team WoS Importer:2022-07-22

Search for photon-linelike signatures from dark matter annihilations with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Physical Review Letters, 2013)
Gamma-ray line signatures can be expected in the very-high-energy (E >100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼500 GeV and ∼25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. No statistically significant signal could be found. For monochromatic γ-ray line emission, flux limits of (2×107- 2×105) m2 s1 sr1 and (1×108-2×106) m2 s1 sr1 are obtained for the central part of the Milky Way halo and extragalactic observations, respectively. For a DM particle mass of 1 TeV, limits on the velocity-averaged DM annihilation cross section âŸ̈σvâŸ© reach ∼1027 cm3 s 1, based on the Einasto parametrization of the Galactic DM halo density profile. © 2013 American Physical Society.

Search for Spectral Irregularities due to Photon-Axionlike-Particle Oscillations with the Fermi Large Area Telescope - Ajello, M.; Albert, A.; Anderson, B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, R.; Bottacini, E.; et al. (Physical Review Letters, 2016)
We report on the search for spectral irregularities induced by oscillations between photons and axionlike-particles (ALPs) in the gamma-ray spectrum of NGC 1275, the central galaxy of the Perseus cluster. Using 6 years of Fermi Large Area Telescope data, we find no evidence for ALPs and exclude couplings above 5 x 10(-12) GeV-1 for ALP masses 0.5 less than or similar to m(a) less than or similar to 5 neV at 95% confidence. The limits are competitive with the sensitivity of planned laboratory experiments, and, together with other bounds, strongly constrain the possibility that ALPs can reduce the gamma-ray opacity of the Universe.

Search for TeV emission from the Fermi Bubbles at low Galactic latitudes with H.E.S.S. inner Galaxy survey observations - Moulin, Emmanuel; Montanari, Alessandro; Spencer, Samuel; Malyshev, Denys; Malyshev, Dmitry; Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; et al. (Proceedings of Science, 2022)
The Fermi Bubbles were discovered about a decade ago in the Fermi-LAT data as a double-lobe structure extending up to 55° in Galactic latitudes above and below the Galactic Center. At the moment their origin is still unknown. The H.E.S.S. collaboration is currently performing the first ever survey in TeV gamma rays of the Milky Way inner region: the Inner Galaxy Survey. This survey is intended to achieve the best sensitivity to faint and diffuse emissions in a region of several degrees around the Galactic Centre. It provides an unprecedented sensitivity to dark matter signals, new diffuse emissions, and TeV outflows from the Galactic Centre. Understanding the properties of the Fermi Bubbles at low Galactic latitudes will provide key insights into their origin. We search for TeV emission at the base of the Fermi Bubbles using low-latitude spatial templates. The first results obtained with the 2014-2020 H.E.S.S. observations will be reported.
CRIS-Team Scopus Importer:2022-12-23

Search for TeV emission from the region around PSR B1706-44 with the HESS experiment - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The region around PSR B1706 - 44 has been observed with the HESS imaging atmospheric Cherenkov telescopes in 2003. No evidence for gamma-ray emission in the TeV range was found at the pulsar position or at the radio arc which corresponds to the supernova remnant G343.1 - 2.3. The 99% confidence level flux upper limit at the pulsar position is F-ul( E > 350 GeV) = 1.4 x 10(-12) s(-1) cm(-2) assuming a power law (dN/dE proportional to E-Gamma) with photon index of Gamma = 2.5 and F-ul( E > 500 GeV) = 1.3 x 10(-12) s(-1) cm(-2) without an assumption on the spectral shape. The reported upper limits correspond to 8% of the flux from an earlier detection by the CANGAROO experiment.
CRIS-Team WoS Importer:2020-01-15

Search for TeV gamma-ray emission from GRB 100621A, an extremely bright GRB in X-rays, with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
The long gamma-ray burst (GRB) 100621A, at the time the brightest X-ray transient ever detected by Swift-XRT in the 0.3-10 keV range, has been observed with the H.E.S.S. imaging air Cherenkov telescope array, sensitive to gamma radiation in the very-high-energy (VHE, >100 GeV) regime. Due to its relatively small redshift of z 0.5, the favourable position in the southern sky and the relatively short follow-up time (<700 s after the satellite trigger) of the H.E.S.S. observations, this GRB could be within the sensitivity reach of the H.E.S.S. instrument. The analysis of the H.E.S.S. data shows no indication of emission and yields an integral flux upper limit above 380 GeV of 4.2 × 10 cm s (95% confidence level), assuming a simple Band function extension model. A comparison to a spectral-temporal model, normalised to the prompt flux at sub-MeV energies, constraints the existence of a temporally extended and strong additional hard power law, as has been observed in the other bright X-ray GRB 130427A. A comparison between the H.E.S.S. upper limit and the contemporaneous energy output in X-rays constrains the ratio between the X-ray and VHE gamma-ray fluxes to be greater than 0.4. This value is an important quantity for modelling the afterglow and can constrain leptonic emission scenarios, where leptons are responsible for the X-ray emission and might produce VHE gamma rays. © 2014 ESO.
Keywords: Gamma rays: general; Gamma rays: stars; Gamma-ray burst: individual: GRB 100621A; X-rays: stars

Search for the imprint of axion-like particles in the highest-energy photons of hard γ-ray blazars - Buehler, R.; Gallardo, G.; Maier, G.; Domínguez, A.; López, M.; Meyer, Manuel (Journal of Cosmology and Astroparticle Physics, 2020)
Axion-like particles (ALPs), predicted in theories beyond the Standard Model, can have observational effects on the transparency of the Universe to γ rays in the presence of magnetic fields. In this work, we search for effects compatible with the existence of ALPs with 80 months of data from the Fermi Large Area Telescope, by comparing the distributions of observed highest energy photons from sources beyond redshifts of z ≥ 0.1 with theoretical predictions in the presence of ALPs. We find no evidence for an increased γ-ray transparency due to ALPs and therefore we set limits on the ALPs parameters assuming a value of the intergalactic magnetic field strength of 1 nG. Photon-ALP couplings above 10-11 GeV-1 are excluded for ALP masses ma ≲ 3.0 neV . As the allowed magnetic field parameter space is large, we also test lower magnetic field strengths and no constraints can be set for B≤0.1 nG below the CAST limit. These constraints exclude a region of the parameter space not covered by other γ-ray telescopes and are compatible with limits imposed by other experiments.
CRIS-Team Scopus Importer:2020-10-16
Keywords: active galactic nuclei; gamma ray experiments

Search for very-high-energy γ-ray emission from Galactic globular clusters with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Context. Globular clusters (GCs) are established emitters of high-energy (HE, 100 MeV < E < 100 GeV) γ-ray radiation which could originate from the cumulative emission of the numerous millisecond pulsars (msPSRs) in the clusters' cores or from inverse Compton (IC) scattering of relativistic leptons accelerated in the GC environment. These stellar clusters could also constitute a new class of sources in the very-high-energy (VHE, E > 100 GeV) γ-ray regime, judging from the recent detection of a signal from the direction of Terzan 5 with the H.E.S.S. telescope array. Aims. To search for VHE γ-ray sources associated with other GCs, and to put constraints on leptonic emission models, we systematically analyzed the observations towards 15 GCs taken with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes. Methods. We searched for point-like and extended VHE γ-ray emission from each GC in our sample and also performed a stacking analysis combining the data from all GCs to investigate the hypothesis of a population of faint emitters. Assuming IC emission as the origin of the VHE γ-ray signal from the direction of Terzan 5, we calculated the expected γ-ray flux from each of the 15 GCs, based on their number of millisecond pulsars, their optical brightness and the energy density of background photon fields. Results. We did not detect significant VHE γ-ray emission from any of the 15 GCs in either of the two analyses. Given the uncertainties related to the parameter determinations, the obtained flux upper limits allow to rule out the simple IC/msPSR scaling model for NGC 6388 and NGC 7078. The upper limits derived from the stacking analyses are factors between 2 and 50 below the flux predicted by the simple leptonic scaling model, depending on the assumed source extent and the dominant target photon fields. Therefore, Terzan 5 still remains exceptional among all GCs, as the VHE γ-ray emission either arises from extra-ordinarily efficient leptonic processes, or from a recent catastrophic event, or is even unrelated to the GC itself. © 2013 ESO.
Keywords: Gamma rays: general; Globular clusters: general; Pulsars: general; Radiation mechanisms: non-thermal

Searching for >177 TeV Gamma Rays in the Vicinity of Mrk 501 with HAWC - Albert, Andrea; Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
HAWC has recently developed 2 new analysis techniques that reconstructs the energy of each gamma-ray event. With this new analysis HAWC has detected several Galactic sources with emission above 100 TeV. Additionally the HAWC Collaboration has developed new event reconstruction algorithms called “Pass 5”. Using the energy estimators and Pass 5 we search for >177 TeV emission in the vicinity of Mrk 501. High-energy emission from Mrk 501 could, for example, be evidence of Axion Like Particles, a theoretical dark matter candidate. We find a hint of a high-energy lobe within 0.5◦ of Mrk 501 using both energy estimators.
CRIS-Team Scopus Importer:2022-12-23

Searching for Dark Matter Annihilation from Milky Way Dwarf Spheroidal Galaxies with Six Years of Fermi Large Area Telescope Data - Ackermann, Markus; Albert, A.; Anderson, B.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Physical Review Letters, 2015)
The dwarf spheroidal satellite galaxies (dSphs) of the Milky Way are some of the most dark matter (DM) dominated objects known. We report on gamma-ray observations of Milky Way dSphs based on six years of Fermi Large Area Telescope data processed with the new PASS8 event-level analysis. None of the dSphs are significantly detected in gamma rays, and we present upper limits on the DM annihilation cross section from a combined analysis of 15 dSphs. These constraints are among the strongest and most robust to date and lie below the canonical thermal relic cross section for DM of mass less than or similar to 100 GeV annihilating via quark and tau-lepton channels.
CRIS-Team WoS Importer:2020-01-15

Searching for TeV Dark Matter in Irregular Dwarf Galaxies with HAWC Observatory - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Chaparro-Amaro, O.; et al. (Astrophysical Journal, 2023)
We present the results of dark matter (DM) searches in a sample of 31 dwarf irregular (dIrr) galaxies within the field of view of the HAWC Observatory. dIrr galaxies are DM-dominated objects in which astrophysical gamma-ray emission is estimated to be negligible with respect to the secondary gamma-ray flux expected by annihilation or decay of weakly interacting massive particles (WIMPs). While we do not see any statistically significant DM signal in dIrr galaxies, we present the exclusion limits (95% C.L.) for annihilation cross section and decay lifetime for WIMP candidates with masses between 1 and 100 TeV. Exclusion limits from dIrr galaxies are relevant and complementary to benchmark dwarf Spheroidal (dSph) galaxies. In fact, dIrr galaxies are targets kinematically different from benchmark dSph, preserving the footprints of different evolution histories. We compare the limits from dIrr galaxies to those from ultrafaint and classical dSph galaxies previously observed with HAWC. We find that the constraints are comparable to the limits from classical dSph galaxies and ∼2 orders of magnitude weaker than the ultrafaint dSph limits.
CRIS-Team Scopus Importer:2023-03-24

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

Searching signals of dark matter from unidentified Fermi-LAT objects with H.E.S.S. - Montanari, A.; Moulin, E.; Malyshev, Dmitry; Glawion, D. (Journal of Physics: Conference Series, 2022)
Milky Way-sized galaxies harbor a population of unmerged dark matter subhalos, as shown from cosmological N-body simulations. These subhalos could shine in gamma-rays and be eventually detected as unidentified sources in gamma-ray surveys. From a thorough selection of unidentified Fermi-LAT Objects (UFOs), we observe four UFOs with H.E.S.S. and we search for very high-energy (VHE, E ≥ 100 GeV) gamma-ray emission. Considering dark matter masses above a few hundred GeV, the observed UFOs could be identified as dark matter subhalos, given their hard gamma-ray spectra in the few-ten-to-hundred GeV energy range. Since no significant very-high-energy gamma-ray emission is detected in any of the four UFOs dataset nor in the combined one, we derive constraints on the product of the velocity-weighted annihilation cross-section hσvi by the J-factor for the dark matter models. We derive 95% CL upper limits on hσviJ in W+W− and τ+τ− annihilation channels for the TeV dark matter particles. Considering thermal WIMPs, we derive constraints on the J-factors from the H.E.S.S. observations. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the dark matter models with masses greater than 0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team Scopus Importer:2022-06-24

SEARCHING THE GAMMA-RAY SKY FOR COUNTERPARTS TO GRAVITATIONAL WAVE SOURCES: FERMI GAMMA-RAY BURST MONITOR. AND LARGE AREA TELESCOPE OBSERVATIONS OF LVT151012 AND GW151226 - Racusin, J. L.; Burns, E.; Goldstein, A.; Connaughton, V.; Wilson-Hodge, C. A.; Jenke, P.; Blackburn, L.; Briggs, M. S.; Broida, J.; Camp, J.; Christensen, Nelson; Hui, C. M.; et al. (Astrophysical Journal, 2017)
We present the Fermi Gamma-ray Burst Monitor (GBM) and Large Area Telescope (LAT) observations of the LIGO binary black hole merger event GW151226 and candidate LVT151012. At the time of the LIGO triggers on LVT151012 and GW151226, GBM was observing 68% and 83% of the localization regions, and LAT was observing 47% and 32%, respectively. No candidate electromagnetic counterparts were detected by either the GBM or LAT. We present a detailed analysis of the GBM and LAT data over a range of timescales from seconds to years, using automated pipelines and new techniques for characterizing the flux upper bounds across large areas of the sky. Due to the partial GBM and LAT coverage of the large LIGO localization regions at the trigger times for both events, differences in source distances and masses, as well as the uncertain degree to which emission from these sources could be beamed, these non-detections cannot be used to constrain the variety of theoretical models recently applied to explain the candidate GBM counterpart to GW150914.
CRIS-Team WoS Importer:2020-01-15

SECOND CATALOG OF ACTIVE GALACTIC NUCLEI DETECTED BY THE FERMI LARGE AREA TELESCOPE (vol 743, 171, 2011) - Ackermann, M.; Ajello, M.; Allafort, A.; Antolini, E.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2015)

Sensitivity of the Cherenkov Telescope Array to a dark matter signal from the Galactic centre - Acharyya, A.; Adam, R.; van Eldik, Christopher; Spencer, Samuel; Adams, C.; Agudo, I.; Aguirre-Santaella, A.; Alfaro, R.; Alfaro, J.; Alispach, C.; Aloisio, R.; Alves Batista, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
We provide an updated assessment of the power of the Cherenkov Telescope Array (CTA) to search for thermally produced dark matter at the TeV scale, via the associated gamma-ray signal from pair-annihilating dark matter particles in the region around the Galactic centre. We find that CTA will open a new window of discovery potential, significantly extending the range of robustly testable models given a standard cuspy profile of the dark matter density distribution. Importantly, even for a cored profile, the projected sensitivity of CTA will be sufficient to probe various well-motivated models of thermally produced dark matter at the TeV scale. This is due to CTA's unprecedented sensitivity, angular and energy resolutions, and the planned observational strategy. The survey of the inner Galaxy will cover a much larger region than corresponding previous observational campaigns with imaging atmospheric Cherenkov telescopes. CTA will map with unprecedented precision the large-scale diffuse emission in high-energy gamma rays, constituting a background for dark matter searches for which we adopt state-of-the-art models based on current data. Throughout our analysis, we use up-to-date event reconstruction Monte Carlo tools developed by the CTA consortium, and pay special attention to quantifying the level of instrumental systematic uncertainties, as well as background template systematic errors, required to probe thermally produced dark matter at these energies.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Dark matter experiments; Dark matter theory; Galaxy morphology; Gamma ray experiments

Sensitivity of the Cherenkov Telescope Array to spectral signatures of hadronic PeVatrons with application to Galactic Supernova Remnants - Acero, F.; Acharyya, A.; Spencer, Samuel; Adam, R.; Aguasca-Cabot, A.; Agudo, I.; Aguirre-Santaella, A.; Alfaro, J.; Aloisio, R.; Crespo, N. Álvarez; Batista, R. Alves; Amati, L.; et al. (Astroparticle Physics, 2023)
The local Cosmic Ray (CR) energy spectrum exhibits a spectral softening at energies around 3 PeV. Sources which are capable of accelerating hadrons to such energies are called hadronic PeVatrons. However, hadronic PeVatrons have not yet been firmly identified within the Galaxy. Several source classes, including Galactic Supernova Remnants (SNRs), have been proposed as PeVatron candidates. The potential to search for hadronic PeVatrons with the Cherenkov Telescope Array (CTA) is assessed. The focus is on the usage of very high energy γ-ray spectral signatures for the identification of PeVatrons. Assuming that SNRs can accelerate CRs up to knee energies, the number of Galactic SNRs which can be identified as PeVatrons with CTA is estimated within a model for the evolution of SNRs. Additionally, the potential of a follow-up observation strategy under moonlight conditions for PeVatron searches is investigated. Statistical methods for the identification of PeVatrons are introduced, and realistic Monte-Carlo simulations of the response of the CTA observatory to the emission spectra from hadronic PeVatrons are performed. Based on simulations of a simplified model for the evolution for SNRs, the detection of a γ-ray signal from in average 9 Galactic PeVatron SNRs is expected to result from the scan of the Galactic plane with CTA after 10 h of exposure. CTA is also shown to have excellent potential to confirm these sources as PeVatrons in deep observations with O(100) hours of exposure per source.
CRIS-Team Scopus Importer:2023-04-28
Keywords: (Stars:) supernovae: general; Cosmic rays; Galactic PeVatrons; Gamma rays: general; Methods: data analysis; Methods: statistical

Serendipitous discovery of the unidentified extended TeV gamma-ray source HESS J1303-631 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The serendipitous discovery of an unidentified extended TeV gamma-ray source close to the galactic plane named HESSJ1303-631 at a significance of 21 standard deviations is reported. The observations were performed between February and June 2004 with the HESS stereoscopic system of Cherenkov telescopes in Namibia. HESS J1303-631 was discovered roughly 0.6 degrees north of the binary system PSRB1259-63/SS2883, the target object of the initial observation campaign which was also detected at TeV energies in the same field of view. HESS J1303-631 is extended with a width of an assumed intrinsic Gaussian emission profile of sigma = (0.16 +/- 0.02)degrees. and the integral flux above 380 GeV is compatible with constant emission over the entire observational period of (17 +/- 3)% of the Crab Nebula flux. The measured energy spectrum can be described by a power-law dN/dE similar to E-Gamma with a photon index of G = 2.44 +/- 0.05(stat) +/- 0.2(syst). Up to now, no counterpart at other wavelengths is identified. Various possible TeV production scenarios are discussed.
CRIS-Team WoS Importer:2020-01-15

Setup for meV-resolution inelastic X-ray scattering measurements and X-ray diffraction at the Matter in Extreme Conditions endstation at the Linac Coherent Light Source - Mcbride, E. E.; White, T. G.; Descamps, A.; Fletcher, L. B.; Appel, K.; Condamine, F. P.; Curry, C. B.; Dallari, Francesco; Funk, Stefan; Galtier, E.; Gauthier, Maxence; Goede, S.; et al. (Review of Scientific Instruments, 2018)
We describe a setup for performing inelastic X-ray scattering and X-ray diffraction measurements at the Matter in Extreme Conditions (MEC) endstation of the Linac Coherent Light Source. This technique is capable of performing high-, meV-resolution measurements of dynamic ion features in both crystalline and non-crystalline materials. A four-bounce silicon (533) monochromator was used in conjunction with three silicon (533) diced crystal analyzers to provide an energy resolution of similar to 50 meV over a range of similar to 500 meV in single shot measurements. In addition to the instrument resolution function, we demonstrate the measurement of longitudinal acoustic phonon modes in polycrystalline diamond. Furthermore, this setup may be combined with the high intensity laser drivers available at MEC to create warm dense matter and subsequently measure ion acoustic modes. Published by AIP Publishing.
CRIS-Team WoS Importer:2020-01-15

Simultaneous HESS and Chandra observations of Sagitarius A during an X-ray flare - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
The rapidly varying ( 10 min timescale) non-thermal X-ray emission observed from Sgr A implies that particle acceleration is occuring close to the event horizon of the supermassive black hole. The TeV γ-ray source HESSJ1745-290 is coincident with Sgr A* and may be closely related to its X-ray emission. Simultaneous X-ray and TeV observations are required to elucidate the relationship between these objects. We report on joint HESS/Chandra observations performed in July 2005, during which an X-ray flare was detected. Despite a factor of ≈9 increase in the X-ray flux of Sgr A*, no evidence is found for an increase in the TeV γ-ray flux from this region. We find that an increase in the γ-ray flux of a factor of 2 or greater can be excluded at a confidence level of 99%. This finding disfavours scenarios in which the keV and TeV emission are associated with the same population of accelerated particles and in which the bulk of the γ-ray emission is produced within ∼ cm (∼100 Rs) of the supermassive black hole. © 2008 ESO.
Keywords: Gamma rays: observations; X-rays: individuals: Sgr A

Simultaneous multiwavelength observations of the second exceptional γ-ray flare of PKS 2155-304 in July 2006 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Keywords: galaxies: active; galaxies: BL Lacertae objects: individual: PKS 2155-304; gamma rays: observations; X-rays: galaxies

Single-exposure X-ray phase imaging microscopy with a grating interferometer - Wolf, Andreas; Akstaller, Bernhard; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Meyer, Pascal; Schropp, Andreas; Schuster, Max; Seifert, Maria; Weule, Mareike; Michel, Thilo; et al. (Journal of Synchrotron Radiation, 2022)
The advent of hard X-ray free-electron lasers enables nanoscopic X-ray imaging with sub-picosecond temporal resolution. X-ray grating interferometry offers a phase-sensitive full-field imaging technique where the phase retrieval can be carried out from a single exposure alone. Thus, the method is attractive for imaging applications at X-ray free-electron lasers where intrinsic pulse-to-pulse fluctuations pose a major challenge. In this work, the single-exposure phase imaging capabilities of grating interferometry are characterized by an implementation at the I13-1 beamline of Diamond Light Source (Oxfordshire, UK). For comparison purposes, propagation-based phase contrast imaging was also performed at the same instrument. The characterization is carried out in terms of the quantitativeness and the contrast-to-noise ratio of the phase reconstructions as well as via the achievable spatial resolution. By using a statistical image reconstruction scheme, previous limitations of grating interferometry regarding the spatial resolution can be mitigated as well as the experimental applicability of the technique.
CRIS-Team Scopus Importer:2022-05-27
Keywords: grating interferometry; phase contrast X-ray imaging; phase retrieval; X-ray microscopy

Single-shot grating-based phase-contrast imaging of a micrometer sample at a laser-driven x-ray backlighter source - Akstaller, Bernhard; Schreiner, Stephan; Hofmann, Fabian; Meyer, P.; Neumayer, P.; Schuster, Max; Wolf, Andreas; Zielbauer, B.; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Instrumentation, 2021)
A single-shot x-ray phase-contrast imaging technique with short exposure time allows to capture sharp images of fast dynamic processes despite low absorption contrast. We demonstrate the capabilities of a robust single-shot grating-based phase-contrast imaging setup at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. A static test sample was imaged at 47-fold magnification using a laser-driven high-energy x-ray backlighter source. The retrieved transmission and phase-contrast images yield reproducible results. The reconstructed differential phase-images are quantitatively explained. In addition to the phase-images, propagation signatures are found in the data and used for result verification. The obtained results demonstrate the capabilities of the grating setup which can be used to image microscopic dynamic processes in high-energy density plasma experiments at PHELIX or similar high-power laser facilities.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Solution to the Cosmic Ray Anisotropy Problem - Mertsch, Philipp; Funk, Stefan (Physical Review Letters, 2015)
In the standard diffusive picture for transport of cosmic rays (CRs), a gradient in the CR density induces a typically small, dipolar anisotropy in their arrival directions. This is being widely advertised as a tool for finding nearby sources. However, the predicted dipole amplitude at TeV and PeV energies exceeds the measured one by almost 2 orders of magnitude. Here, we critically examine the validity of this prediction, which is based on averaging over an ensemble of turbulent magnetic fields. We focus on (1) the deviations of the dipole in a particular random realization from the ensemble average, and (2) the possibility of a misalignment between the regular magnetic field and the CR gradient. We find that if the field direction and the gradient direction are close to similar to 90 degrees, the dipole amplitude is considerably suppressed and can be reconciled with observations, which sheds light on a long-standing problem. Furthermore, we show that the dipole direction in general does not coincide with the gradient direction, thus hampering the search for nearby sources.

Spectral analysis and interpretation of the γ-ray emission from the starburst galaxy NGC253 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astrophysical Journal, 2012)
Very high energy (VHE; E ≥ 100 GeV) and high-energy (HE; 100 MeV ≤ E ≤ 100 GeV) data from γ-ray observations performed with the H.E.S.S. telescope array and the Fermi-LAT instrument, respectively, are analyzed in order to investigate the non-thermal processes in the starburst galaxy NGC253. The VHE γ-ray data can be described by a power law in energy with differential photon index Γ = 2.14 ± 0.18 ± 0.30 and differential flux normalization at 1TeV of F = (9.6 ± 1.5(+ 5.7, -2.9)) × 10 TeV cm s. A power-law fit to the differential HE γ-ray spectrum reveals a photon index of Γ = 2.24 ± 0.14 ± 0.03 and an integral flux between 200MeV and 200GeV of F(0.2-200 GeV) = (4.9 ± 1.0 ± 0.3) × 10 cm s. No evidence for a spectral break or turnover is found over the dynamic range of both the LAT instrument and the H.E.S.S. experiment: a combined fit of a power law to the HE and VHE γ-ray data results in a differential photon index Γ = 2.34 ± 0.03 with a p-value of 30%. The γ-ray observations indicate that at least about 20% of the energy of the cosmic rays (CRs) capable of producing hadronic interactions is channeled into pion production. The smooth alignment between the spectra in the HE and VHE γ-ray domain suggests that the same transport processes dominate in the entire energy range. Advection is most likely responsible for charged particle removal from the starburst nucleus from GeV to multiple TeV energies. In a hadronic scenario for the γ-ray production, the single overall power-law spectrum observed would therefore correspond to the mean energy spectrum produced by the ensemble of CR sources in the starburst region. © 2012. The American Astronomical Society. All rights reserved.
Keywords: convection; diffusion; galaxies: individual (NGC 253); galaxies: starburst; gamma rays: galaxies; radiation mechanisms: non-thermal

Spectrum and morphology of the very-high-energy source HAWC J2019+368 - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Astrophysical Journal, 2021)
The MGRO J2019+37 region is one of the brightest sources in the sky at TeV energies. It was detected in the second HAWC catalog as 2HWC J2019+367 and here we present a detailed study of this region using data from HAWC. This analysis resolves the region into two sources: HAWC J2019+368 and HAWC J2016+371. We associate HAWC J2016+371 with the evolved supernova remnant CTB 87, although its low significance in this analysis prevents a detailed study at this time. An investigation of the morphology (including possible energy-dependent morphology) and spectrum for HAWC J2019+368 is the focus of this work. We associate HAWC J2019+368 with PSR J2021+3651 and its X-ray pulsar wind nebula, the Dragonfly nebula. Modeling the spectrum measured by HAWC and Suzaku reveals a ∼7 kyr pulsar and nebula system producing the observed emission at X-ray and γ-ray energies.
CRIS-Team Scopus Importer:2021-05-21

Spectrum and variability of the Galactic center VHE γ-ray source HESS J1745-290 - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. A detailed study of the spectrum and variability of the source HESS J1745-290 in the Galactic Center (GC) region using new data from the H.E.S.S. array of Cherenkov telescopes is presented. Flaring activity and quasi periodic oscillations (QPO) of HESS J1745-290 are investigated. Methods. The image analysis is performed with a combination of a semi-analytical shower model and the statistical moment-based Hillas technique. The spectrum and lightcurves of HESS J1745-290 are derived with a likelihood method based on a spectral shape hypothesis. Rayleigh tests and Fourier analysis of the H.E.S.S. GC signal are used to study the periodicity of the source. Results. With a three-fold increase in statistics compared to previous work, a deviation from a simple power law spectrum is detected for the first time. The measured energy spectrum over the three years 2004, 2005 and 2006 of data taking is compatible with both a power law spectrum with an exponential cut-off and a broken power law spectrum. The curvature of the energy spectrum is likely to be intrinsic to the photon source, as opposed to effects of interstellar absorption. The power law spectrum with an exponential cut-off is characterized by a photon index of 2.10 ± 0.04 ± 0.10 and a cut-off energy at 15.7 ± 3.4±2.5 TeV. The broken power law spectrum exhibits spectral indices of 2.02 ± 0.08 ± 0.10 and 2.63 ± 0.14 ± 0.10 with a break energy at 2.57 ± 0.19stat ± 0.44 TeV. No significant flux variation is found. Increases in the γ-ray flux of HESS J1745-290 by at least a factor of two would be required for a 3cr detection of a flare with time scales of an hour. Investigation of possible QPO activity at periods claimed to be detected in X-rays does not show any periodicities in the H.E.S.S. signal. © ESO 2009.
Keywords: Galaxy: center; gamma rays: observations; methods: data analysis

Status of identification of VHE gamma-ray sources - Funk, Stefan (Astrophysics and Space Science, 2007)
With the recent advances made by Cherenkov telescopes such as H.E.S.S. the field of very high-energy (VHE) gamma-ray astronomy has recently entered a new era in which for the first time populations of Galactic sources such as e.g. Pulsar wind nebulae (PWNe) or Supernova remnants (SNRs) can be studied. However, while some of the new sources can be associated by positional coincidence as well as by consistent multi-wavelength data to a known counterpart at other wavelengths, most of the sources remain not finally identified. In the following, the population of Galactic H.E.S.S. sources will be used to demonstrate the status of the identifications, to classify them into categories according to this status and to point out outstanding problems.
CRIS-Team WoS Importer:2020-01-15

Status of the photomultiplier-based FlashCam camera for the Cherenkov Telescope Array - Puehlhofer, Gerd; Jung-Richardt, Ira; Kalekin, Oleg; Lahmann, Robert; et al. (Proceedings of SPIE, 2014)

Status of the technologies for the production of the Cherenkov telescope array (CTA) mirrors - Pareschi, Giovanni; Armstrong, T.; Baba, H.; Baehr, J.; Bonardi, A.; Bonnoli, Giacomo; Brun, P.; Canestrari, Rodolfo; Chadwick, Paula; Chikawa, M.; Carton, P. -H.; De Souza, V.; et al. (Optics for EUV, X-Ray, and Gamma-Ray Astronomy VI, 2013)
The Cherenkov Telescope Array (CTA) is the next generation very high-energy gamma-ray observatory, with at least 10 times higher sensitivity than current instruments. CTA will comprise several tens of Imaging Atmospheric Cherenkov Telescopes (IACTs) operated in array-mode and divided into three size classes: large, medium and small telescopes. The total reflective surface could be up to 10,000 m requiring unprecedented technological efforts. The properties of the reflector directly influence the telescope performance and thus constitute a fundamental ingredient to improve and maintain the sensitivity. The R&D status of lightweight, reliable and cost-effective mirror facets for the CTA telescope reflectors for the different classes of telescopes is reviewed in this paper. © 2013 SPIE.
Keywords: Cherenkov Telescope Array; Cherenkov Telescopes; mirrors; reflecting coatings

Studies towards an understanding of global array pointing for the cherenkov telescope array - Eschbach, Stefan; Ziegler, Alexander; van Eldik, Christopher; Veh, Johannes; Berge, David; Gaug, Markus (34th International Cosmic Ray Conference (ICRC2015), 2015)
Current arrays of Imaging Atmospheric Cherenkov Telescopes (IACTs) routinely achieve an astrometric point-source location accuracy of 20-30 seconds of arc (given large photon statistics), which is well below the angular resolution obtained for individual photons. The location accuracy is mainly limited by systematic uncertainties due to possible deformations of the telescopes' structures, causing a mis-orientation between the nominal optical axes of the telescopes and their actual pointing directions. Usually, only a subset of telescopes is triggered for a given gammaray event, and their mis-orientations enter the gamma-ray direction reconstruction in a combined manner. Hence, in general, the average location accuracy for a set of gamma-ray observations depends in a complex way on the individual telescope accuracy and the geometry of the array, but also on the observing conditions, the energy spectrum of the source and the chosen event selection cuts. For the proposed Cherenkov Telescope Array (CTA), a post-calibration point-source location accuracy of 3 seconds of arc is aimed for under favorable observing conditions and for gamma-ray energies exceeding 100 GeV. In this contribution, results of first studies on the location accuracy are presented. These studies are based on a toy Monte Carlo simulation of a typical CTA-South array layout, taking into account the expected trigger rates of the different CTA telescope types and the gamma-ray spectrum of the simulated source. With this simulation code it is possible to study the location accuracy as a function of arbitrary telescope mis-orientations and for typical observing patterns on the sky. Results are presented for various scenarios, including one for which all individual telescopes are randomly mis-oriented within their specified limits. The study provides solid lower limits for the expected source location accuracy of CTA, and can be easily extended to include various other important effects like atmospheric refraction or partial cloud coverage.

Study of the Very High Energy Emission of M87 through its Broadband Spectral Energy Distribution - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Belmont-Moreno, E.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; Cotzomi, J.; Coutiño de León, S.; et al. (Astrophysical Journal, 2022)
The radio galaxy M87 is the central dominant galaxy of the Virgo Cluster. Very high-energy (VHE, ≳0.1 TeV) emission from M87 has been detected by imaging air Cherenkov telescopes. Recently, marginal evidence for VHE long-term emission has also been observed by the High Altitude Water Cherenkov Observatory, a gamma-ray and cosmic-ray detector array located in Puebla, Mexico. The mechanism that produces VHE emission in M87 remains unclear. This emission originates in its prominent jet, which has been spatially resolved from radio to X-rays. In this paper, we construct a spectral energy distribution from radio to gamma rays that is representative of the nonflaring activity of the source, and in order to explain the observed emission, we fit it with a lepto-hadronic emission model. We found that this model is able to explain nonflaring VHE emission of M87 as well as an orphan flare reported in 2005.
CRIS-Team Scopus Importer:2022-08-19

SUPPLEMENT: "LOCALIZATION AND BROADBAND FOLLOW-UP OF THE GRAVITATIONAL-WAVE TRANSIENT GW150914" (2016, ApJL, 826, L13) - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Astrophysical Journal Supplement Series, 2016)
This Supplement provides supporting material for Abbott et al. (2016a). We briefly summarize past electromagnetic (EM) follow-up efforts as well as the organization and policy of the current EM follow-up program. We compare the four probability sky maps produced for the gravitational-wave transient GW150914, and provide additional details of the EM follow-up observations that were performed in the different bands.
Keywords: gravitational waves; methods: observational

TARGET: A Digitizing And Trigger ASIC For The Cherenkov Telescope Array - Funk, Stefan; Jankowsky, David; Katagiri, Hideaki; Kraus, Michael; Okumura, Akira; Schoorlemmer, Harm; Shigenaka, A.; Tajima, H.; Tibaldo, Luigi; Varner, G.; Zink, Adrian; Zorn, Justus (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2017)
CRIS-Team WoS Importer:2020-01-15

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

TeV Gamma-Ray Observations of the Binary Neutron Star Merger GW170817 with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astrophysical Journal Letters, 2017)
We search for high-energy gamma-ray emission from the binary neutron star merger GW170817 with the H.E.S.S. Imaging Air Cherenkov Telescopes. The observations presented here have been obtained starting only 5.3 hr after GW170817. The H.E.S.S. target selection identified regions of high probability to find a counterpart of the gravitational-wave event. The first of these regions contained the counterpart SSS17a that has been identified in the optical range several hours after our observations. We can therefore present the first data obtained by a ground-based pointing instrument on this object. A subsequent monitoring campaign with the H.E.S.S. telescopes extended over several days, covering timescales from 0.22 to 5.2 days and energy ranges between 270 GeV to 8.55 TeV. No significant gamma-ray emission has been found. The derived upper limits on the very-high-energy gamma-ray flux for the first time constrain non-thermal, high-energy emission following the merger of a confirmed binary neutron star system.
CRIS-Team WoS Importer:2020-01-15

TeV γ-ray observations of the young synchrotron-dominated SNRs G1.9+0.3 and G330.2+1.0 with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The non-thermal nature of the X-ray emission from the shell-type supernova remnants (SNRs) G1.9+0.3 and G330.2+1.0 is an indication of intense particle acceleration in the shock fronts of both objects. This suggests that the SNRs are prime candidates for very-high-energy (VHE; E > 0.1 TeV) γ -ray observations. G1.9+0.3, recently established as the youngest known SNR in the Galaxy, also offers a unique opportunity to study the earliest stages of SNR evolution in the VHE domain. The purpose of this work is to probe the level of VHE γ -ray emission from both SNRs and use this to constrain their physical properties. Observations were conducted with the H.E.S.S. (High Energy Stereoscopic System) Cherenkov Telescope Array over a more than six-year period spanning 2004-2010. The obtained data have effective livetimes of 67 h for G1.9+0.3 and 16 h for G330.2+1.0. The data are analysed in the context of the multiwavelength observations currently available and in the framework of both leptonic and hadronic particle acceleration scenarios. No significant γ -ray signal from G1.9+0.3 or G330.2+1.0 was detected. Upper limits (99 per cent confidence level) to the TeV flux from G1.9+0.3 and G330.2+1.0 for the assumed spectral index Γ = 2.5 were set at 5.6 × 10 cm s above 0.26 TeV and 3.2 × 10 cm s above 0.38 TeV, respectively. In a one-zone leptonic scenario, these upper limits imply lower limits on the interior magnetic field to B ≳ 12 μG for G1.9+0.3 and to B ≳ 8 μG for G330.2+1.0. In a hadronic scenario, the low ambient densities and the large distances to the SNRs result in very low predicted fluxes, for which the H.E.S.S. upper limits are not constraining. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Gamma-rays: ISM; ISM: magnetic fields; ISM: supernova remnants; Radiation mechanisms: non-thermal

The 2012 flare of PG 1553+113 seen with H.E.S.S. and Fermi-lat - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, Anna; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal, 2015)
Very high energy (VHE, E > 100 GeV) γ-ray flaring activity of the high-frequency peaked BL Lac object PG 1553+113 has been detected by the H.E.S.S. telescopes. The flux of the source increased by a factor of 3 during the nights of 2012 April 26 and 27 with respect to the archival measurements with a hint of intra-night variability. No counterpart of this event has been detected in the Fermi-Large Area Telescope data. This pattern is consistent with VHE γ-ray flaring being caused by the injection of ultrarelativistic particles, emitting γ-rays at the highest energies. The dataset offers a unique opportunity to constrain the redshift of this source at z = 0.49 ± 0.04 using a novel method based on Bayesian statistics. The indication of intra-night variability is used to introduce a novel method to probe for a possible Lorentz invariance violation (LIV), and to set limits on the energy scale at which Quantum Gravity (QG) effects causing LIV may arise. For the subluminal case, the derived limits are E,1 > 4.10 × 10 GeV and E,2 > 2.10 × 10 GeV for linear and quadratic LIV effects, respectively.
Keywords: BL Lacertae objects: individual (PG 1553+113); galaxies: active; galaxies: distances and redshifts; gamma-rays: galaxies

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The Advanced Particle-astrophysics Telescope (APT) Project Status - Buckley, James H.; Alnussirat, S.; Altomare, C.; Bose, R. G.; Braun, D.; Buhler, J. D.; Burns, E.; Chamberlain, R. D.; Chen, W.; Cherry, M. L.; Di Venere, L.; Dumonthier, J.; et al. (Proceedings of Science, 2022)
We describe the development of a future gamma-ray/cosmic-ray mission called the Advanced Particle-astrophysics Telescope (APT). The instrument will combine a pair tracker and Compton telescope in a single monolithic design. By using scintillating fibers for the tracker and wavelength-shifting fibers to readout CsI detectors, the instrument will achieve an order of magnitude improvement in sensitivity compared with Fermi but with fewer readout channels, and lower complexity. By incorporating multiple Compton imaging over a very large effective area, the instrument will also achieve orders of magnitude improvement in MeV sensitivity compared with other proposed instruments. The mission would have a broad impact on astroparticle physics, but the primary science drivers for the mission include: (1) probing WIMP dark matter across the entire natural mass range and annihilation cross section for a thermal WIMP, (2) providing a nearly all-sky instantaneous FoV, with prompt sub-degree localization and polarization measurements for gamma-ray transients such as neutron-star mergers and (3) making measurements of rare utraheavy cosmic ray nuclei to distinguish between n-star merger and SNae r-process synthesis of the heavy elements. We will describe ongoing work including a series of accelerator beam tests, a piggy-back Antactic flight (APTlite) and the recently funded long-duration balloon mission: the Antarctic Demonstrator for APT (ADAPT).
CRIS-Team Scopus Importer:2022-12-23

The Advanced Particle-astrophysics Telescope: Simulation of the Instrument Performance for Gamma-Ray Detection - Alnussirat, S.; Altomare, C.; Bose, R. G.; Braun, D.; Buckley, James H.; Buhler, J. D.; Burns, E.; Chamberlain, R. D.; Chen, Wenlei; Cherry, M. L.; Di Venere, L.; Dumonthier, J.; et al. (Proceedings of Science, 2022)
We present simulations of the instrument performance of the Advanced Particle-astrophysics Telescope (APT), a mission concept of a γ-ray and cosmic-ray observatory in a sun-Earth Lagrange orbit. The key components of the APT detector include a multiple-layer tracker composed of scintillating fibers and an imaging calorimeter composed of thin layers of CsI:Na scintillators. The design is aimed at maximizing effective area and field of view for γ-ray and cosmic-ray measurements, subject to constraints on instrument cost and total payload mass. We simulate a detector design based on 3-meter scintillating fibers and develop reconstruction algorithms for γ-rays from a few hundreds of keV up to a few TeV energies. At the photon energy above 30 MeV, pair-production/shower reconstruction is applied; the results show that APT could provide an order of magnitude improvement in effective area and sensitivity for γ-ray detection compared with the Fermi Large Area Telescope (LAT). A multiple-Compton-scattering reconstruction at photon energies below 10 MeV achieves sensitive detection of faint γ-ray bursts (GRBs) and other γ-ray transients down to ∼ 0.01 MeV/cm2 with degree-level to sub-degree-level localization accuracy. The Compton analysis also provides a measurement of polarization where the minimum detectable degree of polarization for ∼ 1 MeV/cm2 GRBs is below 20%. In addition to the APT simulations, we present the simulated performance of the Antarctic Demonstrator for APT, a 0.5m-square cross section balloon experiment that includes all of the key elements of the full APT detector.
CRIS-Team Scopus Importer:2022-12-23

The ASTRO-H X-ray Astronomy Satellite - Takahashi, Tadayuki; Mitsuda, Kazuhisa; Kelley, Richard; Aharonian, Felix; Akamatsu, Hiroki; Akimoto, Fumie; Allen, Steve; Anabuki, Naohisa; Angelini, Lorella; Arnaud, Keith; Asai, Makoto; Audard, Marc; et al. (International Society for Optical Engineering; 1999, 2014)
The joint JAXA/NASA ASTRO-H mission is the sixth in a series of highly successful X-ray missions developed by the Institute of Space and Astronautical Science (ISAS), with a planned launch in 2015. The ASTRO-H mission is equipped with a suite of sensitive instruments with the highest energy resolution ever achieved at E > 3 keV and a wide energy range spanning four decades in energy from soft X-rays to gamma-rays. The simultaneous broad band pass, coupled with the high spectral resolution of Delta E <= 7 eV of the micro-calorimeter, will enable a wide variety of important science themes to be pursued. ASTRO-H is expected to provide breakthrough results in scientific areas as diverse as the large-scale structure of the Universe and its evolution, the behavior of matter in the gravitational strong field regime, the physical conditions in sites of cosmic-ray acceleration, and the distribution of dark matter in galaxy clusters at different redshifts.
Keywords: X-ray; Hard X-ray; Gamma-ray; X-ray Astronomy; Gamma-ray Astronomy; micro-calorimeter

The central trigger system of the HESS telescope array - Funk, Stefan; et al. (High Energy Gamma-Ray Astronomy, 2005)
CRIS-Team WoS Importer:2020-01-15

THE DISCOVERY OF gamma-RAY EMISSION FROM THE BLAZAR RGB J0710+591 - Acciari, V. A.; Aliu, E.; Arlen, T.; Aune, T.; Bautista, M.; Beilicke, M.; Benbow, W.; Boettcher, M.; Boltuch, D.; Bradbury, S. M.; Buckley, J. H.; Bugaev, V.; et al. (Astrophysical Journal Letters, 2010)
The high-frequency-peaked BL Lacertae object RGB J0710+591 was observed in the very high-energy (VHE; E > 100 GeV) wave band by the VERITAS array of atmospheric Cherenkov telescopes. The observations, taken between 2008 December and 2009 March and totaling 22.1 hr, yield the discovery of VHE gamma rays from the source. RGB J0710+591 is detected at a statistical significance of 5.5 standard deviations (5.5 sigma) above the background, corresponding to an integral flux of (3.9 +/- 0.8) x 10(-12) cm(-2) s(-1) (3% of the Crab Nebula's flux) above 300 GeV. The observed spectrum can be fit by a power law from 0.31 to 4.6 TeV with a photon spectral index of 2.69 +/- 0.26(stat) +/- 0.20(sys). These data are complemented by contemporaneous multiwavelength data from the Fermi Large Area Telescope, the Swift X-ray Telescope, the Swift Ultra-Violet and Optical Telescope, and the Michigan-Dartmouth-MIT observatory. Modeling the broadband spectral energy distribution (SED) with an equilibrium synchrotron self-Compton model yields a good statistical fit to the data. The addition of an external-Compton component to the model does not improve the fit nor brings the system closer to equipartition. The combined Fermi and VERITAS data constrain the properties of the high-energy emission component of the source over 4 orders of magnitude and give measurements of the rising and falling sections of the SED.
CRIS-Team WoS Importer:2020-01-15

The e-ASTROGAM gamma-ray space observatory for the multimessenger astronomy of the 2030s - Tatischeff, V.; De Angelis, A.; Tavani, M.; Grenier, I.; Oberlack, U.; Hanlon, L.; Walter, R.; Argan, Andrea; Von Ballmoos, Peter; Bulgarelli, Andrea; Donnarumma, I.; Hernanz, M.; et al. (SPACE TELESCOPES AND INSTRUMENTATION 2018: ULTRAVIOLET TO GAMMA RAY, 2018)
CRIS-Team WoS Importer:2020-01-15

The e-ASTROGAM mission Exploring the extreme Universe with gamma rays in the MeV - GeV range - De Angelis, Alessandro; Tatischeff, V.; Tavani, M.; Oberlack, U.; Grenier, I.; Hanloni, L.; Walter, R.; Argan, A.; Von Ballmoos, P.; Bulgarelli, Andrea; Donnarumma, Immacolata; Hernanz, Margarita; et al. (Experimental Astronomy, 2017)
e-ASTROGAM ('enhanced ASTROGAM') is a breakthrough Observatory space mission, with a detector composed by a Silicon tracker, a calorimeter, and an anticoincidence system, dedicated to the study of the non-thermal Universe in the photon energy range from 0.3 MeV to 3 GeV - the lower energy limit can be pushed to energies as low as 150 keV, albeit with rapidly degrading angular resolution, for the tracker, and to 30 keV for calorimetric detection. The mission is based on an advanced space-proven detector technology, with unprecedented sensitivity, angular and energy resolution, combined with polarimetric capability. Thanks to its performance in the MeV-GeV domain, substantially improving its predecessors, e-ASTROGAM will open a new window on the non-thermal Universe, making pioneering observations of the most powerful Galactic and extragalactic sources, elucidating the nature of their relativistic outflows and their effects on the surroundings. With a line sensitivity in the MeV energy range one to two orders of magnitude better than previous generation instruments, e-ASTROGAM will determine the origin of key isotopes fundamental for the understanding of supernova explosion and the chemical evolution of our Galaxy. The mission will provide unique data of significant interest to a broad astronomical community, complementary to powerful observatories such as LIGO-Virgo-GEO600-KAGRA, SKA, ALMA, E-ELT, TMT, LSST, JWST, Athena, CTA, IceCube, KM3NeT, and the promise of eLISA.
Keywords: High-Energy Gamma-Ray Astronomy; High-Energy Astrophysics; Nuclear Astrophysics; Compton and Pair Creation Telescope; Gamma-Ray Bursts; Active Galactic Nuclei; Jets; Outflows; Multiwavelength Observations of the Universe; Counterparts of gravitational waves; Fermi; Dark Matter; Nucleosynthesis; Early Universe; Supernovae; Cosmic Rays; Cosmic Antimatter

The e-ASTROGAM mission Exploring the extreme Universe with gamma rays in the MeV - GeV range - De Angelis, Alessandro; Tatischeff, V.; Tavani, M.; Oberlack, U.; Grenier, I.; Hanloni, L.; Walter, R.; Argan, A.; Von Ballmoos, P.; Bulgarelli, Andrea; Donnarumma, Immacolata; Hernanz, Margarita; et al. (Experimental Astronomy, 2017)
e-ASTROGAM ('enhanced ASTROGAM') is a breakthrough Observatory space mission, with a detector composed by a Silicon tracker, a calorimeter, and an anticoincidence system, dedicated to the study of the non-thermal Universe in the photon energy range from 0.3 MeV to 3 GeV - the lower energy limit can be pushed to energies as low as 150 keV, albeit with rapidly degrading angular resolution, for the tracker, and to 30 keV for calorimetric detection. The mission is based on an advanced space-proven detector technology, with unprecedented sensitivity, angular and energy resolution, combined with polarimetric capability. Thanks to its performance in the MeV-GeV domain, substantially improving its predecessors, e-ASTROGAM will open a new window on the non-thermal Universe, making pioneering observations of the most powerful Galactic and extragalactic sources, elucidating the nature of their relativistic outflows and their effects on the surroundings. With a line sensitivity in the MeV energy range one to two orders of magnitude better than previous generation instruments, e-ASTROGAM will determine the origin of key isotopes fundamental for the understanding of supernova explosion and the chemical evolution of our Galaxy. The mission will provide unique data of significant interest to a broad astronomical community, complementary to powerful observatories such as LIGO-Virgo-GEO600-KAGRA, SKA, ALMA, E-ELT, TMT, LSST, JWST, Athena, CTA, IceCube, KM3NeT, and the promise of eLISA.
Keywords: High-Energy Gamma-Ray Astronomy; High-Energy Astrophysics; Nuclear Astrophysics; Compton and Pair Creation Telescope; Gamma-Ray Bursts; Active Galactic Nuclei; Jets; Outflows; Multiwavelength Observations of the Universe; Counterparts of gravitational waves; Fermi; Dark Matter; Nucleosynthesis; Early Universe; Supernovae; Cosmic Rays; Cosmic Antimatter

The exceptionally powerful TeV γ-ray emitters in the Large Magellanic Cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker-Tjus, J.; Berge, D.; et al. (Science, 2015)
The Large Magellanic Cloud, a satellite galaxy of the Milky Way, has been observed with the High Energy Stereoscopic System (H.E.S.S.) above an energy of 100 billion electron volts for a deep exposure of 210 hours. Three sources of different types were detected: the pulsar wind nebula of the most energetic pulsar known, N 157B; the radio-loud supernova remnant N 132D; and the largest nonthermal x-ray shell, the superbubble 30 Dor C. The unique object SN 1987A is, unexpectedly, not detected, which constrains the theoretical framework of particle acceleration in very young supernova remnants. These detections reveal the most energetic tip of a γ-ray source population in an external galaxy and provide via 30 Dor C the unambiguous detection of γ-ray emission from a superbubble.

THE FERMI ALL-SKY VARIABILITY ANALYSIS: A LIST OF FLARING GAMMA-RAY SOURCES AND THE SEARCH FOR TRANSIENTS IN OUR GALAXY - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Antolini, E.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; et al. (Astrophysical Journal, 2013)
In this paper, we present the Fermi All-sky Variability Analysis (FAVA), a tool to systematically study the variability of the gamma-ray sky measured by the Large Area Telescope on board the Fermi Gamma-ray Space Telescope. For each direction on the sky, FAVA compares the number of gamma-rays observed in a given time window to the number of gamma-rays expected for the average emission detected from that direction. This method is used in weekly time intervals to derive a list of 215 flaring gamma-ray sources. We proceed to discuss the 27 sources found at Galactic latitudes smaller than 10 degrees and show that, despite their low latitudes, most of them are likely of extragalactic origin.
Keywords: binaries: general; BL Lacertae objects: general; catalogs; galaxies: active; stars: flare; surveys

The Fermi Galactic Center GeV Excess and Implications for Dark Matter - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2017)
The region around the Galactic Center (GC) is now well established to be brighter at energies of a few GeV than what is expected from conventional models of diffuse gamma-ray emission and catalogs of known gamma-ray sources. We study the GeV excess using 6.5 yr of data from the Fermi Large Area Telescope. We characterize the uncertainty of the GC excess spectrum and morphology due to uncertainties in cosmic-ray source distributions and propagation, uncertainties in the distribution of interstellar gas in the Milky Way, and uncertainties due to a potential contribution from the Fermi bubbles. We also evaluate uncertainties in the excess properties due to resolved point sources of gamma rays. The GC is of particular interest, as it would be expected to have the brightest signal from annihilation of weakly interacting massive dark matter (DM) particles. However, control regions along the Galactic plane, where a DM signal is not expected, show excesses of similar amplitude relative to the local background. Based on the magnitude of the systematic uncertainties, we conservatively report upper limits for the annihilation cross-section as a function of particle mass and annihilation channel.
CRIS-Team WoS Importer:2020-01-15

The first catalog of Fermi-LAT sources below 100 MeV - Principe, Giacomo; Malyshev, Dmitry; Ballet, J.; Funk, Stefan (Astronomy & Astrophysics, 2018)
We present the first Fermi Large Area Telescope (LAT) low energy catalog (1FLE) of sources detected in the energy range 30-100 MeV. The imaging Compton telescope (COMPTEL) onboard NASA's Compton Gamma-Ray Observatory detected sources below 30 MeV, while catalogs of point sources released by the Fermi-LAT and EGRET collaborations use energies above 100 MeV. Because the Fermi-LAT detects gamma rays with energies as low as 20 MeV, we create a list of sources detected in the energy range between 30 and 100 MeV, which closes a gap of point source analysis between the COMPTEL catalog and the Fermi-LAT catalogs. One of the main challenges in the analysis of point sources is the construction of the background diffuse emission model. In our analysis, we use a background-independent method to search for point-like sources based on a wavelet transform implemented in the PGWave code. The 1FLE contains 198 sources detected above 3 sigma significance with eight years and nine months of the Fermi-LAT data. For 187 sources in the 1FLE catalog we have found an association in the Fermi-LAT 3FGL catalog: 148 are extragalactic, 22 are Galactic, and 17 are unclassified in the 3FGL. The ratio of the number of flat spectrum radio quasars (FSRQ) to BL Lacertae (BL Lacs) in 1FLE is three to one, which can be compared with an approximately 1:1 ratio for the 3FGL or a 1:6 ratio for 3FHL. The higher ratio of the FSRQs in the 1FLE is expected due to generally softer spectra of FSRQs relative to BL Lacs. Most BL Lacs in 1FLE are of low-synchrotron peaked blazar type (18 out of 31), which have softer spectra and higher redshifts than BL Lacs on average. Correspondingly, we find that the average redshift of the BL Lacs in 1FLE is higher than in 3FGL or 3FHL. There are 11 sources that do not have associations in the 3FGL. Most of the unassociated sources either come from regions of bright diffuse emission or have several known 3FGL sources in the vicinity, which can lead to source confusion. The remaining unassociated sources have significance less than 4 sigma.
CRIS-Team WoS Importer:2020-01-15

The first Cherenkov Telescope Array Science Symposium - Funk, Stefan; Hinton, J. A. (Nature Astronomy, 2019)
Held in Bologna, Italy, in May 2019, the conference served to engage a wide community in the planning for this first open observatory in very-high-energy gamma rays, expected to start full operation in 2025.
CRIS-Team Scopus Importer:2019-07-16

THE FIRST FERMI-LAT CATALOG OF SOURCES ABOVE 10 GeV - Ackermann, M.; Ajello, M.; Allafort, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Belfiore, A.; Bellazzini, R.; Bernieri, E.; et al. (Astrophysical Journal Supplement Series, 2013)
We present a catalog of gamma-ray sources at energies above 10 GeV based on data from the Large Area Telescope (LAT) accumulated during the first 3 yr of the Fermi Gamma-ray Space Telescope mission. The first Fermi catalog of > 10 GeV sources (1FHL) has 514 sources. For each source we present location, spectrum, a measure of variability, and associations with cataloged sources at other wavelengths. We found that 449 (87%) could be associated with known sources, of which 393 (76% of the 1FHL sources) are active galactic nuclei. Of the 27 sources associated with known pulsars, we find 20 (12) to have significant pulsations in the range > 10 GeV (> 25 GeV). In this work we also report that, at energies above 10 GeV, unresolved sources account for 27% +/- 8% of the isotropic. gamma-ray background, while the unresolved Galactic population contributes only at the few percent level to the Galactic diffuse background. We also highlight the subset of the 1FHL sources that are best candidates for detection at energies above 50-100 GeV with current and future ground-based gamma-ray observatories.
Keywords: catalogs; gamma rays: general

THE FIRST FERMI LAT SUPERNOVA REMNANT CATALOG - Acero, F.; Ackermann, M.; Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal Supplement Series, 2016)
To uniformly determine the properties of supernova remnants (SNRs) at high energies, we have developed the first systematic survey at energies from 1 to 100 GeV using data from the Fermi Large Area Telescope (LAT). Based on the spatial overlap of sources detected at GeV energies with SNRs known from radio surveys, we classify 30 sources as likely GeV SNRs. We also report 14 marginal associations and 245 flux upper limits. A mock catalog in which the positions of known remnants are scrambled in Galactic longitude allows us to determine an upper limit of 22% on the number of GeV candidates falsely identified as SNRs. We have also developed a method to estimate spectral and spatial systematic errors arising from the diffuse interstellar emission model, a key component of all Galactic Fermi LAT analyses. By studying remnants uniformly in aggregate, we measure the GeV properties common to these objects and provide a crucial context for the detailed modeling of individual SNRs. Combining our GeV results with multiwavelength (MW) data, including radio, X-ray, and TeV, we demonstrate the need for improvements to previously sufficient, simple models describing the GeV and radio emission from these objects. We model the GeV and MW emission from SNRs in aggregate to constrain their maximal contribution to observed Galactic cosmic rays.
Keywords: acceleration of particles; catalogs; cosmic rays; gamma-rays: ISM; ISM: supernova remnants; radiation mechanisms: nonthermal

The Fourth Catalog of Active Galactic Nuclei Detected by the Fermi Large Area Telescope - Ajello, M.; Angioni, R.; Axelsson, M.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, R.; Bottacini, E.; et al. (Astrophysical Journal, 2020)
The fourth catalog of active galactic nuclei (AGNs) detected by the Fermi Gamma-ray Space Telescope Large Area Telescope (4LAC) between 2008 August 4 and 2016 August 2 contains . It includes 85% more sources than the previous 3LAC catalog based on 4 yr of data. AGNs represent at least 79% of the high-latitude sources in the fourth Fermi-Large Area Telescope Source Catalog (4FGL), which covers the energy range from 50 MeV to 1 TeV. In addition, gamma-ray AGNs are found at low Galactic latitudes. Most of the 4LAC AGNs are blazars (98%), while the remainder are other types of AGNs. The blazar population consists of 24% Flat Spectrum Radio Quasars (FSRQs), 38% BL Lac-type objects, and 38% blazar candidates of unknown types (BCUs). On average, FSRQs display softer spectra and stronger variability in the gamma-ray band than BL Lacs do, confirming previous findings. All AGNs detected by ground-based atmospheric Cerenkov telescopes are also found in the 4LAC.
CRIS-Team WoS Importer:2020-04-17

The Fourth Catalog of Active Galactic Nuclei Detected by the Fermi Large Area Telescope: Data Release 3 - Ajello, M.; Baldini, L.; Ballet, J.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Bonino, R.; Brill, A.; Bruel, P.; Buson, S.; et al. (Astrophysical Journal Supplement Series, 2022)
An incremental version of the fourth catalog of active galactic nuclei (AGNs) detected by the Fermi Large Area Telescope is presented. This version (4LAC-DR3) derives from the third data release of the 4FGL catalog based on 12 yr of E > 50 MeV gamma-ray data, where the spectral parameters, spectral energy distributions (SEDs), yearly light curves, and associations have been updated for all sources. The new reported AGNs include 587 blazar candidates and four radio galaxies. We describe the properties of the new sample and outline changes affecting the previously published one. We also introduce two new parameters in this release, namely the peak energy of the SED high-energy component and the corresponding flux. These parameters allow an assessment of the Compton dominance, the ratio of the inverse-Compton to the synchrotron-peak luminosities, without relying on X-ray data.
CRIS-Team WoS Importer:2023-01-20

The Gamma-ray Cherenkov Telescope, an end-to end Schwarzschild-Couder telescope prototype proposed for the Cherenkov Telescope Array - Dournaux, J. L.; Abchiche, A.; Allan, D.; Amans, J. P.; Armstrong, T. P.; Balzer, A.; Berge, D.; Boisson, C.; Bousquet, J. -J.; Brown, A. M.; Bryan, M.; Buchholtz, G.; et al. (GROUND-BASED AND AIRBORNE INSTRUMENTATION FOR ASTRONOMY VI, 2016)
CRIS-Team WoS Importer:2020-01-15

The Gamma-ray Cherenkov Telescope for the Cherenkov Telescope Array - Tibaldo, Luigi; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Bergey, D.; Boisson, C.; Bousquet, J. -J.; Brown, A. M.; Bryan, M.; Buchholtz, G.; et al. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2017)
CRIS-Team WoS Importer:2020-01-15

The gamma-ray spectrum of the core of Centaurus A as observed with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) gamma-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE gamma-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter satisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the gamma-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous gamma-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12 sigma on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index Gamma = 2.52 +/- 0.13(stat) +/- 0.20(sys). An updated Fermi-LAT analysis provides evidence for spectral hardening by Delta Gamma similar or equal to 0.4 +/- 0.1 at gamma-ray energies above 2.8(-0.6)(+1.0) GeV at a level of 4.0 sigma. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy distribution (SED) of the core and is suggestive of a new gamma-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies. The absence of significant variability at both GeV and TeV energies does not yet allow disentanglement of the physical nature of this component, though a jet-related origin is possible and a simple two-zone SED model fit is provided to this end.
CRIS-Team WoS Importer:2020-01-15
Keywords: Radiation mechanisms: non-thermal; Gamma rays: galaxies

The GCT camera for the Cherenkov Telescope Array - Lapington, J. S.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, David; Boisson, C.; Bousquet, J. -J.; Bose, R.; Brown, A. M.; Bryan, M.; et al. (ELSEVIER SCIENCE BV, 2017)
The Gamma Cherenkov Telescope (GCT) is one of the designs proposed for the Small Sized Telescope (SST) section of the Cherenkov Telescope Array (CTA). The GCT uses dual-mirror optics, resulting in a compact telescope with good image quality and a large field of view with a smaller, more economical, camera than is achievable with conventional single mirror solutions. The photon counting GCT camera is designed to record the flashes of atmospheric Cherenkov light from gamma and cosmic ray initiated cascades, which last only a few tens of nanoseconds.The GCT optics require that the camera detectors follow a convex surface with a radius of curvature of 1 m and a diameter of similar to 35 cm, which is approximated by tiling the focal plane with 32 modules. The first camera prototype is equipped with multi-anode photomultipliers, each comprising an 8x8 array of 6x6 mm(2) pixels to provide the required angular scale, adding up to 2048 pixels in total. Detector signals are shaped, amplified and digitised by electronics based on custom ASICs that provide digitisation at 1 GSample/s. The camera is self-triggering, retaining images where the focal plane light distribution matches predefined spatial and temporal criteria. The electronics are housed in the liquid-cooled, sealed camera enclosure. LED flashers at the corners of the focal plane provide a calibration source via reflection from the secondary mirror.The first GCT camera prototype underwent preliminary laboratory tests last year. In November 2015, the camera was installed on a prototype GCT telescope (SST-GATE) in Paris and was used to successfully record the first Cherenkov light of any CTA prototype, and the first Cherenkov light seen with such a dual-mirror optical system. A second full-camera prototype based on Silicon Photomultipliers is under construction. Up to 35 GCTs are envisaged for CTA.
Keywords: GCT; Cherenkov Telescope Array; Schwarzschild-Couder; Imaging air Cherenkov telescope; Photon-counting; Camera

The GCT camera for the Cherenkov Telescope Array - Lapington, J. S.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, David; Boisson, C.; Bousquet, J. -J.; Bose, R.; Brown, A. M.; Bryan, M.; et al. (ELSEVIER SCIENCE BV, 2017)
The Gamma Cherenkov Telescope (GCT) is one of the designs proposed for the Small Sized Telescope (SST) section of the Cherenkov Telescope Array (CTA). The GCT uses dual-mirror optics, resulting in a compact telescope with good image quality and a large field of view with a smaller, more economical, camera than is achievable with conventional single mirror solutions. The photon counting GCT camera is designed to record the flashes of atmospheric Cherenkov light from gamma and cosmic ray initiated cascades, which last only a few tens of nanoseconds.The GCT optics require that the camera detectors follow a convex surface with a radius of curvature of 1 m and a diameter of similar to 35 cm, which is approximated by tiling the focal plane with 32 modules. The first camera prototype is equipped with multi-anode photomultipliers, each comprising an 8x8 array of 6x6 mm(2) pixels to provide the required angular scale, adding up to 2048 pixels in total. Detector signals are shaped, amplified and digitised by electronics based on custom ASICs that provide digitisation at 1 GSample/s. The camera is self-triggering, retaining images where the focal plane light distribution matches predefined spatial and temporal criteria. The electronics are housed in the liquid-cooled, sealed camera enclosure. LED flashers at the corners of the focal plane provide a calibration source via reflection from the secondary mirror.The first GCT camera prototype underwent preliminary laboratory tests last year. In November 2015, the camera was installed on a prototype GCT telescope (SST-GATE) in Paris and was used to successfully record the first Cherenkov light of any CTA prototype, and the first Cherenkov light seen with such a dual-mirror optical system. A second full-camera prototype based on Silicon Photomultipliers is under construction. Up to 35 GCTs are envisaged for CTA.
Keywords: GCT; Cherenkov Telescope Array; Schwarzschild-Couder; Imaging air Cherenkov telescope; Photon-counting; Camera

The HESS Galactic plane survey - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
We present the results of the most comprehensive survey of the Galactic plane in very high-energy (VHE) gamma-rays, including a public release of Galactic sky maps, a catalog of VHE sources, and the discovery of 16 new sources of VHE gamma-rays. The High Energy Spectroscopic System (H.E.S.S.) Galactic plane survey (HGPS) was a decade-long observation program carried out by the H.E.S.S. I array of Cherenkov telescopes in Namibia from 2004 to 2013. The observations amount to nearly 2700 h of quality-selected data, covering the Galactic plane at longitudes from l = 250 degrees to 65 degrees and latitudes vertical bar b vertical bar <= 3 degrees. In addition to the unprecedented spatial coverage, the HGPS also features a relatively high angular resolution (0.08 degrees approximate to 5 arcmin mean point spread function 68% containment radius), sensitivity (less than or similar to 1.5% Crab flux for point-like sources), and energy range (0.2-100 TeV). We constructed a catalog of VHE gamma-ray sources from the HGPS data set with a systematic procedure for both source detection and characterization of morphology and spectrum. We present this likelihood-based method in detail, including the introduction of a model component to account for unresolved, large-scale emission along the Galactic plane. In total, the resulting HGPS catalog contains 78 VHE sources, of which 14 are not reanalyzed here, for example, due to their complex morphology, namely shell-like sources and the Galactic center region. Where possible, we provide a firm identification of the VHE source or plausible associations with sources in other astronomical catalogs. We also studied the characteristics of the VHE sources with source parameter distributions. 16 new sources were previously unknown or unpublished, and we individually discuss their identifications or possible associations. We firmly identified 31 sources as pulsar wind nebulae (PWNe), supernova remnants (SNRs), composite SNRs, or gamma-ray binaries. Among the 47 sources not yet identified, most of them (36) have possible associations with cataloged objects, notably PWNe and energetic pulsars that could power VHE PWNe.
Keywords: gamma rays: general; surveys; Galaxy: general

The HESS survey of the inner galaxy in very high energy gamma rays - Funk, Stefan; et al. (Astrophysical Journal, 2006)
We report on a survey of the inner part of the Galactic plane in very high energy gamma rays with the H. E. S. S. Cerenkov telescope system. The Galactic plane between +/- 30 degrees in longitude and 3 +/-degrees in latitude relative to the Galactic center was observed in 500 pointings for a total of 230 hr, reaching an average flux sensitivity of 2% of the Crab Nebula at energies above 200 GeV. Fourteen previously unknown sources were detected at a significance level greater than 4 sigma after accounting for all trials involved in the search. Initial results on the eight most significant of these sources were already reported elsewhere (Aharonian and coworkers). Here we present detailed spectral and morphological information for all the new sources, along with a discussion on possible counterparts in other wavelength bands. The distribution in Galactic latitude of the detected sources appears to be consistent with a scale height in the Galactic disk for the parent population smaller than 100 pc, consistent with expectations for supernova remnants and/or pulsar wind nebulae.
CRIS-Team WoS Importer:2020-01-15

The High-Altitude Water Cherenkov (HAWC) observatory in México: The primary detector - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Araya, M.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Barber, A. S.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
The High-Altitude Water Cherenkov (HAWC) observatory is a second-generation continuously operated, wide field-of-view, TeV gamma-ray observatory. The HAWC observatory and its analysis techniques build on experience of the Milagro experiment in using ground-based water Cherenkov detectors for gamma-ray astronomy. HAWC is located on the Sierra Negra volcano in México at an elevation of 4100 meters above sea level. The completed HAWC observatory principal detector (HAWC) consists of 300 closely spaced water Cherenkov detectors, each equipped with four photomultiplier tubes to provide timing and charge information to reconstruct the extensive air shower energy and arrival direction. The HAWC observatory has been optimized to observe transient and steady emission from sources of gamma rays within an energy range from several hundred GeV to several hundred TeV. However, most of the air showers detected are initiated by cosmic rays, allowing studies of cosmic rays also to be performed. This paper describes the characteristics of the HAWC main array and its hardware.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Astrophysics; High energy physics — experiment; Nuclear experiment; Physics — instrumentation and detectors; Water Cherenkov Detectors

The high-energy γ-ray emission of AP Librae - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
The γ-ray spectrum of the low-frequency-peaked BL Lac (LBL) object AP Librae is studied, following the discovery of very-high-energy (VHE; E > 100 GeV) γ-ray emission up to the TeV range by the H.E.S.S. experiment. This makes AP Librae one of the few VHE emitters of the LBL type. The measured spectrum yields a flux of (8.8 ± 1.5stat ± 1.8sys) × 10-12 cm-2 s-1 above 130 GeV and a spectral index of Γ = 2.65 ± 0.19stat ± 0.20sys. This study also makes use of Fermi-LAT observations in the high energy (HE, E> 100 MeV) range, providing the longest continuous light curve (5 years) ever published on this source. The source underwent a flaring event between MJD 56 306-56 376 in the HE range, with a flux increase of a factor of 3.5 in the 14 day bin light curve and no significant variation in spectral shape with respect to the low-flux state. While the H.E.S.S. and (low state) Fermi-LAT fluxes are in good agreement where they overlap, a spectral curvature between the steep VHE spectrum and the Fermi-LAT spectrum is observed. The maximum of the γ-ray emission in the spectral energy distribution is located below the GeV energy range.
Keywords: BL Lacertae objects: individual: AP Librae; Galaxies: active; Gamma rays: galaxies

The Influence of Satellite Trails on H.E.S.S. Gamma-Ray Astronomical Observations - Spencer, Samuel; Lang, Thomas; Mitchell, Alison (38th International Cosmic Ray Conference (ICRC2023), 2023)
The number of satellites launched into low earth orbit has almost tripled (to over 4000) in the last three years due to the increasing commercialisation of space. Satellite constellations with a total of over 400,000 satellites are proposed to be launched in the near future. Many of these satellites are highly reflective, resulting in a high optical brightness that affects ground-based astronomical observations across the electromagnetic spectrum. Despite this, the potential effect of these satellites on Imaging Atmospheric Cherenkov Telescopes (IACTs) has so far been assumed to be negligible due to their nanosecond integration times. This has, however, never been verified. We aim to identify satellite trails in data taken by the High Energy Stereoscopic System (H.E.S.S.) IACT array in Namibia, using Night Sky Background (NSB) data from the CT5 camera installed in 2019. We determine which observation times and pointing directions are affected the most, and evaluate the impact on Hillas parameters used for classification and reconstruction of high-energy Extensive Air Shower events. Finally, we predict how future planned satellite launches will affect gamma-ray observations with IACTs.<br

The KM3NeT potential for the next core-collapse supernova observation with neutrinos: KM3NeT Collaboration - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (European Physical Journal C: Particles and Fields, 2021)
The KM3NeT research infrastructure is under construction in the Mediterranean Sea. It consists of two water Cherenkov neutrino detectors, ARCA and ORCA, aimed at neutrino astrophysics and oscillation research, respectively. Instrumenting a large volume of sea water with ∼ 6200 optical modules comprising a total of ∼ 200 , 000 photomultiplier tubes, KM3NeT will achieve sensitivity to ∼10MeV neutrinos from Galactic and near-Galactic core-collapse supernovae through the observation of coincident hits in photomultipliers above the background. In this paper, the sensitivity of KM3NeT to a supernova explosion is estimated from detailed analyses of background data from the first KM3NeT detection units and simulations of the neutrino signal. The KM3NeT observational horizon (for a 5σ discovery) covers essentially the Milky-Way and for the most optimistic model, extends to the Small Magellanic Cloud (∼60kpc). Detailed studies of the time profile of the neutrino signal allow assessment of the KM3NeT capability to determine the arrival time of the neutrino burst with a few milliseconds precision for sources up to 5–8 kpc away, and detecting the peculiar signature of the standing accretion shock instability if the core-collapse supernova explosion happens closer than 3–5 kpc, depending on the progenitor mass. KM3NeT’s capability to measure the neutrino flux spectral parameters is also presented.
CRIS-Team Scopus Importer:2021-06-11

THE LOW-FREQUENCY RADIO CATALOG OF FLAT-SPECTRUM SOURCES - Massaro, F.; Giroletti, M.; D'Abrusco, R.; Masetti, N.; Paggi, A.; Cowperthwaite, Philip S.; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2014)
A well known property of the gamma-ray sources detected by Cos-B in the 1970s, by the Compton Gamma-Ray Observatory in the 1990s, and recently by the Fermi observations is the presence of radio counterparts, particularly for those associated with extragalactic objects. This observational evidence is the basis of the radio-gamma-ray connection established for the class of active galactic nuclei known as blazars. In particular, the main spectral property of the radio counterparts associated with gamma-ray blazars is that they show a flat spectrum in the GHz frequency range. Our recent analysis dedicated to search blazar-like candidates as potential counterparts for the unidentified gamma-ray sources allowed us to extend the radio-gamma-ray connection in the MHz regime. We also showed that blazars below 1 GHz maintain flat radio spectra. Thus, on the basis of these new results, we assembled a low-frequency radio catalog of flat-spectrum sources built by combining the radio observations of the Westerbork Northern Sky Survey and of the Westerbork in the southern hemisphere catalog with those of the NRAO Very Large Array Sky survey (NVSS). This could be used in the future to search for new, unknown blazar-like counterparts of gamma-ray sources. First, we found NVSS counterparts of Westerbork Synthesis Radio Telescope radio sources, and then we selected flat-spectrum radio sources according to a new spectral criterion, specifically defined for radio observations performed below 1 GHz. We also described the main properties of the catalog listing 28,358 radio sources and their logN-logS distributions. Finally, a comparison with the Green Bank 6 cm radio source catalog was performed to investigate the spectral shape of the low-frequency flat-spectrum radio sources at higher frequencies.
Keywords: galaxies: active; quasars: general; radiation mechanisms: non-thermal; surveys

The magnetic bootstrap - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

The Observability of Plasmoid-powered gamma-Ray Flares with the Fermi Large Area Telescope - Meyer, Manuel; Petropoulou, Maria; Christie, Ian M. (Astrophysical Journal, 2021)
The exact mechanism for the production of fast gamma-ray variability in blazars remains debated. Magnetic reconnection, in which plasmoids filled with relativistic particles and magnetic fields are formed, is a viable candidate to explain the broadband electromagnetic spectrum and variability of these objects. Using state-of-the-art magnetic reconnection simulations, we generate realistic gamma-ray light curves that would be observed with the Fermi Large Area Telescope. A comparison with observed gamma-ray flares from flat spectrum radio quasars (FSRQs) reveals that magnetic reconnection events lead to comparable flux levels and variability patterns, in particular, when the reconnection layer is slightly misaligned with the line of sight. Emission from fast plasmoids moving close to the line of sight could explain the fast variability on the timescales of minutes for which evidence has been found in observations of FSRQs. Our results motivate improvements in existing radiative transfer simulations as well as dedicated searches for fast variability as evidence for magnetic reconnection events.
CRIS-Team WoS Importer:2021-05-14

The origin of UHECR: the distance to the nearest source and the dipole - Guedes Lang, Rodrigo; Taylor, Andrew M.; de Souza, Vitor (Proceedings of Science, 2022)
A semi-analytical, fast and robust method for the propagation of ultra-high-energy cosmic rays (UHECR) under extra-galactic turbulent magnetic fields presented by the authors in previous works is described in detail. Under the assumption of dominant turbulent fields, it is possible to obtain the energy spectrum, as well as the relative contribution from each source, and the angular distribution of arrival directions without the need for 4-D simulations. This method provides an important tool in the quest for the origin of UHECR. A brief overview of the results already obtained with it is presented. The relative contribution to the energy spectrum from sources in different distance shells is elucidated and constraints of a few tens of Mpc, depending on composition, are imposed to the distance to the nearest source. A solid understanding of the arising of the dipole as well as its evolution with energy is built. The importance of a power spectrum analysis in energies detected by experiments is discussed.
CRIS-Team Scopus Importer:2022-12-23

The radio counterpart of the likely TeV binary HESS J0632+057 - Skilton, J. L.; Pandey-Pommier, M.; Hinton, J. A.; Cheung, C. C.; Aharonian, F. A.; Brucker, Julia; Dubus, Guillaume; Fiasson, A.; Funk, Stefan; Gallant, Y.; Marcowith, A.; Reimer, Olaf (Monthly Notices of the Royal Astronomical Society, 2009)
The few known gamma-ray binary systems are all associated with variable radio and X-ray emission. The TeV source HESS J0632+057, apparently associated with the Be star MWC 148, is plausibly I new member of this class. Following the identification of a variable X-ray counterpart to the TeV source we conducted Giant Metrewave Radio Telescope (GMRT) and Very Large Array (VLA) observations in 2008 June-September to search for the radio counterpart of this object. A point-like radio source at the position of the star is detected in both 1280-MHz GMRT and 5-GHz VLA observations, with an average spectral index, alpha, of similar to 0.6. In the VLA data there is significant flux variability oil similar to month time-scales around the mean flux density of approximate to 0.3 mJy. These radio properties (and the overall spectral energy distribution) are consistent with an interpretation of HESS J0632+057 as a lower power analogue of the established gamma-ray binary systems.
CRIS-Team WoS Importer:2020-01-15

The Search for Spatial Extension in High-latitude Sources Detected by the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal Supplement Series, 2018)
We present a search for spatial extension in high-latitude (vertical bar b vertical bar > 5 degrees) sources in recent Fermi point source catalogs. The result is the Fermi High-Latitude Extended Sources Catalog, which provides source extensions (or upper limits thereof) and likelihood profiles for a suite of tested source morphologies. We find 24. extended sources, 19 of which were not previously characterized as extended. These include sources that are potentially associated with supernova remnants and star-forming regions. We also found extended.-ray emission in the vicinity of the Cen. A radio lobes and-at GeV energies for the first time-spatially coincident with the radio emission of the SNR CTA 1, as well as from the Crab Nebula. We also searched for halos around active galactic nuclei, which are predicted from electromagnetic cascades induced by the e(+)e(-) pairs that are deflected in intergalactic magnetic fields. These pairs are produced when gamma-rays interact with background radiation fields. We do not find evidence for extension in individual sources or in stacked source samples. This enables us to place limits on the flux of the extended source components, which are then used to constrain the intergalactic magnetic field to be stronger than 3 x 10(-16) G for a coherence length lambda greater than or similar to 10 kpc, even when conservative assumptions on the source duty cycle are made. This improves previous limits by several orders of magnitude.
Keywords: BL Lacertae objects: general; catalogs; gamma rays: general; ISM: H II Regions; ISM: supernova remnants

The Search for Spatial Extension in High-latitude Sources Detected by the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal Supplement Series, 2018)
We present a search for spatial extension in high-latitude (vertical bar b vertical bar > 5 degrees) sources in recent Fermi point source catalogs. The result is the Fermi High-Latitude Extended Sources Catalog, which provides source extensions (or upper limits thereof) and likelihood profiles for a suite of tested source morphologies. We find 24. extended sources, 19 of which were not previously characterized as extended. These include sources that are potentially associated with supernova remnants and star-forming regions. We also found extended.-ray emission in the vicinity of the Cen. A radio lobes and-at GeV energies for the first time-spatially coincident with the radio emission of the SNR CTA 1, as well as from the Crab Nebula. We also searched for halos around active galactic nuclei, which are predicted from electromagnetic cascades induced by the e(+)e(-) pairs that are deflected in intergalactic magnetic fields. These pairs are produced when gamma-rays interact with background radiation fields. We do not find evidence for extension in individual sources or in stacked source samples. This enables us to place limits on the flux of the extended source components, which are then used to constrain the intergalactic magnetic field to be stronger than 3 x 10(-16) G for a coherence length lambda greater than or similar to 10 kpc, even when conservative assumptions on the source duty cycle are made. This improves previous limits by several orders of magnitude.
Keywords: BL Lacertae objects: general; catalogs; gamma rays: general; ISM: H II Regions; ISM: supernova remnants

The Second Catalog of Flaring Gamma-Ray Sources from the Fermi All-sky Variability Analysis - Abdollahi, S.; Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; et al. (Astrophysical Journal, 2017)
We present the second catalog of flaring gamma-ray sources (2FAV) detected with the Fermi All-sky Variability Analysis (FAVA), a tool that blindly searches for transients over the entire sky observed by the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope. With respect to the first FAVA catalog, this catalog benefits from a larger data set, the latest LAT data release (Pass 8), as well as from an improved analysis that includes likelihood techniques for a more precise localization of the transients. Applying this analysis to the first 7.4 years of Fermi observations, and in two separate energy bands 0.1-0.8 GeV and 0.8-300 GeV, a total of 4547 flares were detected with significance greater than 6s (before trials), on the timescale of one week. Through spatial clustering of these flares, 518 variable gamma-ray sources were identified. Based on positional coincidence, likely counterparts have been found for 441 sources, mostly among the blazar class of active galactic nuclei. For 77 2FAV sources, no likely gamma-ray counterpart has been found. For each source in the catalog, we provide the time, location, and spectrum of each flaring episode. Studying the spectra of the flares, we observe a harder-when-brighter behavior for flares associated with blazars, with the exception of BL Lac flares detected in the low-energy band. The photon indexes of the flares are never significantly smaller than 1.5. For a leptonic model, and under the assumption of isotropy, this limit suggests that the spectrum of freshly accelerated electrons is never harder than p similar to 2.
Keywords: astroparticle physics; catalogs; galaxies: active; gamma rays: general; techniques: photometric

THE SECOND FERMI LARGE AREA TELESCOPE CATALOG OF GAMMA-RAY PULSARS - Abdo, A. A.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; Belfiore, A.; Bellazzini, R.; Bhattacharyya, B.; Bissaldi, E.; et al. (Astrophysical Journal Supplement Series, 2013)
This catalog summarizes 117 high-confidence >= 0.1 GeV gamma-ray pulsar detections using three years of data acquired by the Large Area Telescope (LAT) on the Fermi satellite. Half are neutron stars discovered using LAT data through periodicity searches in gamma-ray and radio data around LAT unassociated source positions. The 117 pulsars are evenly divided into three groups: millisecond pulsars, young radio-loud pulsars, and young radio-quiet pulsars. We characterize the pulse profiles and energy spectra and derive luminosities when distance information exists. Spectral analysis of the off-peak phase intervals indicates probable pulsar wind nebula emission for four pulsars, and off-peak magnetospheric emission for several young and millisecond pulsars. We compare the gamma-ray properties with those in the radio, optical, and X-ray bands. We provide flux limits for pulsars with no observed gamma-ray emission, highlighting a small number of gamma-faint, radio-loud pulsars. The large, varied gamma-ray pulsar sample constrains emission models. Fermi's selection biases complement those of radio surveys, enhancing comparisons with predicted population distributions.
Keywords: catalogs; pulsars: general; stars: neutron

The Southern Wide-Field Gamma-Ray Observatory (SWGO): A Next-Generation Ground-Based Survey Instrument for VHE Gamma-Ray Astronomy - Spencer, Samuel; et al. (2019)

THE SPECTRUM AND MORPHOLOGY OF THE FERMI BUBBLES - Ackermann, M.; Albert, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; Bottacini, E.; et al. (Astrophysical Journal, 2014)
The Fermi bubbles are two large structures in the gamma-ray sky extending to 55 degrees above and below the Galactic center. We analyze 50 months of Fermi Large Area Telescope data between 100MeV and 500 GeV above 10 degrees in Galactic latitude to derive the spectrum and morphology of the Fermi bubbles. We thoroughly explore the systematic uncertainties that arise when modeling the Galactic diffuse emission through two separate approaches. The gamma-ray spectrum is well described by either a log parabola or a power law with an exponential cutoff. We exclude a simple power law with more than 7 sigma significance. The power law with an exponential cutoff has an index of 1.9 +/- 0.2 and a cutoff energy of 110 +/- 50 GeV. We find that the gamma-ray luminosity of the bubbles is 4.4(-0.9)(+2.4) x 10(37) erg s(-1). We confirm a significant enhancement of gamma-ray emission in the southeastern part of the bubbles, but we do not find significant evidence for a jet. No significant variation of the spectrum across the bubbles is detected. The width of the boundary of the bubbles is estimated to be 3.4(-2.6)(+3.7) deg. Both inverse Compton (IC) models and hadronic models including IC emission from secondary leptons fit the gamma-ray data well. In the IC scenario, synchrotron emission from the same population of electrons can also explain the WMAP and Planck microwave haze with a magnetic field between 5 and 20 mu G.
Keywords: astroparticle physics; cosmic rays; Galaxy: general; Galaxy: halo; gamma rays: diffuse background; methods: data analysis

THE SPECTRUM OF ISOTROPIC DIFFUSE GAMMA-RAY EMISSION BETWEEN 100 MeV AND 820 GeV - Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; et al. (Astrophysical Journal, 2015)
The gamma-ray sky can be decomposed into individually detected sources, diffuse emission attributed to the interactions of Galactic cosmic rays with gas and radiation fields, and a residual all-sky emission component commonly called the isotropic diffuse gamma-ray background (IGRB). The IGRB comprises all extragalactic emissions too faint or too diffuse to be resolved in a given survey, as well as any residual Galactic foregrounds that are approximately isotropic. The first IGRB measurement with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope (Fermi) used 10 months of sky-survey data and considered an energy range between 200 MeV and 100 GeV. Improvements in event selection and characterization of cosmic-ray backgrounds, better understanding of the diffuse Galactic emission (DGE), and a longer data accumulation of 50 months allow for a refinement and extension of the IGRB measurement with the LAT, now covering the energy range from 100 MeV to 820 GeV. The IGRB spectrum shows a significant high-energy cutoff feature and can be well described over nearly four decades in energy by a power law with exponential cutoff having a spectral index of 2.32 +/- 0.02 and a break energy of (279 +/- 52) GeV using our baseline DGE model. The total intensity attributed to the IGRB is (7.2 +/- 0.6) x 10(-6) cm(-2) s(-1) sr(-1) above 100 MeV, with an additional +15%/-30% systematic uncertainty due to the Galactic diffuse foregrounds.
Keywords: diffuse radiation; gamma rays: diffuse background

The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit gamma-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E> 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.
CRIS-Team WoS Importer:2020-01-15
Keywords: Astroparticle physics; Galaxies: starburst; Gamma rays: galaxies

The supernova remnant W49B as seen with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
The supernova remnant (SNR) W49B originated from a core-collapse supernova that occurred between one and four thousand years ago, and subsequently evolved into a mixed-morphology remnant, which is interacting with molecular clouds (MC). Gamma-ray observations of SNR-MC associations are a powerful tool to constrain the origin of Galactic cosmic rays, as they can probe the acceleration of hadrons through their interaction with the surrounding medium and subsequent emission of non-thermal photons. We report the detection of a gamma-ray source coincident with W49B at very high energies (VHE; E > 100 GeV) with the H.E.S.S. Cherenkov telescopes together with a study of the source with five years of Fermi-LAT high-energy gamma-ray (0.06-300 GeV) data. The smoothly connected, combined source spectrum, measured from 60 MeV to multi-TeV energies, shows two significant spectral breaks at 304 +/- 20 MeV and 8.4(-2.5)(+2.5) GeV; the latter is constrained by the joint fit from the two instruments. The detected spectral features are similar to those observed in several other SNR-MC associations and are found to be indicative of gamma-ray emission produced through neutral-pion decay.
Keywords: gamma rays: general; ISM: supernova remnants; ISM: clouds

The trigger system of the HESS telescope array - Funk, Stefan; et al. (Astroparticle Physics, 2004)
H.E.S.S. - The High Energy Stereoscopic System - is a new system of large atmospheric Cherenkov telescopes for GeV/TeV gamma-ray astronomy. This paper describes the trigger system of H.E.S.S. with emphasis on the multi-telescope array level trigger. The system trigger requires the simultaneous detection of air-showers by several telescopes at the hardware level. This requirement allows a suppression of background events which in turn leads to a lower system energy threshold for the detection of gamma-rays. The implementation of the H.E.S.S. trigger system is presented along with data taken to characterise its performance. (C) 2004 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Three-dimensional imaging of xylem at cell wall level through near field nano holotomography - Koddenberg, Tim; Greving, Imke; Hagemann, Johannes; Flenner, Silja; Krause, Andreas; Laipple, Daniel; Klein, Kim C.; Schmitt, Uwe; Schuster, Max; Wolf, Andreas; Seifert, Maria; Ludwig, Veronika; et al. (Scientific Reports, 2021)
Detailed imaging of the three-dimensionally complex architecture of xylary plants is important for studying biological and mechanical functions of woody plants. Apart from common two-dimensional microscopy, X-ray micro-computed tomography has been established as a three-dimensional (3D) imaging method for studying the hydraulic function of wooden plants. However, this X-ray imaging method can barely reach the resolution needed to see the minute structures (e.g. pit membrane). To complement the xylem structure with 3D views at the nanoscale level, X-ray near-field nano-holotomography (NFH) was applied to analyze the wood species Pinus sylvestris and Fagus sylvatica. The demanded small specimens required focused ion beam (FIB) application. The FIB milling, however, influenced the image quality through gallium implantation on the cell-wall surfaces. The measurements indicated that NFH is appropriate for imaging wood at nanometric resolution. With a 26 nm voxel pitch, the structure of the cell-wall surface in Pinus sylvestris could be visualized in genuine detail. In wood of Fagus sylvatica, the structure of a pit pair, including the pit membrane, between two neighboring fibrous cells could be traced tomographically.
CRIS-Team Scopus Importer:2021-03-19

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Towards a 3D likelihood analysis in very-high-energy γ-ray astronomy: The case of H.E.S.S. - Mohrmann, Lars; Nakashima, Kaori; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; van Eldik, Christopher; Ohm, Stefan (Proceedings of Science, 2019)
The estimation of the residual background due to cosmic ray-induced air showers represents a key element of every analysis of Imaging Atmospheric Cherenkov Telescope (IACT) data. In the past, most techniques have relied on a measurement of the background in supposedly source-free regions within the observed field of view. However, this approach is problematic in regions with many (potentially overlapping) γ-ray sources or large-scale diffuse γ-ray emission, like e.g. the Galactic Plane. For these cases, a template-based 3D likelihood analysis might be superior. In this approach, a spectro-morphological model template, consisting of one or multiple source components and a background component, is fit to the data, resulting in a complete spectral and spatial description of the field of view. In this contribution, we present our efforts to establish a 3D likelihood analysis for data taken with the H.E.S.S. system of IACTs, using the open-source analysis packages ctools and Gammapy. In particular, we focus on the development of a template model for the cosmic ray-induced background - a major challenge in such an approach - from archival H.E.S.S. data. We characterise the obtained model and demonstrate its application using publicly available H.E.S.S. data. The validation of this analysis approach on experimental data also constitutes an important step towards the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team Scopus Importer:2021-04-20

Towards Gaussian States for the Holonomy-Flux Weyl Algebra - Seeger, Robert; Sahlmann, Hanno (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)
The objective of this Master’s thesis is to consider the well-known framework of Weyl algebras and quasifree states in order to find out if it is possible to apply the general ideas, coming from algebraic quantum theory, to the theory of loop quantum gravity. Starting from the U(1) toy-model of the canonical commutation relation of the holonomy-flux algebra, underlying loop quantum gravity, we construct a Weyl C*-algebra generated by so-called Weyl elements that arise from combining holonomies and exponentiated electric fluxes, which are the canonically conjugated variables of the theory. Quasifree states are a certain notion of Gaussian states, directly emerging from Weyl algebras. Because it seems to be impossible to establish such states on the algebra we found, we develop a different notion states that is only Gaussian in one of the variables and hence is referred to as almost-quasifree states. For such a state, which is Gaussian in the fluxes, we find a representation on a Hilbert space that combines the Hilbert space of loop quantum gravity with the Fock space of a scalar field. For the canonical commutation relation of the actual theory, which involves SU(2) Yang-Mills holonomies and the corresponding fluxes, we try to generalize our results. It is possible to define Weyl-like elements for holonomies along a single path and a set of exponentiated fluxes. We work toward a notion of elements that take care of more distinct edges or even graphs. It is, however, not clear if these also generate a C*-algebra. Without an underlying Weyl algebra we successfully generalize the almost-quasifree representation, found for the toy-model, and analyze its properties by re-deriving the area operator of loop quantum gravity in this new representation.<br

Towards high-repetition rate petawatt laser experiments with cryogenic jets using a mechanical chopper system - Rehwald, M.; Assenbaum, S.; Bernert, C.; Curry, C. B.; Gauthier, M.; Glenzer, S. H.; Göde, S.; Schönwälder, Christopher; Schramm, U.; Treffert, F.; Zeil, K. (Journal of Physics: Conference Series, 2023)
Laser-plasma based ion accelerators require suitable high-repetition rate target systems that enable systematic studies at controlled plasma conditions and application-relevant particle flux. Self-refreshing, micrometer-sized cryogenic jets have proven to be an ideal target platform. Yet, operation of such systems in the harsh environmental conditions of high power laser induced plasma experiments have turned out to be challenging. Here we report on recent experiments deploying a cryogenic hydrogen jet as a source of pure proton beams generated with the PW-class ultrashort pulse laser DRACO. Damage to the jet target system during application of full energy laser shots was prevented by implementation of a mechanical chopper system interrupting the direct line of sight between the laser plasma interaction zone and the jet source.
CRIS-Team Scopus Importer:2023-02-10

Trigger performance verification of the FlashCam prototype camera - Sailer, S.; Werner, F.; Hermann, G.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Canelli, F.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
FlashCam is a camera proposed for the medium-sized telescopes of the Cherenkov Telescope Array (CTA). We compare camera trigger rates obtained from measurements with the camera prototype in the laboratory and Monte Carlo simulations, when scanning the parameter space of the fully-digital trigger logic and the intensity of a continuous light source mimicking the night sky background (NSB) during on-site operation. The comparisons of the measured data results to the Monte Carlo simulations are used to verify the FlashCam trigger logic and the expected trigger performance.
CRIS-Team Scopus Importer:2019-06-25
Keywords: CTA; DAQ; Data management; FlashCam; Front end; Trigger

Ultra-High-Energy Astroparticles as Probes for Lorentz Invariance Violation - Guedes Lang, Rodrigo; Martinez-Huerta, Humberto; De Souza, Vitor (Universe, 2022)
Compelling evidence for Lorentz invariance violation (LIV) would demand a complete revision of modern physics. Therefore, searching for a signal or extending the validity of the invariance is fundamental for building our understanding of the extreme phenomena in the Universe. In this paper, we review the potential of ultra-high-energy astroparticles in setting limits on LIV. The standard framework of LIV studies in astroparticle physics is reviewed and its use on the electromagnetic and hadronic sectors are discussed. In particular, the current status of LIV tests using experimental data on ultra-high-energy photons and cosmic rays is addressed. A detailed discussion with improved argumentation about the LIV kinematics of the relevant interactions is shown. The main previous results are presented together with new calculations based on recently published astrophysical models.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Lorentz invariance violation; UHE photons; UHECR

Unconventional conductivity increase in multilayer black phosphorus - Kolesnik-Gray, Maria; Meingast, Laura; Siebert, Martin; Unbehaun, Tim; Huf, Tobias; Ellrott, Günter; Abellan Saez, Gonzalo; Wild, Stefan; Lloret Segura, Vicente Josep; Mundloch, Udo; Schwarz, Julian; Niebauer, Michael; et al. (npj 2D Materials and Applications, 2023)
Multilayers of so-called 2D van der Waals materials have gained considerable attention as active components of next-generation electronic and optoelectronic technologies, with semiconducting black phosphorus (BP) regarded as one of the most promising systems. The applicability and performance limits of BP in both stand-alone and heterostructure-based multilayer devices are determined by individual flake charge transport properties, which synergistically depend on the number of layers and the strength of interlayer coupling between those. In this work, we study the DC electrical transport characteristics of high-quality BP field-effect devices within a wide range of flake thicknesses at room temperature. The experimental data show a non-trivial increase in conductivity and hole density with a reduced number of layers while maintaining constant field-effect mobility due to the prevalence of electron–phonon scattering. Based on the solution of the 1D Schrödinger–Poisson equation, we find that the observed phenomena are a direct consequence of non-negligible interlayer coupling, which in turn causes a local redistribution of free charge carriers towards the central layers. Our data show that due to the electrostatic conditions at the flake surfaces, a naturally protected 2D hole gas can be encapsulated in flakes as high as 10 nm, which preserves the bulk-like bandgap and effective carrier masses due to the electrostatic environment.
CRIS-Team Scopus Importer:2023-04-14

Unresolved Gamma-Ray Sky through its Angular Power Spectrum - Ackermann, M.; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; et al. (Physical Review Letters, 2018)
The gamma-ray sky has been observed with unprecedented accuracy in the last decade by the Fermi-large area telescope (LAT), allowing us to resolve and understand the high-energy Universe. The nature of the remaining unresolved emission [unresolved gamma-ray background (UGRB)] below the LAT source detection threshold can be uncovered by characterizing the amplitude and angular scale of the UGRB fluctuation field. This Letter presents a measurement of the UGRB autocorrelation angular power spectrum based on eight years of Fermi-LAT Pass 8 data products. The analysis is designed to be robust against contamination from resolved sources and noise systematics. The sensitivity to subthreshold sources is greatly enhanced with respect to previous measurements. We find evidence (with similar to 3.7 sigma significance) that the scenario in which two classes of sources contribute to the UGRB signal is favored over a single class. A double power law with exponential cutoff can explain the anisotropy energy spectrum well, with photon indices of the two populations being 2.55 +/- 0.23 and 1.86 +/- 0.15.
CRIS-Team WoS Importer:2020-01-15

UNVEILING THE NATURE OF UNIDENTIFIED gamma-RAY SOURCES. VI. gamma-RAY BLAZAR CANDIDATES IN THE WISH SURVEY AND THEIR RADIO PROPERTIES - Nori, M.; Giroletti, M.; Massaro, F.; D'Abrusco, R.; Paggi, A.; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2014)
According to the Fermi Large Area Telescope Second Source Catalog (2FGL), about one-third of the gamma-ray sources listed have no assigned counterparts at lower energies. Many statistical methods have been developed to find proper counterparts for these sources. We explore the sky area covered at low radio frequency by the Westerbork in the Southern Hemisphere (WISH) survey to search for blazar-like associations among the unidentified gamma-ray sources (UGSs) listed in the 2FGL. Searching the WISH and NRAO Very Large Array Sky Survey radio surveys within the positional uncertainty regions of the 2FGL UGSs, we select as gamma-ray blazar candidates the radio sources characterized by flat radio spectra between 352 MHz and 1400 MHz. We propose new gamma-ray blazar associations for eight UGSs and we also discuss their spectral properties at low radio frequencies. We compare the radio flux density distribution of the low radio frequency gamma-ray blazar candidates with that of gamma-ray blazars associated with other methods. We find significant differences between these distributions. Finally, we discuss the results of this association method and its possible applicability to other regions of the sky and future radio surveys.
Keywords: BL Lacertae objects: general; galaxies: active; radiation mechanisms: non-thermal

Updated search for spectral lines from Galactic dark matter interactions with pass 8 data from the Fermi Large Area Telescope - Ackermann, M.; Ajello, M.; Albert, A.; Anderson, B.; Atwood, W. B.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2015)
Dark matter in the Milky Way may annihilate directly into. rays, producing a monoenergetic spectral line. Therefore, detecting such a signature would be strong evidence for dark matter annihilation or decay. We search for spectral lines in the Fermi Large Area Telescope observations of the Milky Way halo in the energy range 200 MeV-500 GeV using analysis methods from our most recent line searches. The main improvements relative to previous works are our use of 5.8 years of data reprocessed with the Pass 8 event-level analysis and the additional data resulting from the modified observing strategy designed to increase exposure of the Galactic center region. We search in five sky regions selected to optimize sensitivity to different theoretically motivated dark matter scenarios and find no significant detections. In addition to presenting the results from our search for lines, we also investigate the previously reported tentative detection of a line at 133 GeV using the new Pass 8 data.

Upper limits from HESS active galactic nuclei observations in 2005-2007 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Aims: Very high energy (VHE; E > 100 GeV) γ-ray studies were performed for 18 active galactic nuclei (AGN) from a variety of AGN classes. Methods: VHE observations of a sample of 14 AGN, considered candidate VHE emitters, were made with the High Energy Stereoscopic System (HESS) between January 2005 and July 2007. Large-zenith-angle observations of three northern AGN (Mkn 421, Mkn 501, 1ES 1218+304), known to emit VHE γ-rays, were also performed in order to sample their spectral energy distributions (SEDs) above 1 TeV In addition, the VHE flux from 1ES 1101-232, previously detected by HESS in 2004-2005, was monitored during 2006 and 2007. Results: As significant detections from the HESS observation program are reported elsewhere, the results reported here are primarily integral flux upper limits. The average exposure for each of the 14 VHE-candidate AGN is ∼7 h live time, and the observations have an average energy threshold between 230 GeV and 590 GeV. Upper limits for these 14 AGN range from <0.9% to <4.9% of the Crab Nebula flux, and eight of these are the most constraining ever reported for the object. The brief (<2.2 h each) large-zenith-angle observations yield upper limits for Mkn 501 (<20% Crab above 2.5 TeV) and 1ES 1218+304 (<17% Crab above 1.0 TeV), and a marginal detection (3.5σ) of Mkn 421 (50% Crab above 2.1 TeV). 1ES 1101-232 was marginally detected (3.6σ, 1.7% Crab above 260 GeV) during the 2006 (13.7 h live time) observations, but not in the 2007 (4.6 h live time) data. The upper limit in 2007 (<1.9% Crab above 260 GeV) is below the average flux measured by HESS from 2004-2006. © ESO 2008.
Keywords: Galaxies: active; Gamma rays: observations

Upper limits on very-high-energy gamma-ray emission from core-collapse supernovae observed with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, Michael; Martins, V. Barbosa; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2019)
Young core-collapse supernovae with dense-wind progenitors may be able to accelerate cosmic-ray hadrons beyond the knee of the cosmic-ray spectrum, and this may result in measurable gamma-ray emission. We searched for gamma-ray emission from ten super- novae observed with the High Energy Stereoscopic System (H.E.S.S.) within a year of the supernova event. Nine supernovae were observed serendipitously in the H.E.S.S. data collected between December 2003 and December 2014, with exposure times ranging from 1.4 to 53 h. In addition we observed SN 2016adj as a target of opportunity in February 2016 for 13 h. No significant gamma-ray emission has been detected for any of the objects, and upper limits on the >1 TeV gamma-ray flux of the order of similar to 10(-13) cm(-)(2)s(-1) are established, corresponding to upper limits on the luminosities in the range similar to 2 x 10(39) to similar to 1 x 10(42) erg s(-1). These values are used to place model-dependent constraints on the mass-loss rates of the progenitor stars, implying upper limits between similar to 2 x 10(-5) and similar to 2 x 10(-3) M-circle dot yr(-1) under reasonable assumptions on the particle acceleration parameters.
CRIS-Team WoS Importer:2019-06-28

Upper limits to the SN1006 multi-TeV gamma-ray flux from HESS observations - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Observations of the shell-type supernova remnant SN1006 have been carried out with the HESS system of Cherenkov telescopes during 2003 (18.2 h with two operating telescopes) and 2004 (6.3 h with all four telescopes). No evidence for TeV gamma-ray emission from any compact or extended region associated with the remnant is seen and resulting upper limits at the 99.9% confidence level are up to a factor 10 lower than previously-published fluxes from CANGAROO. For SN1006 at its current epoch of evolution we define limits for a number of important global parameters. Upper limits on the gamma-ray luminosity (for E = 0.26 to 10 TeV, distance d = 2 kpc) of L-gamma < 1.7 x 10(33) erg s(-1), and the total energy in corresponding accelerated protons, W-p < 1.6 x 10(50) erg are estimated ( for proton energies E-p similar to 1.5 to 60 TeV and assuming the lowest value n = 0.05 cm(-3) of the ambient target density discussed in literature). Extending this estimate to cover the range of proton energies observed in the cosmic ray spectrum up to the knee (we take here E-p similar to 1 GeV to 3 PeV, assuming a differential particle index -2) gives W-P < 6.3 x 10(50) erg. A lower limit on the post-shock magnetic field of B > 25 G results when considering the synchrotron/inverse-Compton framework for the observed X-ray flux and gamma-ray upper limits.
CRIS-Team WoS Importer:2020-01-15

Validation of open-source science tools and background model construction in gamma-ray astronomy - Mohrmann, Lars; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; Malyshev, Dmitry; Nakashima, Kaori; van Eldik, Christopher (Astronomy & Astrophysics, 2019)
In classical analyses of gamma-ray data from imaging atmospheric Cherenkov telescopes (IACTs), such as the High Energy Stereoscopic System (H.E.S.S.), aperture photometry, or photon counting, is applied in a (typically circular) region of interest (RoI) encompassing the source. A key element in the analysis is to estimate the amount of background in the RoI due to residual cosmic ray-induced air showers in the data. Various standard background estimation techniques have been developed in the last decades, most of them rely on a measurement of the background from source-free regions within the observed field of view. However, in particular in the Galactic plane, source analysis and background estimation are hampered by the large number of, sometimes overlapping, gamma-ray sources and large-scale di ffuse gamma-ray emission. For complicated fields of view, a three-dimensional (3D) likelihood analysis shows the potential to be superior to classical analysis. In this analysis technique, a spectromorphological model, consisting of one or multiple source components and a background component, is fitted to the data, resulting in a complete spectral and spatial description of the field of view. For the application to IACT data, the major challenge of such an approach is the construction of a robust background model. In this work, we apply the 3D likelihood analysis to various test data recently made public by the H.E.S.S. collaboration, using the open analysis frameworks ctools and Gammapy. First, we show that, when using these tools in a classical analysis approach and comparing to the proprietary H.E.S.S. analysis framework, virtually identical high-level analysis results, such as field-of-view maps and spectra, are obtained. We then describe the construction of a generic background model from data of H.E.S.S. observations, and demonstrate that a 3D likelihood analysis using this background model yields high-level analysis results that are highly compatible with those obtained from the classical analyses. This validation of the 3D likelihood analysis approach on experimental data is an important step towards using this method for IACT data analysis, and in particular for the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team WoS Importer:2020-01-17

VERITAS and Fermi-LAT Observations of TeV Gamma-Ray Sources Discovered by HAWC in the 2HWC Catalog - Abeysekara, A. U.; Archer, A.; Benbow, W.; Bird, Ralph; Brose, R.; Buchovecky, M.; Buckley, J. H.; Bugaev, V.; Chromey, A. J.; Connolly, M. P.; Cui, W.; Daniel, M. K.; et al. (Astrophysical Journal, 2018)
The High Altitude Water Cherenkov (HAWC) collaboration recently published their 2HWC catalog, listing 39 very high energy (VHE; >100 GeV) gamma-ray sources based on 507 days of observation. Among these, 19 sources are not associated with previously known teraelectronvolt (TeV) gamma-ray sources. We have studied 14 of these sources without known counterparts with VERITAS and Fermi-LAT. VERITAS detected weak gamma-ray emission in the 1 TeV-30 TeV band in the region of DA 495, a pulsar wind nebula coinciding with 2HWC J1953+294, confirming the discovery of the source by HAWC. We did not find any counterpart for the selected 14 new HAWC sources from our analysis of Fermi-LAT data for energies higher than 10 GeV. During the search, we detected gigaelectronvolt (GeV) gamma-ray emission coincident with a known TeV pulsar wind nebula, SNR G54.1+0.3 (VER J1930+188), and a 2HWC source, 2HWC J1930+188. The fluxes for isolated, steady sources in the 2HWC catalog are generally in good agreement with those measured by imaging atmospheric Cherenkov telescopes. However, the VERITAS fluxes for SNR G54.1+0.3, DA 495, and TeV J2032+4130 are lower than those measured by HAWC, and several new HAWC sources are not detected by VERITAS. This is likely due to a change in spectral shape, source extension, or the influence of diffuse emission in the source region.
Keywords: gamma rays: general

VERITAS and Fermi-LAT Observations of TeV Gamma-Ray Sources Discovered by HAWC in the 2HWC Catalog - Abeysekara, A. U.; Archer, A.; Benbow, W.; Bird, Ralph; Brose, R.; Buchovecky, M.; Buckley, J. H.; Bugaev, V.; Chromey, A. J.; Connolly, M. P.; Cui, W.; Daniel, M. K.; et al. (Astrophysical Journal, 2018)
The High Altitude Water Cherenkov (HAWC) collaboration recently published their 2HWC catalog, listing 39 very high energy (VHE; >100 GeV) gamma-ray sources based on 507 days of observation. Among these, 19 sources are not associated with previously known teraelectronvolt (TeV) gamma-ray sources. We have studied 14 of these sources without known counterparts with VERITAS and Fermi-LAT. VERITAS detected weak gamma-ray emission in the 1 TeV-30 TeV band in the region of DA 495, a pulsar wind nebula coinciding with 2HWC J1953+294, confirming the discovery of the source by HAWC. We did not find any counterpart for the selected 14 new HAWC sources from our analysis of Fermi-LAT data for energies higher than 10 GeV. During the search, we detected gigaelectronvolt (GeV) gamma-ray emission coincident with a known TeV pulsar wind nebula, SNR G54.1+0.3 (VER J1930+188), and a 2HWC source, 2HWC J1930+188. The fluxes for isolated, steady sources in the 2HWC catalog are generally in good agreement with those measured by imaging atmospheric Cherenkov telescopes. However, the VERITAS fluxes for SNR G54.1+0.3, DA 495, and TeV J2032+4130 are lower than those measured by HAWC, and several new HAWC sources are not detected by VERITAS. This is likely due to a change in spectral shape, source extension, or the influence of diffuse emission in the source region.
Keywords: gamma rays: general

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26

Very high energy gamma-ray observations of the galaxy clusters Abell 496 and Abell 85 with HESS - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Aims. The nearby galaxy clusters Abell 496 and Abell 85 are studied in the very high-energy (VHE, 100]]> GeV) band to investigate VHE cosmic rays (CRs) in this class of objects which are the largest gravitationally bound systems in the Universe.Methods. HESS, an array of four imaging atmospheric cherenkov telescopes (IACT), was used to observe the targets in the range of VHE gamma rays.Results. No significant gamma-ray signal is found at the respective position of the two clusters with several different source size assumptions for each target. In particular, emission regions corresponding to the high-density core, to the extension of the entire X-ray emission in these clusters, and to the very extended region where the accretion shock is expected are investigated. Upper limits are derived for the gamma-ray flux at energies 570]]> GeV for Abell 496 and 460]]> GeV for Abell 85.Conclusions. From the non-detection in VHE gamma rays, upper limits on the total energy of hadronic CRs in the clusters are calculated. If the cosmic-ray energy density follows the large-scale gas density profile, the limit on the fraction of energy in these non-thermal particles with respect to the total thermal energy of the intra-cluster medium (ICM) is 51% for Abell 496 and only 8% for Abell 85 due to its higher mass and higher gas density. These upper limits are compared with theoretical estimates. They predict about ∼10% of the thermal energy of the ICM in non-thermal particles. The observations presented here can constrain these predictions especially for the case of the Abell 85 cluster. © 2009 ESO.
Keywords: Galaxies: clusters: individual: Abell 496; Galaxies: clusters: individual: Abell 85; Gamma rays: observations

Very high energy gamma rays from the composite SNR G0.9+0.1 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Very high energy (> 100 GeV) gamma-ray emission has been detected for the first time from the composite supernova remnant G0.9+ 0.1 using the HESS instrument. The source is detected with a significance of approximate to 13sigma, and a photon flux above 200 GeV of ( 5.7 +/- 0.7(stat) +/- 1.2(sys)) x 10(-12) cm(-2) s(-1), making it one of the weakest sources ever detected at TeV energies. The photon spectrum is compatible with a power law ( dN/dE proportional to E-Gamma) with photon index Gamma = 2.40 +/- 0.11(stat) +/- 0.20(sys). The gamma-ray emission appears to originate in the plerionic core of the remnant, rather than the shell, and can be plausibly explained as inverse Compton scattering of relativistic electrons.
CRIS-Team WoS Importer:2020-01-15

Very high energy gamma rays from the direction of Sagittarius A - Funk, Stefan; et al. (Astronomy & Astrophysics, 2004)
We report the detection of a point-like source of very high energy (VHE) gamma-rays coincident within 1' of Sgr A* obtained with the HESS array of Cherenkov telescopes. The gamma-rays exhibit a power-law energy spectrum with a spectral index of -2.2+/-0.09+/-0.15 and a flux above the 165 GeV threshold of (1.82+/-0.22)x10(-7) m(-2) s(-1). The measured flux and spectrum differ substantially from recent results reported in particular by the CANGAROO collaboration.
CRIS-Team WoS Importer:2020-01-15

Very high energy γ-ray observations of the binary PSR B1259-63/SS2883 around the 2007 Periastron - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2009)
Aims. This article presents very-high-energy (VHE; E > 100 GeV) data from the-ray binary PSRB1259-63 as taken during the years 2005, 2006 and before as well as shortly after the 2007 periastron passage. These data extend the knowledge of the lightcurve of this object to all phases of the 3.4 year binary orbit. The lightcurve constrains physical mechanisms present in this TeV source. Methods. Observations of VHE-rays with the HESS telescope array using the Imaging Atmospheric Cherenkov Technique were performed. The HESS instrument features an angular resolution of <0.1° and an energy resolution of <20%. Gamma-ray events in an energy range of 0.5-70 TeV were recorded. From these data, energy spectra and lightcurve with a monthly time sampling were extracted. Results. VHE-ray emission from PSRB1259-63 was detected with an overall significance of 9.5 standard deviations using 55 h of exposure, obtained from April to August 2007. The monthly flux of-rays during the observation period was measured, yielding VHE lightcurve data for the early pre-periastron phase of the system for the first time. No spectral variability was found on timescales of months. The spectrum is described by a power law with a photon index of G = 2.8 ± 0.2stat ± 0.2sys and flux normalisation F0 = (1.1 ± 0.1stat ± 0.2sys) × 10-12 TeV-1 cm-2 s-1. PSRB1259-63 was also monitored in 2005 and 2006, far from periastron passage, comprising 8.9 h and 7.5 h of exposure, respectively. No significant excess of-rays is seen in those observations. Conclusions.PSRB1259-63 has been re-confirmed as a variable TeV-ray emitter. The firm detection of VHE photons emitted at a true anomaly ? ≈-0.35 of the pulsar orbit, i.e. already 50 days prior to the periastron passage, disfavors the stellar disc target scenario as a primary emission mechanism, based on current knowledge about the companion star's disc inclination, extension, and density profile. © 2009 ESO.
Keywords: radiation mechanisms: non-thermal; methods: observational; stars: binaries: general; stars: neutron; gamma rays: observations; telescopes

VHE gamma-ray discovery and multiwavelength study of the blazar 1ES 2322-409 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
A hotspot at a position compatible with the BL. Lac object 1ES 2322-409 was serendipitously detected with H.E.S.S. during observations performed in 2004 and 2006 on the blazar PKS 2316-423. Additional data on 1ES 2322-409 were taken in 2011 and 2012, leading to a total live-time of 22.3 h. Point-like very-high-energy (VHE; E > 100 GeV) gamma-ray emission is detected from a source centred on the IFS 2322-409 position, with an excess of 116.7 events at a significance of 6.0 sigma. The average VHE gamma-ray spectrum is well described with a power law with a photon index Gamma = 3.40 +/- 0.66(stat) +/- 0.20(sys) and an integral flux Phi(E > 200 GeV) = (3.11 +/- 0.71(stat) 0.62(sys)) x 10(-2)cm(-2)s(-1), which corresponds to 1.1 per cent of the Crab nebula flux above 200 GeV. Multiwavelength data obtained with Fermi LAT, Swift XRT and UVOT, RXTE PCA, ATOM, and additional data from WISE, GROND, and Catalina are also used to characterize the broad-band non-thermal emission of lES 2322-409. The multiwavelength behaviour indicates day-scale variability. Swift UVOT and XRT data show strong variability at longer scales. A spectral energy distribution (SED) is built from contemporaneous observations obtained around a high state identified in Swift data. A modelling of the SED is performed with a stationary homogeneous one-zone synchrotronself-Compton leptonic model. The redshift of the source being unknown, two plausible values were tested for the modelling. A systematic scan of the model parameters space is performed, resulting in a well-constrained combination of values providing a good description of the broad-band behaviour of 1ES 2322-409.
CRIS-Team WoS Importer:2019-04-09
Keywords: BL Lacertae objects: individual: 1ES 2322-409; galaxies: active; gamma-rays: galaxies; Radiation mechanisms: non-thermal

VHE,gamma-ray emitting pulsar wind nebulae discovered by HESS - Funk, Stefan; et al. (40 YEARS OF PULSARS: MILLISECOND PULSARS, MAGNETARS AND MORE, 2007)
CRIS-Team WoS Importer:2020-01-15

VHE γ-ray emission of PKS2155-304: Spectral and temporal variability - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Context. Observations of very high-energy γ-rays from blazars provide information about acceleration mechanisms occurring in their innermost regions. Studies of variability in these objects lead to a better understanding of the mechanisms in play. Aims. To investigate the spectral and temporal variability of VHE (>100 GeV) γ-rays of the well-known high-frequency-peaked BL Lac object PKS 2155-304 with the HESS imaging atmospheric Cherenkov telescopes over a wide range of flux states. Methods. Data collected from 2005 to 2007 were analyzed. Spectra were derived on time scales ranging from 3 years to 4 min. Light curve variability was studied through doubling timescales and structure functions and compared with red noise process simulations. Results. The source was found to be in a low state from 2005 to 2007, except for a set of exceptional flares that occurred in July 2006. The quiescent state of the source is characterized by an associated mean flux level of (4.32 ± 0.09 ± 0.86) × 10 cm s above 200 GeV, or approximately 15% of the Crab Nebula, and a power-law photon index of Γ = 3.53 ± 0.06 ± 0.10. During the flares of July 2006, doubling timescales of ∼2 min are found. The spectral index variation is examined over two orders of magnitude in flux, yielding different behavior at low and high fluxes, which is a new phenomenon in VHE γ-ray emitting blazars. The variability amplitude characterized by the fractional rms F is strongly energy-dependent and is E. The light curve rms correlates with the flux. This is the signature of a multiplicative process that can be accounted for as a red noise with a Fourier index of ∼2. Conclusions. This unique data set shows evidence of a low-level γ-ray emission state from PKS 2155-304 that possibly has a different origin than the outbursts. The discovery of the light curve lognormal behavior might be an indicator of the origin of aperiodic variability in blazars. © ESO, 2010.
Keywords: BL Lacertae objects: individual: PKS 2155-304; galaxies: active; galaxies: jets; gamma rays: general

XMM-Newton and Fermi /LAT view on the supernova remnant 3C434.1 - Doroshenko, Victor; Malyshev, Dmitry; Pühlhofer, G.; Dincel, Baha; Sasaki, Manami; Santangelo, Andrea (Astronomy & Astrophysics, 2019)
We report on XMM-Newton observations of the supernova remnant (SNR) 3C434.1 (G94.0+1.0), the first in X-rays since the ROSAT era. Our analysis confirms the thermal origin of the observed extended X-ray emission, whose morphology appears more complex than previously reported. In particular, part of the shell shows a significantly harder spectrum which is consistent with a power law, and it is, therefore, likely of non-thermal origin. Motivated by these finding, we revisited the GeV observations of the field taken with the Fermi observatory. A significant excess associated with the remnant was detected, which is likely associated with non-thermal X-ray emission from part of the shell. The analysis of the Fermi data resulted in the serendipity discovery of GeV emission from the nearby SNR G093.7-00.2. Finally, we searched for a possible compact remnants within the shell, however, no obvious candidates could be identified due to the fairly large positional uncertainties.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Gamma rays: general; ISM: supernova remnants; Stars: neutron

XMM-Newton observations of HESS J1813-178 reveal a composite Supernova remnant - Funk, Stefan; et al. (Astronomy & Astrophysics, 2007)
Aims. We present X-ray and (CO)-C-12(J = 1-0) observations of the very-high-energy (VHE) gamma-ray source HESS J1813-178 with the aim of understanding the origin of the gamma-ray emission.
CRIS-Team WoS Importer:2020-01-15

XMM-Newton observations reveal the x-ray counterpart of the very high energy gamma-ray source hess J1640-465 - Funk, Stefan; et al. (Astrophysical Journal, 2007)
We present X-ray observations of the as of yet unidentified very high energy (VHE) gamma-ray source HESS J1640-465 with the aim of establishing a counterpart of this source in the keV energy range, and identifying the mechanism responsible for the VHE emission. The 21.8 ks XMM-Newton observation of HESS J1640-465 in 2005 September represents a significant improvement in sensitivity and angular resolution over previous ASCA studies in this region. These new data show a hard-spectrum X-ray-emitting object at the centroid of the H. E. S. S. source, within the shell of the radio supernova remnant (SNR) G338.3-0.0. This object is consistent with the position and flux previously measured by both ASCA and Swift XRT, but is now shown to be significantly extended. We argue that this object is very likely the counterpart to HESS J1640-465, and that both objects may represent the pulsar wind nebula of an as of yet undiscovered pulsar associated with G338.3-0.0.
CRIS-Team WoS Importer:2020-01-15

X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lisa; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging

X-ray observations of unidentified HESS gamma-ray sources - Funk, Stefan (First GLAST Symposium, 2007)
CRIS-Team WoS Importer:2020-01-15

γ-Ray Emission from Classical Nova V392 Per: Measurements from Fermi and HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Rojas, D. Avila; Solares, H. A.Ayala; Babu, R.; Belmont-Moreno, E.; Blochwitz, C.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; et al. (Astrophysical Journal, 2022)
This paper reports on the γ-ray properties of the 2018 Galactic nova V392 Per, spanning photon energies ∼0.1 GeV-100 TeV by combining observations from the Fermi Gamma-ray Space Telescope and the HAWC Observatory. As one of the most rapidly evolving γ-ray signals yet observed for a nova, GeV γ-rays with a power-law spectrum with an index Γ = 2.0 ± 0.1 were detected over 8 days following V392 Per’s optical maximum. HAWC observations constrain the TeV γ-ray signal during this time and also before and after. We observe no statistically significant evidence of TeV γ-ray emission from V392 Per, but present flux limits. Tests disfavor the extension of the Fermi Large Area Telescope spectrum to energies above 5 TeV by 2 standard deviations (95%) or more. We fit V392 Per’s GeV γ-rays with hadronic acceleration models, incorporating optical observations, and compare the calculations with HAWC limits.
CRIS-Team Scopus Importer:2022-12-23